Natural Disasters and Rehabilitation: Post‐Disaster Aid, Corruption, Misallocation, and Mistargeting - Ahmad, Muhammad Irshad; Shen, Qiong; Boota, Muhammad Waseem; Liu, Ruifeng; Ma, Hengyun (Sustainable Development, 2025)
ABSTRACT The increasing frequency of natural disasters, such as floods, droughts, and tsunamis, has made vulnerable communities less resilient, pushing them toward long‐term poverty and food insecurity. Effective post‐disaster rehabilitation is critical to restoring livelihoods, infrastructure, and food security. However, challenges such as corruption, misallocation, and mistargeting undermine post‐disaster aid programs. This study systematically reviews 86 peer‐reviewed articles (1990–2023) using the preferred reporting items for systematic reviews and meta‐analyses (PRISMA) protocol to investigate aid inefficiencies in disaster recovery. The findings reveal that aid often fails to reach the most affected communities, being diverted to unaffected areas due to political influence and local elites, exacerbating inequalities. Corruption further hampers institutional performance and long‐term disaster resilience efforts. The study calls for transparent, accountable, and inclusive strategies for aid distribution, aligning with SDG 10 (reduced inequalities) and SDG 11 (sustainable cities and communities). Future research should focus on gender‐sensitive strategies, local governance, and technological innovations to enhance aid transparency and effectiveness.
Keywords: Scopus_Alert_12_Septembre_2025

Determinants and relationships of climate change, climate change hazards, mental health, and well-being: a systematic review - Rückle, Karolin; Rohrer, Mario; Mihók, Barbara; Johansson, Maria; Andersson, Hanna; Pomee, Muhammad Saleem; Vergadi, Eleni; Rouva, Glykeria; Agrawal, Apoorv; Balázs, Balint; Brattich, Erika; Carelli, Maria; et al. (Frontiers in Psychiatry, 2025)
Introduction Impacts of climate change on human health receive increasing attention. However, the connections of climate change with well-being and mental health are still poorly understood. Objective As part of the Horizon Europe project TRIGGER, we aim to deepen the understanding of the relationships between climate change and human mental health and well-being in Europe by focusing on environmental and socio-individual determinants. Methods This study is a systematic literature review based on the PRISMA guidelines using Embase, Medline and Web of Science. Results 143 records were retrieved. The results show that climate change and its specific hazards (air pollution, floods, wildfires, meteorological variables, and temperature extremes) impact human well-being and mental health. Discussion Mental health and well-being outcomes are complex, extremely individual, and can be long lasting. Determinants like the living surrounding, human’s life activities as well as socio-individual determinants alter the linkage between climate change and mental health. The same determinant can exert both a pathogenic and a salutogenic effect, depending on the outcome. Knowing the effects of the determinants is of high relevance to improve resilience. Several pathways were identified. For instance, higher level of education and female gender lead to perceiving climate change as a bigger threat but increase preparedness to climate hazards. Elderly, children and adolescents are at higher risks of mental health problems. On the other hand, social relation, cohesiveness and support from family and friends are generally protective. Green and blue spaces improve well-being and mental health. Overall, comparing the different hazard-outcome relationships is difficult due to varying definitions, measurement techniques, spatial and temporal range, scales, indicators and population samples. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/home , identifier CRD42023426758.
Keywords: Scopus_Alert_12_Septembre_2025

Predicting current habitat suitability for intermediate snail hosts of urogenital and intestinal schistosomiasis in the Lower Shire Valley floodplain of southern Malawi - Nkolokosa, Clinton; Chirombo, James; Jones, Christopher M.; Mbewe, Rex B.; Kambewa, Eggrey Aisha; Makaula, Peter; Tangena, Julie-Anne Akiko; Stothard, J. Russell (Parasites & Vectors, 2025)
Abstract Background Relating the geographical distribution of intermediate freshwater snail hosts (viz. vectors of schistosomes) to local environmental attributes offers value for understanding the epidemiological landscape of schistosomiasis transmission in a changing aquatic environment. Schistosomiasis—both urogenital and intestinal—causes significant human suffering, affecting approximately 240 million people globally and grouped within the neglected tropical disease (NTD) umbrella. This study addresses the following questions: 1. Where are the most suitable habitats for intermediate host snails in the Lower Shire Valley (LSV) in Malawi? 2. Which environmental factors are strongly associated with the geographical distribution of such snails in the LSV? Methods This paper presents the first species distribution models (SDMs) for intermediate snail hosts for urogenital and intestinal schistosomiasis in Chikwawa and Nsanje Districts, which together form the LSV). The SDMs developed for this study are ensemble machine learning approaches based on Random Forest (RF), Support Vector Machines (SVM), and multilayer perceptron (MLP) and are specific to the Bulinus africanus group and Biomphalaria pfeifferi . The former transmits urogenital schistosomiasis ( Schistosoma haematobium ), while the latter transmits intestinal schistosomiasis ( Schistosoma mansoni ). Results The SDMs reveal the following: 1) currently, Bu. africanus group not only has a wide distribution across central Chikwawa and eastern Nsanje but is also concentrated in floodplains, and the LSV has few habitats that can support Bi. pfeifferi , and 2) vegetation cover is the most important predictor of Bu. africanus group distribution, whereas precipitation variables are most important for Bi. pfeifferi in the LSV. Thus, Bu. africanus group habitat is the most dominant and abundant, while Bi. pfeifferi suitable habitat is patchy and scarce. Conclusion The distribution of suitable habitats for potential urogenital and intestinal schistosomiasis transmission across LSV is not uniform and typically non-overlapping. Understanding the spatial and temporal distributions of these snails is important for controlling and eliminating schistosomiasis. Graphical Abstract
Keywords: Scopus_Alert_12_Septembre_2025

Market-based instruments to fund nature-based solutions for flood risk management can disproportionately benefit affluent areas - Hill, Bartholomew; Marjoribanks, Tim; Moore, Harriet; Bosher, Lee; Gussy, Mark (Communications Earth & Environment, 2025)
Abstract Market-based instruments, including competitive tenders, are central to funding global environmental restoration and management projects. Recently, tenders have been utilised to fund Nature-based Solutions schemes for Natural Flood Management, with the explicit purpose of achieving co-benefits; flood management and reducing inequities. While multiple studies consider the efficacy of Nature-based Solutions for tackling inequities, no prior research has quantified whether the resource allocation for these projects has been conducted equitably. We analyse two national natural flood management programmes funded through competitive tenders in England to explore who benefits by considering the characteristics of projects, including socio-economic, geographical (e.g. rurality) and flood risk dynamics. Our results suggest that inequity occurs at both the application and funding stages of Nature-based Solutions projects for flood risk management. This reflects wider international challenges of using market-based instruments for environmental resource allocation. Competitive tenders have the potential to undermine the equitable benefits of Nature-based Solutions.
Keywords: Scopus_Alert_12_Septembre_2025

Research on Extreme Precipitation Risk Considering Physical-social-environmental Attributes - Zhang, Jianlei; Chu, Chenkun; Wang, Peng (Journal of Disaster Prevention and Mitigation Engineering, 2025)
This study aims to conduct a grid-scale extreme precipitation risk assessment in Xuanwu District, Nanjing, so as to fill the gaps in existing indicator systems and improve the precision of risk characterization. By integrating physical, social, and environmental indicators, a risk assessment framework was constructed to comprehensively represent the characteristics of extreme precipitation risk. This study applied the entropy weight method to calculate indicator weights, combined with ArcGIS technology and the K-means clustering algorithm, to analyze the spatial distribution characteristics of risk under a 100-year extreme precipitation scenario and to identify key influencing indicators across different risk levels. The results showed that extreme precipitation risk levels in Xuanwu District exhibited significant spatial heterogeneity, with an overall distribution pattern of low risk in the central area and high risk in the surrounding areas. The influence mechanisms of key indicators showed tiered response characteristics: the low-risk areas were mainly controlled by the submerged areas of urban and rural, industrial and mining, and residential lands, water body area, soil erosion level, and normalized difference vegetation index (NDVI). The medium-risk areas were influenced by the submerged areas of urban and rural, industrial and mining, residential lands, the submerged areas of forest land, emergency service response time to disaster-affected areas, soil erosion level, and NDVI. The high-risk areas were jointly dominated by the submerged areas of urban and rural, industrial and mining, residential lands, the submerged areas of forest land, and NDVI. The extremely high-risk areas were driven by three factors—the submerged areas of forest land, emergency service response time to disaster-affected areas, and the proportion of the largest patch to the landscape area. This study improves the indicator system for extreme precipitation risk assessment and clarifies the tiered response patterns of risk-driving indicators, providing a scientific basis for developing differentiated flood control strategies in Xuanwu District while offering important theoretical support for improving regional flood disaster resilience. © 2025 Editorial Office of Journal of Disaster Prevention and Mitigation Engineering. All rights reserved.
Keywords: Scopus_Alert_5_Septembre_2025

Integrative strategies for urban flood resilience and risk: A meta-analysis of policy, infrastructural, and ecosystem-based interventions - Wang, Shitao; Bi, Xuehao (Physics and Chemistry of the Earth, 2025)
Urban flooding, intensified by climate change and rapid urbanization, demands robust and operationally effective resilience strategies. However, empirical evidence on the comparative effectiveness of such strategies remains limited. This study presents the first meta-analytic synthesis evaluating urban flood resilience interventions across institutional, infrastructural, and socio-ecological domains. By synthesizing data from 29 peer-reviewed studies (2000–2024), this study applies standardized effect sizes (Cohen's d) and meta-regression models to assess the effectiveness of different strategies. Results reveal a substantial overall effect (pooled d = 2.96, 95 % CI: [1.92, 3.99]) with high heterogeneity (I2 = 93.8 %). Institutional mechanisms, such as policy coordination, regulatory frameworks, and risk governance, consistently show the strongest and most statistically significant impacts (d ≈ 2.96). Low Impact Development (LID) demonstrates limited, non-significant effects (d ≈ 0.08). The study introduces a novel hierarchical resilience framework spanning different dimensions and establishes an evidence-based typology of urban flood resilience strategies. These findings highlight the importance of integrated, multi-level governance and context-specific planning in enhancing urban flood resilience. The study findings provides critical insights for implementing resilience strategies in flood-prone urban areas, and support the formulation of adaptive and sustainable urban policies. © 2025
Keywords: Scopus_Alert_5_Septembre_2025

Predictive Modeling and Strategic Planning for Urban Flood Risk Mitigation - Mitali, Patel; Patel, Nishit; Modi, Kshitish; Patel, Samir (Communications in Computer and Information Science, 2026)
Urban flooding threatens Indian cities and is made worse by rapid urbanization, climate change and poor infrastructure. Severe flooding occurred in cities such as Mumbai, Chennai and Ahmedabad. This has caused huge economic losses and displacement. This study addresses the limitations of traditional flood forecasting methods. It has to contend with the complex dynamics of urban flooding. We offer a deep learning approach which uses the network Convolutional Neural Networks (CNN) and Long Short-Term Memory (LSTM) networks to improve flood risk prediction. Our CNN-LSTM model combines spatial data (water table, topography) and temporal data (historical model) to classify flood risk as low or high. This method includes collecting data pre-processing (MinMaxScaler, LabelEncoder) Modeling, Training and Evaluation. The results demonstrate the accuracy of flood risk predictions and provide insights into flexible strategies for urban flood management. This research highlights the role of data-driven approaches in improving urban planning to reduce flood risk in high-risk areas. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2026.
Keywords: Scopus_Alert_5_Septembre_2025

Impact of Land Use Patterns on Flood Risk in the Chang-Zhu-Tan Urban Agglomeration, China - Zhang, Ting; Wu, Kai; Wang, Xiulian; Li, Xinai; Li, Long; Chen, Longqian (Remote Sensing, 2025)
Flood risk assessment is an effective tool for disaster prevention and mitigation. As land use is a key factor influencing flood disasters, studying the impact of different land use patterns on flood risk is crucial. This study evaluates flood risk in the Chang-Zhu-Tan (CZT) urban agglomeration by selecting 17 socioeconomic and natural environmental factors within a risk assessment framework encompassing hazard, exposure, vulnerability, and resilience. Additionally, the Patch-Generating Land Use Simulation (PLUS) and multilayer perceptron (MLP)/Bayesian network (BN) models were coupled to predict flood risks under three future land use scenarios: natural development, urban construction, and ecological protection. This integrated modeling framework combines MLP’s high-precision nonlinear fitting with BN’s probabilistic inference, effectively mitigating prediction uncertainty in traditional single-model approaches while preserving predictive accuracy and enhancing causal interpretability. The results indicate that high-risk flood zones are predominantly concentrated along the Xiang River, while medium-high- and medium-risk areas are mainly distributed on the periphery of high-risk zones, exhibiting a gradient decline. Low-risk areas are scattered in mountainous regions far from socioeconomic activities. Simulating future land use using the PLUS model with a Kappa coefficient of 0.78 and an overall accuracy of 0.87. Under all future scenarios, cropland decreases while construction land increases. Forestland decreases in all scenarios except for ecological protection, where it expands. In future risk predictions, the MLP model achieved a high accuracy of 97.83%, while the BN model reached 87.14%. Both models consistently indicated that the flood risk was minimized under the ecological protection scenario and maximized under the urban construction scenario. Therefore, adopting ecological protection measures can effectively mitigate flood risks, offering valuable guidance for future disaster prevention and mitigation strategies. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Enhanced Urban Flood Hazard Assessment by Stochastic Event Catalog - Yan, Haochen; Guo, Kaihua; Guan, Mingfu (Water Resources Research, 2025)
Assessing flood severity in urban areas is a pivotal task for urban resilience and climate adaptation. However, the lack of in situ measurements hinders direct spatial estimation of flood return periods, while conventional assumptions about rainstorm-flood consistency introduce significant uncertainties due to rainstorm spatiotemporal variability (STV). This study proposes a novel framework that utilizes multivariate frequency analysis of flood variables at the street level (50 m) through a stochastic rainstorm-flood event catalog. The rainstorm events in the catalog are generated by a random field generator and resampled to match the joint distribution of STV variables consistent with radar observations. Urban flood processes are then simulated by a hydrodynamic model for flood hazard assessment (FHA). We applied the framework to a rural-urban watershed using 3,000 cases randomly resampled from the catalog. Results reveal that inundation characteristics respond more rapidly to increasing rainfall intensities than downstream flood peaks, particularly during the early stages of rainstorms. The complex joint probability structures of rainstorm severity and STV variables obscure the mechanistic control of individual factors on flood response. A significant underestimation of street-level flood hazards occurs when assuming the same return periods (RPs) as those for watershed-level hazards. The inconsistency between rainstorm and flood severities results in widespread underestimation of street-level flood hazards in upstream regions, while traditional storm designs that neglect STV lead to overestimations in mid- and downstream areas. This study highlights the complex probabilistic behavior of spatially distributed flood hazards across multiple scales, enhancing the insights and methodologies for street-level FHA. © 2025 The Author(s).
Keywords: Scopus_Alert_5_Septembre_2025

Spatial–Temporal Characteristics and Drivers of Summer Extreme Precipitation in the Poyang Lake City Group (PLCG) from 1971 to 2022 - Liu, Hua; Zhang, Ziqing; Liu, Bo (Remote Sensing, 2025)
Global warming has intensified the hydrological cycle, resulting in more frequent extreme precipitation events and altered spatiotemporal precipitation patterns in urban areas, thereby increasing the risk of urban flooding and threatening socio-economic and ecological security. This study investigates the characteristics of summer extreme precipitation in the Poyang Lake City Group (PLCG) from 1971 to 2022, utilizing the China Daily Precipitation Dataset and NCEP/NCAR reanalysis data. Nine extreme precipitation indices were examined through linear trend analysis, Mann–Kendall tests, wavelet transforms, and correlation methods to quantify trends, periodicity, and atmospheric drivers. The key findings include: (1) All indices exhibited increasing trends, with RX1Day and R95p exhibiting significant rises (p < 0.05). PRCPTOT, R20, and SDII also increased, indicating heightened precipitation intensity and frequency. (2) R50, RX1Day, and SDII demonstrated east-high-to-west-low spatial gradients, whereas PRCPTOT and R20 peaked in the eastern and western PLCG. More than over 88% of stations recorded rising trends in PRCPTOT and R95p. (3) Abrupt changes occurred during 1993–2009 for PRCPTOT, R50, and SDII. Wavelet analysis revealed dominant periodicities of 26–39 years, linked to atmospheric oscillations. (4) Strong subtropical highs, moisture convergence, and negative OLR anomalies were closely associated with extreme precipitation. Warmer SSTs in the eastern equatorial Pacific amplified precipitation in preceding seasons. This study provides a scientific basis for flood prevention and climate adaptation in the PLCG and highlighting the region’s vulnerability to monsoonal shifts under global warming. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Producing Hydrological Projections Under Climate Change: A Groundwater-Inclusive Practical Guide - Mourot, Frédérique M.; Irvine, Dylan J.; Remenyi, Tomas A.; Hutley, Lindsay B.; Crosbie, Russell S.; Moore, Catherine R. (Earth's Future, 2025)
With global warming, the hydrological cycle is intensifying with more frequent and severe droughts and floods, placing water resources and their dependent communities under increasing stress. Guidance and insights into the projection of future water conditions are, therefore, increasingly needed to inform climate change adaptation. Hydrological projections can provide such insights when suitably designed for user needs, produced from the best available climate knowledge, and leverage appropriate hydrological models. However, producing such hydrological projections is a complex process that requires skills and knowledge spanning from the often-siloed disciplines of climate, hydrology, communication, and decision-making. Groundwater projections are still underrepresented compared to surface water projections, despite the importance of groundwater to sustain society and the environment. Accordingly, this paper bridges these silos and fills a gap by providing detailed guidance on the important steps and best practices to develop groundwater-inclusive hydrological projections that can effectively support decision-making. Using an extensive literature review and our practical experience as climate scientists, hydro(geo)logists, numerical modelers, uncertainty experts and decision-makers, here we provide: (a) an overview of climate change hydrological impacts as background knowledge; (b) a step-by-step guide to produce groundwater-inclusive hydrological projections under climate change, targeted to both scientists and water practitioners; (c) a summary of important considerations related to hydrological projection uncertainty; and (d) insights to use hydrological projections and their associated uncertainty for impactful communication and decision-making. By providing this practical guide, our paper addresses a critical interdisciplinary knowledge gap and supports enhanced decision-making and resilience to climate change threats. © 2025 Commonwealth of Australia. Earth Science New Zealand. Acclimatised Pty Ltd and The Author(s). Earth's Future published by Wiley Periodicals LLC on behalf of American Geophysical Union.
Keywords: Scopus_Alert_5_Septembre_2025

Interest Flooding Attacks in Named Data Networking and Mitigations: Recent Advances and Challenges - Ogunbunmi, Simeon; Chen, Yu; Zhao, Qi; Nagothu, Deeraj; Wei, Sixiao; Chen, Genshe; Blasch, Erik (Future Internet, 2025)
Named Data Networking (NDN) represents a promising Information-Centric Networking architecture that addresses limitations of traditional host-centric Internet protocols by emphasizing content names rather than host addresses for communication. While NDN offers advantages in content distribution, mobility support, and built-in security features, its stateful forwarding plane introduces significant vulnerabilities, particularly Interest Flooding Attacks (IFAs). These IFA attacks exploit the Pending Interest Table (PIT) by injecting malicious interest packets for non-existent or unsatisfiable content, leading to resource exhaustion and denial-of-service attacks against legitimate users. This survey examines research advances in IFA detection and mitigation from 2013 to 2024, analyzing seven relevant published detection and mitigation strategies to provide current insights into this evolving security challenge. We establish a taxonomy of attack variants, including Fake Interest, Unsatisfiable Interest, Interest Loop, and Collusive models, while examining their operational characteristics and network performance impacts. Our analysis categorizes defense mechanisms into five primary approaches: rate-limiting strategies, PIT management techniques, machine learning and artificial intelligence methods, reputation-based systems, and blockchain-enabled solutions. These approaches are evaluated for their effectiveness, computational requirements, and deployment feasibility. The survey extends to domain-specific implementations in resource-constrained environments, examining adaptations for Internet of Things deployments, wireless sensor networks, and high-mobility vehicular scenarios. Five critical research directions are proposed: adaptive defense mechanisms against sophisticated attackers, privacy-preserving detection techniques, real-time optimization for edge computing environments, standardized evaluation frameworks, and hybrid approaches combining multiple mitigation strategies. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Injectivity, Potential Wettability Alteration, and Mineral Dissolution in Low-Salinity Waterflood Applications: The Role of Salinity, Surfactants, Polymers, Nanomaterials, and Mineral Dissolution - Sarma, Hemanta K.; Awolayo, Adedapo N.; Olayiwola, Saheed O.; Fakir, Shasanowar H.; Belhaj, Ahmed F. (Processes, 2025)
Waterflooding, a key method for secondary hydrocarbon recovery, has been employed since the early 20th century. Over time, the role of water chemistry and ions in recovery has been studied extensively. Low-salinity water (LSW) injection, a common technique since the 1930s, improves oil recovery by altering the wettability of reservoir rocks and reducing residual oil saturation. Recent developments emphasize the integration of LSW with various recovery methods such as CO2 injections, surfactants, alkali, polymers, and nanoparticles (NPs). This article offers a comprehensive perspective on how LSW injection is combined with these enhanced oil recovery (EOR) techniques, with a focus on improving oil displacement and recovery efficiency. Surfactants enhance the effectiveness of LSW by lowering interfacial tension (IFT) and improving wettability, while ASP flooding helps reduce surfactant loss and promotes in situ soap formation. Polymer injections boost oil recovery by increasing fluid viscosity and improving sweep efficiency. Nevertheless, challenges such as fine migration and unstable flow persist, requiring additional optimization. The combination of LSW with nanoparticles has shown potential in modifying wettability, adjusting viscosity, and stabilizing emulsions through careful concentration management to prevent or reduce formation damage. Finally, building on discussions around the underlying mechanisms involved in improved oil recovery and the challenges associated with each approach, this article highlights their prospects for future research and field implementation. By combining LSW with advanced EOR techniques, the oil industry can improve recovery efficiency while addressing both environmental and operational challenges. © 2025 by the authors.
Keywords: Scopus_Alert_5_Septembre_2025

Copula-based joint distribution modelling of precipitation, temperature and humidity events in the assessments of agricultural risks, with a case study in Morocco - Latif, Shahid; El Ouadi, Ihssan; Ouarda, Taha B. M. J. (Stochastic Environmental Research and Risk Assessment, 2025)
The agriculture sector is profoundly impacted by the abiotic stresses in arid or semi-arid regions that experience extreme weather patterns related to temperature (T), precipitation (P), humidity (H), and other factors. This study adopts a flexible approach that incorporates the D-vine copula density to analyze trivariate (and bivariate) joint and conditional hazard risk. The methodology was applied to a case study in the Ait Ben Yacoub region of Morocco. Monthly series for T, H, and P were modeled using the Weibull-2P and Weibull-3P models, selected based on fitness statistics. The survival BB8 copula was best described as joint dependence for pair T–P, rotated BB8 270 degrees copula for T–H, while rotated Joe 270 degrees copula for P–H. The analysis of joint probability stress focused on both primary joint scenarios (for OR and AND-hazard conditions) and conditional return periods (RPs) for trivariate and bivariate case. Lower univariate RPs resulted in higher marginal quantiles for T and lower for H and P events. Lower trivariate (and bivariate) AND-joint RPs (or higher concurrence probabilities) were associated with higher T with lower P and H quantiles. The occurrence of trivariate (and bivariate) events was less frequent in the AND-joint case compared to the OR-joint case. The conditional joint RP of T (or T with P, or T with H) was significantly affected by different P (at 10th and 25th percentile) and H (at 5th and 25th percentile) (or P, or H) conditions. Lower conditional RPs of T (or T with H, or T with P) had resulted at given low P and H (or low P, or low H levels). In conclusion, the estimated risk statistics are vital for the study region, highlighting the need for effective adaptation and resilience planning in agriculture crop management.
Keywords: Infolettre_Septembre_2025

Natural disasters and individual economic performance: a case study from the slave lake wildfire - Kabore, Philippe; Rivers, Nicholas; Armstrong, Catherine Deri (Climate Change Economics, 2025)
In May 2011, the municipality of Slave Lake, Alberta, was hit by a devastating wildfire; the second costliest natural disaster in Canada at the time. Residents of Slave Lake were forced to evacuate for at least a month. This case study uses longitudinal income tax data from 2004 to 2018 to estimate the short, medium, and long-term individual economic effects of this wildfire. Estimates suggest an average drop in total income of 10.5% relative to a counter-factual scenario with no wildfire over the 7 years following the wildfire, mainly driven by a decrease in employment income. The percentage of total income lost is similar for males and females. The largest effects are found for workers in the agriculture and forestry sectors. Back-of-the- envelope calculations suggest an aggregate loss in employment income of $150 million in the 7 years following the disaster, equivalent to over 13% of direct economic losses due to property damage, firefighting, and contemporaneous business closure.
Keywords: Infolettre_Septembre_2025

High-Resolution Daily XCH4 Prediction Using New Convolutional Neural Network Autoencoder Model and Remote Sensing Data - Awad, Mohamad M.; Homayouni, Saeid (Atmosphere, 2025)
Atmospheric methane (CH4) concentrations have increased to 2.5 times their pre-industrial levels, with a marked acceleration in recent decades. CH4 is responsible for approximately 30% of the global temperature rise since the Industrial Revolution. This growing concentration contributes to environmental degradation, including ocean acidification, accelerated climate change, and a rise in natural disasters. The column-averaged dry-air mole fraction of methane (XCH4) is a crucial indicator for assessing atmospheric CH4 levels. In this study, the Sentinel-5P TROPOMI instrument was employed to monitor, map, and estimate CH4 concentrations on both regional and global scales. However, TROPOMI data exhibits limitations such as spatial gaps and relatively coarse resolution, particularly at regional scales or over small areas. To mitigate these limitations, a novel Convolutional Neural Network Autoencoder (CNN-AE) model was developed. Validation was performed using the Total Carbon Column Observing Network (TCCON), providing a benchmark for evaluating the accuracy of various interpolation and prediction models. The CNN-AE model demonstrated the highest accuracy in regional-scale analysis, achieving a Mean Absolute Error (MAE) of 28.48 ppb and a Root Mean Square Error (RMSE) of 30.07 ppb. This was followed by the Random Forest (RF) regressor (MAE: 29.07 ppb; RMSE: 36.89 ppb), GridData Nearest Neighbor Interpolator (NNI) (MAE: 30.06 ppb; RMSE: 32.14 ppb), and the Radial Basis Function (RBF) Interpolator (MAE: 80.23 ppb; RMSE: 90.54 ppb). On a global scale, the CNN-AE again outperformed other methods, yielding the lowest MAE and RMSE (19.78 and 24.7 ppb, respectively), followed by RF (21.46 and 27.23 ppb), GridData NNI (25.3 and 32.62 ppb), and RBF (43.08 and 54.93 ppb).
Keywords: Infolettre_Septembre_2025

Optimizing ensemble learning for satellite-based multi-hazard monitoring and susceptibility assessment of landslides, land subsidence, floods, and wildfires - Razavi-Termeh, Seyed Vahid; Sadeghi-Niaraki, Abolghasem; Ali, Farman; Pradhan, Biswajeet; Choi, Soo-Mi (Scientific Reports, 2025)
The preparation of accurate multi-hazard susceptibility maps is essential to effective disaster risk management. Past studies have relied mainly on traditional machine learning models, but these models do not perform well for complex spatial patterns. To address this gap, this study uses two meta-heuristic algorithms (Genetic Algorithm (GA) and Particle Swarm Optimization (PSO)) to provide an optimized Random Forest (RF) model with better predictive ability. We focus on four significant hazards—landslides, land subsidence, wildfires, and floods—in Kurdistan Province, Iran, using Sentinel-1 and Sentinel-2 satellite imagery collected between 2015 and 2022. Furthermore, two models of RF-GA and RF-PSO were utilized to create multi-hazard susceptibility, which were evaluated using receiver operating characteristic (ROC) curves and area under the curve (AUC). The RF-GA algorithm achieved 91.1% accuracy for flood hazards, 83.8% for wildfires, and 99.1% for landslide hazards. In contrast, utilizing RF-PSO resulted in a 95.9% accuracy for land subsidence hazards. The combined RF-GA algorithm demonstrated superior accuracy to individual RF modeling techniques. Furthermore, eastern regions are more prone to floods and land subsidence, whereas western areas face more significant risks from landslides and wildfires. Additionally, floods and land subsidence exhibit a considerable correlation, impacting each other’s occurrence, while wildfires and landslides demonstrate interacting dynamics, influencing each other’s likelihood of occurrence. © The Author(s) 2025.

A novel and scalable flood risk assessment framework for cultural heritage based on unmanned aerial vehicle photogrammetry and multi-scale rain-on-grid hydraulic modeling - Alexopoulos, M.J.; Iliopoulou, T.; Modé, P.; Istrati, D.; Spyrakos, C.C.; Soile, S.; Verykokou, S.; Ioannidis, C.; Koutsoyiannis, D. (Science of the Total Environment, 2025)
This study presents a novel multi-scale flood risk assessment framework for cultural heritage sites, applied to the Temple of Apollo, Aegina Island, Greece. Three modeling configurations were developed and compared: (i) an island-wide Rain-on-Grid (RoG) hydraulic model at 5 m resolution, (ii) a site-only model driven by inflows from the island-scale simulation, and (iii) a high-resolution nested model coupling island-scale outputs with centimeter-scale site RoG simulations enabled by UAV photogrammetry. Simulations for 100-, 1000-, and 2000-year return periods revealed strong scale-dependent differences: island-wide inundation extents of 7.3–10.3 km2, site-specific inundation of 2–24 %, and water volumes of 92–1483 m3 depending on the model configuration and return period. Flow velocities remained below 1.0 m/s, indicating low erosive potential but possible material degradation. Limestone deterioration analysis showed 4–10 % compressive strength reduction, 3–9 % elastic modulus decrease, and mass losses of 0.64–26.08 kg after 24-h inundations. The nested approach provided more realistic water volume accumulation over the single-scale model and revealed critical micro-topographic controls on flood behavior. This scalable, built on readily accessible tools (HEC-RAS and UAV), framework supports rapid deployment to heritage sites globally, enabling quantitative risk assessments for adaptation planning and conservation prioritization. © 2025 The Authors

Editorial preface to special issue: Temporal and spatial patterns in Holocene floods under the influence of past global change, and their implications for forecasting “unpredecented” future events - Schulte, Lothar; Santisteban, Juan I.; Fuller, Ian C.; Ballesteros-Cánovas, Juan Antonio (Global and Planetary Change, 2025)
Floods constitute the most significant natural hazard to societies worldwide. Population growth and unchecked development have led to floodplain encroachment. Modelling suggests that climate change will regionally intensify the threat posed by future floods, with more people in harm's way. From a global change perspective, past flood events and their spatial-temporal patterns are of particular interest because they can be linked to former climate patterns, which can be used to guide future climate predictions. Millennial and centennial time series contain evidence of very rare extreme events, which are often considered by society as ‘unprecedented’. By understanding their timing, magnitude and frequency in conjunction with prevailing climate regime, we can better forecast their future occurrence. This Virtual Special Issue (VSI) entitled Temporal and spatial patterns in Holocene floods under the influence of past global change, and their implications for forecasting “unpredecented” future events comprises 14 papers that focus on how centennial and millennia-scale natural and documentary flood archives help improve future flood science. Specifically, documentation of large and very rare flood episodes challenges society's lack of imagination regarding the scale of flood disasters that are possible (what we term here, the “unknown unknowns”). Temporal and spatial flood behaviour and related climate patterns as well as the reconstruction of flood propagation in river systems are important foci of this VSI. These reconstructions are crucial for the provision of robust and reliable data sets, knowledge and baseline information for future flood scenarios and forecasting. We argue that it remains difficult to establish analogies for understanding flood risk during the current period of global warming. Most studies in this VSI suggest that the most severe flooding occurred during relatively cool climate periods, such as the Little Ice Age. However, flood patterns have been significantly altered by land use and river management in many catchments and floodplains over the last two centuries, thereby obscuring the climate signal. When the largest floods in instrumental records are compared with paleoflood records reconstructed from natural and documentary archives, it becomes clear that precedent floods should have been considered in many cases of flood frequency analysis and flood risk modelling in hydraulic infrastructure. Finally, numerical geomorphological analysis and hydrological simulations show great potential for testing and improving our understanding of the processes and factors involved in the temporal and spatial behaviour of floods. © 2025 The Authors

Effects of long-term wetland variations on flood risk assessments in the Yangtze River Basin - Guo, Ziying; Shi, Xiaogang; Zhang, Dingfan; Zhao, Qunshan (Environmental Impact Assessment Review, 2026)
Flooding is the most frequent natural disaster in the Yangtze River Basin (YRB), causing significant socio-economic damages. In recent decades, abundant wetland resources in the YRB have experienced substantial changes and played a significant role in strengthening the hydrological resilience to flood risks. However, wetland-related approaches remain underdeveloped for mitigating flood risks in the YRB due to the lack of considering long-term wetland effects in the flood risk assessment. Therefore, this study develops an wetland-related GIS-based spatial multi-index flood risk assessment model by incorporating the effects of wetland variations, to investigate the long-term implications of wetland variations on flood risks, to identify dominant flood risk indicators under wetland effects, and to provide wetland-related flood risk management suggestions. These findings indicate that wetlands in the Taihu Lake Basin, Wanjiang Plain, Poyang Lake Basin, and Dongting and Honghu Lake Basin could enhance flood control capacity and reduce flood risks in most years between 1985 and 2021 except years with extreme flood disasters. Wetlands in the Sichuan Basin have aggravated but limited impacts on flood risks. Precipitation in the Taihu Lake Basin and Poyang Lake Basin, runoff and vegetation cover in the Wanjiang Plain, GDP in the Taihu Lake Basin, population density in the Taihu lake Basin, Dongting and Honghu Lake Basin, and the Sichuan Basin are dominant flood risk indicators under wetland effects. Reasonably managing wetlands, maximizing stormwater storage capacity, increasing vegetation coverage in urbanized and precipitated regions are feasible suggestions for developing wetland-related flood resilience strategies in the YRB. © 2025 The Authors

Reservoir Potential Unlocked: Synergies Between Low-Salinity Water Flooding, Nanoparticles and Surfactants in Enhanced Oil Recovery─A Review - Mumbere, Walidi; Sagala, Farad; Gupta, Uttam; Bbosa, Denis (ACS Omega, 2025)
This review explores the synergistic application of low-salinity water flooding (LSWF), nanoparticles, and surfactants in enhanced oil recovery (EOR), emphasizing their combined potential to address modern oil production challenges. It highlights the ability of LSWF to alter reservoir wettability, improve sweep efficiency, nanoparticles to enhance fluid mobility, and reduce interfacial tension, and surfactants to lower the interfacial tension and promote emulsification. All of this aim to provide practical, easy-to-use, and sustainable solutions for oil recovery. The review discusses existing research gaps in the long-term stability of nanoparticle-surfactant complexes, site-specific differences in rock-fluid interactions, and economic viability across diverse reservoirs. The review summarizes experimental findings, demonstrating recovery rates of 45–55% for nanoparticles, 50–60% for surfactants, and 40–50% for LSWF with improvements of 75–82% through this integrated approach. Additionally, the review addresses technological advancements, environmental considerations, and economic feasibility, highlighting challenges such as nanoparticle agglomeration and surfactant adsorption. A bibliographic analysis of global research trends, mechanisms, and field applications underscores the importance of interdisciplinary collaboration in optimizing this strategy for sustainable and efficient EOR processes. The findings aim to guide researchers and industry professionals in leveraging the synergistic effects of these methods to maximize oil recovery and reduce environmental footprints with a proposition to develop advanced characterization techniques, and verifying practicality through field implementation studies © 2025 The Authors. Published by American Chemical Society

Impact of Climate Change on Human Health in Thailand: A Literature Review - Ratanawong, Pitcha; Nunthaitaweekul, Pachanat; Huynh, Phuong Trang; Weesakul, Uruya (Journal of Disaster Research, 2025)
This study aims to find and summarize published studies that examined the effects of climate change on human health and diseases in Thailand by conducting aliterature review using the preferred reporting items for systematic reviews and meta-analysis guidelines between October 17, 2023, and January 31, 2024. We earched PubMed and OvidSP for relevant research. We included studies that were written in English orThai; primary research focused on climate change or its subsets (natural disasters or climate issues, such as rising temperatures and altered weather patterns that increase the frequency, intensity, and severity of manynatural disasters and climate issues); focused on human health; indexed by PubMed or OvidSP; available as published research with full-text journal articles; and published in 2013 or later. Our search yielded 53 relevant articles. These articles identified five main categories of climate issues: temperature, rainfall/precipitation, humidity, wind speed, and flooding. We identified five categories of health issues: dengue, respiratory diseases and infections, malaria, skin diseases/symptoms, and other health issues. The most studied relationship is between temperature and dengue. Most articles reported the harmful effects of climate issues on health, although four reported opposite effects, and seven reported no significant associations. Among the 53 articles, ten utilized prediction models. The main goal of this review is to summarize current research to guide future studies and assist policymakers in prioritizing climate-related health policies in Thailand. Study limitations include the use of only two databases, the restriction to articles from 2013 onwards, and the inclusion of only articles in English and Thai, which may have limited the number of articles found for this literature review. © 2025, Fuji Technology Press. All rights reserved.

Non-Aquatic Fauna of Amazonian Floodplain Forests and its Responses to Seasonal Flooding - Pedroza, Diego; Cohn-Haft, Mario; Haugaasen, Torbjørn (Wetlands, 2025)
The non-aquatic fauna (e.g. insects, birds, mammals) that occupies seasonally flooded floodplain forests in the Amazon is a major component of the region’s biodiversity, and the responses portrayed to cope with this inundation are varied. However, no systematic review of these species, including specialist species (exclusive to this environment), and their responses to seasonal inundation has yet been performed. Here, we provide an up-to-date and thorough examination of research on non-aquatic fauna that utilize Amazonian floodplain forests and their responses to seasonal flooding. We conducted a survey of published and unpublished studies from 1853 to 2023 through the Web of Science and Google Scholar platforms. We found a total of 445 studies, including 11,513 species of non-aquatic animals that inhabit floodplain forests. We identified ten main types of responses to flooding, the three most common being vertical migration, occupation of floating substrates and eggs submerged in a dormant state. Results suggest great behavioral, morphological and physiological plasticity among non-aquatic species, including those that are not floodplain forest specialists. Several types of responses occur independently in widely distinct taxonomic groups, emphasizing convergent strategies to deal with seasonal flooding. Our findings underline the uniqueness of the floodplain fauna and its importance for the regional biodiversity conservation agenda. © The Author(s), under exclusive licence to Society of Wetland Scientists 2025.

Managing floods and droughts synergistically: A transformative governance approach - Sánchez, Ana Núñez; Koehler, Johanna; Van Loon, Anne F. (PLOS Water, 2025)
Floods and droughts cause large economic and environmental impacts and incalculable human suffering. Despite growing evidence of important synergies in their management, floods and droughts tend to be mostly managed in silos. The synergistic management of flood and drought risk is limited by the inability of current governance systems to change at the scope, depth and speed required to address the emerging challenges of climate change induced hydroclimatic risks. Building on the concept of continuous transformational change and combining key elements across sectoral governance frameworks, this paper proposes a transformative governance conceptual framework that enables national governments to work across silos in a whole of government approach to lead a whole of society effort to manage the whole hydroclimatic spectrum. Spain, a country with an advanced hydroclimatic risk management system, is presented as an illustrative example to explore the possible idiosyncrasies of implementing the proposed changes on the ground. © 2025 Núñez Sánchez et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Extreme and compound events in lakes - Woolway, R. Iestyn; Zhang, Yunlin; Jennings, Eleanor; Zohary, Tamar; Jane, Stephen F.; Jansen, Joachim; Weyhenmeyer, Gesa A.; Long, Di; Fleischmann, Ayan; Feng, Lian; Qin, Boqiang; Shi, Kun; et al. (Nature Reviews Earth and Environment, 2025)
Extreme and compound events disrupt lake ecosystems worldwide, with their frequency, intensity and duration increasing in response to climate change. In this Review we outline evidence of the occurrence, drivers and impact of extreme and compound events in lakes. Univariate extremes, which include lake heatwaves, droughts and floods, underwater dimming episodes and hypoxia, can occur concurrently, sequentially or simultaneously at different locations to form multivariate, temporal or spatial compound events, respectively. The probability of extreme and compound events is increasing owing to climate warming, declining lake water levels in half of lakes globally, and basin-scale anthropogenic stressors, such as nutrient pollution. Most in-lake extreme events are inherently compound in nature owing to tightly coupled physical, chemical and biological underlying processes. The cascading effects of compound events propagate or dissipate through lakes. For example, a heatwave might trigger stratification and oxygen depletion, subsequently leading to fish mortality or the proliferation of harmful algal blooms. Interactions between extremes are increasingly observed and can trigger feedback loops that exacerbate harmful algal blooms and fishery declines, leading to severe ecological and socio-economic consequences. Managing the increasing risk of compound events requires integrated models, coordinated monitoring and proactive adaptation strategies tailored to the vulnerabilities of lake ecosystems. © Springer Nature Limited 2025.

Solastalgies. Changements climatiques et deuils inégaux - Uhl, Magali; Niemeyer, Katharina (Frontières, 2025)
Le présent numéro de la revue Frontières se penche sur le concept et les expériences de la solastalgie en les liant aux changements climatiques et aux inégalités sociales et géographiques subséquentes devant le deuil. Par conséquent, la solastalgie se conjugue ici au pluriel pour témoigner des manières différenciées de la vivre et de la penser. Le numéro accueille des articles provenant de plusieurs pays, en sciences sociales, en humanités environnementales, en histoire de l’art ainsi qu’en études des médias et de la communication afin de nourrir un regard transdisciplinaire et international sur le sujet. Partant de corpus ou de cas d’études empiriques ou artistiques, la variété des contributions publiées souligne l’étendue actuelle des recherches sur la solastalgie et sur le deuil écologique.

L’espace vécu sur Tshitassinu : cartographie participative et représentations du territoire des jeunes Pekuakamiulnuatsh (Québec) - Hirt, Irène; Desbiens, Caroline; Boivin, Hélène; Nepton, Michel (Revue d’études autochtones, 2025)
Au Canada, les Premières Nations accordent une importance croissante aux points de vue des jeunes dans leurs projets d’autodétermination politique et territoriale. Cet article présente un atelier de cartographie participative d’une journée mis en oeuvre dans le cadre du partenariat de recherche « Tshishipiminu » (2011 à 2019) entre des géographes de l’Université Laval et Pekuakamiulnuatsh Takuhikan, autorité politique de la Nation Ilnu de Mashteuiatsh (Québec). L’atelier a été réalisé en avril 2016 avec des jeunes Pekuakamiulnuatsh de 15 et 16 ans pour documenter leurs représentations et pratiques du territoire. L’activité a mobilisé cartes et objets comme supports de discussions collectives et la production de cartes mentales comme outils d’expression des espaces vécus. L’atelier montre que si les jeunes n’ont pas tous et toutes une vision politique de leur territoire, ils et elles continuent généralement à y pratiquer les activités liées à la culture ilnu (chasse, pêche, artisanat, etc.). Les transformations coloniale et industrielle du territoire ne les empêchent pas, en outre, d’éprouver des sentiments d’appartenance à l’égard de celui-ci. Enfin, ils et elles se réapproprient des espaces d’origine coloniale, dont l’ilnu assi (la « réserve »), devenu un marqueur d’identification.

Research on the Comprehensive Evaluation Model of Risk in Flood Disaster Environments - Yu, Yan; Zhou, Tianhua (Water (Switzerland), 2025)
Losses from floods and the wide range of impacts have been at the forefront of hazard-triggered disasters in China. Affected by large-scale human activities and the environmental evolution, China’s defense flood situation is undergoing significant changes. This paper constructs a comprehensive flood disaster risk assessment model through systematic analysis of four key factors—hazard (H), exposure (E), susceptibility/sensitivity (S), and disaster prevention capabilities (C)—and establishes an evaluation index system. Using the Analytic Hierarchy Process (AHP), we determined indicator weights and quantified flood risk via the following formula R = H × E × V × C. After we applied this model to 16 towns in coastal Zhejiang Province, the results reveal three distinct risk tiers: low (R < 0.04), medium (0.04 ≤ R ≤ 0.1), and high (R > 0.1). High-risk areas (e.g., Longxi and Shitang towns) are primarily constrained by natural hazards and socioeconomic vulnerability, while low-risk towns benefit from a robust disaster mitigation capacity. Risk typology analysis further classifies towns into natural, social–structural, capacity-driven, or mixed profiles, providing granular insights for targeted flood management. The spatial risk distribution offers a scientific basis for optimizing flood control planning and resource allocation in the district. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Assessing Community Perception, Preparedness, and Adaptation to Urban Flood Risks in Malaysia - Kumaresen, Maniyammai; Teo, Fang Yenn; Selvarajoo, Anurita; Sivapalan, Subarna; Falconer, Roger A. (Water (Switzerland), 2025)
Urban flooding has significantly impacted the livelihoods of households and communities worldwide. It highlights the urgency of focusing on both flood preparedness and adaptation strategies to understand the community’s perception and adaptive capacity. This study investigates the levels of risk perception, flood preparedness, and adaptive capacity, while also exploring the inter-relationships among these factors within the context of urban flooding in Malaysia. A quantitative approach was employed, involving a structured questionnaire administered to residents in flood-prone urban areas across Greater Kuala Lumpur, Malaysia. A total of 212 responses were analysed using descriptive statistics, categorical index classification, and Spearman correlation analysis. The findings indicate that residents generally reported high levels of risk perception and preparedness, although adaptive capacity exhibited greater variability, with a mean score of 3.97 (SD = 0.64). Positive associations were found among risk perception, flood preparedness, and adaptive capacity. This study contributes to the existing knowledge by providing evidence on community resilience and highlighting key factors that can guide flood management policies and encourage adaptive planning at the community level. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

The Impact of Land Use Change on Improving Surface Runoff, Peak Flood Discharge, and Sedimentation in the Maros Watershed - Mansida, Amrullah; Gaffar, Farida; Zainuddin, Muh Amir; Syamsuri, Andi Makbul (Engineering, Technology and Applied Science Research, 2025)
The present study aims to analyze how land use changes affect surface runoff, flood peak discharge, and sedimentation. Moreover, it aims to assess the specific impact of these changes on the flood peak discharge and to propose effective strategies for reducing flood risks. Visual interpretation of the land use changes was utilized based on Landsat imagery from 2010, 2017, and 2021, along with SPOT 4 satellite data. Soil samples were collected to measure the erosion rates, water discharge, and sediment loads (both suspended and bedload). The findings showed a significant reduction in the secondary dryland forest, which shrank by 52.71 km² (a 7.99% decrease), while shrub and agricultural areas expanded by 51.03 km² (a 7.73% increase). This shift contributed to a greater surface runoff and an increased erosion, especially in dryland-shrubland areas, where erosion reached 4,248.33 tons/ha/year. The flood peak discharges rose sharply in areas converted to agriculture and settlements, halving the flood return period from 50 years to just 25 years. During the wet season, the sediment loads peaked at 782.17 tons/day (equivalent to 377,293.48 m³ per year), while the dry season sedimentation—mostly driven by quarrying—reached 10.45 tons/day. To address these issues, the current study proposes adopting adaptive spatial planning, restoring the watershed, and applying nature-based solutions, such as Biopore Absorption Holes (BAH), Rainwater Infiltration Wells (RIW), and similar technologies. © by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Identification of Critical Exposed Elements and Strategies for Mitigating Secondary Hazards in Flood-Induced Coal Mine Accidents - Yang, Xue; Liu, Chen; Pan, Langxuan; Su, Xiaona; He, Ke; Mao, Ziyu (Water (Switzerland), 2025)
Natech events, involving multi-hazard coupling and cascading effects, pose serious threats to coal mine safety. This paper addresses flood-induced Natech scenarios in coal mining and introduces a two-stage cascading analysis framework based on hazard systems theory. A tri-layered network—comprising natural hazards, exposed elements, and secondary hazards—models hazard propagation. In Stage 1, an improved adjacency information entropy algorithm with multi-hazard coupling coefficients identifies critical exposed elements. In Stage 2, Dijkstra’s algorithm extracts key risk transmission paths. A dual-dimensional classification method, based on entropy and transmission risk, is then applied to prioritize emergency responses. This method integrates the criticality of exposed elements with the risk levels associated with secondary disaster propagation paths. Case studies validate the framework, revealing: (1) Hierarchical heterogeneity in the network, with surface facilities and surrounding hydrological systems as central hubs; shaft and tunnel systems and surrounding geological systems are significantly affected by propagation from these core nodes, exhibiting marked instability. (2) Strong risk polarization in secondary hazard propagation, with core-node-originated paths being more efficient and urgent. (3) The entropy-risk classification enables targeted hazard control, improving efficiency. The study proposes chain-breaking strategies for precise, hierarchical, and timely emergency management, enhancing coal mine resilience to flood-induced Natech events. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Response of Grain Yield to Extreme Precipitation in Major Grain-Producing Areas of China Against the Background of Climate Change—A Case Study of Henan Province - Sheng, Keding; Li, Rui; Zhang, Fengqiuli; Chen, Tongde; Liu, Peng; Hu, Yanan; Li, Bingyin; Song, Zhiyuan (Water (Switzerland), 2025)
Based on the panel data of daily meteorological stations and winter wheat yield in Henan Province from 2000 to 2023, this study comprehensively used the Mann–Kendall trend test, wavelet coherence analysis (WTC), and other methods to reveal the temporal and spatial evolution of extreme precipitation and its multi-scale stress mechanism on grain yield. The results showed the following: (1) Extreme precipitation showed the characteristics of ‘frequent fluctuation-gentle trend-strong spatial heterogeneity’, and the maximum daily precipitation in spring (RX1DAY) showed a significant uplift. The increase in rainstorm events (R95p/R99p) in the southern region during the summer is particularly prominent; at the same time, the number of consecutive drought days (CDDs > 15 d) in the middle of autumn was significantly prolonged. It was also found that 2010 is a significant mutation node. Since then, the synergistic effect of ‘increasing drought days–increasing rainstorm frequency’ has begun to appear, and the short-period coherence of super-strong precipitation (R99p) has risen to more than 0.8. (2) The spatial pattern of winter wheat in Henan is characterized by the three-level differentiation of ‘stable core area, sensitive transition zone and shrinking suburban area’, and the stability of winter wheat has improved but there are still local risks. (3) There is a multi-scale stress mechanism of extreme precipitation on winter wheat yield. The long-period (4–8 years) drought and flood events drive the system risk through a 1–2-year lag effect (short-period (0.5–2 years) medium rainstorm intensity directly impacted the production system). This study proposes a ‘sub-scale governance’ strategy, using a 1–2-year lag window to establish a rainstorm warning mechanism, and optimizing drainage facilities for high-risk areas of floods in the south to improve the climate resilience of the agricultural system against the background of climate change. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Empirical Modelling of Ice-Jam Flood Hazards Along the Mackenzie River in a Changing Climate - Lindenschmidt, Karl-Erich; Gomez, Sergio; Saade, Jad; Perry, Brian; Das, Apurba (Water (Switzerland), 2025)
This study introduces a novel methodology for assessing ice-jam flood hazards along river channels. It employs empirical equations that relate non-dimensional ice-jam stage to discharge, enabling the generation of an ensemble of longitudinal profiles of ice-jam backwater levels through Monte-Carlo simulations. These simulations produce non-exceedance probability profiles, which indicate the likelihood of various flood levels occurring due to ice jams. The flood levels associated with specific return periods were validated using historical gauge records. The empirical equations require input parameters such as channel width, slope, and thalweg elevation, which were obtained from bathymetric surveys. This approach is applied to assess ice-jam flood hazards by extrapolating data from a gauged reach at Fort Simpson to an ungauged reach at Jean Marie River along the Mackenzie River in Canada’s Northwest Territories. The analysis further suggests that climate change is likely to increase the severity of ice-jam flood hazards in both reaches by the end of the century. This methodology is applicable to other cold-region rivers in Canada and northern Europe, provided similar fluvial geomorphological and hydro-meteorological data are available, making it a valuable tool for ice-jam flood risk assessment in other ungauged areas. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Analysis of the Availability of Residential Locations Based on Flood Mitigation in Momunu District, Buol Regency - Assiddiqi, Moh. Hasbi; Lanuru, Mahatma; Tumpu, Miswar (Engineering, Technology and Applied Science Research, 2025)
The population growth and limited land availability for housing have forced some communities to reside in disaster-prone areas, particularly those vulnerable to flooding. This study, presents a spatial-based assessment that integrates physical and regulatory criteria to identify safe and appropriate residential zones. Using spatial analysis through map overlays, scoring, and weighting techniques, the research evaluates seven key physical variables: land slope, drainage, erosion, land use, road accessibility, access to essential facilities, and flood hazard vulnerability. The novelty of this study lies in the integration of flood mitigation into residential suitability mapping that is aligned with the Regional Spatial Plan (RTRW), offering a comprehensive and policy-relevant framework. The findings reveal that 20.85% of the study area is suitable for housing, 61.83% is conditionally suitable, and 17.32% is unsuitable. Based on the land availability and RTRW compliance, residential land is categorized into Available Location I (47 hectares) and Available Location II (423 hectares). These results provide not only a technical basis for guiding safe settlement, but also a strategic reference for planners and policymakers. The study proposes that future research incorporates socio-economic variables and real-time flood data for dynamic risk assessment. Furthermore, stakeholder engagement and community-based mapping are proposed to enhance the local resilience and ensure participatory planning. Ultimately, this research contributes to sustainable urban development by supporting informed decision-making for safer, flood-resilient settlements. © by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Assessing Flooding from Changes in Extreme Rainfall: Using the Design Rainfall Approach in Hydrologic Modeling - Jalowska, Anna M.; Line, Daniel E.; Spero, Tanya L.; Kurki-Fox, J. Jack; Doll, Barbara A.; Bowden, Jared H.; Gray, Geneva M. E. (Water (Switzerland), 2025)
Quantifying future changes in extreme events and associated flooding is challenging yet fundamental for stormwater managers. Along the U.S. Atlantic Coast, Eastern North Carolina (ENC) is frequently exposed to catastrophic floods from extreme rainfall that is typically associated with tropical cyclones. This study presents a novel approach that uses rainfall data from five dynamically and statistically downscaled (DD and SD) global climate models under two scenarios to visualize a potential future extent of flooding in ENC. Here, we use DD data (at 36-km grid spacing) to compute future changes in precipitation intensity–duration–frequency (PIDF) curves at the end of the 21st century. These PIDF curves are further applied to observed rainfall from Hurricane Matthew—a landfalling storm that created widespread flooding across ENC in 2016—to project versions of “Matthew 2100” that reflect changes in extreme precipitation under those scenarios. Each Matthew-2100 rainfall distribution was then used in hydrologic models (HEC-HMS and HEC-RAS) to simulate “2100” discharges and flooding extents in the Neuse River Basin (4686 km2) in ENC. The results show that DD datasets better represented historical changes in extreme rainfall than SD datasets. The projected changes in ENC rainfall (up to 112%) exceed values published for the U.S. but do not exceed historical values. The peak discharges for Matthew-2100 could increase by 23–69%, with 0.4–3 m increases in water surface elevation and 8–57% increases in flooded area. The projected increases in flooding would threaten people, ecosystems, agriculture, infrastructure, and the economy throughout ENC. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Machine learning-based ensemble of Global climate models and trend analysis for projecting extreme precipitation indices under future climate scenarios - Kumar, G. Praveen; Dwarakish, G.S. (Environmental Monitoring and Assessment, 2025)
Monitoring changes in climatic extremes is vital, as they influence current and future climate while significantly impacting ecosystems and society. This study examines trends in extreme precipitation indices over an Indian tropical river basin, analyzing and ranking 28 Coupled Model Intercomparison Project Phase 6 (CMIP6) Global Climate Models (GCMs) based on their performance against India Meteorological Department (IMD) data. The top five performing GCMs were selected to construct multi-model ensembles (MMEs) using Machine Learning (ML) algorithms, Random Forest (RF), Support Vector Machine (SVM), Multiple Linear Regression (MLR), and the Arithmetic Mean. Statistical metrics reveal that the application of an RF model for ensembling performs better than other models. The analysis focused on six IMD-convention indices and eight indices recommended by the Expert Team on Climate Change Detection and Indices (ETCCDI). Future projections were examined for three timeframes: near future (2025–2050), mid-future (2051–2075), and far future (2076–2100) for SSP245 and SSP585 scenarios. Statistical trend analysis, the Mann-Kendall test, Sen’s Slope estimator, and Innovative Trend Analysis (ITA), were applied to the MME to assess variability and detect changes in extreme precipitation trends. Compared to SSP245, in the SSP585 scenario, Total Precipitation (PRCPTOT) shows a significant decreasing trend in the near future, mid-future, and far future and Moderate Rain (MR) shows a decreasing trend in the near future and far future of monsoon season. The findings reveal significant future trends in extreme precipitation, impacting Sustainable Development Goals (SDGs) achievement and providing crucial insights for sustainable water resource management and policy planning in the Kali River basin. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.
Keywords: Scopus_Alert_22_Aout_2025

Multi-Sensor Flood Mapping in Urban and Agricultural Landscapes of the Netherlands Using SAR and Optical Data with Random Forest Classifier - Narin, Omer Gokberk; Sekertekin, Aliihsan; Bayik, Caglar; Bektas Balcik, Filiz; Arıkan, Mahmut; Sanli, Fusun Balik; Abdikan, Saygin (Remote Sensing, 2025)
Floods stand as one of the most harmful natural disasters, which have become more dangerous because of climate change effects on urban structures and agricultural fields. This research presents a comprehensive flood mapping approach that combines multi-sensor satellite data with a machine learning method to evaluate the July 2021 flood in the Netherlands. The research developed 25 different feature scenarios through the combination of Sentinel-1, Landsat-8, and Radarsat-2 imagery data by using backscattering coefficients together with optical Normalized Difference Water Index (NDWI) and Hue, Saturation, and Value (HSV) images and Synthetic Aperture Radar (SAR)-derived Grey Level Co-occurrence Matrix (GLCM) texture features. The Random Forest (RF) classifier was optimized before its application based on two different flood-prone regions, which included Zutphen’s urban area and Heijen’s agricultural land. Results demonstrated that the multi-sensor fusion scenarios (S18, S20, and S25) achieved the highest classification performance, with overall accuracy reaching 96.4% (Kappa = 0.906–0.949) in Zutphen and 87.5% (Kappa = 0.754–0.833) in Heijen. For the flood class F1 scores of all scenarios, they varied from 0.742 to 0.969 in Zutphen and from 0.626 to 0.969 in Heijen. Eventually, the addition of SAR texture metrics enhanced flood boundary identification throughout both urban and agricultural settings. Radarsat-2 provided limited benefits to the overall results, since Sentinel-1 and Landsat-8 data proved more effective despite being freely available. This study demonstrates that using SAR and optical features together with texture information creates a powerful and expandable flood mapping system, and RF classification performs well in diverse landscape settings. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

Predictive Flood Uncertainty Associated with the Overtopping Rates of Vertical Seawall on Coral Reef Topography - Zhang, Hongqian; Lu, Bin; Geng, Yumei; Liu, Ye (Water (Switzerland), 2025)
Accurate prediction of wave overtopping rates is essential for flood risk assessment along coral reef coastlines. This study quantifies the uncertainty sources affecting overtopping rates for vertical seawalls on reef flats, using ensemble simulations with a validated non-hydrostatic SWASH model. By generating extensive random wave sequences, we identify spectral resolution, wave spectral width, and wave groupiness as the dominant controls on the uncertainty. Statistical metrics, including the Coefficient of Variation ((Formula presented.)) and Range Uncertainty Level ((Formula presented.)), demonstrate that overtopping rates exhibit substantial variability under randomized wave conditions, with (Formula presented.) exceeding 40% for low spectral resolutions (50–100 bins), while achieving statistical convergence ((Formula presented.) around 20%) requires at least 700 frequency bins, far surpassing conventional standards. The (Formula presented.), which describes the ratio of extreme to minimal overtopping rates, also decreases markedly as the number of frequency bins increases from 50 to 700. It is found that the overtopping rate follows a normal distribution with 700 frequency bins in wave generation. Simulations further demonstrate that overtopping rates increase by a factor of 2–4 as the JONSWAP spectrum peak enhancement factor ((Formula presented.)) increases from 1 to 7. The wave groupiness factor ((Formula presented.)) emerges as a predictor of overtopping variability, enabling a more efficient experimental design through reduction in groupiness-guided replication. These findings establish practical thresholds for experimental design and highlight the critical role of spectral parameters in hazard assessment. © 2025 by the authors.
Keywords: Scopus_Alert_22_Aout_2025

A multi-hazard assessment approach to reveal and compare heat- and flood-related risks and inequalities in London, Boston, and Sydney - Longato, Davide; Maragno, Denis (International Journal of Disaster Risk Reduction, 2025)
Keywords: Scopus_Alert_22_Aout_2025

Floods, land loss, and gendered vulnerability: Assessing the social impacts of small hydropower in Vietnam - Swe, Khin Nilar; Phuong, Ho Thi; Thinh, Tran Duc; Chan, Nyien (Environmental Development, 2025)
Keywords: Scopus_Alert_22_Aout_2025

The Paradigm Shift in Scientific Interest on Flood Risk: From Hydraulic Analysis to Integrated Land Use Planning Approaches - Franco, Ángela; García-Ayllón, Salvador (Water, 2025)
Floods are natural hazards that have the greatest socioeconomic impact worldwide, given that 23% of the global population live in urban areas at risk of flooding. In this field of research, the analysis of flood risk has traditionally been studied based mainly on approaches specific to civil engineering such as hydraulics and hydrology. However, these patterns of approaching the problem in research seem to be changing in recent years. During the last few years, a growing trend has been observed towards the use of methodology-based approaches oriented towards urban planning and land use management. In this context, this study analyzes the evolution of these research patterns in the field by developing a bibliometric meta-analysis of 2694 scientific publications on this topic published in recent decades. Evaluating keyword co-occurrence using VOSviewer software version 1.6.20, we analyzed how phenomena such as climate change have modified the way of addressing the study of this problem, giving growing weight to the use of integrated approaches improving territorial planning or implementing adaptive strategies, as opposed to the more traditional vision of previous decades, which only focused on the construction of hydraulic infrastructures for flood control.
Keywords: Scopus_Alert_22_Aout_2025

Exploring Waterlogging Challenges, Causes and Mitigating Strategies in Maize ( Zea mays L.) - Behera, Supriya; Kar, Ipsita; Yadav, Ashok; Sahu, Ankita (Journal of Agronomy and Crop Science, 2025)
ABSTRACT Waterlogging is a critical abiotic stress factor severely affecting maize, one of the World's most widely cultivated cereal crops. Globally, maize is a crucial food crop, grown in diverse agro‐climatic zones, from subtropical to temperate climates. Waterlogging, resulting from flooding, intense rainfall and inefficient drainage systems, continues to be a major abiotic stress factor influencing crop productivity globally. Prolonged exposure to excess soil moisture leads to oxygen depletion in the root zone, resulting in restricted aerobic respiration, impaired nutrient uptake and disruption of physiological processes. This review aims to provide a comprehensive overview of the morphological, physiological and biochemical changes maize undergoes in response to waterlogging stress. Key aspects such as root system adaptation, reduction in photosynthetic efficiency, accumulation of reactive oxygen species (ROS) and hormonal imbalances are systematically examined. Furthermore, we delve into the metabolic shifts that enable maize to survive under anaerobic conditions, including alterations in energy metabolism, carbohydrate partitioning, and activating antioxidant defence mechanisms. The role of key signalling molecules such as ethylene is explored, highlighting their involvement in regulating stress responses. Additionally, the review discusses agronomic and genetic approaches for improving waterlogging tolerance in maize, including the development of stress‐resilient cultivars through breeding and biotechnological interventions. By synthesising recent advances in understanding maize's response to waterlogging, this paper identifies gaps and proposes future research directions, focusing on the integration of molecular and field‐based strategies. The insights from this review are crucial for developing sustainable agricultural practices aimed at mitigating the adverse impacts of waterlogging on maize productivity, particularly in flood‐prone areas. Breeding for waterlogging resilience integrates the creation of robust varieties, plant morphology optimisation, and utilisation of tolerant secondary traits through combined conventional and biotechnological breeding strategies.
Keywords: Scopus_Alert_22_Aout_2025

Quantifying the spatiotemporal dynamics of urban flooding susceptibility in the greater bay area under shared socio-economic pathways using the SD-PLUS-LightGBM framework - Zhou, Shiqi; Jia, Weiyi; Geng, Xiwen; Xu, Haowen; Diao, Haifeng; Liu, Zhiyu; Wang, Mo; Fu, Xiaoping; Wu, Yuwei; Qiao, Renlu; Wu, Zhiqiang (Resources, Conservation and Recycling, 2025)
Urbanization and climate change keep intensifying extreme rainfall events. Previous studies have explored urban flood susceptibility, yet a comprehensive approach that unifies these perspectives has remained underdeveloped. This study established a holistic framework using the SD-PLUS-LightGBM model with multiple variables under three SSP-RCP scenarios to predict spatial-temporal dynamics of flood susceptibility in the Greater Bay Area between 2030 and 2050. Compared with traditional models, LightGBM established superior predictive accuracy and operational reliability for urban flood susceptibility mapping. The results indicated a non-linear expansion of high-susceptibility zones, with SSP5–8.5 projections showing a two-fold increase in vulnerable areas by 2050 relative to 2020 baselines. Regions experiencing pronounced susceptibility transitions were expected to grow significantly (0.23 % of the total area), concentrated in historic urban cores and peri‑urban interfaces. This study offered an in-depth approach to stormwater management along with targeted recommendations for sustainable urban planning and design. © 2025
Keywords: Scopus_Alert_15_Aout_2025

Seasonal Influences of Precipitation and River Stage on Groundwater Levels in Platte River Watersheds Vulnerable to Spring Floods - Kim, Incheol; Koya, Sinan Rasiya; Roy, Tirthankar; Eun, Jongwan (Journal of Hydrologic Engineering, 2025)
Spring floods occurring in the Midwest US are often aggravated by meteorological and hydrological conditions. In this study, the seasonal influences of precipitation (PRCP) and river stage (RS) on groundwater level (GWL) fluctuations were analyzed for the Middle and Lower Platte watersheds along the Platte River in a Midwestern catchment that is vulnerable to spring floods. Statistical analysis was conducted to simulate GWL with a moving average-based time lag consideration approach by using multiple hydrological data sets for 25 study sites. The results showed that the time lag consideration approach appropriately provided the regional information of water infiltration characteristics among GWL, PRCP, and RS for each study site. Also, the correlations of GWL with PRCP and RS were found to vary depending on the season. Especially in the early spring season, the correlation of GWL with PRCP is very weak (correlation coefficient=0.001 to 0.198). This may be due to entirely or partially frozen ground, which prevents rainwater from penetrating into the aquifer, causing large amounts of runoff and contributing to frequent flooding in early spring. In addition, statistical analysis showed that accounting for the time lag of PRCP and RS improved GWL simulation performance, and their influence varied by season. © 2025 American Society of Civil Engineers.
Keywords: Scopus_Alert_15_Aout_2025

Comparative assessment of flood risk to critical infrastructure: The case of Utah, USA - Clark, Austin S.; Collins, Tim (International Journal of Disaster Risk Reduction, 2025)
During and after a disaster, selected services and systems are needed to recover and maintain important functions of society. These are deemed critical infrastructure (CI). When these services are disrupted due to the impacts of a disaster, response and recovery may be slowed or halted. As flooding events are occurring more often across larger geographic extents, advancing methods for assessing risks of flooding to CI is vital. We use Utah, USA as a case study to demonstrate a novel, transferable approach for assessing fine-scale flood risks to CI across large geographic areas. Specifically, our assessment approach integrates high-resolution building footprints of schools, first responder facilities, and hospitals, and flood risk maps from a state-of-the-art big data flood model and the U.S. Federal Emergency Management Agency (FEMA). We show that 94 CI facilities across Utah are at risk of severe flooding, and that those risks to CI are almost entirely overlooked by FEMA flood risk maps. Though nearly every CI building is located outside of FEMA flood zones, FEMA maps inaccurately and incompletely represent flood risks, indicating that future flood risk assessment approaches should use flood risk maps from other sources. The approach we introduce can be used to assess flood risks to CI elsewhere, and case study results can be applied to inform flood risk reduction efforts in Utah. © 2025 Elsevier Ltd
Keywords: Scopus_Alert_15_Aout_2025

Impact of climate change scenario on sea level rise and future coastal flooding in major coastal cities of India - Chakrabortty, Rabin; Ali, Tarig; Atabay, Serter; Roy, Paramita; Pande, Chaitanya Baliram (Scientific Reports, 2025)
This study evaluates the impacts of projected sea level rise (SLR) on coastal flooding across major Indian cities: Mumbai, Kolkata, Chennai, Visakhapatnam, Surat, Kochi, Thiruvananthapuram, and Mangaluru. Machine learning models, including Long Short-Term Memory (LSTM), Random Forest (RF), and Gradient Boosting (GB), has been employed to assess flood risks under four Shared Socioeconomic Pathways (SSP 126, 245, 370, and 585) emission scenarios. The research utilized these models because they demonstrate high performance in handling difficult data relationships and both temporal patterns and sophisticated environmental data. SLR projections provided by computers generate forecasts that combine with digital elevation models (DEMs) to determine coastal flooding risks and locate flood-prone areas. Results reveal that Mumbai and Kolkata face the highest flood risks, particularly under high emission scenarios, while Kochi and Mangaluru exhibit moderate exposure. Model performance is validated using residual analysis and Receiver Operating Characteristic (ROC) curves, confirming reliable predictive accuracy. These findings provide essential information for urban planners and policymakers to prioritize climate adaptation strategies in vulnerable coastal cities. © The Author(s) 2025.
Keywords: Scopus_Alert_15_Aout_2025

Multi-Criteria Decision Analysis for Managed Aquifer Recharge (MAR): A Flood-Responsive Approach in Milpa Alta, Mexico City - Areu-Rangel, Omar S.; Singh, Amrie; Bonasia, Rosanna (Environmental Quality Management, 2025)
Milpa Alta, located southeast of Mexico City, is a key region for environmental sustainability due to its volcanic soil, biodiversity, and critical role in aquifer recharge, which supports the city's water supply. However, rapid urbanization has severely impacted the area, causing reduced vegetation cover, increased runoff, and diminished groundwater recharge, which intensify flooding, soil erosion, and water scarcity. This study aims to identify optimal sites for managed aquifer recharge (MAR) structures in Milpa Alta through a multi-criteria analysis incorporating criteria such as topography, land use, proximity to urban areas, and drainage networks. Uniquely, hydraulic simulations of flood scenarios were integrated into the analysis to improve the precision of site selection. Geographic information systems (GIS) were used to assess and combine these criteria, providing a spatial evaluation of suitability. Results indicate that the central and northern regions of Milpa Alta, particularly around San Francisco Tecoxpa and San Antonio Tecómitl, are most suitable for MAR implementation due to their permeable soils, gentle slopes, and proximity to agricultural lands and drainage networks. These MAR structures can enhance groundwater recharge and mitigate flood risks during extreme rainfall events, with the potential to capture up to 300,000 m3 of surface runoff during a single high-intensity storm event. Despite its strengths, the study acknowledges limitations such as the absence of detailed water quality analyses and the need for sensitivity testing of the criteria weighting. This research provides an innovative approach to MAR site selection by integrating flood simulations, offering a replicable model for similar regions. Successful implementation of MAR in Milpa Alta requires addressing water quality concerns, engaging stakeholders, and ensuring compliance with regulatory frameworks. The findings emphasize MAR's potential to balance urbanization pressures with sustainable water management and flood mitigation strategies in Mexico City's rapidly developing areas. © 2025 Wiley Periodicals LLC.
Keywords: Scopus_Alert_15_Aout_2025

HyEco: A hybrid hydrodynamic-cum-ecological modelling framework to demystify flood and human-health risks over flood-prone metropolis - Deopa, Rahul; Mohanty, Mohit Prakash (Water Research X, 2025)
Urban flooding, exacerbated by climate change and unregulated urbanization, poses significant risks to the built environment. In addition to physical damage, floodwaters often mobilize a hazardous mix of untreated sewage, industrial effluents, and undesirable pollutants, leading to severe microbial contamination in the floodwaters. This study introduces “HyEco”-an integrated framework comprising high-fidelity 3-way coupled hydrodynamic and ecological modelling with an aim to capture the “unhidden tangible flood risks” and “hidden intangible public-health risks” in tandem. Focusing on Delhi, India, a densely populated metropolis prone to recurrent urban flooding and associated health crises, the framework simulates the 2023 mega-flood event. Results show that approximately 63.5 % of the region is categorized under ‘high’ to ‘very high’ flood risk zones, with over 20 % of these areas housing around 15 % of the city's dense population. The hydrodynamic model outputs were forced into the ecological model to simulate the fate and transport of microbial contamination in floodwaters. Escherichia coli concentrations ranged from 772,868 to 790,000 MPN/100 mL, far exceeding established safety thresholds. A Quantitative Microbial Risk Assessment (QMRA) reveals elevated infection probabilities, particularly among children, with risks up to 2.60×10⁻³ under repeated exposure and 8.38×10⁻⁴ to 8.57×10⁻⁴ for pedestrian splash exposures. Unlike prior approaches that examine flood and microbial risks in isolation or depend on static datasets, HyEco overcomes key methodological gaps by dynamically integrating flood and microbial processes at high spatio-temporal resolution. The HyEco framework offers a scalable and actionable tool for integrated flood risk management and climate-resilient public health planning. © 2025
Keywords: Scopus_Alert_15_Aout_2025

Pedestrian vulnerability assessment of underground staircases in urban flooding - Wu, Wenqi; Zhu, Zhongfan; Zheng, Xinyu; Liu, Shuyou; Zhang, Dawei (Sustainable Cities and Society, 2025)
Urban underground flooding occurs frequently worldwide in the context of climate change and rapid urbanization, posing a serious threat to the travel safety of urban populations; in particular, staircases play an important role in the emergency evacuation of pedestrians in floodwater. Previous studies have identified the staircase configuration as a crucial factor influencing the evacuation difficulty of pedestrians in floodwater. However, the correlation between the geometric characteristics of staircase structures and pedestrian vulnerability is not fully understood, and few parametric studies have focused on the effects of wind intrusion into underground spaces and the effects of various engineering measures. This study thereby aims to assess pedestrian vulnerability in underground staircase floodwater as the width of the lower segment of the staircase increases, the effect of wind in the staircase is incorporated, and several flood prevention and/or windproof measures are implemented. Computational fluid dynamics (CFD) simulations were performed to reproduce the mean floodwater flow field and wind flow field on underground staircases. The findings show that (i) a variation in the width of the lower staircase after the rest platform affects pedestrian vulnerability, i.e., an increasing lower staircase width decreases the pedestrian risk to a certain degree; however, the jet behind the rest platform intensifies it; (ii) the incorporation of the wind effect when it intrudes the staircase obviously deteriorates the pedestrian vulnerability, and a discrepancy exists in the evacuation speeds of different pedestrian groups under a joint effect of wind and floodwater; and (iii) some engineering measures, especially windproof measures, have the potential to mitigate pedestrian vulnerability. These findings can serve as a reference for policymakers and stakeholders in coping with urban underground flooding hazards and guiding the emergency evacuation of people trapped in floodwater in the context of resilient city construction. © 2025 Elsevier Ltd
Keywords: Scopus_Alert_15_Aout_2025

Extreme precipitation risk assessment with improved WOA-Optimized copula model under composite conditions - Wang, Zhaocai; Ma, Chao; Wu, Junhao; Wu, Tunhua (Theoretical and Applied Climatology, 2025)
An accurate study of extreme precipitation risk events is crucial for flood control, urban planning, and engineering design. The Copula function effectively handles uncertainties and nonlinear interactions among multiple hydrological variables, capturing complex correlations in extreme precipitation events for more precise risk assessments. Selecting the parameters of the Copula function is critical, as it defines the function’s shape and the dependence structure between variables, influencing its application. Traditional parameterization methods, like maximum likelihood estimation and least squares, often require large datasets and distribution assumptions, making them cumbersome for high-dimensional data. This research presents a model using an enhanced whale optimization algorithm to estimate Copula parameters (CLCWOA-Copula), aiming to assess return period (RP) and failure probability associated with extreme precipitation risk events. Monthly precipitation data from Zhengzhou, China, from 1950 to 2024 is analyzed, using the 90th percentile as the extreme precipitation threshold. Marginal distributions are fitted using the P-III and gamma distributions, etc., which are then combined using CLCWOA-Copula to analyze coincident RP, joint RP, Kendall RP, and failure probability under composite conditions. The results demonstrate that this optimization method possesses strong global search capabilities and parallel computing abilities, yielding optimal Copula parameter values within few iterations and selecting the best-fit Copula function based on AIC, R², and RMSE. The Kendall RP and failure probability offer more accurate tools for extreme precipitation risk analysis; when Pmax reaches 540 mm, P90 reaches 1080 mm, or R90 reaches 0.83, a one-in-a-century extreme precipitation event is indicated. This study provides important insights for risk metrics applicable to extreme weather. © The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature 2025.
Keywords: Scopus_Alert_15_Aout_2025

Projections of extreme weather events according to climate change scenarios and populations at-risk in Brazil - Dantas, Leydson Galvíncio; Ferreira, Andrêa Jacqueline Fortes; Pinto Junior, Jony Arrais; Cortes, Taísa Rodrigues; Neves, Danielson Jorge Delgado; de Oliveira, Beatriz Fátima Alves; da Silveira, Ismael Henrique (Climatic Change, 2025)
Extreme weather events, such as heat waves, heavy rainfall and droughts, have become more frequent and intense in Brazil. According to climate change scenarios, this trend, which has a negative impact on people’s health and living conditions, will continue. Here, we analysed indicators for extreme weather events resulting from climate change, projected for the 21st century, alongside socio-demographic indicators for Brazilian municipalities, in an attempt to identify populations exposed to the risks of the climate crisis. We calculated the values of indicators for extreme air temperature and precipitation events, based on NEX-GDDP-CMIP6 data, for a reference period and for the future, as well as socio-demographic indicators based on recent census data. Using Spearman’s coefficient, we then calculated anomaly indicators for the future time intervals and analysed correlations with the socio-demographic indicators. Our results indicate a reduction in cold days and an increase in hot days and heat waves in both scenarios (SSP2-4.5 and SSP5-8.5), with the most changes occurring in the highest emission scenario. The extreme precipitation indicators suggest both an increase and a reduction in intense precipitation and droughts in a number of the country’s regions. The projected changes are more intense in the highest emission scenario, and in the North and Northeast regions. We noted a trend for greatest occurrence of extreme events in locations with a higher proportion of Black, Parda/Brown, Indigenous and Quilombola populations, and the socially vulnerable. We recommend that policies to adapt and mitigate the impacts of climate change focus on reducing inequalities and promoting climate justice. © The Author(s) 2025.
Keywords: Scopus_Alert_15_Aout_2025

Future Projection of Rainstorm and Flood Disaster Risk in Sichuan-Chongqing Region under CMIP6 Different Climate Change Scenarios - Yao, Ying; Li, Xiehui; Wang, Lei; Li, Hongying (Plateau Meteorology, 2025)
In recent years，rapid urbanization and global warming have led to frequent and severe rainstorm and flood disasters in the Sichuan-Chongqing region. This change will not only have a serious impact on the ecological environment and socio-economic development of the area，but also significantly increase the pressure on urban infrastructure and threaten the safety of people's lives and property. Therefore，it is particularly important to scientifically and accurately analyze the disaster risk of rainstorm and flood in Sichuan-Chongqing region in the past and future. This paper utilized daily precipitation data from 50 selected meteorological stations in the Sichuan-Chongqing region，precipitation data from 5 CMIP6 models，gridded population and economic data under Shared Socioeconomic Pathways（SSPs），as well as DEM and land use remote sensing data. Firstly，using Taylor diagrams，quantitative indices（S），and standardized anomaly sequences，the study evaluated the simulation performance of 5 individual CMIP6 models，an equal-weighted aggregation of 5 models（EWA-5），and unequally-weighted aggregations of 5 models（UEWA-5）for five selected extreme precipitation indices. Then，by building a comprehensive risk assessment model of rainstorm and flood disaster based on disaster risk and vulnerability of disaster bearing body，the study conducted risk assessments，future projections，and comparative analyses of rainstorm and flood disasters during baseline（1995-2014）and future near-term（2025-2044）and long-term （2045-2064）periods under three different climate change scenarios（SSP1-2. 6，SSP2-4. 5，SSP5-8. 5）. Results indicated：（1）The EC-Earth3 model performed best in simulating the five extreme precipitation indices，with correlation coefficients between simulated and observed values of 0. 78 for R95p，0. 90 for RX1day，and 0. 77 for RX5day. Overall，the simulation performance of UEWA-5 exceeded that of EWA-5.（2）During the baseline period，central Sichuan exhibited high values for the five extreme precipitation indices，followed by eastern Sichuan and Chongqing，while western Sichuan showed lower values. The year 1998 recorded peak values for all five indices，with a maximum single-day precipitation of 86 mm for RX1day and an intensity（SDII）value of 11. 3 mm·d-1.（3）In future periods，the five extreme precipitation indices display a spatial distribution characterized by higher values in central regions and lower values around the periphery. Higher levels of social vulnerability and radiative forcing correlate with larger values of extreme precipitation indices. Comparing the two future periods，values of the indices are larger in the long term，notably with R95p averaging 846. 8 mm，an increase of 169. 2 mm compared to the near term.（4）During historical periods，areas with higher comprehensive risk of rainstorm and flood disasters were concentrated in central Sichuan and downtown Chongqing. In the two future periods，the high and moderately high-risk areas in central Sichuan are expected to expand，while the moderate-risk areas will shrink. The range of low-risk areas in the western Sichuan Plateau will also decrease，and the risk levels in southern Sichuan and eastern Sichuan-Chongqing border areas will respectively decrease to moderate-low and low-risk zones. Comparing the two future periods，the range of moderately high and moderate-risk areas in central Sichuan is expected to expand，while southwestern Chongqing will transition to a moderate-risk area in the long term. Other regions will generally maintain their original risk levels. Changes in disaster risk levels in the Sichuan-Chongqing region are less pronounced with increasing social vulnerability and radiative forcing，especially in the western Sichuan Plateau and northeastern Sichuan，where changes in disaster risk levels are minimal. The study results can provide important references for reducing disaster risks，enhancing emergency response capabilities，and making scientifically informed decisions for disaster prevention in the Sichuan-Chongqing region. © Editorial Department of Plateau Meteorology.
Keywords: Scopus_Alert_15_Aout_2025

Interactive Effects of Climate Change and Contaminants in Aquatic Ecosystems on Environmental-Human Health - Yu, Kaifeng; Mohapatra, Sanjeeb; Chen, Yihan; Jiang, Peng; Tong, Xuneng (Current Pollution Reports, 2025)
Purpose of the Review: Climate change is intensifying the pressures on aquatic ecosystems by altering the dynamics of contaminants, with cascading effects on ecological and human health. This review synthesizes recent evidence on how rising temperatures, altered precipitation patterns, and extreme weather events influence chemical and microbial contaminant dynamics in aquatic environments. Recent Findings: Key findings reveal that elevated temperatures enhance phosphorus pollution and algal blooms, increase heavy metal release from sediments, and promote the mobilization of organic pollutants. Concurrently, climate change exacerbates microbial contamination by facilitating the spread of waterborne microbial contaminants, especially posing more pressure to antimicrobial resistance-related contaminants through temperature-driven horizontal gene transfer and extreme precipitation events. Complex interactions between chemical and microbial contaminants like heavy metals co-selecting for antibiotic resistance further amplify risks. The compounded effects of climate change and contaminants threaten water quality, ecosystem resilience, and public health, particularly through increased toxicant exposure via seafood and waterborne disease outbreaks. Despite growing recognition of these interactions, critical gaps remain in understanding their synergistic mechanisms, especially in data-scarce regions. Summary: This review highlights the urgent need for integrated monitoring, predictive modeling, and adaptive policies under a One Health framework to mitigate the multifaceted impacts of climate-driven contamination. Future research should prioritize real-world assessments of temperature effects, urban overflow dynamics during extreme weather, and the socio-behavioral dimensions of contaminant spread to inform effective mitigation strategies. © The Author(s), under exclusive licence to Springer Nature Switzerland AG 2025.
Keywords: Scopus_Alert_15_Aout_2025

Entendre et comprendre les expériences de désastre par la recherche narrative - Leclerc, Typhaine; Lessard, Lily; Saint-Charles, Johanne (Intervention, 2024)
Les événements météorologiques extrêmes (EME) et les désastres qu’ils entrainent provoquent des conséquences psychosociales qui sont modulées en fonction de différents facteurs sociaux. On constate aussi que les récits médiatiques et culturels qui circulent au sujet des EME ne sont pas représentatifs de l’ensemble des expériences de personnes sinistrées : celles qui en subissent les conséquences les plus sévères tendent aussi à être celles qu’on « entend » le moins dans l’espace public. Ces personnes sont ainsi susceptibles de vivre de l’injustice épistémique, ce qui a des effets délétères sur le soutien qu’elles reçoivent. Face à ces constats s’impose la nécessité de mieux comprendre la diversité des expériences d’EME et d’explorer des stratégies pour soutenir l’ensemble des personnes sinistrées dans leur rétablissement psychosocial. Cet article soutient que la recherche narrative peut contribuer à répondre à ces objectifs. En dépeignant des réalités multiples, la recherche narrative centrée sur les récits de personnes sinistrées présente aussi un intérêt significatif pour l’amélioration des pratiques d’intervention en contexte de désastre. , Extreme weather events (EWE) and their resulting disasters cause psychosocial consequences that are moderated by different social factors. Media and cultural accounts of EWEs do not represent the full range of disaster survivor experiences, that is, those who experienced the most severe consequences also tend to be those least “heard” in the public arena. These people are therefore most likely to experience forms of epistemic injustice that negatively impact the support offered to cope with disaster. Considering these findings, there is a need to better understand the diversity of EWE experiences and explore strategies for supporting all disaster survivors in their psychosocial recovery. This article argues that narrative research can help meet these needs. By portraying the multiple realities of people affected by EWEs, narrative research focusing on the stories of disaster survivors is also of significant interest for improving intervention practices in this context.

Planetary-Scale Dynamics of Extreme Precipitation Regimes: Precursors and Contributors to Intensity and Longevity - Low, Yeechian; Gyakum, John R. (Monthly Weather Review, 2025)
Abstract Extreme precipitation is often challenging to predict but has substantial societal impacts, especially when it is persistent and affects a large region. We analyze Rossby wave packets, jet streams, atmospheric blocking, Madden–Julian oscillation (MJO), and El Niño–Southern Oscillation (ENSO) and elucidate the associated large-scale physical mechanisms contributing to the occurrence and persistence of extreme precipitation regimes (EPRs) in eastern North America as identified in an earlier study. The large temporal and spatial scales of EPRs, as well as the climatological study of EPRs, distinguish this study from previous precipitation studies, which are mostly on shorter-duration events. EPRs are characterized by an unusually slow-moving and persistent large-scale synoptic-scale circulation structure favorable for the southerly flow of subtropical moisture into eastern North America. The strength of the southerly flow is critical in producing large precipitation rates. The favorable synoptic structure is established by the start of the EPR, moves very slowly eastward until the middle of the EPR, and then travels faster eastward by the end of the EPR. The persistence of midlatitude ridges and the long-wavelength and slow-moving nature of the synoptic structure are critical to the longevity of EPRs. The latent heat release associated with moisture transport and ascent in cyclones provides a feedback mechanism contributing to the persistence. MJO phase 3 is favored before the EPR start, while phases 4 and 5 are favored during the EPR. During EPRs, there is no significant preference for El Niño or La Niña conditions, but a negative Pacific decadal oscillation (PDO) is favored. Significance Statement Cool-season extreme precipitation regimes often lead to flooding and other societal impacts and represent a significant forecast challenge. We analyze large-scale weather patterns and physical mechanisms in the North Pacific and North America contributing to the occurrence and persistence of extreme precipitation regimes. Recognizing them could promote their predictability since the North Pacific is a climatologically favored area for persistent anomalous large-scale weather patterns. The regimes are characterized by an unusually slow-moving and persistent large-scale weather pattern favoring the southerly flow of subtropical moisture into eastern North America. The persistence, size, and slow-moving nature of the weather pattern are critical to the regimes’ longevity. Storms tracking on the west of high pressure areas provide a feedback mechanism that helps maintain the regimes.
Keywords: Infolettre_Ete_2025

Enhancing Research-to-Operations in Hydrological Forecasting: Innovations across Scales and Horizons - Pechlivanidis, Ilias G.; Du, Yiheng; Bennett, James; Boucher, Marie-Amélie; Chang, Annie Y. Y.; Crochemore, Louise; Dasgupta, Antara; Di Baldassarre, Giuliano; Luterbacher, Jürg; Pappenberger, Florian; Ramos, Maria-Helena; Slater, Louise; et al. (Bulletin of the American Meteorological Society, 2025)
Abstract Over the past 20 years, the Hydrological Ensemble Prediction Experiment (HEPEX) international community of practice has advanced the science and practice of hydrological ensemble prediction and its application in impact- and risk-based decision-making, fostering innovations through cutting-edge techniques and data that enhance water-related sectors. Here, we present insights from those 20 years on the key priorities for (co)creating broadly applicable hydrological forecasting systems that add value across spatial scales and time horizons. We highlight the advancement of hydrological forecasting chains through rigorous data management that incorporates diverse, high-quality data sources, data assimilation techniques, and the application of artificial intelligence (AI) to improve predictive accuracy. HEPEX has played a critical role in enhancing the reliability of water resources and water-related risk management globally by standardizing ensemble forecasting. This effort complements HEPEX’s broader initiative to strengthen research to operations, making innovative forecasting solutions both practical and accessible. Additionally, efforts have been made toward supporting the United Nations Early Warnings for All initiative through developing robust and reliable early warning systems by means of global training, education and capacity development, and the sharing of technology. Finally, we note that the integration of advanced science, user-centric methods, and global collaboration can provide a solid framework for improving the prediction and management of hydrological extremes, aligning forecasting systems with the dynamic needs of water resource and risk management in a changing climate. To effectively meet future demands, it is crucial to accelerate the integration of innovative science within operational frameworks, fostering adaptable and resilient hydrological forecasting systems globally.
Keywords: Infolettre_Ete_2025

The Needs, Challenges, and Priorities for Advancing Global Flood Research - Samadi, Vidya; Fowler, Hayley J.; Lamond, Jessica; Wagener, Thorsten; Brunner, Manuela; Gourley, Jonathan; Moradkhani, Hamid; Popescu, Ioana; Wasko, Conrad; Wright, Daniel; Wu, Huan; Zhang, Ke; et al. (WIREs Water, 2025)
ABSTRACT In recent years, numerous flood events have caused loss of life, widespread disruption, and damage across the globe. These devastating impacts highlight the importance of a better understanding of flood generating processes, their impacts, and their variability under climate and landscape changes. Here, we argue that the ability to better model flooding is underpinned by the grand challenge of understanding flood generation mechanisms and potential impacts. To address this challenge, the World Meteorological Organization‐Global Energy and Water Exchanges (GEWEX) Hydrometeorology Panel (GHP) aims to establish a Global Flood Crosscutting project to propagate flood modeling and research knowledge across regions and to synthesize results at the global scale. This paper outlines a framework for understanding the dynamics and impacts of runoff generation processes and a rationale for the role of a Global Flood Crosscutting project to address these challenges. Within this Global Flood Crosscutting project, we will establish a common terminology and methods to enable the global research community to exchange knowledge and experiences, and to design experiments toward developing actionable recommendations for more effective flood management practices and policies for improved resilience. This harmonization of rich perspectives across disciplines will foster the co‐production of knowledge primed to advance flood research, particularly in the current period of heightened climate variability and rapid change. It will create a new transdisciplinary paradigm for flood science, wherein different dimensions of mechanistic understanding and processes are rigorously considered alongside socioeconomic impacts, early warning communications, and longer‐term adaptation to alleviate flood risks in society.
Keywords: Infolettre_Ete_2025

Projecting climate and socioeconomic contributions to global flood-induced displacements using a data-driven approach - Del Rio Amador, Lenin; Boudreault, Mathieu; Carozza, David A. (Natural Hazards, 2025)
Keywords: Infolettre_Ete_2025

Full-scale characterization of the effects of a bioretention system on water quality and quantity following the replacement of a mixed stormwater and combined sewer system - Le Cauchois, Pia; Doucet, Samuel; Bouattour, Ons; McQuaid, Natasha; Beral, Henry; Kõiv-Vainik, Margit; Bichai, Françoise; McCarthy, David; St-Laurent, Julien; Dagenais, Danielle; Bennekrela, Nesrine; Guerra, Juan; et al. (Blue-Green Systems, 2025)
ABSTRACT Urbanization is leading to more frequent flooding as cities have more impervious surfaces and runoff exceeds the capacity of combined sewer systems. In heavy rainfall, contaminated excess water is discharged into the natural environment, damaging ecosystems and threatening drinking water sources. To address these challenges aggravated by climate change, urban blue-green water management systems, such as bioretention cells, are increasingly being adopted. Bioretention cells use substrate and plants adapted to the climate to manage rainwater. They form shallow depressions, allowing infiltration, storage, and gradual evacuation of runoff. In 2018, the City of Trois-Rivières (Québec, Canada) installed 54 bioretention cells along a residential street, several of which were equipped with access points to monitor performance. Groundwater quality was monitored through the installation of piezometers to detect potential contamination. This large-scale project aimed to improve stormwater quality and reduce sewer flows. The studied bioretention cells reduced the flow and generally improved water quality entering the sewer system, as well as the quality of stormwater, with some exceptions. Higher outflow concentrations were observed for contaminants such as manganese and nitrate. The results of this initiative provide useful recommendations for similar projects for urban climate change adaptation.
Keywords: Infolettre_Ete_2025

The Impact of Flood Adaptation Measures on Affected Population’s Mental Health: A mixed method Scoping Review - El-Mousawi, Fatima; Ortiz, Ariel Mundo; Berkat, Rawda; Nasri, Bouchra (Cold Spring Harbor Laboratory, 2023)
AbstractThe frequency and severity of floods has increased in different regions of the world due to climate change. Although the impact of floods on human health has been extensively studied, the increase in the segments of the population that are likely to be impacted by floods in the future makes it necessary to examine how adaptation measures impact the mental health of individuals affected by these natural disasters. The goal of this scoping review is to document the existing studies on flood adaptation measures and their impact on the mental health of affected populations, in order to identify the best preventive strategies as well as limitations that deserve further exploration. This study employed the methodology of the PRISMA-ScR extension for scoping reviews to systematically search the databases Medline and Web of Science to identify studies that examined the impact of adaptation measures on the mental health of flood victims. The database queries resulted in a total of 857 records from both databases. Following two rounds of screening, 9 studies were included for full-text analysis. Most of the analyzed studies sought to identify the factors that drive resilience in flood victims, particularly in the context of social capital (6 studies), whereas the remaining studies analyzed the impact of external interventions on the mental health of flood victims, either from preventive or post-disaster measures (3 studies). There is a very limited number of studies that analyze the impact of adaptation measures on the mental health of populations and individuals affected by floods, which complicates the generalizability of their findings. There is a need for public health policies and guidelines for the development of flood adaptation measures that adequately consider a social component that can be used to support the mental health of flood victims.

« J’ai juste besoin de parler » : les histoires de femmes sinistrées au coeur de la recherche sur les conséquences psychosociales des inondations - Leclerc, Typhaine; Lessard, Lily; Saint-Charles, Johanne (Le Climatoscope, 2024)
Les récits médiatiques et culturels qui circulent sur les événements météorologiques extrêmes (EME) ne sont pas représentatifs de l’ensemble des expériences de personnes sinistrées. Les groupes qui en subissent les conséquences les plus sévères tendent à être ceux que l’on « entend » le moins dans l’espace public. L’approche de recherche narrative permet de documenter une diversité d’expériences d’EME pour en tracer un panorama plus complet. Adoptant une approche narrative féministe, notre recherche a été menée auprès de femmes touchées par des inondations en Beauce. Des extraits d’entrevues semi-directives menées avec des femmes sinistrées offrent une illustration des conséquences psychosociales entrainées par les inondations. Les forces des participantes et certains défis rencontrés en lien avec leurs rôles dans la famille et la communauté sont aussi abordés. La méthode adoptée a permis de collecter des récits d’expérience riches et singuliers qui rendent plus tangibles les effets différenciés des EME. Tenir compte de cette diversité d’expériences favoriserait une prise en charge plus équitable des personnes sinistrées à court, moyen et long terme.

Éduquer aux risques dès l’école primaire: de la représentation à la conscientisation - Julien, Marie-Pierre; Bédouret, David; Chalmeau, Raphaël; Mainar, Christine Vergnolle; Léna, Jean-Yves; Calvet, Anne (VertigO - la revue électronique en sciences de l'environnement, 2021)
Le territoire de la vallée du Gave de Gavarnie a connu un épisode d’inondation/crue particulièrement catastrophique en 2013, ayant entrainé de forts dégâts matériels et des pertes humaines. Dans ce contexte, la culture du risque est un enjeu tant pour les acteurs de la gestion de ce territoire que pour les citoyens, d’autant plus que les risques présents y sont multiples (avalanches, glissements de terrain et séismes). Dans cette perspective, l’école peut jouer un rôle déterminant à travers la mise en place de projets d’éducations au(x) risque(s). Ce type d’éducation doit commencer par la perception et la conscience du (des) risque(s), rendues possibles par le vécu et/ou par la culture du groupe dans lequel l’élève vit. Cette étude a pour objectif d’examiner les représentations et la perception du risque des élèves d’une école élémentaire française située sur une commune fortement impactée par cette crue, et l’évolution de ces représentations et cette perception un an après la mise en œuvre du projet éducatif. Les résultats montrent une représentation plurielle du risque par les élèves avec des différences entre classes. La classe de CP-CE (enfants âgés de 6 à 8 ans) associe essentiellement le risque à l’aléa naturel (avalanche, inondation…) alors que les élèves en CM (enfants âgés de 9 à 10 ans) sont centrés sur ce qui pourrait leur arriver (accident, maladie…). Le risque inondation/crue est dans un premier temps très peu évoqué dans les représentations des élèves, mais lorsque les activités pédagogiques permettent de contextualiser cette notion sur leur territoire, il est alors plus fortement perçu.

Flood Risk and Community Resilience: An Interdisciplinary Approach - McEwen, Lindsey (2024)
This book details the impact of flooding on our environment, and the ways in which communities, and those that work with them, can act to manage the associated risks. Flooding is an increasingly significant environmental hazard which inflicts major costs to the economies and livelihoods of developed countries. This book explores how local communities can identify, manage, and adapt to the ever-increasing damage flooding causes. Focusing on the future role of local communities, the benefits and c

Investigating incomplete mixing models in cross junctions under real-world conditions of water distribution networks - Yousefian, Reza; Duchesne, Sophie; Schwarz, Pierre-Olivier (Water Supply, 2024)
Questions have been raised about the correctness of water quality models with complete mixing assumptions in cross junctions of water distribution systems. Recent developments in the mixing phenomenon within cross junctions of water distribution networks (WDNs) have heightened the need for evaluating the existing incomplete mixing models under real-world conditions. Therefore, in this study, two cross junctions with pipe diameters of 100 Â 100 Â 100 Â 100 mm and 150 Â 150 Â 150 Â 150 mm were employed in laboratory experiments to evaluate six existing incomplete mixing models for 25 ﬂow rate scenarios ranging between 1.5 and 3.0 L/s. It was observed that within the same ﬂow rate scenario, the degree of mixing in a cross junction with a pipe relative roughness of 6.00 Â 10À5 (pipe diameter of 25 mm) was higher than that in a cross junction with a pipe relative roughness of 3.00 Â 10À5 (pipe diameter of 50 mm) and smaller. Considering the real-world size of pipes in evaluating the incomplete mixing models showed that two incomplete mixing models, AZRED and the one by Shao et al., had the best accordance with the results of the laboratory experiments.

Integration of Incomplete Mixing at Junctions of Water Distribution Networks in Contamination Source Identification Tools - Yousefian, Reza; Émond, Laurent; Duchesne, Sophie (Journal of Water Resources Planning and Management, 2025)
The water quality models used in contamination source identification (CSI) tools assume complete mixing at the junctions of drinking water distribution networks. Two extensions of the contamination status algorithm (CSA)—a CSI tool that employs water quality models in a reverse-time manner—were accordingly developed in this study, one assuming complete mixing (CSA-CMX) and the other assuming incomplete mixing (CSA-IMX) at cross-junctions. Both algorithms identified contamination sources based on the results of grab sampling at iteratively suggested locations. The performances of CSA-CMX and CSA-IMX were evaluated through laboratory experiments using three contamination identification problems: CSA-IMX identified the contamination source in all three problems, whereas CSA-CMX identified the contamination source in only one. Furthermore, the specificity (i.e., the ability to distinguish the real contamination source from other possible contamination sources) was higher for CSA-IMX than for CSA-CMX in two of the three problems. Therefore, the incomplete mixing assumption was confirmed to be a crucial factor in CSI tools.

Evaluating real-time control of stormwater drainage network and green stormwater infrastructure for enhancing flooding resilience under future rainfall projections - Li, Jiada; Burian, Steven J. (Resources, Conservation and Recycling, 2023)
Traditional stormwater control measures are designed to handle system loadings induced by fixed-size storm events. However, climate change is predicted to alter the frequency and intensity of flooding events, stimulating the need to explore another more adaptive flooding solution like real-time control (RTC). This study assesses the performance of RTC to mitigate impacts of climate change on urban flooding resilience. A simulated, yet realistic, urban drainage system in Salt Lake City, Utah, USA, shows that RTC improves the flooding resilience by up to 17% under climatic rainfall changes. Compared with green stormwater infrastructure (GSI), RTC exhibits a lower resistibility, lower flooding failure level, and higher recovery rate in system performance curves. Results articulate that keeping RTC's performance consistent under ‘back-to-back’ storms requires a tradeoff between upstream dynamical operation and downstream flooding functionality loss. This research suggests that RTC provides a path towards smart and resilient stormwater management strategy.

Adaptation of Dual Drainage to Control Flooding and Enhance Combined Sewer Systems in Highly Urbanized Areas - Ossa Ossa, Juan Esteban; Duchesne, Sophie; Pelletier, Geneviève (2024)
Combined sewer surcharges in densely urbanized areas have become more frequent due to the expansion of impervious surfaces and intensified precipitation caused by climate change. These surcharges can generate system overflows, causing urban flooding and pollution of urban areas. This paper presents a novel methodology to mitigate sewer system surcharges and control surface water. In this methodology, flow control devices and urban landscape retrofitting are proposed as strategies to reduce water inflow into the sewer network and manage excess water on the surface during extreme rainfall events. For this purpose, a 1D/2D dual drainage model was developed for two case studies located in Montreal, Canada. Applying the proposed methodology to these two sites led to a reduction of the volume of wastewater overflows by 100% and 86%, and a decrease in the number of surface overflows by 100% and 71%, respectively, at the two sites for a 100-year return period 3-h Chicago design rainfall. It also controlled the extent of flooding, reduced the volume of uncontrolled surface floods by 78% and 80% and decreased flooded areas by 68% and 42%, respectively, at the two sites for the same design rainfall.

Flood inundation modeling in ungauged basins using Unmanned Aerial Vehicles imagery - Yavari, Adel; Homayouni, Saeid; Oubennaceur, Khalid; Chokmani, Karem (Earth Observation and Geomatics Engineering, 2020)
This paper presents a new framework for floodplain inundation modeling in an ungauged basin using unmanned aerial vehicles (UAVs) imagery. This method is based on the integrated analysis of high-resolution ortho-images and elevation data produced by the structure from motion (SfM) technology. To this end, the Flood-Level Marks (FLMs) were created from high-resolution UAV ortho-images and compared to the flood inundated areas simulated using the HEC-RAS hydraulic model. The flood quantiles for 25, 50, 100, and 200 return periods were then estimated by synthetic hydrographs using the Natural Resources Conservation Service (NRCS). The proposed method was applied to UAV image data collected from the Khosban village, in Taleghan County, Iran, in the ungauged sub-basin of the Khosban River. The study area is located along one kilometre of the river in the middle of the village. The results showed that the flood inundation areas modeled by the HEC-RAS were 33%, 19%, and 8% less than those estimated from the UAV’s FLMs for 25, 50, and 100 years return periods, respectively. For return periods of 200 years, this difference was overestimated by more than 6%, compared to the UAV’s FLM. The maximum flood depth in our four proposed scenarios of hydraulic models varied between 2.33 to 2.83 meters. These analyses showed that this method, based on the UAV imagery, is well suited to improve the hydraulic modeling for seasonal inundation in ungauged rivers, thus providing reliable support to flood mitigation strategies

Imaging Floods and Glacier Geohazards with Remote Sensing - Cigna, Francesca; Xie, Hongjie (Remote Sensing, 2020)
Geohazards associated with the dynamics of the liquid and solid water of the Earth’s hydrosphere, such as floods and glacial processes, may pose significant risks to populations, activities and properties [...]

Development of an approach based on historical Landsat data for delineating Canadian flood zones at different return periods - Chokmani, Karem; Zidi, Haythem; El Alem, Anas; Gill-Fortin, Jasmin (EGU General Assembly Conference Abstracts, 2024)
The study addresses the need for flood risk anticipation and planning, through the development of a flood zone mapping approach for different return periods, in order to best prevent and protect populations. Today, traditional methods are too costly, too slow or require too many requirements to be applied over large areas. As part of a project funded by the Canadian Space Agency, Geosapiens and the Institut National de la Recherche Scientifique set themselves the goal of designing an automatic process to generate water presence maps for different return periods at a resolution of 30 m, based on the historical database of Landsat missions from 1982 to the present day. This involved the design, implementation and training of a deep learning algorithm model based on the U-Net architecture for the detection of water pixels in Landsat imagery. The resulting maps were used as the basis for applying a frequency analysis model to fit a probability of occurrence function for the presence of water at each pixel. The frequency analysis data were then used to obtain maps of water occurrence at different return preiods such as 2, 5 and 20 years.

A PCA spatial pattern based artificial neural network downscaling model for urban flood hazard assessment - Carreau, J.; Guinot, V. (Advances in Water Resources, 2021)

Impacts et coûts indirects des stresseurs secondaires sur la santé biopsychosociale des sinistrés des inondations de 2019 - Maltais, Danielle; Bourdeau-Brien, Michaël; Gilbert, Simon; Normandin, Julie-Maude; Tchassem Pinlap, Jonas; Généreux, Mélissa; Landaverde, Elsa; Boudreault, Mathieu (2023)
Les inondations de 2017 et 2019 au Québec ont affecté respectivement 293 et 240 municipalités. Ces inondations ont généré une cascade d’évènements stressants (stresseurs primaires et secondaires) qui ont eu des effets sur la santé mentale de la population et retardé le processus de rétablissement des individus. Cette période de rétablissement peut s’échelonner sur plusieurs mois voire plusieurs années. Cette étude s’inscrit dans la spécificité de la recherche mixte mise de l’avant à travers trois stratégies de recherche, réalisées de façon séquentielle : 1) sondage populationnelle réalisé auprès de 680 personnes, 2) analyse de documents produits par les organisations participant au processus de rétablissement social des sinistrés, ou sur des analyses externes portant sur ces interventions de rétablissement et 3) entrevues semi-dirigées auprès de 15 propriétaires occupants ayant complété une demande d’indemnisation à la suite des inondations de 2019 et auprès de 11 professionnels et gestionnaires participant au processus de rétablissement social. Les entrevues semi-dirigées et les questionnaires complétés par les personnes sinistrées lors des inondations de 2019 démontrent que les principales sources de stress ayant des impacts sur la santé et le bien-être des répondants sont : 1) l’absence d’avertissement et la vitesse de la montée des eaux; 2) l’obligation de se relocaliser et la peur d’être victime de pillage; 3) le manque de solidarité et d’empathie de la part de certains employés du MSP; 4) la gestion des conflits familiaux; 5) la gestion de problèmes de santé nouveaux ou préexistants; 6) la complexité des demandes d’indemnisation; 7) la lourdeur et les délais des travaux de nettoyage ou de restauration; 8) les indemnités inférieures aux coûts engendrés par l’inondation; 9) les pertes matérielles subies, particulièrement ceux d’une valeur de plus de 50 000 $; et 10) la diminution anticipée de la valeur de sa résidence. À cela s’ajoute l’insatisfaction à l’égard du programme d’indemnisation du gouvernement du Québec (PGIAF) qui fait plus que doubler la prévalence des symptômes de stress post-traumatique. Les inondations entraînent également une perte de satisfaction ou de bien-être statistiquement significative. La valeur monétaire de cette perte de jouissance peut être exprimée en équivalent salaires. En moyenne, cette diminution du bien-être équivaut à une baisse de salaire de 60 000$ pour les individus ayant vécu une première inondation et à 100 000$ pour les individus ayant vécu de multiples inondations. Ces résultats suggèrent que les coûts indirects et intangibles représentent une part importante des dommages découlant des inondations. Ce projet de recherche vise également à analyser l’application du PGIAF et son influence sur les stresseurs vécus par les sinistrés dans le contexte de la pandémie de COVID-19. La principale recommandation de cette étude repose sur une analyse de documents, un sondage populationnel et des entrevues semi-dirigées. Ainsi, s’attaquer à la réduction de principaux stresseurs nécessite 1) d’améliorer la gouvernance du risque d’inondation, 2) d’intensifier la communication et le support aux sinistrés, et 3) de revoir les mécanismes d’indemnisation existants.

A Global Flood Risk Modeling Framework Built With Climate Models and Machine Learning - Carozza, David A.; Boudreault, Mathieu (Journal of Advances in Modeling Earth Systems, 2021)
AbstractLarge scale flood risk analyses are fundamental to many applications requiring national or international overviews of flood risk. While large‐scale climate patterns such as teleconnections and climate change become important at this scale, it remains a challenge to represent the local hydrological cycle over various watersheds in a manner that is physically consistent with climate. As a result, global models tend to suffer from a lack of available scenarios and flexibility that are key for planners, relief organizations, regulators, and the financial services industry to analyze the socioeconomic, demographic, and climatic factors affecting exposure. Here we introduce a data‐driven, global, fast, flexible, and climate‐consistent flood risk modeling framework for applications that do not necessarily require high‐resolution flood mapping. We use statistical and machine learning methods to examine the relationship between historical flood occurrence and impact from the Dartmouth Flood Observatory (1985–2017), and climatic, watershed, and socioeconomic factors for 4,734 HydroSHEDS watersheds globally. Using bias‐corrected output from the NCAR CESM Large Ensemble (1980–2020), and the fitted statistical relationships, we simulate 1 million years of events worldwide along with the population displaced in each event. We discuss potential applications of the model and present global flood hazard and risk maps. The main value of this global flood model lies in its ability to quickly simulate realistic flood events at a resolution that is useful for large‐scale socioeconomic and financial planning, yet we expect it to be useful to climate and natural hazard scientists who are interested in socioeconomic impacts of climate.

Climate, Spatial Dependence and Flood Risk: A U.S. - Erhardt, R; Boudreault, M; Carozza, D; Yu, K (Case Study. e-forum, Casualty Actuarial Society, 2022)

Large‐scale turbulent mixing at a mesoscale confluence assessed through drone imagery and eddy‐resolved modelling - Duguay, Jason; Biron, Pascale; Buffin‐Bélanger, Thomas (Earth Surface Processes and Landforms, 2022)
Abstract Confluences are sites of intense turbulent mixing in fluvial systems. The large‐scale turbulent structures largely responsible for this mixing have been proposed to fall into three main classes: vertically orientated (Kelvin–Helmholtz) vortices, secondary flow helical cells and smaller, strongly coherent streamwise‐orientated vortices. Little is known concerning the prevalence and causal mechanisms of each class, their interactions with one another and their respective contributions to mixing. Historically, mixing processes have largely been interpreted through statistical moments derived from sparse pointwise flow field and passive scalar transport measurements, causing the contribution of the instantaneous flow field to be largely overlooked. To overcome the limited spatiotemporal resolution of traditional methods, herein we analyse aerial video of large‐scale turbulent structures made visible by turbidity gradients present along the mixing interface of a mesoscale confluence and complement our findings with eddy‐resolved numerical modelling. The fast, shallow main channel (Mitis) separates over the crest of the scour hole's avalanche face prior to colliding with the slow, deep tributary (Neigette), resulting in a streamwise‐orientated separation cell in the lee of the avalanche face. Nascent large‐scale Kelvin–Helmholtz instabilities form along the collision zone and expand as the high‐momentum, separated near‐surface flow of the Mitis pushes into them. Simultaneously, the strong downwelling of the Mitis is accompanied by strong upwelling of the Neigette. The upwelling Neigette results in ∼50% of the Neigette's discharge crossing the mixing interface over the short collision zone. Helical cells were not observed at the confluence. However, the downwelling Mitis, upwelling Neigette and separation cell interact to generate considerable streamwise vorticity on the Mitis side of the mixing interface. This streamwise vorticity is strongly coupled to the large‐scale Kelvin–Helmholtz instabilities, which greatly enhances mixing. Comparably complex interactions between large‐scale Kelvin–Helmholtz instabilities and coherent streamwise vortices are expected at other typical asymmetric confluences exhibiting a pronounced scour hole.

Climate‐Driven Variations in Nitrogen Retention From a Riverine Submerged Aquatic Vegetation Meadow - Botrel, M.; Hudon, C.; Heffernan, J. B.; Biron, P. M.; Maranger, R. (Water Resources Research, 2022)
Abstract Large rivers can retain a substantial amount of nitrogen (N), particularly in submerged aquatic vegetation (SAV) meadows that may act as disproportionate control points for N retention. However, the temporal variation of N retention in large rivers remains unknown since past measurements were snapshots in time. Using high‐frequency plants and NO 3 − measurements over the summers 2012–2017, we investigated how the climate variation influenced N retention in a SAV meadow (∼10 km 2 ) at the confluence zone of two agricultural tributaries entering the St. Lawrence River. Distinctive combinations of water temperature and level were recorded between years, ranging from extreme hot‐low (2012) and cold‐high (2017) summers (2°C and 1.4 m interannual range). Using an indicator of SAV biomass, we found that these extreme hot‐low and cold‐high years had reduced biomass compared to hot summers with intermediate levels. In addition, changes in main stem water levels were asynchronous with the tributary discharges that controlled NO 3 − inputs at the confluence. We estimated daily N uptake rates from a moored NO 3 − sensor and partitioned these into assimilatory and dissimilatory pathways. Measured rates were variable but among the highest reported in rivers (median 576 mg N m −2 d −1 , range 60–3,893 mg N m −2 d −1 ) and SAV biomass promoted greater proportional retention and permanent N loss through denitrification. We estimated that the SAV meadow could retain up to 0.8 kt N per year and 87% of N inputs, but this valuable ecosystem service is contingent on how climate variations modulate both N loads and SAV biomass. , Plain Language Summary Large rivers remove significant amounts of nitrogen pollution generated by humans in waste waters and from fertilizers applied to agricultural lands. Underwater meadows of aquatic plants remove nitrogen particularly well. To keep the river clean, plants use the nitrogen themselves and promote conditions where bacteria can convert this pollution into a gas typically found in air. Measuring nitrogen removal in rivers is really difficult, and we do not know how climate conditions influence this removal or plant abundance. We successfully measured nitrogen pollution removal from an underwater plant meadow in a large river over six summers. We found that plant abundance and river nitrogen inputs were critical to determine how much pollution was removed, and that these were controlled by climatic conditions. Plant abundance was controlled by both water temperatures and levels. When water was warm and levels were neither too high nor too low, conditions were perfect for lots of plants to grow, which mainly stimulated bacteria that permanently eliminated nitrogen. We showed that the amount of nitrogen pollution removed over the summer by the meadow changes with climatic conditions but in general represents the amount produced by a city of half a million people. , Key Points Nitrogen retention and biomass were measured at a high resolution over six summers in a submerged aquatic vegetation meadow of a large river Among the highest riverine, nitrate uptake rates were recorded, and 47%–87% of loads were retained with plants favoring denitrification Interannual climate variations influenced nitrate retention by altering water levels, temperature, plant biomass, and tributary nitrate load

Trajectoires et visées de l'hydrogéomorphologie au Québec - Buffin‐Bélanger, Thomas; Lachapelle, Félix; Biron, Pascale; Boivin, Maxime (Canadian Geographies / Géographies canadiennes, 2024)
Résumé L'hydrogéomorphologie étudie la dynamique des rivières en se concentrant sur les interactions liant la structure des écoulements, la mobilisation et le transport des sédiments et les morphologies qui caractérisent les cours d'eau et leur bassin‐versant. Elle offre un cadre d'analyse et des outils pour une meilleure intégration des connaissances sur la dynamique des rivières pour la gestion des cours d'eau au sens large, et plus spécifiquement, pour leur restauration, leur aménagement et pour l'évaluation et la prévention des risques liés aux aléas fluviaux. Au Québec, l'hydrogéomorphologie émerge comme contribution significative dans les approches de gestion et d'évaluation du risque et se trouve au cœur d'un changement de paradigme dans la gestion des cours d'eau par lequel la restauration des processus vise à augmenter la résilience des systèmes et des sociétés et à améliorer la qualité des environnements fluviaux. Cette contribution expose la trajectoire de l'hydrogéomorphologie au Québec à partir des publications scientifiques de géographes du Québec et discute des visées de la discipline en recherche et en intégration des connaissances pour la gestion des cours d'eau . , Abstract Hydrogeomorphology studies river dynamics, focusing on the interactions between flow structure, sediment transport, and the morphologies that characterize rivers and their watersheds. It provides an analytical framework and tools for better integrating knowledge of river dynamics into river management in the broadest sense, and more specifically, into river restoration as well as into the assessment and prevention of risks associated with fluvial hazards. In Quebec, hydrogeomorphology is emerging as a significant contribution to risk assessment and management approaches, and is at the heart of a paradigm shift in river management whereby process restoration aims to increase the resilience of fluvial systems and societies, and improve the quality of fluvial environments. This contribution outlines the trajectory of hydrogeomorphology in Quebec, based on scientific publications by Quebec geographers, and discusses the discipline's aims in research and knowledge integration for river management . , Messages clés Les géographes du Québec ont contribué fortement au développement des connaissances et outils de l'hydrogéomorphologie. L'hydrogéomorphologie a évolué d'une science fondamentale à une science où les connaissances fondamentales sont au service de la gestion des cours d'eau. L'hydrogéomorphologie et le cortège de connaissances et d'outils qu'elle promeut font de cette discipline une partenaire clé pour une gestion holistique des cours d'eau.

Societal drivers for the integration of hydrogeomorphology and human benefits in river restoration projects - Gariépy‐Girouard, Étienne; Buffin‐Bélanger, Thomas; Biron, Pascale M. (River Research and Applications, 2025)
Abstract Integrating hydrogeomorphological (HGM) principles into the restoration of degraded rivers can achieve sustainable results and provide various human benefits. HGM principles mainly involve understanding the context and processes that shape a fluvial system before any intervention, in order to support its dynamism and to align with its potential functioning and uses. Despite recent management approaches inspired by HGM principles, most restoration projects carried out in Quebec (Canada) are not process‐based and target specific one‐dimensional objectives. Although there is an overall lack of post‐project monitoring, several projects appear to have failed or had mixed success. This research aims to shed light on the diversity of societal drivers behind river restoration projects and to examine how they influence the integration of HGM principles and human benefits. Four restoration projects were characterized through participant observation and interviews with the organizations running them. Representatives of two ministries involved in river restoration and management were also interviewed. The results show that projects were mainly shaped by public acceptance disregarding HGM principles, which can lead to poorly‐informed action. Project funding and stakeholders' expertise have also challenged project implementation and played a key role in defining their objectives. The addition of these components improve the current analytical frameworks for identifying river restoration objectives. Depending on specific sociocultural, political and legislative contexts, funding programs and stakeholders' expertise may either facilitate or restrict the integration of HGM principles and human benefits in the projects. Recognizing these key drivers reframes river restoration as a fundamentally social activity and enlightens how they could impel innovative approaches towards more sustainable results.

Données d’utilisation d’un autotraitement guidé en ligne pour promouvoir la résilience après une catastrophe naturelle - Lebel, Jessica; Flores-Tremblay, Thalie; Binet, Émilie; Ouellet, Marie-Christine; Belleville, Geneviève (Santé mentale au Québec, 2021)
Objectifs Malgré l’existence de plusieurs traitements en ligne pour les personnes avec un trouble de stress posttraumatique (TSPT), peu d’études se sont penchées sur les données d’utilisation d’une telle intervention. Étant donné le potentiel de la modalité en ligne à pallier les obstacles limitant l’accès à l’aide psychologique, il importe de documenter les interactions des usagers avec ces outils en lien avec l’amélioration des symptômes ciblés. L’objectif de cette étude est de documenter les données d’utilisation de la plateforme de traitement en ligne RESILIENT par les personnes évacuées des feux de Fort McMurray, Alberta (Canada), et d’examiner leur association avec l’efficacité du traitement sur les symptômes de trouble de stress posttraumatique (TSPT), d’insomnie et de dépression, et l’adhésion au traitement, mesurée par le nombre de modules consultés par les participants. Méthode Quatre-vingt-dix-sept personnes évacuées des feux de Fort McMurray présentant des symptômes de TSPT, d’insomnie et de dépression sont incluses dans la présente étude. Les participants étaient invités à utiliser la plateforme RESILIENT, un autotraitement en ligne guidé par un thérapeute qui cible les symptômes de TSPT, le sommeil et l’humeur, et comprend 12 modules offrant des stratégies de thérapies cognitives et comportementales (TCC) basées sur les données probantes. Des données d’utilisation objectives (p. ex. nombre de modules consultés) et subjectives (p. ex. niveau d’efforts investis) ont été recueillies. Résultats Afin de prédire la réduction des symptômes de TSPT, de dépression et d’insomnie, ainsi que le nombre de modules consultés par les participants, des modèles de régressions séquentielles ont été effectués, avec un contrôle statistique pour les symptômes prétraitement, l’âge et le genre. Les modèles finaux ont révélé qu’une réduction des symptômes de TSPT, de dépression et d’insomnie était prédite significativement par le nombre de modules consultés (β = - 0,41 ; - 0,53 ; - 0,49 respectivement, tous p < 0,001) ainsi que par le niveau d’efforts moyen autorapporté au module 7 (mi-parcours) (β = - 0,43 ; p < 0,001 ; β = - 0,38 ; p = 0,005 et β = - 0,36 ; p = 0,007 respectivement). Le nombre de modules consultés, par ailleurs, était prédit significativement par le nombre de mots dans le 4 e module (β = 0,34 ; p < 0,001) et dans le 7 e module (β = 0,44 ; p < 0,001), ainsi que par le nombre d’entrées dans le journal du sommeil (β = 0,28 ; p < 0,001). Conclusion Les résultats ont confirmé qu’une plus grande interaction avec la plateforme influence positivement l’efficacité du traitement et qu’une utilisation accrue en début de traitement semble être un bon prédicteur de l’achèvement de celui-ci. Cette étude confirme l’importance de soutenir l’engagement des participants envers le traitement en ligne afin d’optimiser son efficacité. , Objectives Despite the existence of several online treatments for people with posttraumatic stress disorder (PTSD), few studies have examined usage data for such interventions. Given the potential of the online modality to alleviate barriers limiting access to psychological help, it is important to document users’ interactions with these tools in relation to the improvement of targeted symptoms. The objective of this study is to document usage data of the online treatment platform RESILIENT by people evacuated from the Fort McMurray, Alberta (Canada) fires, and to examine their association with the effectiveness of treatment on symptoms of posttraumatic stress disorder (PTSD), insomnia and depression, and adherence to treatment, as measured by the number of modules accessed by participants. Methods Ninety-seven people evacuated from the Fort McMurray fires with symptoms of PTSD, insomnia and depression were included in this study. Participants were invited to use the RESILIENT platform, an online therapist-assisted self-help treatment program that targets PTSD symptoms, sleep and mood, and includes 12 modules offering evidence-based cognitive-behavioural therapy (CBT) strategies. Both objective (e.g., number of modules accessed) and subjective (e.g., level of effort invested) usage data were collected. Results In order to predict the reduction in PTSD, depression and insomnia symptoms, as well as the number of modules accessed by participants, sequential regression models were conducted, with statistical control for pretreatment symptoms, age and gender. The final models revealed that a reduction in PTSD, depression and insomnia symptoms was significantly predicted by the number of modules accessed (β = -.41; -.53; -.49 respectively, all p <.001) as well as the mean self-reported level of effort at module 7 (midway) (β = -.43; p <.001; β = -.38; p = .005 and β = -.36; p = .007 respectively). The number of modules accessed, on the other hand, was significantly predicted by the number of words in the 4th module (β = .34; p <.001) and 7th module (β = .44; p <.001) and the number of sleep diary entries (β = .28; p <.001). Conclusion These results confirmed that increased interaction with the platform positively influences treatment effectiveness and that increased use at the beginning of treatment appears to be a good predictor of treatment completion. This study confirms the importance of sustaining participants’ commitment to online treatment in order to optimize its effectiveness.

Évaluation préliminaire du risque lié aux aléas HGM des petits cours d'eau dans la région du Bas-Saint-Laurent - Bilé, Dahoua Virginie (Université du Québec à Rimouski, 2025)
RÉSUMÉ : Peu d’outils permettent de faire un audit des aléas hydrogéomorphologiques (HGM) auxquels les petits cours d’eau (PCE) sont sujets, pourtant à ces PCE sont associés plusieurs aléas HGM qui compromettent l’intégrité d’enjeux qui y sont exposés. L’objectif du projet vise à appliquer des outils SIG (ExZeco et Geomorphon landform) employés avec un modèle numérique d’élévation à haute résolution, pour l’évaluation préliminaire du risque lié aux aléas HGM des PCE. Cette évaluation préliminaire ne tient pas compte de la probabilité d’occurrence de l’aléa. Elle est plutôt basée sur la position des enjeux par rapport aux aléas HGM simulés sur les cônes alluviaux et les plaines d’inondations. Pour ce faire, quatre bassins versants de la région du Bas-Saint-Laurent ont été identifiés comme sites d’étude. La méthodologie se base dans un premier temps sur l’établissement d’un portrait d’aléa HGM, puis dans un deuxième temps sur la caractérisation de ces aléas en évaluant leur intensité, leur étendue et leur distribution spatiale et finalement, l’évaluation de l’exposition des enjeux vis-à-vis des aléas. Les résultats montrent que des enjeux (parcelle agricole, route, résidences) sont exposés à l’aléa torrentiel sur deux cônes alluviaux cartographiés dans les bassins versants pilotes, et des résidences sont exposées à un débordement probable de cours d’eau. L’analyse du risque a été réalisée avec obstruction probable des ponceaux sur le LiDAR et sans obstruction des ponceaux. L’aléa est de forte intensité dans le risque probable lié aux obstructions, et les enjeux exposés sont notamment les résidences, les routes et des portions de terre agricole. Des témoignages de riverains ont permis de valider l’intensité des aléas prédits par ExZeco. -- Mot(s) clé(s) en français : Aléa HGM, Évaluation préliminaire, cône alluvial, plaine d’inondation, LiDAR. -- ABSTRACT : Few tools are available for auditing the hydrogeomorphic hazards (HGM) to which small watercourses (PCE) are subject, yet these PCE are associated with several HGM hazards that compromise the integrity of issues exposed to them. The aim of the project is to apply GIS tools (ExZeco and Geomorphon landform) used in conjunction with a high-resolution digital elevation model, for the preliminary assessment of the risk associated with HGM hazards in PCE. This is an assessment based solely on the position of issues in relation to the HGM hazards to which alluvial fans and floodplains are subject. To this end, four watersheds in the Lower St. Lawrence region were identified as study sites. The methodology is based firstly on the establishment of a HGM hazard profile, then on the characterization of these hazards by assessing their intensity, extent and spatial distribution, and finally on the assessment of the level of exposure of issues to these hazards. The results show that issues (agricultural plots, roads, residences) are exposed to torrential hazards on two alluvial fans mapped in the pilot watersheds, and residences are exposed to probable river overflow. The risk analysis was carried out with probable culvert obstructions on the LiDAR and without culvert obstructions. The probable risk associated with obstructions is of high intensity, and the stakes exposed include residences, roads and portions of agricultural land. Testimonials from residents validated the intensity of the hazards predicted by ExZeco. -- Mot(s) clé(s) en anglais : HGM Hazard, Preliminary Assessment, Alluvial Fan, Floodplain, LiDAR.

Information Seeking and Information Sharing Related to Hurricane Harvey - Yang, Janet Z.; Zhuang, Jun (Journalism & Mass Communication Quarterly, 2020)
This study is focused on social cognitive variables that motivate information seeking and information sharing related to Hurricane Harvey. Survey results from a nationally representative sample and a quota sample of Houston residents indicate that climate change beliefs and issue salience are consistent predictors of risk perception, which increases individuals’ negative emotions and information insufficiency. This need for information subsequently motivates information seeking and information sharing. Informational subjective norms are significantly related to seeking and sharing in the Houston sample, whereas perceived information gathering capacity and trust in media are significant predictors in the national sample.

Review of social influence in crisis communications and evacuation decision-making - Sadri, Arif Mohaimin; Ukkusuri, Satish V.; Ahmed, Md Ashraf (Transportation Research Interdisciplinary Perspectives, 2021)

Flood Risk Management via Risk Communication, Cognitive Appraisal, Collective Efficacy, and Community Action - Lin, Carolyn A. (Sustainability, 2023)
Climate change and more frequent severe storms have caused persistent flooding, storm surges, and erosion in the northeastern coastal region of the United States. These weather-related disasters have continued to generate negative environmental consequences across many communities. This study examined how coastal residents’ exposure to flood risk information and information seeking behavior were related to their threat appraisal, threat-coping efficacy, and participation in community action in the context of building social resilience. A random sample of residents of a coastal community in the Northeastern United States was selected to participate in an online survey (N = 302). Key study results suggested that while offline news exposure was weakly related to flood vulnerability perception, online news exposure and mobile app use were both weakly associated with flood-risk information seeking. As flood vulnerability perception was strongly connected to flood severity perception but weakly linked to lower self-efficacy beliefs, flood severity perception was weakly and moderately associated with response-efficacy beliefs and information seeking, respectively. Furthermore, self-efficacy beliefs, response efficacy beliefs, and flood-risk information seeking were each a weak or moderate predictor of collective efficacy beliefs. Lastly, flood risk information-seeking was a strong predictor and collective efficacy beliefs were a weak predictor of community action for flood-risk management. This study tested a conceptual model that integrated the constructs from risk communication, information seeking, and protection motivation theory. Based on the modeling results reflecting a set of first-time findings, theoretical and practical implications are discussed.

The role of public relations in building community resilience to natural disasters: perspectives from Sri Lanka and New Zealand - Dharmasena, M. K. Gayadini Imesha; Toledano, Margalit; Weaver, C. Kay (Journal of Communication Management, 2020)
The paper identifies a role for public relations in disaster management by analysing disaster and communication managers' understanding of community resilience and their use of communication in the context of two different cultural environments.,The research study comprised 51 in-depth qualitative interviews with disaster managers in Sri Lanka and New Zealand, which were thematically analysed using the software programme NVivo 10.,The study identified cultural differences in Sri Lanka and New Zealand that impact on how managers' communicate in natural disaster situations. The findings indicated that public relations’ understanding of communities’ cultures, their communication, networking and lobbying skills could further enhance the effectiveness of efforts to build community resilience to disasters.,Nations are complex multicultural realities; the findings cannot be generalized to make claims about how natural disasters are managed in different national contexts.,The paper identifies the unrealized potential of public relations’ expertise in communication, community relations, networking and lobbying to contribute to building community resilience to natural disasters.,By supporting efforts to build community resilience to disasters, public relations practitioners can contribute to social well-being in times of catastrophic natural disasters.,The paper adds an innovative perspective to public relations crisis literature by identifying the potential contribution of public relations’ concepts and practices to build community resilience to natural disasters. It demonstrates how sociocultural differences may affect disaster communication strategies.

Lessons learned from the NSERC Canadian FloodNet on improving flood forecasting systems and management capacity - Xenopoulos, Marguerite; Coulibaly, Paulin; Anctil, Francois; Burn, Donald; Nguyen, Van-Thanh-Van (AGU Fall Meeting Abstracts, 2021)
In Canada, floods are the most common largely distributed hazard to life, property, the economy, water systems, and the environment costing the Canadian economy billions of dollars. Arising from this is FloodNet: a transdisciplinary strategic research network funded by Canadas Natural Sciences and Engineering Research Council, as a vehicle for a concerted nation-wide effort to improve flood forecasting and to better assess risk and manage the environmental and socio-economic consequences of floods. Four themes were explored in this network which include 1) Flood regimes in Canada; 2) Uncertainty of floods; 3) Development of a flood forecasting and early warning system and 4) Physical, socio-economic and environmental effects of floods. Over the years a range of statistical, hydrologic, modeling, and economic and psychometric analyses were used across the themes. FloodNet has made significant progress in: assessing spatial and temporal variation of extreme events; updating intensity-duration-frequency (IDF) curves; improving streamflow forecasting using novel techniques; development and testing of a Canadian adaptive flood forecasting and early warning system (CAFFEWS); a better understanding of flood impacts and risk. Despite these advancements FloodNet ends at a time when the World is still grappling with severe floods (e.g., Europe, China, Africa) and we report on several lessons learned. Mitigating the impact of flood hazards in Canada remains a challenging task due to the countrys varied geography, environment, and jurisdictional political boundaries. Canadian technical guide for developing IDF relations for infrastructure design in the climate change context has been recently updated. However, national guidelines for flood frequency analyses are needed since across the country there is not a unified approach to flood forecasting as each jurisdiction uses individual models and procedures. From the perspective of risk and vulnerability, there remains great need to better understand the direct and indirect impacts of floods on society, the economy and the environment.

Development of interactive diagnostic tools and metrics for the socio-economic consequences of floods - Parent, Annie-Claude; Fournier, Frédéric; Anctil, François; Morse, Brian; Baril-Boyer, Jean-Philippe; Marceau, Pascal (2021)
Spring floods have generated colossal damages to residential areas in the Province of Quebec, Canada, in 2017 and 2019. Government authorities need accurate modelling of the impact of theoretical floods in order to prioritize pre-disaster mitigation projects to reduce vulnerability. They also need accurate modelling of forecasted floods in order to direct emergency responses. We present a governmental-academic collaboration that aims at modelling flood impact for both theoretical and forecasted flooding events over all populated river reaches of meridional Quebec. The project, funded by the ministère de la Sécurité publique du Québec (Quebec ministry in charge of public security), consists in developing a diagnostic tool and methods to assess the risk and impacts of flooding. Tools under development are intended to be used primarily by policy makers. The project relies on water level data based on the hydrological regimes of nearly 25,000 km of rivers, on high-precision digital terrain models, and on a detailed database of building footprints and characterizations. It also relies on 24h and 48h forecasts of maximum flow for the subject rivers. The developed tools integrate large data sets and heterogeneous data sources and produce insightful metrics on the physical extent and costs of floods and on their impact on the population. The software also provides precise information about each building affected by rising water, including an estimated cost of the damages and impact on inhabitants.

High-resolution mapping of tree species and associated uncertainty by combining aerial remote sensing data and convolutional neural networks ensemble - Sylvain, Jean-Daniel; Drolet, Guillaume; Thiffault, Évelyne; Anctil, François (International Journal of Applied Earth Observation and Geoinformation, 2024)

Modeling Heat and Water Exchanges between the Atmosphere and an 85-km2 Dimictic Subarctic Reservoir Using the 1D Canadian Small Lake Model - Kallel, Habiba; Thiboult, Antoine; Mackay, Murray D.; Nadeau, Daniel F.; Anctil, François (Journal of Hydrometeorology, 2024)
Abstract Accurately modeling the interactions between inland water bodies and the atmosphere in meteorological and climate models is crucial, given the marked differences with surrounding landmasses. Modeling surface heat fluxes remains a challenge because direct observations available for validation are rare, especially at high latitudes. This study presents a detailed evaluation of the Canadian Small Lake Model (CSLM), a one-dimensional mixed-layer dynamic lake model, in reproducing the surface energy budget and the thermal stratification of a subarctic reservoir in eastern Canada. The analysis is supported by multiyear direct observations of turbulent heat fluxes collected on and around the 85-km 2 Romaine-2 hydropower reservoir (50.7°N, 63.2°W) by two flux towers: one operating year-round on the shore and one on a raft during ice-free conditions. The CSLM, which simulates the thermal regime of the water body including ice formation and snow physics, is run in offline mode and forced by local weather observations from 25 June 2018 to 8 June 2021. Comparisons between observations and simulations confirm that CSLM can reasonably reproduce the turbulent heat fluxes and the temperature behavior of the reservoir, despite the one-dimensional nature of the model that cannot account for energy inputs and outputs associated with reservoir operations. The best performance is achieved during the first few months after the ice break-up (mean error = −0.3 and −2.7 W m −2 for latent and sensible heat fluxes, respectively). The model overreacts to strong wind events, leading to subsequent poor estimates of water temperature and eventually to an early freeze-up. The model overestimated the measured annual evaporation corrected for the lack of energy balance closure by 5% and 16% in 2019 and 2020. Significance Statement Freshwater bodies impact the regional climate through energy and water exchanges with the atmosphere. It is challenging to model surface energy fluxes over a northern lake due to the succession of stratification and mixing periods over a year. This study focuses on the interactions between the atmosphere of an irregular shaped northern hydropower reservoir. Direct measurements of turbulent fluxes using an eddy covariance system allowed the model assessment. Turbulent fluxes were successfully predicted during the open water period. Comparison between observed and modeled time series showed a good agreement; however, the model overreacted to high wind episodes. Biases mostly occur during freeze-up and breakup, stressing the importance of a good representation of the ice cover processes.

Impacts of forest canopy heterogeneity on plot-scale hydrometeorological variables - Insights from an experiment in the humid boreal forest with the Canadian Land Surface Scheme - Lagueux, Philippe; Sylvain, Jean-Daniel; Drolet, Guillaume; Isabelle, Pierre-Erik; Leonardini, Gonzalo; Nadeau, Daniel F.; Anctil, François (Agricultural and Forest Meteorology, 2024)

Assessing the hydroclimatic sensitivity of tree species in Northeastern America through spatiotemporal modelling of annual tree growth - Sylvain, Jean-Daniel; Drolet, Guillaume; Kiriazis, Nicholas; Thiffault, Évelyne; Anctil, François (Agricultural and Forest Meteorology, 2024)

The Great Lakes Runoff Intercomparison Project Phase 4: the Great Lakes (GRIP-GL) - Mai, Juliane; Shen, Hongren; Tolson, Bryan A.; Gaborit, Étienne; Arsenault, Richard; Craig, James R.; Fortin, Vincent; Fry, Lauren M.; Gauch, Martin; Klotz, Daniel; Kratzert, Frederik; O'Brien, Nicole; et al. (Hydrology and Earth System Sciences, 2022)
Abstract. Model intercomparison studies are carried out to test and compare the simulated outputs of various model setups over the same study domain. The Great Lakes region is such a domain of high public interest as it not only resembles a challenging region to model with its transboundary location, strong lake effects, and regions of strong human impact but is also one of the most densely populated areas in the USA and Canada. This study brought together a wide range of researchers setting up their models of choice in a highly standardized experimental setup using the same geophysical datasets, forcings, common routing product, and locations of performance evaluation across the 1×106 km2 study domain. The study comprises 13 models covering a wide range of model types from machine-learning-based, basin-wise, subbasin-based, and gridded models that are either locally or globally calibrated or calibrated for one of each of the six predefined regions of the watershed. Unlike most hydrologically focused model intercomparisons, this study not only compares models regarding their capability to simulate streamflow (Q) but also evaluates the quality of simulated actual evapotranspiration (AET), surface soil moisture (SSM), and snow water equivalent (SWE). The latter three outputs are compared against gridded reference datasets. The comparisons are performed in two ways – either by aggregating model outputs and the reference to basin level or by regridding all model outputs to the reference grid and comparing the model simulations at each grid-cell. The main results of this study are as follows: The comparison of models regarding streamflow reveals the superior quality of the machine-learning-based model in the performance of all experiments; even for the most challenging spatiotemporal validation, the machine learning (ML) model outperforms any other physically based model. While the locally calibrated models lead to good performance in calibration and temporal validation (even outperforming several regionally calibrated models), they lose performance when they are transferred to locations that the model has not been calibrated on. This is likely to be improved with more advanced strategies to transfer these models in space. The regionally calibrated models – while losing less performance in spatial and spatiotemporal validation than locally calibrated models – exhibit low performances in highly regulated and urban areas and agricultural regions in the USA. Comparisons of additional model outputs (AET, SSM, and SWE) against gridded reference datasets show that aggregating model outputs and the reference dataset to the basin scale can lead to different conclusions than a comparison at the native grid scale. The latter is deemed preferable, especially for variables with large spatial variability such as SWE. A multi-objective-based analysis of the model performances across all variables (Q, AET, SSM, and SWE) reveals overall well-performing locally calibrated models (i.e., HYMOD2-lumped) and regionally calibrated models (i.e., MESH-SVS-Raven and GEM-Hydro-Watroute) due to varying reasons. The machine-learning-based model was not included here as it is not set up to simulate AET, SSM, and SWE. All basin-aggregated model outputs and observations for the model variables evaluated in this study are available on an interactive website that enables users to visualize results and download the data and model outputs.

The sensitivity of simulated streamflow to individual hydrologic processes across North America - Mai, Juliane; Craig, James R.; Tolson, Bryan A.; Arsenault, Richard (Nature Communications, 2022)
Abstract Streamflow sensitivity to different hydrologic processes varies in both space and time. This sensitivity is traditionally evaluated for the parameters specific to a given hydrologic model simulating streamflow. In this study, we apply a novel analysis over more than 3000 basins across North America considering a blended hydrologic model structure, which includes not only parametric, but also structural uncertainties. This enables seamless quantification of model process sensitivities and parameter sensitivities across a continuous set of models. It also leads to high-level conclusions about the importance of water cycle components on streamflow predictions, such as quickflow being the most sensitive process for streamflow simulations across the North American continent. The results of the 3000 basins are used to derive an approximation of sensitivities based on physiographic and climatologic data without the need to perform expensive sensitivity analyses. Detailed spatio-temporal inputs and results are shared through an interactive website.

Investigation of an Arctic hypertidal estuary under summer and winter conditions : cryo-hydrodynamic and hydrokinetic implications - Mohammadian, Abdolvahid (2021)
La modélisation numérique des estuaires hypertidaux intéresse particulièrement les ingénieurs impliqués dans la navigation maritime et le développement de projets d'énergie marémotrice. Au Québec (Canada), la majorité de ces estuaires à marée extrême sont situés dans des régions isolée de l'Arctique canadien et sont souvent des lieux de résidence des communautés autochtones du Nord canadien. La présente thèse vise à mieux comprendre les processus se manifestent dans ces environnements, avec une emphase particulière sur l'importance (1) de la forte dominance des marées, (2) de l'extrême variabilité bathymétrique et (3) de l'immense forçage climatique. La thèse tente de démontrer comment les modèles numériques peuvent être utilisés pour traiter ces particularités et peuvent être la meilleure méthode disponible pour étudier leurs effets dans des environnements éloignés peu étudies. Premièrement, dans le but d'évaluer le potentiel de courant de marée en eau libre (sans glace) de l'estuaire hypertidal de la rivière Koksoak (KRE), nous avons modélisé le débit de marée en utilisant un model numérique hydrodynamique réputé (Delft3D). Différents aspects de l'hydrodynamique côtière ont été étudiés grâce à la modélisation numérique 1D2D-3D. La variabilité spatio-temporelle de la densité de puissance hydrocinétique disponible a ensuite été quantifiée. Les résultats ont révélé l'énorme potentiel (1000 MW) d'énergie marémotrice présente à plusieurs endroits le long de l'estuaire, ce qui nécessite des études numériques plus approfondies. En mettant davantage l'accent sur la modélisation numérique du site, par exemple la publication d'un Atlas des courants de marée pour aider à la navigation maritime dans le KRE, nous avons constaté que certains problèmes de modélisation des estuaires n'étaient pas abordés. Compte tenu des conditions limites précises et des mesures in situ recueillies au cours de l'hiver 2017-2018, nous avons constaté que les meilleurs résultats pour l'étalonnage du modèle (niveau d'eau) en utilisant les paramètres/options disponibles conduisaient encore à certains ordres d'imprécision. sur les conditions aux limites de formse qualité (campagnes 2017-2018) qui ont effectivement amélioré les résultats numériques, nous avons constaté que les meilleurs résultats pour l'étalonnage du modèle (niveau d'eau) en utilisant les paramètres/options disponibles étaient encore associés à certains ordres d'imprécision. Par conséquent, l'objectif du deuxième travail était d'améliorer l'efficacité de la modélisation hydrodynamique pour les environnements de marée peu profonde. Nous avons introduit quelques hypothèses décrivant pourquoi les modèles de turbulence et de rugosité disponibles ne sont pas bien adaptés à la modélisation des estuaires avec de fortes variabilités spatiales et temporelles des profondeurs de marée. En conséquence (i) un modèle de turbulence k-ε étendu pour la paramétrisation adaptative de la viscosité turbulente en fonction de la profondeur, et une approche basée sur la direction de l'écoulement pour la paramétrisation de la rugosité du lit ont été développés, incorporés dans le modèle hydrodynamique employé (Delft3D). Le modèle modifié a montré une amélioration constante des prévisions du modèle dans les stations de champ proche et de champ lointain, par rapport aux schémas de paramétrage classiques. Enfin, un aspect manquant et mal compris des estuaires de latitude nordique est l'immense impact de l'hiver sur le flux des marées. Situé à la latitude 58°, le KRE subit l'effet intensif du climat arctique pendant la majeure partie de l'année, ce qui entraîne la formation de glace estuarienne rapide sur une grande partie de sa longueur. Plus précisément, et ce qui est le plus pertinent pour cette recherche, il est important de savoir comment le long hiver affecte les potentiels hydrocinétiques des estuaires des régions froides. Ainsi, la surfusion entraîne la formation de frasil et de glace de fond qui peuvent adhérer aux pales des turbines et provoquer leur dysfonctionnement. Dans les estuaires, la surfusion a une nature transitoire complexe car le point de congélation de l'eau salée est une fonction de la salinité et de la profondeur qui est changée par les marées au cours des cycles de marée. En raison du manque de données de terrain en hiver, nous avons collecté des paramètres hydrodynamiques en utilisant de nouvelles campagne de mesures en hiver 2018. Les observations ont montré que le risque de surfusion diminue à l'intérieur de l'estuaire, car en l'absence de débit fluvial, la salinité peut s'infiltrer beaucoup plus loin dans le fleuve. À l'intérieur, une modulation apparente de ∆T (la différence entre la température de l'eau et la température de congélation de l'eau), dépendant de la marée, a été observée avec une augmentation de la température pendant des marées montantes. Cette augmentation retarderait la surfusion, ce qui est un avantage majeur pour turbines. En réglant le module Delft3D-Ice, différents scénarios ont été définis pour l'étendue et l'épaisseur de la couvert de glace, et leurs réponses hydrodynamiques ont été analysées. Il a été démontré que la glace a des impacts complexes et non uniformes sur les caractéristiques hydrodynamiques de la KRE. Surtout, le débit des prismes de marée, qui est la principale source d'élan, peut être modifiée de manière démonstrative par la couverture de glace et la glace de marée plate. Les résultats suggèrent que les zones énergétiques sont légèrement affectées par la glace pendant la plus grande partie de l'hiver. Pendant l'hiver de pointe seulement, la glace pourrait considérablement diminuer densité moyenne de puissance des courants (par exemple, la puissance moyenne est égale ou supérieure à 7 kW m-2). Ces implications cryohydrodynamiques indiquent que l'hiver arctique n'est pas un obstacle à la production d'électricité dans le fleuve Koksoak, et l'énergie marémotrice serait un avantage annuel pour Kuujjuaq

Disaster risk reduction and the limits of truisms: Improving the knowledge and practice interface - Nohrstedt, Daniel; Parker, Charles F.; von Uexkull, Nina; Mård, Johanna; Nyberg, Lars; Petrova, Kristina; Albrecht, Frederike; Göteman, Malin; Hileman, Jacob; Messori, Gabriele; Di Baldassarre, Giuliano (International journal of disaster risk reduction, 2021)
Abstract Action toward strengthened disaster risk reduction (DRR) ideally builds from evidence-based policymaking to inform decisions and priorities. This is a guiding principle for the Sendai Framework for Disaster Risk Reduction (SFDRR), which outlines priorities for action to reduce disaster risk. However, some of these practical guidelines conceal oversimplified or unsubstantiated claims and assumptions, what we refer to as “truisms”, which, if not properly addressed, may jeopardize the long-term goal to reduce disaster risks. Thus far, much DRR research has focused on ways to bridge the gap between science and practice while devoting less attention to the premises that shape the understanding of DRR issues. In this article, written in the spirit of a perspective piece on the state of the DRR field, we utilize the SFDRR as an illustrative case to identify and interrogate ten selected truisms, from across the social and natural sciences, that have been prevalent in shaping DRR research and practice. The ten truisms concern forecasting, loss, conflict, migration, the local level, collaboration, social capital, prevention, policy change, and risk awareness. We discuss central claims associated with each truism, relate those claims to insights in recent DRR scholarship, and end with suggestions for developing the field through advances in conceptualization, measurement, and causal inference.

Exposure to natural hazard events unassociated with policy change for improved disaster risk reduction - Nohrstedt, Daniel; Mazzoleni, Maurizio; Parker, Charles F.; Di Baldassarre, Giuliano (Nature Communications, 2021)
Abstract Natural hazard events provide opportunities for policy change to enhance disaster risk reduction (DRR), yet it remains unclear whether these events actually fulfill this transformative role around the world. Here, we investigate relationships between the frequency (number of events) and severity (fatalities, economic losses, and affected people) of natural hazards and DRR policy change in 85 countries over eight years. Our results show that frequency and severity factors are generally unassociated with improved DRR policy when controlling for income-levels, differences in starting policy values, and hazard event types. This is a robust result that accounts for event frequency and different hazard severity indicators, four baseline periods estimating hazard impacts, and multiple policy indicators. Although we show that natural hazards are unassociated with improved DRR policy globally, the study unveils variability in policy progress between countries experiencing similar levels of hazard frequency and severity.

Mapping SWE in near real time across a large territory using a particle filter - Odry, Jean; Boucher, Marie-Amélie; Lachance Cloutier, Simon; Turcotte, Richard; Saint-Louis, Pierre-Yves (2020)
In snow-prone regions, snowmelt is one of the main drivers of runoff. For operational flood forecasting and mitigation, the spatial distribution of snow water equivalent (SWE) in near real time is necessary. In this context, in situ observations of SWE provide a valuable information. Nonetheless, the high spatial variability of snowpack characteristics makes it necessary to implement some kind of snow modelling to get a spatially continuous estimation. Data assimilation is thus a useful approach to combine information from both observation and modeling in near real-time. For example, at the provincial government of Quebec (eastern Canada), the HYDROTEL Snowpack Model is applied on a daily basis over a 0.1 degree resolution mesh covering the whole province. The modelled SWE is corrected in real time by in situ manual snow survey which are assimilated using a spatial particles filter (Cantet et al., 2019). This assimilation method improves the reliability of SWE estimation at ungauged sites. The availability of manual snow surveys is however limited both in space and time. These measurements are conducted on a bi-weekly basis in a limited number of sites. In order to further improve the temporal and spatial observation coverage, alternative sources of data should be considered. In this research, it is hypothesized that data gathered by SR50 sonic sensors can be assimilated in the spatial particle filter to improve the SWE estimation. These automatic sensors provide hourly measurements of snow depth and have been deployed in Quebec since 2005. Beforehand, probabilistic SWE estimations were derived from the SR50 snow depth measurements using an ensemble of artificial neural networks (Odry et al. 2019). Considering the nature of the data and the conversion process, the uncertainty associated with this dataset is supposed larger than for the manual snow surveys. The objective of the research is to evaluate the potential interest of adding this lower-quality information in the assimilation framework. The addition of frequent but uncertain data in the spatial particle filter required some adjustments in term of assimilation frequency and particle resampling. A reordering of the particles was implemented to maintain the spatial coherence between the different particles. With these changes, the consideration of both manual snow surveys and SR50 data in the spatial particle filter reached performances that are comparable to the initial particle filter that combines only the model and manual snow survey for estimating SWE in ungauged sites. However, the addition of SR50 data in the particle filter allows for continuous information in time, between manual snow surveys. References: Cantet, P., Boucher, M.-A., Lachance-Coutier, S., Turcotte, R., Fortin, V. (2019). Using a particle filter to estimate the spatial distribution of the snowpack water equivalent. J. Hydrometeorol, 20. Odry, J., Boucher, M.-A., Cantet,P., Lachance-Cloutier, S., Turcotte, R., St-Louis, P.-Y. (2019). Using artificial neural networks to estimate snow water equivalent from snow depth. Canadian water ressources journal (under review)

Thermal exposure risk in different life stages of Chinook salmon in the Nechako River system, British Columbia - Oyinlola, Muhammed Alolade; Khorsandi, Mostafa; Mayer, Noa; Butler, Natalie; Wert, Jacey C. Van; Eliason, Erika J.; Arsenault, Richard; Brauner, Colin J.; Hinch, Scott G.; St-Hilaire, Andre (2024)
Abstract Climate change is affecting freshwater systems, leading to increased water temperatures, which is posing a threat to freshwater ecological communities. In the Nechako River, a water management program has been in place since the 1980s to maintain water temperatures at 20°C during the migration of Sockeye salmon. However, the program's effectiveness in mitigating the impacts of climate change on resident species like Chinook salmon's thermal exposure is uncertain. In this study, we utilised the CEQUEAU hydrological model and life stage-specific physiological data to evaluate the consequences of the current program on Chinook salmon's thermal exposure under two contrasting climate change and socio-economic scenarios (SSP2-4.5 and SSP5-8.5). The results indicate that the thermal exposure risk is projected to be above the optimal threshold for parr and adult life stages under both scenarios relative to the 1980s. These life stages could face an increase in thermal exposure ranging from up to 2 and 5 times by 2090s relative to the 1980s during the months they occurred under the SSP5-8.5 scenario, including when the program is active (July 20th to August 20th). Additionally, our study shows that climate change will result in a substantial rise in cumulative heat degree days, ranging from 1.9 to 5.8 times (2050s) and 2.9 to 12.9 times (2090s) in comparison to the 1980s under SSP5-8.5. Our study highlights the need for a holistic approach to review the current Nechako management plan and consider all species in the Nechako River system in the face of climate change.

Arctic precipitation and surface wind speed associated with cyclones in a changing climate - Oh, Seok-Geun; Sushama, Laxmi; Teufel, Bernardo (Climate Dynamics, 2020)

Climate Gentrification: Risk, Rent, and Restructuring in Greater Miami - Taylor, Zac J.; Aalbers, Manuel B. (Annals of the American Association of Geographers, 2022)

Human–water research: discussion of “guiding principles for hydrologists conducting interdisciplinary research and fieldwork with participants” - Thaler, Thomas (Hydrological Sciences Journal-journal Des Sciences Hydrologiques, 2022)
Rangecroft et al. provide an important and interesting paper on the challenges of interdisciplinary research and fieldwork with participants in water resource management. The paper shows the challenges of interaction between their research areas and demonstrates the importance of how a researcher interacts with their selected study sites. My key points reflect the use of different methodologies within social and natural sciences and across them as well as the main challenge of who has the power to influence the research directions. Research is not value-free and is highly influenced by one’s own training and knowledge, which needs to be addressed in the research activities. Finally, an option might be to move beyond interdisciplinary constraints and to work within a stronger transdisciplinary framework. Water research very much needs to interact with non-academic people to understand the challenges and possible solutions.

Generating Ensemble Streamflow Forecasts: A Review of Methods and Approaches Over the Past 40 Years - Troin, Magali; Arsenault, Richard; Wood, Andrew W.; Brissette, François; Martel, Jean‐Luc (Water Resources Research, 2021)
Abstract Ensemble forecasting applied to the field of hydrology is currently an established area of research embracing a broad spectrum of operational situations. This work catalogs the various pathways of ensemble streamflow forecasting based on an exhaustive review of more than 700 studies over the last 40 years. We focus on the advanced state of the art in the model‐based (dynamical) ensemble forecasting approaches. Ensemble streamflow prediction systems are categorized into three leading classes: statistics‐based streamflow prediction systems, climatology‐based ensemble streamflow prediction systems and numerical weather prediction‐based hydrological ensemble prediction systems. For each ensemble approach, technical information, as well as details about its strengths and weaknesses, are provided based on a critical review of the studies listed. Through this literature review, the performance and uncertainty associated with the ensemble forecasting systems are underlined from both operational and scientific viewpoints. Finally, the remaining key challenges and prospective future research directions are presented, notably through hybrid dynamical ‐ statistical learning approaches, which obviously present new challenges to be overcome in order to allow the successful employment of ensemble streamflow forecasting systems in the next decades. Targeting students, researchers and practitioners, this review provides a detailed perspective on the major features of an increasingly important area of hydrological forecasting. , Key Points This work summarizes the 40 years of research in the generation of streamflow forecasts based on an exhaustive review of studies Ensemble prediction systems are categorized into three classes: statistics‐based, climatology‐based and numerical weather prediction‐based hydrological ensemble prediction systems For each ensemble forecasting system, thorough technical information is provided

Integrating Multiple Research Methods to Unravel the Complexity of Human‐Water Systems - Di Baldassarre, Giuliano; Cloke, Hannah; Lindersson, Sara; Mazzoleni, Maurizio; Mondino, Elena; Mård, Johanna; Odongo, Vincent; Raffetti, Elena; Ridolfi, Elena; Rusca, Maria; Savelli, Elisa; Tootoonchi, Faranak (AGU Advances, 2021)
Abstract Predicting floods and droughts is essential to inform the development of policy in water management, climate change adaptation and disaster risk reduction. Yet, hydrological predictions are highly uncertain, while the frequency, severity and spatial distribution of extreme events are further complicated by the increasing impact of human activities on the water cycle. In this commentary, we argue that four main aspects characterizing the complexity of human‐water systems should be explicitly addressed: feedbacks, scales, tradeoffs and inequalities. We propose the integration of multiple research methods as a way to cope with complexity and develop policy‐relevant science. , Plain Language Summary Several governments today claim to be following the science in addressing crises caused by the occurrence of extreme events, such as floods and droughts, or the emergence of global threats, such as climate change and COVID‐19. In this commentary, we show that there are no universal answers to apparently simple questions such as: Do levees reduce flood risk? Do reservoirs alleviate droughts? We argue that the best science we have consists of a plurality of legitimate interpretations and a range of foresights, which can be enriched by integrating multiple disciplines and research methods. , Key Points Accounting for both power relations and cognitive heuristics is key to unravel the interplay of floods, droughts and human societies Flood and drought predictions are complicated by the increasing impact of human activities on the water cycle We propose the integration of multiple research methods as a way to cope with uncertainty and develop policy‐relevant science

A Canadian River Ice Database from National Hydrometric Program Archives - De Rham, Laurent; Dibike, Yonas; Beltaos, Spyros; Peters, Daniel; Bonsal, Barrie; Prowse, Terry (Hydrology and Soil Science – Hydrology, 2020)
Abstract. River ice is a common occurrence in cold climate hydrological systems. The annual cycle of river ice formation, growth, decay and clearance can include low flows and ice jams, as well as mid-winter and spring break-up events. Reports and associated data on river ice occurrence are often limited to site and season-specific studies. Within Canada, the National Hydrometric Program (NHP) operates a network of gauging stations with water level as the primary measured variable to derive discharge. In the late 1990s, the Water Science and Technology Directorate of Environment and Climate Change Canada initiated a long-term effort to compile, archive and extract river ice related information from NHP hydrometric records. This data article describes the original research data set produced by this near 20-year effort: the Canadian River Ice Database (CRID). The CRID holds almost 73,000 variables from a network of 196 NHP stations throughout Canada that were in operation within the period 1894 to 2015. Over 100,000 paper and digital files were reviewed representing 10,378 station-years of active operation. The task of compiling this database involved manual extraction and input of more than 460,000 data entries on water level, discharge, date, time and data quality rating. Guidelines on the data extraction, rating procedure and challenges are provided. At each location, a time series of up to 15 variables specific to the occurrence of freeze-up and winter-low events, mid-winter break-up, ice thickness, spring break-up and maximum open-water level were compiled. This database follows up on several earlier efforts to compile information on river ice, which are summarized herein, and expands the scope and detail for use in Canadian river ice research and applications. Following the Government of Canada Open Data initiative, this original river ice data set is available at: https://doi.org/10.18164/c21e1852-ba8e-44af-bc13-48eeedfcf2f4 (de Rham et al., 2020).

Interdecadal variability of streamflow in the Hudson Bay Lowlands watersheds driven by atmospheric circulation - Champagne, Olivier; Arain, M. Altaf; Wang, Shusen; Leduc, Martin; Russell, Hazen A. J. (Journal of Hydrology: Regional Studies, 2021)
Study region Hudson Bay Lowlands watersheds, Ontario, Canada. Study Focus The rivers in the Hudson Bay Lowlands are a major source of freshwater entering the Arctic Ocean and they also cause major floods. In recent decades, this region has been affected by major changes in hydroclimatic processes attributed to climate change and natural climate variability. In this study, we used ERA5 reanalysis data, hydrometric observations, and the hydrological model MESH, to investigate the impact of atmospheric circulation on the inter-decadal variability of streamflow between 1979 and 2018 in the Hudson Bay Lowlands. The natural climate variability was assessed using a weather regimes approach based on the discretization of daily geopotential height anomalies (Z500) from ERA5 reanalysis, as well as large scale oceanic and atmospheric variability modes. New hydrological insights The results showed an anomalous convergence of atmospheric moisture flux between 1995–2008 that enhanced precipitation and increased streamflow in the western part of the region. This moisture convergence was likely driven by the combination of (i) low pressure anomalies in the East Coast of North America and (ii) low pressure anomalies in western regions of Canada, associated with the cold phase of the pacific decadal oscillation (PDO). Since 2009, streamflow remains high, likely due to more groundwater discharge associated with the degradation of permafrost.

Future shift in winter streamflow modulated by the internal variability of climate in southern Ontario - Champagne, Olivier; Arain, M. Altaf; Leduc, Martin; Coulibaly, Paulin; McKenzie, Shawn (Hydrology and Earth System Sciences, 2020)
Fluvial systems in southern Ontario are regularly affected by widespread early-spring flood events primarily caused by rain-on-snow events. Recent studies have shown an increase in winter floods in this region due to increasing winter temperature and precipitation. Streamflow simulations are associated with uncertainties mainly due to the different scenarios of greenhouse gas emissions, global climate models (GCMs) or the choice of the hydrological model. The internal variability of climate, defined as the chaotic variability of atmospheric circulation due to natural internal processes within the climate system, is also a source of uncertainties to consider. Uncertainties of internal variability can be assessed using hydrological models fed by downscaled data of a global climate model large ensemble (GCM-LE), but GCM outputs have too coarse of a scale to be used in hydrological modeling. The Canadian Regional Climate Model Large Ensemble (CRCM5-LE), a 50-member ensemble downscaled from the Canadian Earth System Model version 2 Large Ensemble (CanESM2-LE), was developed to simulate local climate variability over northeastern North America under different future climate scenarios. In this study, CRCM5-LE temperature and precipitation projections under an RCP8.5 scenario were used as input in the Precipitation Runoff Modeling System (PRMS) to simulate streamflow at a near-future horizon (2026–2055) for four watersheds in southern Ontario. To investigate the role of the internal variability of climate in the modulation of streamflow, the 50 members were first grouped in classes of similar projected change in January–February streamflow and temperature and precipitation between 1961–1990 and 2026–2055. Then, the regional change in geopotential height (Z500) from CanESM2-LE was calculated for each class. Model simulations showed an average January–February increase in streamflow of 18 % (±8.7) in Big Creek, 30.5 % (±10.8) in Grand River, 29.8 % (±10.4) in Thames River and 31.2 % (±13.3) in Credit River. A total of 14 % of all ensemble members projected positive Z500 anomalies in North America's eastern coast enhancing rain, snowmelt and streamflow volume in January–February. For these members the increase of streamflow is expected to be as high as 31.6 % (±8.1) in Big Creek, 48.3 % (±11.1) in Grand River, 47 % (±9.6) in Thames River and 53.7 % (±15) in Credit River. Conversely, 14 % of the ensemble projected negative Z500 anomalies in North America's eastern coast and were associated with a much lower increase in streamflow: 8.3 % (±7.8) in Big Creek, 18.8 % (±5.8) in Grand River, 17.8 % (±6.4) in Thames River and 18.6 % (±6.5) in Credit River. These results provide important information to researchers, managers, policymakers and society about the expected ranges of increase in winter streamflow in a highly populated region of Canada, and they will help to explain how the internal variability of climate is expected to modulate the future streamflow in this region.

The quantification of water storage capacity of peatlands across different hydroclimatic settings using a simple rainfall event to water-table response ratio method - Bourgault, Marc-André; Bechtold, Michel; Holden, Joseph; Blundell, Antony; Dettman, Ullrich; Garneau, Michelle; Howson, Tim; Jutras, Sylvain; Kløve, Bjørn; Larocque, Marie; Marttila, Hannu; McKendrick-Smith, Kathryn; et al. (2021)
In wetlands, the water budget is traditionally quantified by measuring the hydrologic components including precipitation, evapotranspiration and surface water-groundwater inflows and outflows. However, the reliability of measurements is often questioned due to the difficulty of rigorously monitoring all components of the water budget. Quantifying the rainfall event to water table response ratio is an alternative approach with minimal need for data commonly collected in peatland studies. However, the method has been used only in a limited number of biophysical settings including different microforms, hydroclimatic and hydrogeological settings. The objectives of this study are to quantify the reactivity of the water table to precipitation for different pristine peatlands located in different hydroclimatic conditions and to provide quantitative assessments of water storage of as many peatlands as possible. To do so, site-specific hourly water table and precipitation measurements was collected from northern peatlands worldwide. In total, data from more than 30 sites were retrieved from 8 research groups. For all peatlands, water-table depths varied between 80 cm below the peat surface and 10 cm above the peat surface. The results highlight that the hydrology of all peatlands is characterized by a shift from an environment that can store water to an environment that contributes to rapid outflow, and this is a uniform feature across sites. However, for peatlands with the lowest water storage capacities, this shift occurs during relatively moderate rainfall events (40 mm) or successive small rainfall events. Blanket peat bog best embodied this type of hydrological response. For peatlands with the highest water storage capacity, this shift occurs following multiple moderate to large precipitation events (40 mm – 80 mm) and it is strongly enhanced by the shift from high to low evaporative periods. The peatlands with the highest storage capacity are raised bogs with deep water-table. These conditions are best observed in peatlands located in geographical settings with high evaporation rates. Among all the peatlands, maximum water storage capacity for given rainfall events was equal to ≈150 mm. These analyses also confirm that the water table rise caused by precipitation events contain sufficient information to constrain water storage variations around monitored wells peatlands for a wide array of biophysical settings.

A Mutual Catastrophe Insurance Framework for Horizontal Collaboration in Prepositioning Strategic Reserves - Zbib, Hani; Balcik, Burcu; Rancourt, Marie-Ève; Laporte, Gilbert (Operations Research, 2024)
Improving Disaster Preparedness Through Mutual Catastrophe Insurance In “A Mutual Catastrophe Insurance Framework for Horizontal Collaboration in Prepositioning Strategic Reserves,” H. Zbib, B. Balcik, M.-È. Rancourt, and G. Laporte present an innovative approach to collaborative disaster preparedness. The novel framework considers a risk-averse mutual insurer offering multiyear insurance contracts with coverage deductibles and limits to a portfolio of risk-averse policyholders. It is designed to foster horizontal collaboration among policyholders for joint disaster preparedness by effectively integrating operational and financial functions. The problem is modeled as a large-scale nonlinear multistage stochastic program and solved by using an effective Benders decomposition algorithm. The framework is validated with real data from 18 Caribbean countries focusing on hurricane preparedness. Given the predicted impacts of climate change, the proposed multiyear mutual catastrophe insurance framework promises to reshape global disaster preparedness and make a profound societal impact by providing a transparent disaster financing plan to protect vulnerable regions. The study’s findings stress the importance of long-term cooperation, prenegotiation of indemnification policies, and strategic setting of deductibles and limits by taking into account the correlation between policyholders. , We develop a mutual catastrophe insurance framework for the prepositioning of strategic reserves to foster horizontal collaboration in preparedness against low-probability high-impact natural disasters. The framework consists of a risk-averse insurer pooling the risks of a portfolio of risk-averse policyholders. It encompasses the operational functions of planning the prepositioning network in preparedness for incoming insurance claims, in the form of units of strategic reserves, setting coverage deductibles and limits of policyholders, and providing insurance coverage to the claims in the emergency response phase. It also encompasses the financial functions of ensuring the insurer’s solvency by efficiently managing its capital and allocating yearly premiums among policyholders. We model the framework as a very large-scale nonlinear multistage stochastic program, and solve it through a Benders decomposition algorithm. We study the case of Caribbean countries establishing a horizontal collaboration for hurricane preparedness. Our results show that the collaboration is more effective when established over a longer planning horizon, and is more beneficial when outsourcing becomes expensive. Moreover, the correlation of policyholders affected simultaneously under the extreme realizations and the position of their claims in their global claims distribution directly affects which policyholders get deductibles and limits. This underlines the importance of prenegotiating policyholders’ indemnification policies at the onset of collaboration. Funding: G. Laporte and M.-È. Rancourt were funded by the Canadian Natural Sciences and Engineering Research Council (NSERC) [Grants 2015-06189 and 2022-04846]. Funding was also provided by the Institute for Data Valorisation (IVADO) and the Canada Research Chair in Humanitarian Supply Chain Analytics. B. Balcik was partially supported by a grant from the Scientific and Technological Research Council of Turkey (TUBITAK) 2219 program. This support is gratefully acknowledged. Supplemental Material: The online appendix is available at https://doi.org/10.1287/opre.2021.0141 .
Keywords: Infolettre; Infolettre_Avril_2024

A dynamics model of the emergency medical supply chain in epidemic considering deprivation cost - Shi, Wenqiang; He, Jie; Wang, Mingyue; Yang, Fang (Socio-Economic Planning Sciences, 2024)
Keywords: Infolettre; Infolettre_Septembre_2024

On optimization of calibrations of a distributed hydrological model with spatially distributed information on snow - Tiwari, Dipti; Trudel, Mélanie; Leconte, Robert (2023)
Abstract. In northern cold-temperate countries, a large portion of annual streamflow is produced by spring snowmelt, which often triggers floods. It is important to have spatial information about snow parameters such as snow water equivalent (SWE), which can be incorporated into hydrological models, making them more efficient tools for improved decision-making. The future Terrestrial Snow Mass Mission (TSMM) aims to provide high-resolution spatially distributed SWE information; thus, spatial SWE calibration should be considered along with conventional streamflow calibration for model optimization since the overall water balance is often a key objective in the hydrological modelling. The present research implements a unique spatial pattern metric in a multi-objective framework for calibration approach of hydrological models and attempts to determine whether raw SNODAS data can be utilized for hydrological model calibration. The SPAtial Efficiency (SPAEF) metric is explored for spatially calibrating SWE. The HYDROTEL hydrological model is applied to the Au Saumon River Watershed (∽1120 km2) in Eastern Canada using MSWEP precipitation data and ERA-5 land reanalysis temperature data as input to generate high-resolution SWE and streamflow. Different calibration experiments are performed combining Nash-Sutcliffe efficiency (NSE) for streamflow and root-mean-square error (RMSE), and SPAEF for SWE, using the Dynamically Dimensioned Search (DDS) and Pareto Archived Multi-Objective Optimization (PADDS) algorithms. Results of the study demonstrate that multi-objective calibration outperforms sequential calibration in terms of model performance. Traditional model calibration involving only streamflow produced slightly higher NSE values; however, the spatial distribution of SWE could not be adequately maintained. This study indicates that utilizing SPAEF for spatial calibration of snow parameters improved streamflow prediction compared to the conventional practice of using RMSE for calibration. SPAEF is further implied to be a more effective metric than RMSE for both sequential and multi-objective calibration. During validation, the calibration experiment incorporating multi-objective SPAEF exhibits enhanced performance in terms of NSE and Kling-Gupta Efficiency (KGE) compared to calibration experiment solely based on NSE. This observation supports the notion that incorporating SPAEF computed on raw SNODAS data within the calibration framework results in a more robust hydrological model.
Keywords: Infolettre; Infolettre_Mai_2024

Failure mechanism, existing constitutive models and numerical modeling of landslides in sensitive clay: a review - Urmi, Zinan Ara; Saeidi, Ali; Chavali, Rama Vara Prasad; Yerro, Alba (Geoenvironmental Disasters, 2023)
Abstract Landslides involving sensitive clays are recurrent events in the world's northern regions and are especially notorious in eastern Canada. The two critical factors that separate sensitive clay landslides from traditional slope stability analysis are the highly brittle behavior in undrained conditions (strain-softening) characteristic of progressive or retrogressive failures and the large deformations associated with them. Conventional limit equilibrium analysis has numerous shortcomings in incorporating these characteristics when assessing landslides in sensitive clays. This paper presents an extensive literature review of the failure mechanics characteristics of landslides in sensitive clays and the existing constitutive models and numerical tools to analyze such slopes' stability and post-failure behavior. The advantages and shortcomings of the different techniques to incorporate strain-softening and large deformation in the numerical modeling of sensitive clay landslides are assessed. The literature review depicts that elastoviscoplastic soil models with non-linear strain-softening laws and rate effects represent the material behavior of sensitive clays. Though several numerical models have been proposed to analyze post-failure runouts, the amount of work performed in line with sensitive clay landslides is very scarce. That creates an urgent need to apply and further develop advanced numerical tools for better understanding and predicting these catastrophic events.
Keywords: Infolettre; Infolettre_Juin_2023

Citizens’ viewpoints on stormwater Beneficial Management Practices (BMPs) in Brazil - Sousa, Bruno José de Oliveira; Fialho, Hailton César Pimentel; Taffarello, Denise; Souza, Felipe Augusto Arguello; Hassanzadeh, Elmira; Mendiondo, Eduardo Mario; de Oliveira, Paulo Tarso Sanches (Journal of Cleaner Production, 2021)
Floods are among the most dangerous and destructive hazards in the world. Stormwater Beneficial Management Practices (BMPs) are a set of strategies that can assist in reducing urban floods and their damages by capturing surface runoff and promoting infiltration. Engagement of citizens in the selection of stormwater BMPs may facilitate the decision-making processes and increase the chance of adopting and maintaining them. Due to existence of catastrophic floods in Brazil, implementing BMPs is essential in the urban areas. The objective of this study is to understand the viewpoints of citizens about a set of stormwater BMPs in Brazil. Moreover, we aim to comprehend whether diverging viewpoints about the BMPs can be associated with existence of different layers in the society. For this purpose, online surveys were used to access wide and diverse groups of citizens from different ages, levels of education and income, as well as geographical location. The questions and descriptions of BMPs were prepared in an accessible language, and then disseminated through various platforms. The responses of more than 1000 participants were analyzed using descriptive and statistical methods. Our results show that the participants found the retention and detention basins, as well as permeable pavement as the most efficient BMPs. Moreover, considering the small-scale practices, although lot related BMPs are considered less efficient, citizens are willing to use green roof, bioretention, and rain barrels in their properties. In addition, most of the respondents support public investments on stormwater BMPs. Our analyses show that participants' age and level of education statistically influenced their choice of BMPs and willingness to pay for their maintenance and construction. These results can help Brazilian policy makers to prepare flood management plans by including stormwater BMPs that would be more accepted by the population. In addition, proposing practices that are aligned with citizens’ perceptions creates a sense of responsibility, and is in accordance with the Brazilian New Framework of Sanitation that includes public participation in policy making.
Keywords: Infolettre; Infolettre_Juillet_2022; Site_internet_RIISQ

Hydrological connectivity controls dissolved organic carbon exports in a peatland-dominated boreal catchment stream - Prijac, Antonin; Gandois, Laure; Taillardat, Pierre; Bourgault, Marc-André; Riahi, Khawla; Ponçot, Alex; Tremblay, Alain; Garneau, Michelle (Hydrology and Earth System Sciences, 2023)
The magnitudes of dissolved organic carbon (DOC) exports from boreal peatlands to streams through lateral subsurface flow vary during the ice-free season. Peatland water table depth and the alternation of low and high flow in peat-draining streams are thought to drive this DOC export variability. However, calculation of the specific DOC exports from a peatland can be challenging considering the multiple potential DOC sources within the catchment. A calculation approach based on the hydrological connectivity between the peat and the stream could help to solve this issue, which is the approach used in the present research. This study took place from June 2018 to October 2019 in a boreal catchment in northeastern Canada, with 76.7 % of the catchment being covered by ombrotrophic peatland. The objectives were to (1) establish relationships between DOC exports from a headwater stream and the peatland hydrology; (2) quantify, at the catchment scale, the amount of DOC laterally exported to the draining stream; and (3) define the patterns of DOC mobilization during high-river-flow events. At the peatland headwater stream outlet, the DOC concentrations were monitored at a high frequency (hourly) using a fluorescent dissolved organic matter (fDOM) sensor, a proxy for DOC concentration. Hydrological variables, such as stream outlet discharge and peatland water table depth (WTD), were continuously monitored at hourly intervals for 2 years. Our results highlight the direct and delayed control of subsurface flow from peat to the stream and associated DOC exports. Rain events raised the peatland WTD, which increased hydrological connectivity between the peatland and the stream. This led to increased stream discharge (Q) and a delayed DOC concentration increase, typical of lateral subsurface flow. The magnitude of the WTD increase played a crucial role in influencing the quantity of DOC exported. Based on the observations that the peatland is the most important contributor to DOC exports at the catchment scale and that other DOC sources were negligible during high-flow periods, we propose a new approach to estimate the specific DOC exports attributable to the peatland by distinguishing between the surfaces used for calculation during high-flow and low-flow periods. In 2018–2019, 92.6 % of DOC was exported during flood events despite the fact that these flood events accounted for 59.1 % of the period. In 2019–2020, 93.8 % of DOC was exported during flood events, which represented 44.1 % of the period. Our analysis of individual flood events revealed three types of events and DOC mobilization patterns. The first type is characterized by high rainfall, leading to an important WTD increase that favours the connection between the peatland and the stream and leading to high DOC exports. The second is characterized by a large WTD increase succeeding a previous event that had depleted DOC available to be transferred to the stream, leading to low DOC exports. The third type corresponds to low rainfall events with an insufficient WTD increase to reconnect the peatland and the stream, leading to low DOC exports. Our results suggest that DOC exports are sensitive to hydroclimatic conditions; moreover, flood events, changes in rainfall regime, ice-free season duration, and porewater temperature may affect the exported DOC and, consequently, partially offset the net carbon sequestration potential of peatlands.
Keywords: Infolettre; Infolettre_Mars_2024

Trend and teleconnection analysis of temperature extremes in New South Wales, Australia - Laz, Orpita U.; Rahman, Ataur; Ouarda, Taha B. M. J. (Natural Hazards, 2024)
Abstract This study investigates possible trends and teleconnections in temperature extremes in New South Wales (NSW), Australia. Daily maximum and minimum temperature data covering the period 1971–2021 at 26 stations located in NSW were used. Three indices, which focus on daily maximum temperature, daily minimum temperature, and average daily temperature in terms of Excessive Heat Factor (EHF) were investigated to identify the occurrence of heatwaves (HWs). The study considered HWs of different durations (1-, 5-, and 10-days) in relation to intensity, frequency, duration, and their first occurrence parameters. Finally, the influences of three global climate drivers, namely – the El Niño/Southern Oscillation (ENSO), the Southern Annular Mode (SAM), and the Indian Ocean Dipole (IOD) were investigated with associated heatwave attributes for extended Austral summers. In this study, an increasing trend in both hot days and nights was observed for most of the selected stations within the study area. The increase was more pronounced for the last decade (2011–2021) of the investigated time period. The number, duration and frequency of the heatwaves increased over time considering the EHF criterion, whereas no particular trend was detected in cases of TX90 and TN90. It was also evident that the first occurrence of all the HWs shifted towards the onset of the extended summer while considering the EHF criterion of HWs. The correlations between heatwave attributes and climate drivers depicted that heatwave over NSW was positively influenced by both the IOD and ENSO and negatively correlated with SAM. The findings of this study will be useful in formulating strategies for managing the impacts of extreme temperature events such as bushfires, floods, droughts to the most at-risk regions within NSW.
Keywords: Infolettre; Infolettre_Novembre_2024

Synthesis of a water‐soluble high hydroxymethyl content phenolic resin crosslinker and the associated polyacrylamide weak gel property investigation - He, Jie; Ye, Zi; Liao, Dong; Chen, Qing‐mei; Liu, Hang‐rui; Fan, Hai‐bo; Luo, Min; Zhong, Cheng (Journal of Polymer Science, 2024)
Abstract As an in‐depth profile control agent, water‐soluble phenolic resin crosslinking polyacrylamide weak gel has been widely used in the middle and high water cut stage of water flooding reservoir. In this study, the phenolic resin was synthesized by two‐step alkali catalysis. Factors influencing the synthesis of phenolic resin, including the molar ratio of phenol and formaldehyde, catalyst types, reaction time, were investigated with hydroxylmethyl and aldehyde content as the criterion. When the molar ratio of phenolic resin was 1:2 and NaOH was catalyst, at 80°C for 4 h, the phenolic resin had the highest hydroxymethyl content (49.37%) and the lowest free aldehyde content (2.95%). Weak gel was formed by the reaction of LT002‐polyacrylamide with phenolic resin. Taking the gelation time and strength as criteria, the factors influencing the crosslinking property, including hydroxymethyl content, crosslinker addition, and polyacrylamide concentration were investigated respectively. Under optimal formulation, the property investigation shows that the hydroxymethyl group in the phenolic resin can be crosslinked with the amide group in polyacrylamide, the gelation time is long (50–60 h), and the gelation strength is larger than 5 × 10 4 mPa s, which is conductive to the plugging of deep oil layers. When the permeability was 5061 × 10 −3 μm 2 , the plugging rate was 72.73%.
Keywords: Infolettre; Infolettre_Ete_2024

Use of Mixed Methods in the Science of Hydrological Extremes: What Are Their Contributions? - Kabo, Raymond; Bourgault, Marc-André; Barrette, Nathalie; Tanguay, Louis (Hydrology, 2023)
Research in hydrological sciences is constantly evolving to provide adequate answers to address various water-related issues. Methodological approaches inspired by mathematical and physical sciences have shaped hydrological sciences from its inceptions to the present day. Nowadays, as a better understanding of the social consequences of extreme meteorological events and of the population’s ability to adapt to these becomes increasingly necessary, hydrological sciences have begun to integrate knowledge from social sciences. Such knowledge allows for the study of complex social-ecological realities surrounding hydrological phenomena, such as citizens’ perception of water resources, as well as individual and collective behaviors related to water management. Using a mixed methods approach to combine quantitative and qualitative approaches has thus become necessary to understand the complexity of hydrological phenomena and propose adequate solutions for their management. In this paper, we detail how mixed methods can be used to research flood hydrology and low-flow conditions, as well as in the management of these hydrological extremes, through the analysis of case studies. We frame our analysis within the three paradigms (positivism, post-positivism, and constructivism) and four research designs (triangulation, complementary, explanatory, and exploratory) that guide research in hydrology. We show that mixed methods can notably contribute to the densification of data on extreme flood events to help reduce forecasting uncertainties, to the production of knowledge on low-flow hydrological states that are insufficiently documented, and to improving participatory decision making in water management and in handling extreme hydrological events.
Keywords: Infolettre; Infolettre_Ete_2023

Interpolation of Precipitation Extremes on a Large Domain Toward IDF Curve Construction at Unmonitored Locations - Jalbert, Jonathan; Genest, Christian; Perreault, Luc (Journal of Agricultural, Biological and Environmental Statistics, 2022)
Abstract An intensity–duration–frequency (IDF) curve describes the relationship between rainfall intensity and duration for a given return period and location. Such curves are obtained through frequency analysis of rainfall data and commonly used in infrastructure design, flood protection, water management, and urban drainage systems. However, they are typically available only in sparse locations. Data for other sites must be interpolated as the need arises. This paper describes how extreme precipitation of several durations can be interpolated to compute IDF curves on a large, sparse domain. In the absence of local data, a reconstruction of the historical meteorology is used as a covariate for interpolating extreme precipitation characteristics. This covariate is included in a hierarchical Bayesian spatial model for extreme precipitations. This model is especially well suited for a covariate gridded structure, thereby enabling fast and precise computations. As an illustration, the methodology is used to construct IDF curves over Eastern Canada. An extensive cross-validation study shows that at locations where data are available, the proposed method generally improves on the current practice of Environment and Climate Change Canada which relies on a moment-based fit of the Gumbel extreme-value distribution.
Keywords: Infolettre; Infolettre_Avril_2022; Site_internet_RIISQ

Entre héritage réglementaire et imaginaire du risque: gestion des zones inondables et pratiques d'adaptation au Québec et à Lachute - Gaudette, Marilyne; Germain, Daniel (Zenodo, 2025)
Floods, intensified by climate change, pose major challenges for flood zone management in Quebec. This report addresses these issues through two complementary aspects: a historical analysis of the evolution of flood zone management in Quebec and the projected impact of the cartographic and regulatory overhaul, as well as an exploration of the imaginary surrounding the flood-prone territory of the city of Lachute, which has faced recurrent floods for decades and yet continues to be inhabited. The historical analysis reveals that the major floods of 1974, 1976, 2017, and 2019 marked significant turning points in Quebec’s risk management, particularly by highlighting gaps in the regulatory framework and flood zone mapping. The adoption of the Act Respecting Land Use Planning and Development (LAU) in 1979 and the Policy for the Protection of Shorelines, Littorals, and Floodplains (PPRLPI) in 1987 represented a shift toward a preventive approach. However, inconsistencies, insufficient updates to maps, and uneven enforcement of standards have hindered their effectiveness. The catastrophic floods of 2017 and 2019 triggered a regulatory overhaul, a modernization of mapping, and measures to strengthen community resilience. In 2022, a transitional regime came into effect to tighten the regulation of activities in flood zones, pending the adoption of a risk-based management framework. However, to this day, the regulatory perimeters proposed in the modernization project fail to account for the adaptive capacities deployed by communities to live with water, thus providing a biased interpretation of flood risk. The second part explores the social and cultural representations associated with Lachute’s flood-prone territory. It highlights the complex relationships that have developed between residents and the Rivière du Nord through successive flooding episodes and the adaptation strategies implemented to cope, particularly by those who have repeatedly experienced flooding. These residents have come to live with overflow events and to (co)exist with water, challenging the persistent notion that flood-prone areas are inherently dangerous. While local strategies are sometimes innovative, they remain constrained by a regulatory framework that disregards the human experience of the territory and the specific ways in which people inhabit exposed areas to learn to manage flood risks. In summary, this report underscores the urgency of a territorialized, risk-based approach to modernizing flood zone management. It also highlights the need to look beyond cartographic boundaries and better integrate human and cultural dimensions into planning policies, as illustrated in the case of Lachute, to more accurately reflect the true level of risk. These reflections aim to promote more coherent, sustainable, and acceptable management, planning, and development of exposed territories in response to the growing challenges posed by climate change.
Keywords: Infolettre; Infolettre_Mai_2025

Projected Changes in Extreme Precipitation Patterns across Algerian Sub-Regions - Hamitouche, Yasmine; Zeroual, Ayoub; Meddi, Mohamed; Assani, Ali A.; Alkama, Ramdane; Şen, Zekâi; Zhang, Xinhua (Water, 2024)
Extreme precipitation events play a crucial role in shaping the vulnerability of regions like Algeria to the impacts of climate change. To delve deeper into this critical aspect, this study investigates the changing patterns of extreme precipitation across five sub-regions of Algeria using data from 33 model simulations provided by the NASA Earth Exchange Global Daily Downscaled Climate Projections (NEX-GDDP-CMIP6). Our analysis reveals a projected decline in annual precipitation for four of these regions, contrasting with an expected increase in desert areas where annual precipitation levels remain low, typically not exceeding 120 mm. Furthermore, key precipitation indices such as maximum 1-day precipitation (Rx1day) and extremely wet-day precipitation (R99p) consistently show upward trends across all zones, under both SSP245 and SSP585 scenarios. However, the number of heavy precipitation days (R20mm) demonstrates varied trends among zones, exhibiting stable fluctuations. These findings provide valuable foresight into future precipitation patterns, offering essential insights for policymakers and stakeholders. By anticipating these changes, adaptive strategies can be devised to mitigate potential climate change impacts on crucial sectors such as agriculture, flooding, water resources, and drought.
Keywords: Infolettre; Infolettre_Ete_2024; Site_internet_RIISQ

Benefit of assimilating satellite all-sky infrared radiances on the cloud and precipitation prediction of a long-lasting mesoscale convective system over the Tibetan plateau - He, Jie; Ma, Xulin; Chen, Xingchao (Quarterly Journal of the Royal Meteorological Society, 2023)
Heavy rainfall events in the warm season (May–September) over the Tibetan Plateau (TP) region and its downstream areas are often closely related to eastward-propagating Tibetan Plateau Vortices (TPVs). Hence, improving the prediction of TPVs and their associated convective activity is of paramount importance, given the significant potential impacts they can have on densely populated downstream regions, including but not limited to flooding and damages. In this study, a typical long-lived TPV that occurred in July 2008 was used for the first time to explore the benefit of assimilating satellite all-sky infrared radiances on the cloud and precipitation prediction of the TPV-induced eastward-propagating mesoscale convective system (MCS). The all-sky infrared radiances from the water vapor (WV) channel of the geostationary Meteosat-7 and other conventional observations were assimilated into a 4-km grid spacing regional model using the ensemble Kalman filter. The results revealed that the all-sky infrared data assimilation improved the cloud, precipitation, dynamical, and thermodynamical analyses as well as 0–12-hr deterministic and ensemble forecasts. Compared with the experiment in which the all-sky infrared radiances were not assimilated (non-radiance experiment), the experiment with assimilated all-sky infrared radiances yielded clearly improved initial wind and cloud fields, 1–12-hr cloud forecasts, and 1–6-hr precipitation forecasts. This study indicates that assimilation of all-sky satellite radiances has the potential for improving the operational cloud and precipitation forecasts over the TP and its downstream areas.
Keywords: Infolettre; Infolettre_Septembre_2023

Do civil engineering fronts emerge from interdisciplinary research? - He, Jie; Yao, Junlan; Chen, Xin; Liu, Fang; Zhu, Hehua (Frontiers of Structural and Civil Engineering, 2023)
Abstract Interdisciplinary research is considered a source of innovativeness and creativity, serving as a key mechanism for creating recombination necessary for the evolution of science systems. The aim of this study is to quantitatively establish the connection between interdisciplinary research and the research fronts that have recently emerged in civil engineering. The degree of interdisciplinarity of the research fronts was measured by developing metrics from bibliographic analyses. As indicated by the consistent increase in the metrics of interdisciplinarity over time, research fronts tend to emerge in studies with increasing diversity in the disciplines involved. The active disciplines involved in the fronts vary over time. The most active disciplines are no longer fundamental but those associated with energy, environment, and sustainable development, focusing on solutions to climate change and integrating intelligence technologies.
Keywords: Infolettre; Infolettre_Fevrier_2023

Evaluation of Concrete Constitutive Models for Finite Element Simulation of Dam Shear Keys - Freitas, Mario; Ben Ftima, Mahdi; Léger, Pierre; Bouaanani, Najib (Proceedings of the Canadian Society of Civil Engineering Annual Conference 2022, 2023)
Keywords: Infolettre; Infolettre_Septembre_2024

Updating the intensity-duration-frequency curves in major Canadian cities under changing climate using CMIP5 and CMIP6 model projections - Crévolin, Vincent; Hassanzadeh, Elmira; Bourdeau-Goulet, Sarah-Claude (Sustainable Cities and Society, 2023)
Keywords: Bourdeau-Brien_Michael; Infolettre; Infolettre_Avril_2023

Using depth specific electrical conductivity estimates to improve hydrological simulations in a heterogeneous tile-drained field - Boico, Vinicius F.; Therrien, René; Højberg, Anker L.; Iversen, Bo V.; Koganti, Triven; Varvaris, Ioannis (Journal of Hydrology, 2022)
In agricultural fields, tile drains represent potential pathways for the migration of solutes, such as nitrates, in groundwater and surface water bodies. Tile drain flow is controlled by the temporal and spatial dynamics of the shallow groundwater table, which results from complex interactions between climate, topography and soil heterogeneity. Studies on the effect of topsoil heterogeneity on shallow water and drainage dynamics by fully 3D surface water and groundwater flow modeling are limited. The objective of our study is to demonstrate the use of depth specific electrical conductivity (EC) estimates to improve hydrological simulations in a tile-drained field. The model was applied to a field site in Denmark where times series of drainage discharge and water table elevations are available. Clay-rich soil zones were identified in a tile-drained field using depth specific electrical conductivity estimates generated by the inversion of apparent electrical conductivity data measured using an electromagnetic induction instrument. One model that included the low-permeability clayey zones in the soil layers down to a depth of 1.2 m was compared to a simpler model that assumed homogeneous soil layers. Both models simulate drainage discharge that compares well to the observations. However, including the clayey zones improves the simulation of hydraulic heads, and water table fluctuations, and generates flooded areas that are more representative of those observed during the wet seasons. Our results suggest that the simulation of water table fluctuations can be improved when the soil heterogeneity determined from depth specific EC estimates is included in integrated hydrological models. A better representation of the subsurface flow dynamics will also improve subsequent simulations of the transport and fate of agrochemical substances leaching from fields such as nitrate, which may deteriorate the quality of groundwater and surface water bodies.
Keywords: Infolettre; Infolettre_Avril_2022

Stream habitat provided by large wood at risk under drainage law - Shirey, Patrick D.; Kenny, Jillian B.; Brueseke, Michael A.; Lamberti, Gary A. (Earth Surface Processes and Landforms, 2020)
Watershed management efforts in agriculturally dominated landscapes of North America face nearly two centuries of laws and policies that encouraged habitat destruction. Although streams and wetlands in these landscapes are actively being restored using designs that incorporate science and engineering, watershed drainage laws can constrain action or impact passively restored or naturalized habitat. In general, drainage laws require removal of any riparian vegetation or wood deemed to obstruct flow in streams regulated as drains. We use a case study from Indiana (USA) to introduce the shortcomings of drainage laws for allowing large wood, which is an important habitat feature, to remain in stream ecosystems. Removals of large wood from monitored stream reaches in a regulated drain were associated with subsequent declines in fish biomass. Such legal activities represent an important environmental management problem that exists under drainage laws which apply to streams over a widespread geographic region of North America. Recent litigation in Wisconsin (USA) suggests that if state legislatures fail to update these antiquated laws, the courts may act in favour of science-based management of drains. The statutes and regulations that govern agricultural drainage warrant careful consideration if streams within drainage districts are to be managed to improve ecological function. © 2020 John Wiley & Sons, Ltd.
Keywords: Ouvrage_Collectif_Numéro1

The ERA5 global reanalysis - Hersbach, Hans; Bell, Bill; Berrisford, Paul; Hirahara, Shoji; Horányi, András; Muñoz‐Sabater, Joaquín; Nicolas, Julien; Peubey, Carole; Radu, Raluca; Schepers, Dinand; Simmons, Adrian; Soci, Cornel; et al. (Quarterly Journal of the Royal Meteorological Society, 2020)
Abstract Within the Copernicus Climate Change Service (C3S), ECMWF is producing the ERA5 reanalysis which, once completed, will embody a detailed record of the global atmosphere, land surface and ocean waves from 1950 onwards. This new reanalysis replaces the ERA‐Interim reanalysis (spanning 1979 onwards) which was started in 2006. ERA5 is based on the Integrated Forecasting System (IFS) Cy41r2 which was operational in 2016. ERA5 thus benefits from a decade of developments in model physics, core dynamics and data assimilation. In addition to a significantly enhanced horizontal resolution of 31 km, compared to 80 km for ERA‐Interim, ERA5 has hourly output throughout, and an uncertainty estimate from an ensemble (3‐hourly at half the horizontal resolution). This paper describes the general set‐up of ERA5, as well as a basic evaluation of characteristics and performance, with a focus on the dataset from 1979 onwards which is currently publicly available. Re‐forecasts from ERA5 analyses show a gain of up to one day in skill with respect to ERA‐Interim. Comparison with radiosonde and PILOT data prior to assimilation shows an improved fit for temperature, wind and humidity in the troposphere, but not the stratosphere. A comparison with independent buoy data shows a much improved fit for ocean wave height. The uncertainty estimate reflects the evolution of the observing systems used in ERA5. The enhanced temporal and spatial resolution allows for a detailed evolution of weather systems. For precipitation, global‐mean correlation with monthly‐mean GPCP data is increased from 67% to 77%. In general, low‐frequency variability is found to be well represented and from 10 hPa downwards general patterns of anomalies in temperature match those from the ERA‐Interim, MERRA‐2 and JRA‐55 reanalyses.
Keywords: Ouvrage_Collectif_Numéro1

The Importance of Climate Risks for Institutional Investors - Krueger, Philipp; Sautner, Zacharias; Starks, Laura T. (Review of Financial Studies, 2020)
According to our survey about climate risk perceptions, institutional investors believe climate risks have financial implications for their portfolio firms and that these risks, particularly regulatory risks, already have begun to materialize. Many of the investors, especially the long-term, larger, and ESG-oriented ones, consider risk management and engagement, rather than divestment, to be the better approach for addressing climate risks. Although surveyed investors believe that some equity valuations do not fully reflect climate risks, their perceived overvaluations are not large.
Keywords: Ouvrage_Collectif_Numéro1

Privatizing climate adaptation: How insurance weakens solidaristic and collective disaster recovery - Lucas, Chloe H.; Booth, Kate I. (WIREs Climate Change, 2020)
Abstract As losses from extreme weather events grow, many governments are looking to privatize the financing and incentivization of climate adaptation through insurance markets. In a pure market approach to insurance for extreme weather events, individuals become responsible for ensuring they are adequately covered for risks to their own properties, and governments no longer contribute funds to post‐disaster recovery. Theoretically, insurance premiums signal the level of risk faced by each household, and incentivize homeowners to invest in adaptive action, such as retrofitting, or drainage work, to reduce premiums. Where risk is considered too high by insurance markets, housing is devalued, in theory leading to retreat from risky areas. In this review article, we evaluate the suitability of private insurance as a mechanism for climate adaptation at a household and community level. We find a mismatch between social understandings of responsibility for climate risks, and the technocratic, market‐based home insurance products offered by private insurance markets. We suggest that by constructing increasingly individualized, technical, and calculative evaluations of risk, market‐based models of insurance for extreme weather events erode the solidaristic and collective discourses and practices that support adaptive behavior. This article is categorized under: Vulnerability and Adaptation to Climate Change > Institutions for Adaptation
Keywords: Ouvrage_Collectif_Numéro1

Besoins psychosociaux d'hommes touchés par la démolition de leur domicile après les inondations majeures de 2019 en Chaudière-Appalaches - Turmel, Joanie (Université du Québec à Rimouski, 2025)
RÉSUMÉ : Les relocalisations de populations et les démolitions de bâtiments sont des moyens pour réduire les risques associés aux inondations, dont ceux pour la santé humaine. Au Québec, l’usage de ces mesures pourrait s’accroître avec les changements climatiques. En Chaudière-Appalaches, au moins 404 bâtiments ont été démolis à Sainte-Marie et 88 à Scott après les inondations de 2019. L’expérience de démolition de domiciles post-inondation est toutefois peu documentée au Québec et encore moins selon le point de vue des personnes touchées, particulièrement chez les hommes. Ce mémoire présente les résultats d’une étude ayant documenté cette expérience auprès de treize hommes propriétaires d’un domicile dans la MRC Nouvelle-Beauce à partir d'entretiens semi-dirigés (méthode photo-élicitation) et d’un groupe de discussion. Cette étude repose sur l’expérience clinique de l’étudiante-chercheuse qui a constaté la présence de détresse chez la population masculine touchée par ce phénomène et sur la littérature scientifique qui démontre une plus faible propension à l’usage de services psychosociaux et de santé chez les hommes. À partir d’une analyse thématique inspirée du cadre théorique « Psychological Processes That Influence Adaptation to and Coping With Climate Change » de Reser et Swim et d’une perspective écosystémique, quatre nouvelles phases ont été dégagées soient : l’inondation, les démarches administratives, la démolition et la relocalisation. Chacune est caractérisée par des besoins et des impacts psychosociaux systémiques, l’usage de stratégies adaptatives spécifiques et des moments critiques pour la santé et le bien-être des hommes. Les résultats suggèrent que des impacts et besoins individuels et collectifs peuvent se cumuler et se prolonger dans le temps comme des manifestations anxio-dépressives ou traumatiques, de la détresse, une désaffiliation sociale ainsi qu’une modification de projets de vie. Une réduction de l’exposition aux inondations et une augmentation du bien-être et de la sécurité ressortent également. La proactivité, les pensées axées sur l’autonomie et le recours au soutien informel sont apparues comme des stratégies aidantes comparativement au repli sur soi et au surinvestissement dans le travail. Les résultats permettent d’exposer des pistes de réflexion et d’action favorisant le bien-être des hommes et d’autres pertinentes pour le travail social. Parmi celles-ci se trouvent d’encourager les hommes touchés par la démolition de leur domicile post-inondation à s’investir dans leur nouveau milieu de vie pour favoriser son appropriation et sa personnalisation ainsi que des recommandations pour le travail social de prendre en compte le genre dans la compréhension des problèmes socioenvironnementaux. -- Mot(s) clé(s) en français : Inondation, chez-soi, hommes, changements climatiques, travail social, désastre, besoins psychosociaux, adaptation, mesures d’atténuation du risque, événements météorologiques extrêmes. -- ABSTRACT : Population relocation and building demolition are ways of reducing the risks associated with flooding, including those to human health. In Quebec, the use of these measures could increase with climate change. In Chaudière-Appalaches, at least 404 buildings were demolished in Sainte-Marie and 88 in Scott after the 2019 floods. However, the experience of post-flood home demolition is poorly documented in Quebec, and even less so from the perspective of those affected, specifically men. This memoir presents the results of a study that documented this experience with thirteen male homeowners in the Nouvelle-Beauce MRC using semi-directed interviews (photo-elicitation method) and a focus group. This study is based on the student-researcher's clinical experience of distress among the male population affected by this phenomenon, and on scientific literature demonstrating a lower propensity to use psychosocial and health services among men. Based on a thematic analysis inspired by the Reser and Swim’s theoretical framework, the Psychological Processes That Influence Adaptation to and Coping With Climate Change, and an ecosystem perspective, four new phases were identified: flooding, administrative procedures, demolition and relocation. Each is characterized by systemic psychosocial needs and impacts, the use of specific adaptive strategies and critical moments for men's health and well-being. The results suggest that individual and collective needs and impacts can accumulate and extend over time, such as anxio-depressive or traumatic manifestations, distress, social disaffiliation and changes in life plans. A reduction in exposure to flooding and an increase in well-being and safety also stand out. Proactivity, autonomy-oriented thinking and reliance on informal support emerged as helpful strategies compared to withdrawal and over-investment in work. The results provide food for thought and action to promote men's well-being, and others relevant to social work. These include encouraging men affected by the demolition of their post-flood home to get involved in their new living environment to promote its appropriation and personalization and taking gender into account in understanding socioenvironmental problems. -- Mot(s) clé(s) en anglais : Flooding, home, men, climate change, social work, disaster, psychosocial needs, adaptation, risk mitigation measures, extreme weather events.

Une première centrale hydroélectrique au fil de l'eau au Nunavik : impacts à court terme sur les cycles du mercure et du carbone - St-Aubin, Mariane (2024)
Une première centrale au fil de l'eau (FDE) au Nunavik (QC, Canada), construite en zone de pergélisol continu, alimente la communauté d'Inukjuak en énergie renouvelable depuis 2024. De petite taille, ces constructions ont été peu étudiées par le passé, notamment en lien avec la modification du cycle du mercure (Hg) et à la bioaccumulation de méthylmercure (MeHg) dans les réseaux alimentaires adjacents. Le pergélisol est cependant un potentiel réservoir substantiel de Hg, et la mise en eau pourrait favoriser son dégel, remobilisant ainsi du Hg historique, co-transporté par du carbone (C) ancien. Afin de mieux cerner les impacts d’une inondation en contexte septentrional, des sols, de l’eau de surface et des invertébrés benthiques ont été échantillonnés le long de la rivière Innuksuac avant, pendant et trois mois suivants la mise en eau. Afin d’investiguer le Hg dans la colonne d’eau, la qualité du carbone organique dissous (COD) (i.e. âge et composition) a été étudiée, tandis que le transfert trophique du MeHg au sein du réseau alimentaire a été clarifié à l’aide de l’isotopie stable (ẟ13C et ẟ15N), reflétant la diète et le niveau trophique des organismes. Le ratio Hg : C suggère que les concentrations de Hg dans le sol de la zone d’étude étaient moindres que ce qui était attendu, en se basant de précédentes estimations circompolaires, tandis que la majorité du Hg mesuré se trouvait dans la couche active du pergélisol et n’était donc pas immobilisé par le gel. Néanmoins, la mise en eau a généré une hausse de la concentration de MeHg (~ 7x) et du potentiel de méthylation (~ 4x) dans la couche organique superficielle des sols ennoyés. Cette hausse d’activité s’est reflétée dans les eaux de surface de la baie inondée, qui présentait des concentrations de MeHg dix fois plus élevées que dans les autres sites échantillonnés. Tandis que le COD exogène dérivant du milieu terrestre semble important pour l’apport de Hg inorganique dans le système riverain, le COD récemment dégradé par l’activité microbienne s’est avéré être le meilleur indicateur du potentiel de la méthylation. Une augmentation de la concentration tissulaire de MeHg a finalement été observée au bas de la chaîne trophique, chez les consommateurs primaires (~ 4x) ainsi que chez les invertébrés benthiques arborant une diète omnivore (~ 3x), mais pas chez les organismes prédateurs, suggérant l’existence d’un délai de transfert trophique. Chez les consommateurs primaires, cette augmentation était surtout apparente chez les invertébrés intimement associés à l’environnement benthique de la nouvelle baie inondée, où les signatures de ẟ13C étaient également les plus faibles. Ces résultats offrent un premier portrait à court terme du transport et des transformations du Hg lors d’une inondation en région subarctique, et les hausses enregistrées, bien que non négligeables, se limitent pour l’instant à une faible superficie (< 1 km2) et ne semblent pas se répercuter en aval de la petite baie inondée.

Occurrence and transport of pollutants from spilled oil and microplastics in the coastal areas - Wang, Zheng (Concordia University, 2023)
The coast is a complex environment that comprises seawater, underwater, soil, atmosphere, and other environmental factors. Traditional and new pollutants, represented by oil spills and microplastic (MPs), persist in posing a constant threat to the ecosystems and social-economic features of coastal regions. Besides, the shoreline is exposed to various environment conditions, which may significantly affect the behaviors of pollutants on beaches. An in-depth understanding of the occurrence and fate of pollutants in coastal areas is a prerequisite for the development of sound prevention and remediation strategies. Firstly, the physicochemical behavior of crude oil on various types of shorelines under different environmental conditions were reviewed. The penetration, remobilization, and retention of stranded oil on shorelines are affected by the beach topography and the natural environment. The attenuation and fate of oil on shorelines from laboratory and field experiments were discussed. In addition, the source, type, distribution, and factors of MPs in the coastal areas were summarized. What is more, the occurrence and environmental risk of emerging plastics waste—personal protective equipment (PPE)—in the coastal environment during and pandemic were discussed. Then, the role of natural nanobubbles (NBs) in the fate and transport of spilled oil were investigated through laboratory experiments and model simulations. NBs significantly increased the concentration of dissolved oxygen as well as changed the pH, zeta potential, and surface tension of the water. With the assistance of external energy, the bulk NBs enhanced the efficiency in oil detachment from the surface of the substrate. At the same time, the surface NBs on the substrate obstructed the downward transport of oil colloids. Considering the behavior between the NBs in two different phases and the oil droplets, the oil droplets tended to bind to the NBs. Next, the behavior and movement of various MPs in the presence of bulk NBs was explored. In the presence of NBs, the binding of MPs and NBs resulted in an increase in the measured average particle size and concentration. The velocity of motion of MPs driven by NBs varies under different salinity conditions. The increase in ionic strength reduced the energy barrier between particles and promoted their aggregation. Thus, the binding of NBs and MPs became more stable, which in turn affected the movement of MPs in the water. Polyethylene (PE1) with small particle size was mainly affected by Brownian motion and its rising was limited, therefore polyethylene (PE2) with large particle size rose faster than PE1 in suspension, especially in the presence of NBs. The effect of nanobubbles on the mobilization of MPs in shorelines subject to seawater infiltration was further studied. The motion of MPs under continuous and transient conditions, as well as the upward transport induced with flood were considered. Salinity altered the energy barriers between particles, which in turn affected the movement of MPs within the matrix. In addition, hydrophilic MPs were more likely to infiltrate within the substrate and had different movement patterns under both continuous and transient conditions. The motion of the MPs within the substrate varied with flow rate, and NBs limited the vertical movement of MPs in the tidal zone. It was also observed that NBs adsorbed readily onto substrates, altering the surface properties of substrates, particularly their ability to attach and detach from other substances. Finally, the changing characteristics and environmental behaviors of PPE wastes when exposed to the shoreline environment were examined. The transformation of chain structure and chemical composition of masks and gloves as well as the decreased mechanical strength after UV weathering were observed. In addition, the physical abrasion caused by sand further exacerbated the release of MPs and leachable hazardous contaminates from masks and gloves. In conclusion, the coastal zone is threatened by various pollutants, including traditional pollutants (like the oil spill) and emerging pollutants (like MPs). Due to the complexity of the coastal zone, the occurrence, transport and fate of pollutants can be controlled by many factors, and some factors that are ignored before can also alter the environmental behavior of pollutants in the coastal zone. Natural NBs can change the properties of the water environment and affect the surface properties of the substrate. Bulk NBs contribute to the oil detachment from the sand surface, and surface nanobubbles in the substrate obstruct the downward transport of oil colloids. The behavior and mobilization of MPs in the coastal `zone are subject to mutual forces between the substrate, MPs, NBs, and other factors. Coastal zones are not only the main receptor of pollutants from oceans and lands but also play a key role in their fate and transport.

Design and Implementation of Machine Learning Models and Algorithms for Flood, Drought and Frazil Prediction - Yagnik, Bhargav Charudatt (Concordia University, 2023)
Natural calamities like floods and droughts pose a significant threat to humanity, impacting millions of people each year and incurring substantial economic losses to society. In response to this challenge, this thesis focuses on developing advanced machine learning techniques to improve water height prediction accuracy that can aid municipalities in effective flood mitigation. The primary objective of this study is to evaluate an innovative architecture that leverages Long Short Term Networks - neural networks to predict water height accurately in three different environmental scenarios, i.e., frazil, droughts and floods due to snow spring melt. A distinguishing feature of our approach is the incorporation of meteorological forecast as an input parameter into the prediction model. By modeling the intricate relationships between water level data, historical meteorological data and meteorological forecasts, we seek to evaluate the impact of meteorological forecasts and if any inaccuracies could impact water-level prediction. We compare the outcomes obtained by incorporating next-hour, next-day and next-week meteorological data into our novel LSTM model. Our results indicate a comprehensive comparison of the usage of various parameters as input and our findings suggest that accurate weather forecasts are crucial in achieving reliable water height predictions. Additionally, this study focuses on the utilization of IoT sensor data in combination with ML models to enhance the effectiveness of flood prediction and management. We present an online machine learning approach that performs online training of the model using real-time data from IoT sensors. The integration of live sensor data provides a dynamic and adaptive system that demonstrates superior predictive capabilities compared to traditional static models. By adopting these advanced techniques, we can mitigate the adverse impacts of natural catastrophes and work towards building more resilient and disaster-resistant communities.

Estimation du débit en rivière à l’aide de l’imagerie RADARSAT en utilisant l’apprentissage profond. - Ziadi, Samar (Maîtrise en sciences de l'eau, 2023)
L’estimation du débit en rivières est un paramètre clé pour la gestion des ressources hydriques, la prévention des risques liés aux inondations et la planification des équipements hydroélectriques. Lorsque le débit d’eau est très élevé lors d'évènements extrêmes, les méthodes de jaugeage traditionnelles ne peuvent pas être utilisées. De plus, les stations du réseau hydrométrique sont généralement éparses et leur répartition spatiale n’est pas optimale. Par conséquent, de nombreuses sections de rivières ne peuvent être suivies par des mesures et observations du débit. Pour ces raisons, pendant la dernière décennie, les capteurs satellitaires ont été considérés comme une source d’observation complémentaire aux observations traditionnelles du niveau d’eau et du débit en rivières. L’utilisation d’une telle approche a fourni un moyen de maintenir et d’étendre le réseau d'observation hydrométrique. L’approche avec télédétection permet d’estimer le débit à partir des courbes de tarage qui met en relation le débit instantané (Q) et la géométrie d’une section transversale du chenal (la largeur ou la profondeur effective de la surface d’eau). En revanche, cette méthode est associée à des limitations, notamment, sa dépendance aux courbes de tarage. En effet, en raison de leurs natures empiriques, les courbes de tarage sont limitées à des sections spécifiques et ne peuvent être appliquées dans d’autres rivières. Récemment, des techniques d’apprentissage profond ont été appliquées avec succès dans de nombreux domaines, y compris en hydrologie. Dans le présent travail, l’approche d’apprentissage profond a été choisie, en particulier les réseaux de neurones convolutifs (CNN), pour estimer le débit en rivière. L’objectif principal de ce travail est de développer une approche d’estimation du débit en rivières à partir de l’imagerie RADARSAT 1&2 à l’aide de l’apprentissage profond. La zone d’étude se trouve dans l’ecozone du bouclier boréal à l’Est du Canada. Au total, 39 sites hydrographiques ont fait l’objet de cette étude. Dans le présent travail, une nouvelle architecture de CNN a été a été proposée, elle s'adapte aux données utilisées et permet d’estimer le débit en rivière instantané. Ce modèle donne un résultat du coefficient de détermination (R²) et de Nash-Sutcliffe égale à 0.91, le résultat d’erreur quadratique moyenne égale à 33 m³ /s. Cela démontre que le modèle CNN donne une solution appropriée aux problèmes d’estimation du débit avec des capteurs satellites sans intervention humaine. Estimating river flow is a key parameter for effective water resources management, flood risk prevention and hydroelectric facilities planning. In cases of very high flow of water or extreme events, traditional gauging methods cannot be reliable. In addition, hydrometric network stations are often sparse and their spatial distribution is not optimal. Therefore, many river sections cannot be monitored using traditional flow measurements and observations. For these reasons, satellite sensors are considered as a complementary observation source to traditional water level and flow observations in the last decades. The use of this kind of approach has provided a way to maintain and expand the hydrometric observation network. Remote sensing data can be used to estimate flow from rating curves that relate the instantaneous flow (Q) to the geometry of a channel cross-section (the effective width or depth of the water surface). On the other hand, remote sensing is also associated with limitations, notably its dependence on the rating curves. Indeed, due to their empirical nature, rating curves are limited to specific sections and cannot be applied in other rivers. Recently, deep learning techniques have been successfully applied in many fields, including hydrology. In the present work, the deep learning approach has been chosen, in particular convolutional neural networks (CNN), to estimate river flow. The main objective of this work is to develop an approach to estimate river flow from RADARSAT 1&2 imagery using deep learning. In this study, 39 hydrographic sites of the Boreal Shield ecozone in Eastern Canada were considered. A new CNN architecture was developed to provide a straightforward estimation of the instantaneous river flow rate. The achieved results demonstrated a coefficient of determination (R²) and Nash-Sutcliffe values of 0.91, and a root mean square error of 33m³ /s. This indicates the effectiveness of CNN in automatic flow estimation with satellite sensors.

Récits de fin du monde : la littérature comme arche - Thuot, Marie-Ève (2021)
Cette thèse s’inscrit dans le champ des études sur les fictions de la fin du monde. J’y explore la question suivante : pourquoi existe-t-il autant de romans et de films racontant la fin d’un monde, et si peu la fin du monde ? En effet, la plupart des fictions dites de « fin du monde » mettent en scène la menace d’une catastrophe évitée, ou une destruction partielle, ou encore un univers post-apocalyptique habité de survivants. L’anéantissement total et définitif de l’espèce humaine, quant à lui, constitue rarement le dénouement de ce type d’œuvres. Ce déséquilibre s’explique en partie par le fait que ces œuvres représentent davantage le renouvellement du monde que sa disparition. Mon hypothèse est que nombre de ces récits de la fin héritent d’un imaginaire, d’une structure, de thèmes, de motifs, etc., provenant du mythe du déluge tel qu’il s’est développé dans l’Antiquité (entre autres dans sa version biblique), lequel symbolise la refondation et la transmission, et non l’anéantissement. Dans le premier chapitre, je propose une exploration de différents concepts et théories permettant de mieux définir les romans et les films de la fin du monde : les dispositif et contre-dispositif de Giorgio Agamben ; la conception des mythes de René Girard (principalement pour les notions d’indifférenciation et de bouc émissaire) ; le décalage prométhéen de Gunther Anders ; le catastrophisme éclairé de Jean-Pierre Dupuy ; les deux raisonnements mythologiques opposés identifiés dans les récits antiques de la fin du monde par Christine Reungoat-Dumas. Dans le deuxième chapitre, j’étudie d’abord comment le thème de la transmission s’articule dans quelques mythes antiques du déluge, avant de proposer un canevas général des mythèmes constituants. À partir de cette délimitation, je procède ensuite à l’analyse de trois mythèmes (la crise indifférenciatrice ; l’abri ; le lâcher d’oiseaux) dans un corpus de romans et de films des 20e et 21e siècles. Cette analyse permet de faire ressortir l’importance du thème de la transmission (de gènes et de mèmes, donc de réplicateurs). La transmission reflète un besoin de transcendance qui définit, oriente, ou du moins colore, pratiquement toutes les œuvres de la fin du monde. Dans ce contexte, la littérature, objet de transmission, peut être appréhendée comme une « arche métaphorique ». Le troisième chapitre se concentre sur l’analyse d’une œuvre, la trilogie MaddAddam (Oryx and Crake ; The Year of the Flood ; MaddAddam) de Margaret Atwood. J’y avance que cette œuvre prend la forme d’une épopée, dans laquelle on assiste à la mise en scène de sa propre écriture. Cette mise en abyme démontre bien que la trilogie, tout en étant une œuvre de fin du monde, raconte également la naissance d’un nouveau monde : l’épopée intradiégétique qui s’y compose tente d’immortaliser une partie du passé et d’orienter le futur. La littérature, sous la forme de cette épopée, figure ainsi une arche qui relie les mondes pré-apocalyptique et post-apocalytique de l’œuvre d’Atwood.

Modélisation hydrologique CLASS-RAPID sous changement climatique sur le bassin versant du Haut-Montmorency - Talbot-Lanciault, Alicia (2020)
Les modèles hydrologiques traditionnels n’imposent pas la contrainte de conservation d’énergie à la surface. Lorsque soumis à des températures plus élevées, ils ont le potentiel de surestimer l’évapotranspiration. Le modèle de surface physique CLASS est couplé au modèle de routage RAPID, basé sur la méthode de Muskingum, pour former un modèle hydrologique plus robuste en contexte de réchauffement global. CLASS-RAPID est implanté sur le bassin versant du Haut-Montmorency (47.4°N, 71.1°O). CLASS est calibré et validé à l’aide d’observations hydrométéorologiques à la Forêt Montmorency ; RAPID est optimisé d’après les observations de débits de la Direction d’expertise hydrique du Québec. Des projections climatiques provenant des modèles CanESM2, CNRM-CM5, GFDL-ESM2M et MPI-ESM du Projet d’intercomparaison des modèles couplés et des scénarios climatiques RCP 4.5 et RCP 8.5 sont fournies en entrées à CLASS-RAPID afin de réaliser des simulations hydrologiques pour la période future de 2041 à 2070. Des projections climatiques provenant des mêmes modèles pour la période de référence de 1981 à 2005 sont également utilisées par CLASS-RAPID afin de générer une séquence de débits pouvant être comparée à celle de la période future. CLASS-RAPID obtient un score de NSE = 0, 66 au critère de performance de Nash-Sutcliffe. Le modèle reproduit fidèlement la séquence des évènements hydrologiques, mais sous-estime systématiquement les pointes de crue. Les simulations de CLASS-RAPID réalisées en condition de changements climatiques projettent que les crues printanières se produisent plusieurs dizaines de jours à l’avance pour la période future de 2041 à 2070 en comparaison à la période de référence. Pour les quatre modèles à l’étude, les simulations en condition de changements climatiques permettent de prévoir une diminution moyenne des débits d’étiage d’été de 40% pour le scénario climatique RCP 4.5 et de 50% pour le scénario climatique RCP 8.5. Pour les mêmes scénarios climatiques, l’Atlas hydroclimatique du Québec, qui repose sur une modélisation hydrologique traditionnelle, prévoit une diminution des débits de respectivement 37% et 45%.

Deep learning applications to climate change mitigation - Schmidt, Victor (2024)
Les changements climatiques sont un défi mondial imminent, dont les conséquences sont déjà observées. On sait que ces effets s’intensifieront, entraînant une augmentation de la fréquence et de la gravité des événements météorologiques extrêmes, une perturbation substantielle de la production alimentaire et le déplacement de dizaines de millions de personnes en raison de vagues de chaleur mortelles et de sécheresses. La question est donc : que peut-on y faire ? Dans cette thèse, nous faisons des changements climatiques notre objet central et explorons les voies par lesquelles la recherche en apprentissage profond peut contribuer à son atténuation. Un obstacle connu à des politiques climatiques ambitieuses est le manque de soutien et de demande populaires. Cela peut être attribué, en partie, aux causes et conséquences extrêmement complexes et imbriquées des changements climatiques. Une mauvaise conception courante est qu'ils affecteront principalement d’autres personnes que soi-même, des personnes éloignées dans le temps ou l’espace. Pour y remédier, la recherche a montré que présenter aux gens des images authentiques, locales et pertinentes d'un concept les aide à mieux comprendre et appréhender ce qui est en jeu. Dans notre première contribution, nous explorons donc comment les récentes avancées en apprentissage profond pour la vision par ordinateur et les réseaux antagonistes génératifs peuvent être utilisées pour générer des images personnalisées représentant les impacts du changement climatique. Notre objectif avec ClimateGAN est de visualiser à quoi pourrait ressembler une inondation d’un mètre à n’importe quelle adresse, indépendamment de son risque réel d’inondation sous l’effet des changements climatiques. Cette approche vise à susciter l’empathie en rendant les impacts abstraits du changement climatique plus tangibles et personnalisés. En utilisant une image de Google Street View et en la traitant avec ClimateGAN, nous générons des images d’inondation physiquement plausibles et visuellement réalistes basées sur l’adaptation de domaine à partir d’un environnement simulé, la prédiction de profondeur et la segmentation sémantique. Ce modèle a été déployé sur un site web dans le but de sensibiliser et d’engager l’action en faveur des changements climatiques. En plus d’aider les gens à mieux visualiser à quoi pourrait ressembler un avenir climatique hors de contrôle, nous étudions également dans cette thèse comment l’apprentissage profond peut améliorer les technologies existantes. Un domaine majeur de recherche dans cette direction est la recherche de nouveaux matériaux. Dans cette thèse, nous explorons plus particulièrement la prédiction des propriétés des matériaux comme moyen d’accélérer la découverte d'électro-catalyseurs, une famille de matériaux impliqués dans le stockage d’énergie à base d’hydrogène. Nous présentons deux contributions, PhAST et FAENet, qui se concentrent sur l’amélioration du compromis performance/scalabilité dans les réseaux de neurones géométriques de graphe (GNN). Avec PhAST, nous introduisons un ensemble de méthodes pour adapter la procédure GNN classique--de la création du graphe d’entrée aux prédictions d’énergie et de forces de sortie--à la tâche spécifique de prédire l’énergie d’un système atomique adsorbant-catalyseur relaxé. Nous démontrons comment, en plus d’améliorer les performances, ces modifications améliorent l’efficacité et permettent un entraînement compétitif des GNN dans des environnements CPU. Dans FAENet, nous présentons un nouveau GNN efficace pour les prédictions équivariantes E(3). En particulier, nous transposons la charge de l’équivarience sur la représentation des données afin de réduire les contraintes sur le modèle lui-même. Cette approche nous permet d’introduire une nouvelle architecture légère et expressive visant à faire des prédictions meilleures et plus rapides de diverses propriétés des matériaux. Enfin, nous examinons de manière critique notre propre domaine et discutons des impacts environnementaux associés aux technologies de l’IA. Nous nous penchons sur la façon dont les praticiens peuvent estimer leurs émissions de carbone, quelles mesures ils peuvent prendre aujourd’hui pour les réduire, et quelles autres étapes sont nécessaires pour des déclarations et responsabilités environnementales plus précises.

Improving hydrological forecasting at multiple lead-times for hydropower reservoir management - Sabzipour, Behmard (École de technologie supérieure, 2023)
Streamflow forecasting is important for managing water resources in sectors like agriculture, hydropower, drought management, and urban flood prevention planning. Our study examines short and long lead-times to create a framework for streamflow forecasting that can benefit water resource management and related sectors. To improve streamflow forecasts for up to ten days of lead-time, the study first focuses on improving initial conditions using an ensemble Kalman filter as a data assimilation method. The goal is to regulate the hyperparameters of the ensemble Kalman filter for each season to produce more accurate forecasts. A sensitivity analysis is conducted to identify the best hyperparameter sets for each season, including uncertainty in temperature, precipitation, observed streamflow, and the water content of three state variables - vadose zone, saturated zone, and snowpack - from the CEQUEAU model. Results indicate that improving initial conditions with the ensemble Kalman filter produces more skillful forecasts until a 6-day leadtime. Temperature uncertainty is particularly sensitive and varies across seasons. The vadose zone state variable was identified as the most important and sensitive state variable, and updating all state variables systematically may not be necessary for improving forecast skill. Recent machine learning advances are improving short-term streamflow forecasting. One such method is the Long Short-Term Memory (LSTM) model. In general, neural networks learn from regression as relationships exist between input-output. However, LSTM models have a feature named ‘forget gate’, which enables them to learn the relationship between inputs (e.g., temperature and precipitation) and output (streamflow), and also to capture temporal dependencies in the data. The study aimed to compare the performance of the Long ShortTerm Memory (LSTM) model with data assimilation-based and process-based hydrological models in short-term streamflow forecasting. All three models were tested using the same ensemble weather forecasts. The LSTM model demonstrated good performance in forecasting streamflow, with a Kling-Gupta efficiency (KGE) greater than 0.88 for 9 lead-times. The LSTM model did not incorporate data assimilation, but it benefited from observed streamflow until the last day before the forecast. This is because the LSTM model learned and incorporated knowledge from the previous days while issuing forecasts, similar to how data assimilation updates initial conditions. The study results also showed that the LSTM model had better performance up to day 6 of lead-time compared to the data assimilation-based models. However, training the LSTM model separately for each lead-time is a time-consuming process and is a disadvantage compared to the data assimilation-based methods. Nonetheless, the study demonstrated the potential of machine learning techniques in improving streamflow forecasting. The forecasting of streamflow for long lead-times such as a month usually involves the use of historical meteorological data to create probable future scenarios, as meteorological forecasts become unreliable beyond this lead-time. In this study, we proposed a novel method for streamflow forecasting based on ensemble streamflow forecasting (ESP) filtering, using a Genetic Algorithm (GA) to filter forecast scenarios. This method quantifies the potential of historical data for each basin. This potential could be utilized to enhance the accuracy of streamflow forecasts. We sorted the selected and unselected scenarios to find out the common features between them, but the results did not help distinguish between the two groups. Nonetheless, the GA method can be used as a benchmark for future studies to improve longterm streamflow forecasting. This method can also be used to compare different forecast methods based on the potential shown by the GA method for a specific size of ESP members. For instance, if a method uses large-scale climate signals to filter ESP members, the forecast skill result could be compared with the potential of historical data for that particular size of ESP members.

Le rôle des rivières dans les dynamiques du carbone, de l’azote, et du phosphore selon des gradients d’utilisation du territoire et des contrastes climatiques - Shousha, Stéphanie (2022)
Les rivières sont des écosystèmes dynamiques qui reçoivent, transforment, et exportent de la matière organique comprenant du carbone (C), de l’azote (N), et du phosphore (P). De par leur grande surface de contact entre l’eau et les sédiments, elles offrent un potentiel élevé pour les processus de transformation de ces éléments, dans lesquels ils sont souvent conjointement impliqués. Ces transformations peuvent retirer les éléments de la colonne d’eau et ainsi diminuer leurs concentrations pour améliorer la qualité de l’eau. Par contre, les conditions climatiques (débit, température, luminosité), la configuration du territoire (forêt, urbanisation, agriculture), et la durée des activités humaines sur terre affectent la quantité, composition, et proportion de C, N, et P livrés aux cours d’eau receveurs. Dans un contexte où un surplus de nutriments (N, P) peut surpasser la capacité des rivières à retirer les éléments de l’eau, et où les extrêmes climatiques s’empirent à cause des changements climatiques, cette thèse met en lumière le rôle des rivières dans les dynamiques de C, N, et P pour une meilleure compréhension de la réponse des écosystèmes lotiques aux pressions actuelles et futures. La Rivière du Nord draine séquentiellement des régions couvertes de forêt, d’urbanisation, et d’agriculture, et oscille entre quatre saisons distinctes, l’exposant à des utilisations du territoire et conditions climatiques contrastées. Nous avons échantillonné les formes de C, N, et P à 13 sites le long du tronçon principal (146 km), une fois par saison pour trois ans. De façon générale, les concentrations de N et P totaux ont augmenté d’amont vers l’aval, concordant avec l’activité humaine plus importante dans la deuxième moitié du bassin versant, mais les concentrations de C organique total sont restées constantes peu importe la saison et l’année. La stœchiométrie écosystémique du C : N : P était donc riche en C comparé au N et P en amont, et s’est enrichie en nutriments vers l’aval. L’étendue (2319 : 119 : 1 à 368 : 60 : 1) couvrait presque le continuum terre – océan à l’intérieur d’une seule rivière. Des formes différentes de C, N, et P dominaient la stœchiométrie totale dépendamment des saisons et de l’utilisation du territoire. En été, la composition du N était dominée en amont par sa forme organique dissoute et par le nitrate en aval, tandis qu’en hiver, l’ammonium et le P dissous avaient préséance sur l’entièreté du continuum. Malgré une concentration constante, la proportion des molécules composant le C différait aussi selon la saison et l’utilisation du territoire. L’été était dominé par des formes dégradées par l’action microbienne et l’hiver par des formes bio- et photo-labiles. Ceci fait allusion au potentiel de transformation de la rivière plus élevé dans la saison chaude plutôt que sous la glace, où les formes plus réactives avaient tendance de s’accumuler. La composition du C en amont était aussi distincte de celle en aval, avec un seul changement abrupt ayant lieu entre la section forestière et la section d’utilisation du territoire urbaine et agricole. Ces changements de compositions n’étaient pas présents durant le printemps de crue typique échantillonné, mais dans l’inondation de fréquence historique nous avons observés des apports nouveaux de molécules provenant soit des apports terrestres normalement déconnectés du réseau fluvial ou de surverses d’égouts. L’influence des facteurs naturels et anthropiques s’est aussi reflétée dans les flux historiques riverains de C, N, et P (1980 – 2020). La précipitation explique le plus les flux de C et les flux de N dans la section pristine. Les apports historiques au territoire de N anthropique (nécessaires pour soutenir la population humaine et les activités agricoles) expliquent fortement la tendance temporelle à la hausse des flux riverains de N dans la section urbaine. Durant les quatre dernières décennies, un peu plus du tiers des apports de N au territoire sont livrés à la rivière annuellement, suggérant que la source urbaine de N anthropique est encore peu gérée. Le manque de corrélation entre les flux de P dans la rivière et les précipitations ou les apports au territoire de P anthropique peut être expliqué par les usines de traitement des eaux usées installées dans la région vers la fin des années 1990 qui ont fait diminuer presque de moitié le P livré à la rivière. La variation de ces flux s’est reflétée dans la stœchiométrie écosystémique historique, qui varie de 130 : 23 : 1 en 1980 à 554 : 87 : 1 en 2007-08 après l’effet de l’usine d’épuration et du N qui a augmenté. À travers les axes historiques, spatiaux, et saisonniers, cette thèse contribue à la compréhension du rôle des rivières dans la réception, la transformation, et l’export du C, N, et P. Combinée aux concentrations, l’approche de stœchiométrie écosystémique propose une façon d’intégrer apports et pertes des éléments pour les étudier de pair au niveau du bassin versant. Puis, comme certaines formes de C, N, et P sont associées à des sources terrestres spécifiques, ou à certains types de transformations, les inclure dans un cadre conceptuel combinant des extrêmes climatiques et des utilisations du territoire différentes offre un aperçu sur le résultat des sources et transformations des éléments. Enfin, les tendances décennales de C, N, et P riverains montrent l’influence des facteurs naturels et anthropiques sur la stœchiométrie écosystémique historique d’une rivière.

Using a stochastic weather generator to account for climate non-stationarity in extended streamflow forecasts - Sohrabi Molla Yousef, Samaneh (École de technologie supérieure, 2020)
Reliable long-term streamflow forecast is essential in water resources management and plays a key role in reservoir management and hydropower generation. Properly framing the uncertainty is the key issue in providing a reliable long-term streamflow forecast, and probabilistic forecasts have been used to this effect. In a probabilistic approach, each observed historical data is taken as a possible realization of the future. Non stationarity of hydrometeorological variables, either due to the climate internal variability or anthropogenic change, is another important problem for long-term streamflow forecasts as it is becoming increasingly clearer that past historical data may not adequately represent the current climate. Therefore, there is a need to develop flexible approaches taking into account non-stationarity for long-term streamflow forecasts. Resampling past historical time series is the main approach used for probabilistic long term streamflow forecasts. However, non-stationarity is a key issue of resampling approaches. One possible approach is to make use of a stochastic weather generator coupled to a hydrological model to generate long-term probabilistic streamflow forecasts. Weather generators can easily be modified to account for climatic trends and therefore have the potential to take non-stationarity into account. However, before weather generators can be modified to account for climate non-stationarity, it is first necessary to evaluate whether the modeling chain consisting of a stochastic weather generator and a hydrological model can generate probabilistic streamflow forecasts with a performance similar to that of more traditional resampling approaches. The first objective of this study is therefore, to compare the performance of a stochastic weather generator against that of resampling historical meteorological time series in order to produce ensemble streamflow forecasts. Results indicate that while there are differences between both methods, they nevertheless largely both perform similarly, thus showing that weather generators can be used as substitutes to resampling the historical past. Based on these results, two approaches for taking non-stationarity into account have been proposed. Both approaches are based on a climate-based perturbation of the stochastic weather generator parameters. The first approach explored a simple perturbation method in which the entire length of the historical record is used to quantify internal variability, while a subset of recent years is used to characterize mean climatic values for precipitation, minimum and maximum temperatures. Results show that the approach systematically improves long-term streamflow forecasts accuracy, and that results are dependent on the time window used to estimate current mean climatic estimates. The second approach conditioned the parameters of a stochastic weather generator on largescale climate indices. In this approach, the most important climate indices are identified by looking at yearly correlations between a set of 40 indices and precipitation and temperature. A linear model is then constructed to identify precipitation and temperature anomalies which are then used to induce perturbations in the stochastic weather generator. Five different time windows are defined to determine the optimal linear model. Results show that temperatures are significantly correlated with large-scale climate indices, whereas precipitation is only weakly related to the same indices. The length of the time window has a considerable impact on the prediction ability of the linear models. The precipitation models based on short-duration time windows performed better than those based on longer windows, while the reverse was found for the temperature models. Results show that the proposed method improves long-term streamflow forecasting, particularly around the spring flood.

Risk-based seismic safety assessment of concrete gravity dams with uncertainty quantification - Patra, Bikram Kesharee (Concordia University, 2024)
Dams are vital national assets that play a crucial role in water storage, hydroelectric power generation, and flood control. Globally, over 61,000 large dams have surpassed 50 years of service, and many show signs of deterioration. With over 300 dam failures recorded worldwide, the potential for catastrophic damage remains alarmingly high if these aging structures are not properly maintained and upgraded. Further, many of the existing dams were built upon outdated standards, and there is an increase in seismic hazards making it imperative to reevaluate their seismic performance to align with current safety standards. The need for improved dam safety measures is urgent, as dam owners, regulators, and policymakers grapple with the challenges of ensuring the structural integrity of aging dams in the face of growing risks. A key solution is shifting from traditional safety approaches to a modern, risk-based methodology, which addresses safety concerns more efficiently and economically. Various, global agencies have developed risk-based safety assessment guidelines; however, these often lack systematic implementation frameworks and sufficient reference studies, making them difficult for dam owners to adopt effectively. Furthermore, various uncertainties can impact the risk assessment and can complicate efforts to ensure dam safety. In this context, this research investigates uncertainties impacting seismic risk assessments for dams, including modeling choices, ground motion selection, aging, and material variability. Case studies of the Koyna Dam and Pine Flat Dam were used to evaluate these factors at each stage of performance evaluation: system response, fragility, and risk assessment. Key findings indicate that dam-foundation-reservoir (DFR) models incorporating acoustic elements exhibit less variability in system response, regardless of model complexity and solution procedure. Ground motion derived from the conditional mean spectrum (CMS) method yields better fragility estimates than the ASCE 7-16 standard, particularly for moderate to severe damage states. Additionally, aging and material variability significantly affect the dynamic characteristics of dams, with increased failure probabilities correlating with both age and return period. Based on these findings, the research proposes a comprehensive, systematic framework for risk-based seismic safety evaluation. This framework aligns with safety assessment objectives and ensures optimal use of computational resources.

L'opportunité de l'admission de la matière cellulaire et génétique humaine à la brevetabilité en droit français - Laulan, Julie (2024)
Les biotechnologies constituent aujourd'hui un secteur d'activités dynamique offrant de nouvelles perspectives d'innovations. Ces connaissances, permettant d'allier deux entités jusqu'ici traitées séparément, la technique et le vivant, sont en proie de révolutionner notre rapport au monde à de nombreux égards. La présente étude a plus spécifiquement vocation à se pencher sur les innovations biologiques produites à partir d'éléments extraits du corps humain, tels que les cellules souches et les gènes. La biologie cellulaire et le génie génétique se sont imposés comme des secteurs phares des biotechnologies en raison des progrès significatifs qu'ils pourraient permettre pour le traitement de certaines maladies génétiques rares. Toutefois, la protection juridique devant être octroyée à ce type de créations suscite un flot de réactions souvent très partagées au sein de l'opinion publique. Si le brevet est reconnu comme l'outil de propriété industrielle privilégié pour protéger efficacement les inventions, son application au domaine du vivant, et qui plus est au corps humain, demeure plus délicate et controversée. L'inadéquation des critères de brevetabilité aux inventions biotechnologiques fait aujourd'hui obstacle à la prise en considération de ces nouvelles formes de créations par la propriété intellectuelle. Ce projet de recherche s'inscrit dans une perspective globale et transversale, visant à comprendre en quoi le domaine brevetable est influencé par une série de considérations éthiques et par la superposition d'intérêts économiques et sociaux divergents. Il s'agit ainsi de tenter de clarifier les délimitations de l'objet brevetable et de réfléchir à l'opportunité de nouvelles admissions dans le champ de la brevetabilité tout en maintenant certains garde-fous essentiels à la protection des droits fondamentaux individuels. Dès lors, cette étude s'intéresse aux outils et stratégies disponibles afin de renforcer la coopération entre les acteurs impliqués dans ce débat et d'assurer un meilleur équilibre entre les différents intérêts en présence.

Design and Implementation of an IoT Platform for Flood Prediction - Mehta, Meet Divyesh (Concordia University, 2023)
Flooding, a major natural calamity, severely threatens communities and infrastructures in areas susceptible to floods. Consequently, implementing an Internet of Things (IoT)-based flood monitoring system becomes crucial. Existing flood monitoring systems lack a comprehensive and scalable IoT platform to collect real-time data from diverse sensors efficiently, visualize flood information, and provide accurate water level forecasts. This thesis proposes a complete system designed to address the challenges associated with efficient data collection and flood monitoring from diverse IoT sensors. Our proposition involves creating and deploying a centralized system known as HYDROSIGHT, which facilitates the real-time gathering, monitoring, and visualization of flooding-related sensor data. HYDROSIGHT system also provides a log monitoring feature for effective debugging and troubleshooting. The IoT environment for flood monitoring and prediction system was designed to promote sustainability and autonomy by preferring sensors with minimal footprints and compatibility with solar panels. The system architecture leverages a 4G network for seamless data transmission. To validate the practical applicability of the proposed design,HYDROSIGHT system was tested at two municipalities of Quebec, namely Terrebonne, and Lac-Supérieur. In addition, the platform was also deployed at the Ericsson facility in Montreal to test the 5G capabilities. The deployment in these locations allowed us to evaluate the performance and effectiveness of the HYDROSIGHT system in a real flood monitoring environment. In addition to implementing the IoT testbed, a preliminary machine learning tool was developed on water level forecasting. In this experiment, we opted for an online machine-learning approach, recognizing the significance of real-time updates and low computational resources of IoT devices. Leveraging the constantly updating data from HYDROSIGHT, we trained and tested our online machine-learning model, enhancing its forecasting capabilities. We conducted a comparative analysis to understand the advantages of online machine learning over traditional batch learning. This analysis involved examining the water level forecasting results obtained from both methods using time series data from the HYDROSIGHT system deployed at Lac-Supérieur in Quebec.

Développement d'un modèle numérique topographique et bathymétrique multisource du fleuve Saint-Laurent dans la région de la Communauté métropolitaine du Québec (CMQuébec) pour la modélisation hydrodynamique - Noman, Juzer (2023)
Les inondations sont une préoccupation majeure avec un potentiel de risques importants pour la sécurité publique ainsi qu'un impact économique et social négatif. Pour développer un modèle hydrodynamique permettant de cartographier et d'évaluer les risques d'inondation, un modèle d'élévation est un élément essentiel. La grande disponibilité de données de télédétection multisources facilite la création d'un modèle numérique d'élévation topo-bathymétrique (TBDEM). Cependant, il peut être très difficile de créer un modèle d'élévation à haute résolution homogène adapté à la cartographie des inondations en raison des divergences entre les données topographiques et bathymétriques causées par des changements temporels, des systèmes de référence horizontaux et verticaux différents, et des différences significatives en termes de résolution, incertitude et zone de couverture. Cette étude présente une méthodologie qui élargit les études précédentes axées sur la cartographie côtière à basse résolution en résolvant les différences spatiales et temporelles des jeux de données multisources tout en maintenant l'intégrité de la morphologie des berges et de l'environnement proche du rivage. Ceci est réalisé en appliquant une nouvelle méthodologie de fusion qui est mieux adaptée aux sources de données en jeu. Une méthode de moindre coût est appliquée aux données topographiques alors qu'une méthode de feathering est appliquée aux données bathymétriques. Pour ce qui est de la zone intermédiaire à l'interface de la terre et de l'eau, des transects sont utilisés pour interpoler entre les données manquantes afin de garantir l'intégrité du littoral. Enfin, une méthode de krigeage empirique bayésien appliqué à l'ensemble des données permet de produire une surface sans discontinuité accompagnée d'une surface d'erreur pour analyser l'incertitude en chaque point du modèle. Des données LiDAR aéroporté ainsi que des données de bathymétrie multifaisceau de la section supérieure du fleuve Saint-Laurent au Québec, Canada ont été combinées en utilisant la méthodologie proposée. Le TBDEM produit dans cette étude constitue une meilleure représentation que les modèles précédents et minimise l'erreur dans les données. La capacité de ce TBDEM à être plus performant que les modèles précédents dans les simulations hydrodynamiques sera testée dans des études futures en utilisant des événements de crue enregistrés précédemment.

Déterminants de l'intention d'adoption d'un nouvel outil prévisionnel des crues dans le cadre du projet info-crue - Mutabazi, Jean-Paul (Université du Québec à Rimouski, 2022)
RÉSUMÉ : Pour atténuer les risques d'inondation au Québec mais aussi partout dans le monde, plusieurs organismes gouvernementaux et des organismes privés, qui ont dans leurs attributions la gestion des risques des catastrophes naturelles, continuent d'améliorer ou d'innover en matière d'outils qui peuvent les aider efficacement à la mitigation des risques d'inondation et aider la société à mieux s'adapter aux changements climatiques, ce qui implique des nouvelles technologies pour la conception de ces outils. Après les inondations de 2017, le ministère de l'Environnement et de la Lutte contre les changements climatiques (MELCC) du gouvernement du Québec, en collaboration avec d'autres ministères et organismes et soutenu par Ouranos, a initié le projet INFO-Crue qui vise d'une part, à revoir la cartographie des zones inondables et, d'autre part, à mieux outiller les communautés et les décideurs en leur fournissant une cartographie prévisionnelle des crues de rivières. De ce fait, l'objectif de notre travail de recherche est d'analyser de façon empirique les facteurs qui influencent l'adoption d'un outil prévisionnel des crues. La revue de la littérature couvre les inondations et les prévisions, les théories et les modèles d'acceptation de la technologie de l'information (TI). Pour atteindre l'objectif de recherche, le modèle développé s'est appuyé particulièrement sur le modèle qui combine les concepts de la théorie unifiée de l'acceptation et l'utilisation des technologies (UTAUT) de Venkatesh et al. (2003) avec le concept « risque d'utilisation ». Afin de répondre à notre objectif de recherche, nous avons utilisé une méthodologie de recherche quantitative hypothético-déductive. Une collecte de données à l'aide d'une enquête par questionnaire électronique a été réalisée auprès de 106 citoyens qui habitent dans des zones inondables. L'analyse des résultats concorde avec la littérature. La nouvelle variable « risque d'utilisation » rajoutée au modèle UTAUT a engendré trois variables qui sont : « risque psychologique d'utilisation »; « risque de performance de l'outil » et « perte de confiance ». Pour expliquer l'adoption d'un nouvel outil prévisionnel des crues, notre analyse a révélé que cinq variables à savoir : « l'utilité perçue », « la facilité d'utilisation », « l'influence sociale », « la perte de confiance » et « le risque psychologique » sont des facteurs significatifs pour l'adoption du nouvel outil prévisionnel. -- Mot(s) clé(s) en français : Inondation, Prévision, UTAUT, Adoption de la technologie, Risque perçu d'utilisation, facteurs d'adoption, Projet INFO-Crue. -- ABSTRACT : With the aim of mitigating flood risks in Canada as well as around the world, several government and private organizations that have the responsibility of natural hazard risk management, are working hard to improve or innovate the flood mitigation approaches that can help effectively reducing flood risks and helping people adapt to climate change. After the 2017 floods, the Ministry of the Environment and the Fight against Climate Change (MELCC) of the Government of Quebec, in collaboration with other ministries and organizations and supported by Ouranos, initiated the INFO-Crue project which aims at reviewing the mapping of flood zones and providing communities and decision-makers with a forecast mapping of river floods. In this context, the objective of our research is to analyze the factors that may influence the adoption of a flood forecasting tool. The literature review covers flood and forecasting, as well as technology adoption models. To achieve the goal of our research, a conceptual model that combines the Unified Theory of Acceptance and Use of Technology (UTAUT) of Venkatesh et al. (2003) with perceived use risk was developed. A quantitative research methodology was used, and we administrate an electronic questionnaire survey to 106 citizens who live in flood-plain area. Results analysis show that the new variable "perceived use risk" introduced in the model generates three variables which are: "psychological risk"; "performance risk" and "loss of trust". To explain the adoption of a new forecasting tool, our analysis revealed that the following five variables which are "perceived usefulness", "ease of use", "social influence", "loss of trust" and "psychological risk" are significant factors for the adoption of the new forecasting tool. -- Mot(s) clé(s) en anglais : Flood, Forecasting, UTAUT, Technology Adoption, perceived Risk of use, adoption factors, INFO-Crue project.

Integrated Modeling of Short-Term Flood Forecasting in the Ottawa River - Ousoukhman, Hamza (Polytechnique Montréal, 2021)
RÉSUMÉ: Les inondations sont considérées comme l'un des risques naturels les plus dangereux au monde. Plusieurs pays souffrent des conséquences néfastes des inondations. Au Canada, plusieurs provinces ont subi des inondations au cours du siècle dernier. Par exemple, la rivière des Outaouais a été confrontée à de nombreuses inondations comme en 2017 et 2019. La population d'Ottawa continue à augmenter d'une année à l'autre. C'est pour cela que nous avons choisi la rivière des Outaouais comme étude de cas pour ce projet dans le but de protéger la société contre les risques causés par les inondations. Les pays adoptent plusieurs solutions basées sur différentes méthodes afin de minimiser les dommages causés par les crues. La plupart des scientifiques s'accordent que la prévision des crues est la meilleure façon de limiter les conséquences des crues. Les systèmes de prévision des crues sont indispensables dans les pays fréquemment confrontés à des crues. Ils visent à fournir un long délai d'exécution et à fournir aux autorités et aux décideurs des informations suffisantes. Par conséquent, ils auront suffisamment de temps pour prendre les mesures adéquates pour sauver la vie de la population et limiter les catastrophes économiques dues aux inondations. ABSTRACT: Floods are one of the most catastrophic natural disasters in Canada and around the world that can cause loss of life and damages to properties and infrastructures. Saguenay flood (1996), southern Alberta flood (2013), and Ottawa floods (2017, 2019), are a few examples of Canadian floods with tremendous socio-economic impacts. Flood forecasting and predicting its characteristics (e.g., its magnitude and extent) has an important role in preventing and mitigating such flood impacts. Particularly, short-term forecasting is crucial for early warning systems and emergency response to floods. This study presents an integrated hydraulic-hydrologic modeling system for flood prediction. In this system, the Delft3D two-dimensional hydrodynamic model is connected with a HEC-HMS hydrologic model and observation data to provide an automatic exchange of data and results. Delft3D and HEC-HMS were chosen for this study because they were widely used and provided good results. In addition, they were applied in several flood forecasting studies. The prediction weather data and watershed characteristics provide input to the hydrological model to predict streamflow conditions, which are then automatically fed into the hydrodynamic model. The hydrodynamic model simulates the flood characteristics such as water level, 2D depth-averaged velocity field, and flood extent.

Essays on Water Infrastructure Investments and Infectious Diseases Management - Kouassi, Régis (2024)
En étant nécessaire à la vie humaine, l’eau est également nécessaire au fonctionnement des économies. Pour qu’elle soit utile à la société, l’eau doit être disponible en quantité et en qualité adéquates, caractéristiques qui ne sont pas toujours disponibles dans la nature. Ainsi, trop ou pas assez d’eau entraînerait des inondations ou des sécheresses, tandis qu’une eau contaminée pourrait être le vecteur de maladies contagieuses mortelles, chacun de ces fléaux entraînant des dommages économiques. Cette thèse est organisée en trois chapitres traitant de thématiques liées aux investissements dans les infrastructures d'eau et à la gestion des maladies infectieuses. Le premier chapitre étudie comment les améliorations apportées aux réseaux d’égouts atténuent les impacts économiques des inondations provoquées par la pluie. Pour estimer l’effet causal de ces investissements, ce chapitre utilise un resserrement inattendu du financement fédéral américain en faveur des réseaux d’égouts, à la suite de l’amendement de 1977 à la politique du Clean Water Act. L'analyse empirique combine un nouveau modèle statistique du risque d'inondation induit par la pluie avec des données horaires sur la quantité de pluie dans les comtés et les codes postaux américains de 1996 à 2019. Les résultats indiquent que des investissements plus importants dans les réseaux d'égouts ont conduit à des réductions substantielles des inondations locales. Les bénéfices de ces investissements sont supérieurs à leurs coûts, économisant près de 23 millions de dollars pour le comté moyen. Dans l’ensemble, ces résultats mettent en évidence à quel point la détérioration des infrastructures publiques peut exacerber les conséquences du changement climatique. Le deuxième chapitre étudie le rôle des épidémies locales de maladies infectieuses dans l'adoption de systèmes centralisés d'approvisionnement en eau dans les premières villes américaines au XIXe siècle. À l’aide d’un vaste corpus de données provenant d’archives de journaux de 1800 à 1896, je construis un nouvel indicateur capturant les épidémies de fièvre jaune, de choléra et de fièvre typhoïde au niveau des villes. Les résultats indiquent que (1) les épidémies locales de maladies infectieuses ont entraîné une augmentation du nombre systèmes d'approvisionnement en eau construits par les villes et ont joué un rôle crucial dans la décision de construire environ 12% des ouvrages d’adduction d’eau en activité en 1897 ; (2) La réponse des villes aux épidémies de typhoïde a été deux fois plus importante que celle qui a suivi les épidémies de fièvre jaune ou de choléra. (3) Les entreprises privées ont construit davantage de nouveaux réseaux d’adduction d’eau après les épidémies locales, tandis que les gouvernements locaux ont procédé à davantage d’améliorations et d’extensions des réseaux d’adduction d’eau publics existants ainsi qu’à des rachats de sociétés d’eau privées. Enfin, je discute du rôle potentiel de divers facteurs sociodémographiques. Le troisième chapitre étudie les coûts économiques associés à une stratégie utilisée pour gérer les épidémies locales lors de la récente pandémie de COVID-19. Dans ce travail en collaboration avec Jian Tang, nous quantifions les effets de la politique ‘zéro-COVID’ à l’aide d’un riche ensemble de données sur les confinements au niveau des comtés en Chine et d’images satellitaires nocturnes. Nous constatons que des confinements plus stricts induisent une forte baisse de la luminosité nocturne au cours de la même période, suivie d’une lente reprise, qui se produit au moins deux trimestres après l’instauration du confinement. En l’absence de contagions généralisées, un comté soumis à un confinement total subit en moyenne une perte de PIB de 6% par rapport aux comtés non confinés. L’effet négatif est particulièrement persistant dans les zones où la production est dominée par les services, par opposition aux zones où la production est dominée par l’activité manufacturière. L’on note par ailleurs la présence d’effets d’entraînement à proximité des comtés confinés, mais ces effets sont de courte durée.

Influence du régime de crues printanières sur la structure et la composition des peuplements riverains de frênes noirs (Fraxinus nigra Marsh.) du lac Duparquet - Delayance, Lou (Université du Québec en Abitibi-Témiscamingue, 2024)
Les débits reconstitués pour le nord-ouest du Québec démontrent une augmentation de la fréquence et de la magnitude des crues printanières en lien avec l’augmentation des précipitations nivales depuis le début du XIXe siècle. Autour du lac Duparquet, une migration des peuplements de frêne noir (Fraxinus nigra Marsh.) vers l’intérieur des terres en réponse à ces changements a été rapportée. Pour anticiper la réponse des frênaies noires du lac Duparquet face aux changements climatiques et hydrologiques à venir, cette étude décrit les conditions favorisant la présence de F. nigra et la structuration des peuplements en lien avec la dynamique des crues printanières depuis le début du XXe siècle. L’étude se structure autour des objectifs suivants : i) déterminer la composition et l’organisation des communautés végétales associées à F. nigra le long du gradient d’élévation; ii) déterminer les facteurs limitant l’expansion des frênaies noires dans les basses et hautes plaines alluviales; et iii) déterminer les fréquences d’occurrence des crues printanières le long du gradient d’élévation des plaines alluviales et identifier les fréquences de retour des crues printanières associées à chaque groupement floristique. Vingt-quatre frênaies noires du lac Duparquet et de ses affluents ont été échantillonnées durant l’été 2022 en utilisant un échantillonnage par stratification verticale de la végétation le long de transects perpendiculaires à la rive, avec mesure de variables environnementales et écologiques. Une analyse par regroupement hiérarchique associée à une analyse d’espèces indicatrices a permis d’identifier des communautés végétales associées aux frênaies noires et notamment trois communautés distribuées le long des gradients d’élévation et de distance à la rive depuis la plaine alluviale basse (communauté i) frênaie à Onoclea sensibilis L.), moyenne (communauté ii) frênaie à Rhamnus alnifiolia L’Her.), et haute (communauté iii) frênaie à Athyrium filix-feminina (Linn.) Roth). Les structures de diamètre révèlent que les zones des basses et hautes plaines alluviales sont moins denses en F. nigra et composées d’arbres plus jeunes. Les analyses des cernes de crues montrent une diminution significative de la fréquence d’occurrence des crues printanières de faible et forte intensité entre les groupements floristiques depuis les basses vers les hautes plaines inondables. Les fréquences moyennes d’occurrences des crues le long du gradient d’élévation participent donc à expliquer la structure des frênaies noires du lac Duparquet. Cette recherche fournit des paramètres écologiques de base, essentiels pour maintenir un équilibre dynamique dans les frênaies noires, notamment en cas de modifications des débits des cours d'eau, comme celles induites par des aménagements hydroélectriques ou de futurs changements climatiques.

Validation et adaptation d’une approche géomatique pour délimiter en première approximation les zones inondées à partir du débit simulé par un modèle hydrologique distribué. - El Batti, Zainab (Maîtrise en sciences de l'eau, 2023)
Au Québec, les conditions printanières extraordinaires de 2017 et 2019 ont incité le gouvernement provincial à commander une mise à jour des cartes des zones inondables. La plupart des cartes existantes ne reflètent pas adéquatement l’aménagement actuel du territoire, ni l’aléa associé. Généralement, pour la cartographie, les modèles hydrodynamiques tel que HEC-RAS sont utilisés, mais ces outils nécessitent une expertise significative, des données hydrométriques et des relevés bathymétriques à haute résolution. Étant donnée la nécessité de mettre à jour ces cartes tout en réduisant les coûts financiers associés, des méthodes conceptuelles simplifiées ont été développées. Ces approches, y compris l’approche géomatique HAND (Height above the nearest drainage), qui reposent uniquement sur un modèle numérique d’élévation (MNE), sont de plus en plus utilisées. HAND permet de calculer la hauteur d’eau nécessaire pour inonder chaque pixel du MNE selon la différence entre son élévation et celle du pixel du cours d’eau dans lequel il se déverse. Les informations sur la géométrie hydraulique dérivées par HAND ainsi que l’application de l’équation de Manning permettent la construction d’une courbe de tarage synthétique (CTS) pour chaque tronçon de rivière homogène. Dans la littérature, cette méthode a été appliquée pour établir une cartographie de la zone inondable de première instance de grands fleuves aux États-Unis avec un taux de correspondance de 90% par rapport à l’utilisation de HEC-RAS. Elle n’a toutefois pas été appliquée sur de petits bassins versants, car ceux-ci engendrent des défis méthodologiques substantiels. Ce projet s’attaque à ces défis sur deux bassins versants Québécois, ceux des rivières à la Raquette et Delisle. Les conditions frontières des modèles sont dérivées d’un traitement statistique empirique des séries de débits simulés avec le modèle hydrologique HYDROTEL. Étant donnée l’absence de stations météorologiques sur le territoire à l’étude, des chroniques du système Canadien d’Analyse de la précipitation (CaPA) ont été utilisées pour cette modélisation hydrologique. Les résultats de ce projet pointent vers des performances satisfaisantes de l’approche géomatique HAND-CTS en comparaison avec le modèle hydrodynamique HEC-RAS (1D/2D et 2D au complet), avec des taux de correspondance entre les étendues des inondations supérieurs à 60 % pour les bassins versants de Delisle et à la Raquette. Les comparaisons étaient effectuées sur une gamme de débit allant d’un débit de période de retour de 2 ans jusqu’à un débit de plus de 350 ans. On notera que l’application sur la rivière à la Raquette a été développée dans les règles de l’art, incluant un processus de calage développé dans le cadre d’un projet de maitrise en sciences de l’eau connexe à ce mémoire, relativement à la longueur du tronçon, le calage vertical de la CTS en considérant la hauteur d’eau présente dans le cours d’eau lors du relevé LiDAR et sa précision verticale. Les résultats ont montré que le coefficient de précision globale le plus bas était de 98 % pour un débit de 350 ans, avec une précision de plus que 99 % pour les autres périodes de retour, ce qui représente une très bonne performance du modèle. Et par ailleurs, le coefficient de Kappa conditionnel humide variait entre 58 % et 28 %. Alors, que pour la rivière Delisle, l’application se veut naïve, c’est-à-dire sans calage préalable de la méthode HANDCTS. La précision globale a varié entre 83 % et 96 %, ce qui est considéré comme "très approprié" et une variation du coefficient Kappa conditionnel humide de 35,2 à 64,3 %. Alors que pour une différence d’élévations d'eau entre les élévations de référence et simulées, la performance était quantifiée par un RMSE qui variait pour les périodes de retour de 100 ans et de 350 ans respectivement de 4,5 m et de 7,1 m. Enfin, la distribution spatiale des différences d’élévations montre une distribution gaussienne avec une moyenne qui est à peu près égale à 0 où la plupart des erreurs se situent entre -0,34 m et 1,1 m La cartographie des zones inondables dérivée de HAND-CTS présente encore certains défis associés notamment à la présence d’infrastructures urbaines complexes (ex. : ponceaux, ponts et seuils) dont l’influence hydraulique n’est pas considérée. Dans le contexte où l’ensemble du Québec (529 000 km²) dispose d’une couverture LiDAR, les résultats de ce mémoire permettront de mieux comprendre les sources d’incertitude associées à la méthode HAND-CTS tout en démontrant son potentiel pour les bassins versants dépourvus de données bathymétriques et hydrométéorologiques. The 2017 and 2019 extraordinary spring conditions prompted the Quebec government to update flood risk maps, as most of them do not adequately reflect current land use and associated hazard. Generally, hydrodynamic models such as HEC-RAS are used for flood mapping, but they require significant expertise, hydrometric data, and high-resolution bathymetric surveys. Given the need to update these maps while reducing the associated financial costs, simplified conceptual methods have been developed over the last decade. These methods are increasingly used, including HAND (height above the nearest drainage), which relies on a Digital Elevation Model (DEM) to delineate the inundation area given the water height in a river segment. Furthermore, the river geometry derived from HAND data and the application of Manning’s equation allow for the construction of a synthetic rating curve (SRC) for each homogeneous river segment. In the scientific literature, this framework has been applied to produce first-instance floodplain mapping of large rivers. For example, in the Continental United States 90% match rates were achieved when compared to the use of HEC-RAS. However, this framework has not been validated for small watersheds, as substantial methodological challenges are anticipated. This project addresses these underlying challenges in two Quebec watersheds, the à la Raquette and Delisle watersheds. The boundary conditions of the HECRAS models were derived from an empirical statistical treatment of flow time series simulated by HYDROTEL, a hydrological model, using Canadian Precipitation Analysis Product (CaPA) time series. The results of this project point towards satisfactory performances, with match rates greater than 60 % for both watersheds. It should be noted that the application on the Delisle River is naive, that is without prior calibration of the HAND-SRC method. The overall accuracy ranged from 83.4 % to 96.2 % while the water surface elevation difference was quantified by an RMSE that was for the 100-year and 350-year return periods of 4.5 m and 7.1 m respectively and where most errors are between -0.34 m and 1.1 m representing a very good model comparing to similar studies. For à la Raquette, the application showed an overall accuracy coefficient of 98 % for a 350-year flow, with an accuracy of over 99 % for other return periods. The mapping of flood risk areas using HAND-SRC still faces certain challenges, notably the presence of complex urban infrastructures (e.g., culverts, bridges, and weirs) whose hydraulic influences are not considered by this geomatic approach. Given that most of Quebec (529,000 km²) topography has been digitized using LiDAR data, the results conveyed in this MSc thesis will allow for a better understanding of the sources of uncertainty associated with the application of the HAND-SRC method while demonstrating its potential for watersheds lacking hydrometeorological and high-resolution bathymetric data.

Dérivation de courbes de tarage synthétiques à partir d'un modèle numérique d'altitude pour délimiter les surfaces inondables de petits bassins versants. - Gordon, Camila Alejandra (Maîtrise en sciences de l'eau, 2022)
Compte tenu de la nécessité de mettre à jour les cartes d'inondation et de minimiser les coûts associés (collecte de données et ressources humaines), il existe un besoin de méthodes alternatives simplifiées ne reposant pas sur la modélisation hydrodynamique classique. L'une des méthodes simplifiées répondant à ce besoin est HAND (Height Above the Nearest Drainage), une approche qui requiert uniquement un modèle numérique d'altitude (MNA) et un réseau hydrographique. Celle-ci a été mise en œuvre dans PHYSITEL, un système d’information géographique SIG spécialisé pour les modèles hydrologiques distribués. Ainsi, pour une hauteur d’eau donnée dans plusieurs tronçons de rivière, il est possible de faire une délimitation de première instance de la surface inondée le long du réseau hydrographique d’un bassin versant. Par ailleurs, l'utilisation des informations fournies par HAND et l'application de l'équation de Manning permettent également de construire une courbe de tarage synthétique pour tout tronçon de rivière en l’absence de données bathymétriques. Ce mémoire présente l’application de cette approche, qui a été validée précédemment en partie sur de grands bassins, sur deux petits bassins, ceux de la rivière à La Raquette, d’une superficie de 133 km², et de la rivière Saint Charles, d’une superficie de 552 km². Trois stations de jaugeage dans chaque bassin ont fourni les informations de base nécessaires au processus de calage de l’approche. L’efficacité et l’adaptabilité de cette approche ont été évaluées dans ce projet en fonction des données disponibles, du temps de calcul et de la précision mesurée par le biais et l’erreur quadratique moyenne. Les incertitudes et sensibilités de l’approche ont été analysées en tenant compte de la résolution spatiale et du manque de données bathymétriques. De plus, des analyses innovatrices ont été produites dans l’application de HAND. Tels qu’une analyse de sensibilité globale pour informer le processus de calage ainsi que l’application d’un critère basé sur le nombre de Froude afin de permettre de valider le respect des hypothèses sous-jacentes à l’application de l’approche sur chaque tronçon de rivière d’un bassin. En utilisant des MNA à haute résolution(<5 m/pixel), des courbes de tarage synthétiques ont été produites avec des biais inférieurs à ±20 % par rapport à des courbes de tarage in-situ. De plus, la détermination d'un critère de sélection des courbes dans un biais de ± 5% par rapport à la courbe de tarage observée a permis d'obtenir des courbes de tarage synthétiques avec des erreurs quadratiques moyennes normalisées comprises entre 0,03 et 0,62. Ainsi, cette approche a été validée pour dériver des courbes de tarage synthétiques et, par conséquent, pour soutenir la délimitation des zones à risque d'inondation dans les petits bassins versants en tenant compte des incertitudes associées à l'application d'une approche de faible complexité. Given the emergent need to update flood inundation maps and minimize associated financial costs (data collection and human resources), simplified alternative methods to the classical hydrodynamic modelling method, are being developed. One of the simplified methods built to fulfill this need is the terrain-based Height Above the Nearest Drainage (HAND) method, which solely relies on a digital elevation model (DEM) and a river network. This approach was implemented in PHYSITEL, a specialized GIS for distributed hydrological models. For a given river reach and water height, HAND can provide a first-hand delineation of the inundated areas within a watershed. In addition, coupling the information provided by HAND and the Manning equation allows for the construction of a synthetic rating curve for any homogeneous river reach where bathymetric data are not available. Since this synthetic rating curve approach has been validated in part for large watersheds, this study tested this approach onto two small watersheds: the 133- km² La Raquette River watershed and the 552-km² Saint Charles River watershed. Three gauging stations on each basin provided the basic data to perform the calibration process. The effectiveness and adaptability of the approach was assessed as a function of available data, computational time, and accuracy measured using the bias and root mean squared error (RMSE). The uncertainties were quantified in terms of spatial resolution and lack of bathymetry data. In addition, innovative analyses were made on the application of the HAND-synthetic rating curve approach. First, a global sensitivity analysis was done to inform the calibration process, and then a Froude number-based criterion was applied to validate the application of the Manning equation on any river reach of a watershed. Using high-resolution DEMs (<5 m/pixel), we obtained synthetic rating curves with bias less than 20% when compared to in-situ rating curves. Finally, a curve selection criterion was applied to identify those curves having a bias of ± 5%. The selected synthetic rating curves had normalized mean squared errors between 0.03 and 0.62. Thus, the proposed approach was deemed appropriate to derive synthetic rating curves and support the delineation of flood risk areas in small watersheds all the while considering the uncertainties associated with applying a low complexity model.

Stress pendant la grossesse en contexte de catastrophe naturelle : revue méta-analytique des conséquences sur le développement de l’enfant et évaluation des besoins informationnels des femmes enceintes - Lafortune, Sandra (2021)
Depuis de nombreuses années, les chercheurs dans le domaine du stress maternel prénatal (SMP) associé à des catastrophes naturelles cumulent des données probantes suggérant un effet de ce type de stresseur sur le développement de l’enfant. Plusieurs obstacles freinent cependant le transfert de ces connaissances (TC) à leurs potentielles bénéficiaires, les femmes enceintes. Un premier obstacle est qu’il n’existe pas de synthèse de connaissances quantifiant l’effet du SMP sur les différentes sphères de développement de l’enfant. De plus, les besoins informationnels des femmes enceintes à ce sujet ne sont pas connus. Ensuite, d’un point de vue éthique, il est difficile de se positionner quant à la meilleure stratégie de TC à employer pour informer les femmes enceintes sans leur imposer un stress additionnel. Cette thèse vise donc à déterminer comment informer les femmes enceintes au sujet des conséquences du stress pendant la grossesse sans les stresser davantage. Pour ce faire, une revue méta-analytique de l’effet du SMP associé à des catastrophes naturelles sur le développement de l’enfant a été réalisée pour quantifier cet effet. Par la suite, un questionnaire a été élaboré pour sonder les femmes issues de deux cohortes distinctes, une première ayant été exposée aux feux de forêt de Fort McMurray pendant la grossesse, puis une seconde localisée à Montréal et n’ayant pas été exposée à une catastrophe naturelle au cours de la grossesse. Les items du questionnaire cherchaient à déterminer leurs connaissances au sujet du SMP ainsi que leur désir d’en avoir su davantage à ce propos au cours de leur dernière grossesse. Une grille d’entretien originale a ensuite permis d’interviewer un sous-échantillon des femmes de la cohorte de Montréal pour préciser leurs besoins informationnels et les paramètres qui devraient guider un processus de TC à cet effet. Cette dernière étude a cependant été interrompue en raison de la pandémie de COVID-19 et seuls les résultats préliminaires en sont ici présentés. Plusieurs constats sont ressortis des méta-analyses et des méta-régressions. D’abord, le SMP a un effet, petit, mais durable, sur l’ensemble des sphères de développement de l’enfant. Ensuite, les difficultés objectives et la détresse psychologique sont les composantes du SMP pour lesquelles les plus grands effets ont été trouvés. Il semble également que l’exposition à une tempête de verglas affecte encore plus le développement de l’enfant que celle à une inondation. Les résultats au questionnaire des deux cohortes de femmes a permis de lever le voile sur le manque de connaissances à combler chez ces dernières concernant principalement les conséquences concrètes du SMP sur le développement de l’enfant, puis d’établir que les deux cohortes de femmes auraient majoritairement voulu en savoir davantage à ce sujet au cours de leur dernière grossesse. Enfin, les données complémentaires issues des entretiens avec les femmes de la cohorte de Montréal indiquent que les professionnels de la santé seraient les utilisateurs de connaissances à privilégier et que l’approche à employer pour faire ce TC devrait être empathique, non culpabilisante, centrée sur la femme dans sa globalité et ajustée à son style de recherche d’informations. De prochaines études dans le domaine du SMP pourront venir pallier certaines limites de cette thèse. Les équipes de recherche pourront utiliser le questionnaire et la grille d’entretien pour évaluer les besoins informationnels des femmes au sujet du SMP dans différents contextes (p.ex. pandémie de COVID-19). Maintenant qu’il a été déterminé que le SMP a un effet sur le développement de l’enfant, il serait utile de réaliser une revue de littérature pour recenser les interventions permettant d’estomper cet effet afin de bien outiller les femmes enceintes. Finalement, connaissant désormais les besoins informationnels des femmes enceintes, l’organisation d’un atelier délibératif avec les professionnels de la santé permettrait de mettre au point une stratégie de TC prenant également en compte leur réalité. En conclusion, cette thèse a permis de jeter les bases d’une stratégie de TC qui pourrait informer les femmes enceintes au sujet des conséquences du SMP associé aux catastrophes naturelles sans les stresser davantage.

Le stress prénatal maternel et les problèmes comportementaux chez les enfants : effet modérateur de la consistance de la discipline - Daniel, Benjhyna (2021)
Le stress prénatal maternel (SPM) est un concept largement étudié et ce, autant par de méthodes objectives que subjectives. Certains chercheurs évaluent les symptômes d’anxiété et de dépression des femmes au cours de leur grossesse alors que d’autres préfèrent mesurer les niveaux de cortisol des femmes enceintes. Pour cette thèse, le SPM a été mesuré par deux méthodes différentes, soit l’exposition des femmes enceintes à une catastrophe naturelle et l’exposition des mêmes femmes enceintes à des événements de vie stressants plus courants. Puisqu’il est bien établi que ce type de stress engendre des répercussions négatives sur la femme enceinte ainsi que sur le développement de l’enfant, il est désormais d’intérêt d’accentuer les recherches sur les moyens qui permettent d’atténuer les conséquences d’un tel stress. Dans les études auprès des animaux, nous savons que les conditions de maternage ainsi que l'enrichissement environnemental semblent renverser les effets du SPM, mais nous ne savons pas si, chez les humains, un bon encadrement parental, c’est-à-dire un cadre structuré avec des règles prévisibles et consistantes, peut protéger les enfants des effets du SPM. L’objectif de cette thèse est donc d’augmenter notre compréhension sur l’effet protecteur de l’encadrement parental dans le développement d’enfants qui ont été exposés à différents types de SPM. Cet objectif pourra être atteint grâce à une collaboration internationale initiée par la Dre Suzanne King suite aux inondations qui se sont produites en 2008 dans l'état d'Iowa. Suite à la catastrophe, la Dre King est entrée en contact avec le Dr O’Hara afin d'évaluer la sévérité du stress dû aux inondations chez les femmes enceintes et pour déterminer les effets de ce stress sur leur enfant. Trois types de stress ont été évalués: le degré objectif de difficulté (p. ex., pertes financières), l'évaluation cognitive de la catastrophe en tant qu'expérience négative, neutre ou positive, et la détresse subjective causée par l'inondation (p. ex., symptômes de TSPT). Suite au recrutement des mères, les enfants de l'échantillon ont été évalués à l’âge de 2, 4, 5 et 7 ans. La présente thèse est composée de trois études. La première étude porte sur l’effet modérateur de l’encadrement parental sur les associations entre le SPM causé par les inondations d’Iowa et les problèmes comportementaux chez les enfants âgés de sept ans. Les résultats indiquent qu’un encadrement parental où la discipline est consistante protège les garçons qui ont été exposés au SPM objectif contre différents symptômes de problèmes internalisés et externalisés. La deuxième étude se penche également sur la question de l’effet protecteur de l’encadrement parental sur les associations entre le SPM et les problèmes comportementaux chez les enfants âgés de sept ans. Toutefois, cette étude s’est plutôt penchée sur l’influence du SPM lorsque celui-ci est causé par des événements de vie qui sont plus communs qu’un désastre naturel. De nouveau, les résultats de cette étude nous révèlent qu’un encadrement parental consistant joue le rôle de facteur de protection, chez les garçons qui ont été exposés au SPM causé par des événements de vie stressants, mais seulement en ce qui concerne les problèmes de comportement externalisés. La troisième étude vient reconsidérer l’effet protecteur de l’encadrement parental sur les liens entre le SPM et les problèmes comportementaux des enfants qui ont été exposés à un désastre naturel. Cependant, pour cette étude, les comportements des enfants n’ont pas été évalués par un questionnaire, mais plutôt par une méthode observationnelle (tâche de frustration). Toutefois, dans cette étude, il n’est ressorti aucun effet significatif de l’encadrement parental comme variable modératrice. En somme, nos résultats rapportent que l’implantation d’un cadre structuré et consistant peut venir pallier et même renverser les conséquences du SPM sur le comportement des garçons.

Évaluation de cultures de couverture de pleine saison dans les champs agricoles inondés au lac Saint-Pierre - Chih, Colline (2021)
La perchaude est un poisson qui pond ses œufs sur les végétaux submergés dans le littoral du lac Saint-Pierre lors de la crue printanière. Cependant, les pratiques agricoles actuelles sur le littoral laissent souvent un sol nu à l'automne, ce qui cause la diminution des habitats de ponte des poissons. Ainsi, l'objectif de cette étude est d'évaluer des cultures de couverture (CC) de pleine saison qui pourraient servir de substrats potentiels pour la ponte des poissons au printemps et qui seraient compétitives envers les adventices. Un dispositif en tiroir systématique avec quatre blocs a été implanté à quatre années-sites. En parcelles principales, six traitements de CC ont été étudiés : le ray-grass vivace (Lolium perenne L.), le seigle d'automne (Secale cereale L.), un mélange de seigle d'automne et de trèfle rouge (Trifolium pratense L.), un mélange de seigle d'automne et de vesce velue (Vicia villosa Roth), un mélange d'avoine (Avena sativa L.), vesce velue et lin (Linum usitatissimum L.), et le témoin sans CC. Le facteur testé en sous-parcelle était le désherbage ou non des parcelles. Le mélange d'avoine, vesce velue et lin a produit le plus de biomasse aérienne (2,5 à 4,9 Mg ha⁻¹) tout en réduisant l'incidence des adventices de 33 à 82 % en comparaison avec le témoin non désherbé. Il est également le seul traitement pour lequel une partie de la biomasse aérienne est restée érigée après la crue à chaque année-site. Ainsi, ce type de CC pourrait constituer un substrat potentiel pour la ponte des perchaudes au printemps mais ce serait à confirmer par des mesures fauniques faites au printemps durant l'inondation. Avec un coût d'implantation peu élevé, le mélange avoine, vesce velue et lin est avantageux à la fois pour les agriculteurs et pour l'environnement.

Improving ensemble streamflow forecasts through targeted post-processing and rating curve uncertainty analysis - Askarinejad, Alireza (2024)
Abstract : Flood forecasting plays a pivotal role in effective water resource management and flood risk mitigation. Despite recent advancements, existing ensemble forecasting systems often grapple with issues of unreliability and under-dispersion. The uncertainty in ensemble forecasts can emanate from various sources, including inputs like precipitation, temperature, and streamflow, as well as initial conditions, model structure and parameters, and boundary conditions. Over the past two decades, numerous endeavors have been made to address bias and under-dispersion through the introduction of various statistical post-processing methods in meteorological and hydrological forecasts. However, a significant challenge lies in selecting the appropriate method and strategy in the forecast chain. Limited research has addressed the integration of pre-processing and post-processing in streamflow ensemble forecasting. Moreover, existing studies have generally focused on lumped hydrological models, while the performance of this integration in distributed hydrological models remains scarcely examined. On the other hand, streamflow data, often indirectly measured through rating curves, are particularly susceptible to errors. While various methods have been proposed to estimate rating curve uncertainty (RCU), the impact of RCU on streamflow forecasting system performance remains underexplored. In addition, current post-processing methods utilized in streamflow forecasting systems have disregarded the inherent uncertainty in observational streamflow data. Thus, this thesis delves into the potential and hurdles associated with considering different sources of uncertainty in flood forecasting systems and their impact on system performance. The primary objectives entail 1) assessing and identifying optimal scenarios from pre-processing of both temperature and precipitation and post-processing of streamflow forecasts approaches, or a combination thereof, and 2) evaluating the consideration of rating curve uncertainty on flood forecasting system performance through incorporating into targeted post-processing methodologies. The thesis focuses on a short-range ensemble streamflow forecasting framework spanning lead times of 1 to 5 days for the au Saumon watershed in southern Quebec, Canada. This watershed, being flood-prone, encountered significant challenges during the 2019 and 2017 flood events, including widespread inundation, road closures, and damage to property and infrastructure. Enhancing streamflow ensemble forecasts and upgrading flood forecasting systems holds the potential to greatly benefit decision-makers and the local populace. Chapter 4 (Results part 1), presented as a scientific article, thus delves into assessing and employing various pre- and post-processing strategy scenarios within the flood forecasting framework employing a spatially distributed hydrological model. By applying different statistical processing and bias correction techniques, the performance and quality of ensemble streamflow forecasts were evaluated across different scenarios. The findings highlight biases and under-dispersion as significant factors affecting raw ensemble forecasts. Pre-processing partially improves raw forecasts but doesn't fully address bias in under-dispersed forecasts. Combining pre- and post-processing enhances forecast skill and reliability, albeit with some variations compared to post-processing alone. Integrating flood events into the training dataset and optimizing its length improves the effectiveness of processing methods, underscoring the critical role of data management strategies in enhancing streamflow forecasting systems. Subsequently, Chapter 5 (Results part 2) , evaluates the consideration of rating curve uncertainty, derived from the Voting Point Method (VPM) and Bayesian Rating curve (BaRatin) estimation methods, on the performance of streamflow ensemble forecasts by integrating into a targeted post-processing approach using Weighted Ensemble Dressing (WED) and Cumulative Distribution Function Matching (CDFM) post-processing methods. Post-processing without RCU enhances forecasting system skill and reliability but overlooks the inherent uncertainty in observational data, posing concerns about its effectiveness. Conversely, integrating RCU improves forecast skill, reliability, and effectively addresses observational data uncertainty, offering a notable advantage over traditional post-processing methods. Comparing WED and CDFM post-processing methods highlighted nuanced differences in forecast outcomes, influenced by uncertainty estimation techniques. Both methods showed favorable accuracy metrics, with RCU integration, especially from VPM, notably enhancing forecast quality. However, variations in RCU from different estimation methods may lead to forecast underestimation or overestimation, warranting careful consideration. These findings collectively shed light on the potential and challenges associated with incorporating different sources of uncertainty into flood forecasting systems.

Investigating the modelling uncertainties associated with the generation of flood projections - Castaneda-Gonzalez, Mariana (École de technologie supérieure, 2022)
Extreme flood events continue to be one of the most threatening natural disasters around the world due to their pronounced social, environmental and economic impacts. Changes in the magnitude and frequency of floods have been documented during the last years, and it is expected that a changing climate will continue to affect their occurrence. Therefore, understanding the impacts of climate change through hydroclimatic simulations has become essential to prepare adaptation strategies for the future. However, the confidence in flood projections is still low due to the considerable uncertainties associated with their simulations, and the complexity of local features influencing these events. The main objective of this doctoral thesis is thus to improve our understanding of the modelling uncertainties associated with the generation of flood projections as well as evaluating strategies to reduce these uncertainties to increase our confidence in flood simulations. To address the main objective, this project aimed at (1) quantifying the uncertainty contributions of different elements involved in the modelling chain used to produce flood projections and, (2) evaluating the effects of different strategies to reduce the uncertainties associated with climate and hydrological models in regions with diverse hydroclimatic conditions. A total of 96 basins located in Quebec (basins dominated by snow-related processes) and Mexico (basins dominated by rain-related processes), covering a wide range of climatic and hydrological regimes were included in the study. The first stage consisted in decomposing the uncertainty contributions of four main uncertainty sources involved in the generation of flood projections: (1) climate models, (2) post-processing methods, (3) hydrological models, and (4) probability distributions used in flood frequency analyses. A variance decomposition method allowed quantifying and ranking the influence of each uncertainty source on floods over the two regions studied and by seasons. The results showed that the uncertainty contributions of each source vary over the different regions and seasons. Regions and seasons dominated by rain showed climate models as the main uncertainty source, while those dominated by snowmelt showed hydrological models as the main uncertainty contributor. These findings not only show the dangers of relying on single climate and hydrological models, but also underline the importance of regional uncertainty analyses. The second stage of this research project focused in evaluating strategies to reduce the uncertainties arising from hydrological models on flood projections. This stage includes two steps: (1) the analysis of the reliability of hydrological model’s calibration under a changing climate and (2) the evaluation of the effects of weighting hydrological simulations on flood projections. To address the first part, different calibration strategies were tested and evaluated using five conceptual lumped hydrological models under contrasting climate conditions with datasets lengths varying from 2 up to 21 years. The results revealed that the climatic conditions of the calibration data have larger impacts on hydrological model’s performance than the lengths of the climate time series. Moreover, changes on precipitation generally showed greater impacts than changes in temperature across all the different basins. These results suggest that shorter calibration and validation periods that are more representative of possible changes in climatic conditions could be more appropriate for climate change impact studies. Following these findings, the effects of different weighting strategies based on the robustness of hydrological models (in contrasting climatic conditions) were assessed on flood projections of the different studied basins. Weighting the five hydrological models based on their robustness showed some improvements over the traditional equal-weighting approach, particularly over warmer and drier conditions. Moreover, the results showed that the difference between these approaches was more pronounced over flood projections, as contrasting flood magnitudes and climate change signals were observed between both approaches. Additional analyses performed over four selected basins using a semi-distributed and more physically-based hydrological model suggested that this type of models might have an added value when simulating low-flows, and high flows on small basins (of about 500 km2). These results highlight once again the importance of working with ensembles of hydrological models and presents the potential impacts of weighting hydrological models on climate change impact studies. The final stage of this study focused on evaluating the impacts of weighting climate simulations on flood projections. The different weighting strategies tested showed that weighting climate simulations can improve the mean hydrograph representation compared to the traditional model “democracy” approach. This improvement was mainly observed with a weighting approach proposed in this thesis that evaluates the skill of the seasonal simulated streamflow against observations. The results also revealed that weighting climate simulations based on their performance can: (1) impact the floods magnitudes, (2) impact the climate change signals, and (3) reduce the uncertainty spreads of the resulting flood projection. These effects were particularly clear over rain-dominated basins, where climate modelling uncertainty plays a main role. These finding emphasize the need to reconsider the traditional climate model democracy approach, especially when studying processes with higher levels of climatic uncertainty. Finally, the implications of the obtained results were discussed. This section puts the main findings into perspective and identifies different ways forward to keep improving the understanding of climate change impacts in hydrology and increasing our confidence on flood projections that are essential to guide adaptation strategies for the future.

An urban political ecology of flood control and population relocation in Ouagadougou - Burkina Faso - Bamba, Madiara (Concordia University, 2022)
Globally, the number of people at risk from flooding has been increasing since 2000, with the population from the South being more vulnerable. Millions of households are displaced by disasters every year. In 2009, the city of Ouagadougou in Burkina Faso experienced its most disastrous flood ever recorded. As a response, the government designed a permanent relocation plan in Yagma, a village located outside the city of Ouagadougou. The relocation plan disrupted the livelihoods of the households that were affected by the flood, leading many of them to return and rebuild their houses in flood prone areas. This paper contributes to a body of literature analyzing the heritage of postcolonialism on the flood vulnerability on the poorer communities in Ouagadougou. Using a political ecology frame, the thesis attempts to understand how the government of Burkina Faso and flood victims understand land and belongings, and how that understanding shaped the relocation program. After interviewing flood victims and government officials, an analysis revealed that contrasting views are at work. A perspective based on technical calculations and a neo-colonialist vision of development, on the one hand, and a grounded perspective based on relationships to the land and each other, on the other.

La surimplication maternelle et l'anxiété chez l'enfant dans un contexte de stress prénatal maternel : une étude observationnelle de QF2011 Queensland Flood Study - Bucur, Alexandra (2021)
Les troubles anxieux apparaissent très tôt chez les jeunes. Les études corrélationnelles suggèrent que plusieurs facteurs, tels que le stress prénatal maternel (SPM) et la surimplication maternelle contribueraient à leur développement et à leur maintien. L’objectif de l’étude est de mieux comprendre si la surimplication maternelle est une cause ou une conséquence de l’anxiété chez l’enfant, le tout dans un contexte de stress prénatal maternel causé par un désastre naturel. L’échantillon fait partie d’un projet plus grand dans lequel les stress objectif et subjectif ont été mesurés chez les femmes enceintes lors de l’inondation en 2011 à Queensland en Australie. L’échantillon de l’étude inclut 72 dyades mère-enfant, ayant complété une tâche difficile de casse-tête, d’une durée de 5 minutes, lorsque les enfants étaient âgés de 4 ans. À partir des vidéos, les observateurs ont évalué le comportement maternel (la surimplication) et le comportement de l’enfant (l’anxiété) en continu. Des techniques d’analyse séquentielle ont été utilisées pour déterminer la probabilité qu’un comportement maternel de surimplication se produise avant ou après un comportement anxieux et vice versa. Les corrélations obtenues entre le SPM (objectif et subjectif), le comportement anxieux de l’enfant et le comportement de surimplication maternelle n’ont pas été significatives. Le comportement de surimplication n’est pas un médiateur entre le SPM (objectif et subjectif) et le comportement anxieux de l’enfant. Toutefois, les chances qu’un comportement maternel de surimplication suive un comportement anxieux chez l’enfant étaient plus grandes que les chances qu’un comportement anxieux suive un comportement maternel de surimplication. Nos résultats suggèrent que le stress prénatal maternel n’est pas associé avec le comportement de surimplication maternelle, ni avec le comportement anxieux de l’enfant. La surimplication maternelle est plutôt une réaction au comportement anxieux de l’enfant. Il est essentiel, pour de futures recherches, de se rappeler que l’enfant est un participant actif dans la relation mère-enfant et qu’il est important d’étudier la bidirectionnalité de la relation pour mieux comprendre et pour mieux intervenir.

Développement d’approches statistiques multivariées pour les modèles de copules, applications en hydrologie. - Ben Nasr, Iméne (Doctorat en sciences de l'eau, 2021)
Les études portant sur les évènements hydrologiques extrêmes sont d’une grande importance vu leurs nombreux impacts socio-économiques. Ces études reposent dans une large mesure sur la capacité à estimer adéquatement les risques associés à ces évènements. Dans ce cadre, l’analyse fréquentielle (AF) est une des approches les plus utilisées pour la modélisation et l’estimation des risques associés aux évènements extrêmes. Généralement, ces évènements sont caractérisés par plusieurs variables dépendantes, comme le volume, la pointe et la durée pour les crues. Par conséquent, l'analyse de chacune de ces variables séparément ne peut pas fournir une évaluation complète des risques et peut engendrer des pertes de vies humaines ou de biens associés à une sous estimation, ou une augmentation des coûts des ouvrages hydrauliques associés à une surestimation. L’AF multivariée (AFM) permet de pallier ce problème en considérant simultanément ces variables. L’AF classique est basée sur trois hypothèses à savoir l’homogénéité, la stationnarité et l’indépendance. Par ailleurs, différentes conditions non standards telles que la complexité topographique, les perturbations par les aménagements urbains et les changements climatiques peuvent influencer la réponse hydrologique. De telles conditions rendent la prédétermination des crues, par les méthodes classiques d’AFM, un exercice non efficace et mal adapté à de tels contextes. L’objectif de cette thèse consiste à proposer de nouvelles méthodes plus prometteuses pour l'analyse et la modélisation des variables hydrologiques à la fois dans un cadre multivarié et en l’absence de l’hypothèse d’homogénéité. Ces méthodes visent à contourner les limites de celles utilisées dans la littérature. Ces nouvelles méthodes, basées sur les copules, permettent une meilleure estimation des risques des extrêmes hydrologiques en tenant compte des interactions et es dépendances entre les différentes variables. Par conséquent, les gestionnaires des ressources hydriques peuvent prendre des décisions éclairées et mieux adaptées au contexte actuel. Précisément, nous nous intéressons dans une première partie à tester l’homogénéité des séries hydrologiques multivariées. Pour ce faire, nous avons proposé un nouveau test, basé sur les L moments multivariés, capable de détecter la rupture dans la structure de dépendance des variables hydrologiques. Les résultats obtenus montrent la bonne performance du test proposé sous différents scénarios. Par la suite, dans le but de modéliser l’hétérogénéité des séries hydrologiques multivariées, un modèle de mélange de copules a été mis au point. Dans ce cadre, nous avons proposé une nouvelle méthode pour l’estimation des différents paramètres du modèle. La méthode proposée est basée sur l’utilisation des algorithmes génétiques. Sa performance est illustrée sur des séries simulées. Les résultats obtenus montrent que la méthode proposée est un outil efficace capable de fournir de bonnes estimations, en particulier dans un contexte hydrologique. Finalement, deux nouveaux tests d’adéquation pour les copules multiparamètres ont été développés. Le but de ces tests est de vérifier la qualité de l’ajustement de la copule aux données et améliorer ainsi l’estimation des risques associés aux évènements extrêmes. Les résultats révèlent que les tests proposés performent bien dans le contexte hydrologique. Studies of hydrological extreme events are of great importance given their many socio-economic impacts. These studies rely on the ability to adequately estimate the associated risk. In this context, frequency analysis (FA) is one of the most widely used approaches for modeling and estimating the risks associated with extreme events. Generally, these events are characterized by several correlated random variables. Therefore, analyzing each of these variables separately cannot provide a complete risk assessment and may result in loss of life or property associated with an underestimation, or an increase in the costs of hydraulic structure associated with an overestimation. Multivariate FA (MFA) overcomes this problem by simultaneously considering these variables. Classical FA is based on three assumptions namely homogeneity, stationarity and independence. However, different non-standard conditions such as topographic complexity, disturbances by urban development and climate change can influence the hydrological response. Such conditions make flood predetermination, by conventional MFA methods, an ineffective exercise and unsuitable to such contexts. The main objective of this thesis is to propose new and more promising methods for the analysis and modeling of hydrological variables both in a multivariate framework and in the lack of the homogeneity assumption. These methods aim to overcome the limitations of classical methods used in the literature. These new proposed methods, based on copulas, allow a better estimation of the risks associated to hydrological extremes by taking into account the dependence between the different variables. As a result, water resource managers can make informed decisions that are better suited to the current context. In the first part, we propose a novel statistical test for multivariate heterogeneity detection, based on copula and multivariate L-moments. A simulation study is conducted to evaluate the performance of the proposed test and to compare it with those of existing tests. Results show the ability of the proposed test to discriminate homogeneous and inhomogeneous series. In the second part, we propose a new model based on mixtures of copulas that take into account the heterogeneity of multivariate hydrological series. To estimate the components of this model, we propose a new parameter estimation approach, based on the maximum pseudo-likelihood using genetic algorithms. Results indicate that the proposed method estimates more accurately the parameters even with small sample sizes compared to the existing classical EM method. In the last part, we introduce new goodness of fit (GOF) tests specifically for multiparameter copulas and adapted to hydrometeorological context. More precisely, the proposed GOF tests are based on multivariate L moments. A simulation study is conducted to evaluate and compare the performances of the proposed tests. The results confirm the usefulness of the new GOF tests in comparison with some well-established ones.

Évaluation de l'incertitude liée à la modélisation hydraulique au sein d'un système de prévision d'ensemble des niveaux d'eau - Bessar, Mohammed Amine (2021)
Les inondations présentent une grande menace à la sécurité humaine et matérielle. Les effets associés à ces phénomènes naturels risquent d'augmenter encore plus avec les tendances liées aux changements climatiques. Il est donc important de disposer d'outils de prévision et de prévention des crues fiables afin de mitiger les conséquences dévastatrices reliées. La mise en œuvre de ces outils implique des processus physiques assez complexes et nécessite beaucoup de données avec toute l'incertitude associée. Dans cette thèse, on explore les différentes sources d'incertitudes liée à la détermination des niveaux d'eau en rivières principalement dans un contexte de prévision où l'incertitude liée aux données de forçage est très importante. Les analyses conduites sont appliquées à la rivière Chaudière au Québec. En premier lieu, nous avons exploré les différentes sources paramétriques d'incertitude associées à la modélisation hydraulique dans un contexte de simulation avec un accent sur l'amélioration de la calibration du modèle hydraulique. Par la suite, dans un contexte de prévision opérationnel, on a évalué la propagation des sources d'incertitude de la prévision atmosphérique au modèle de rivière en passant par les prévisions hydrologiques avec des techniques probabilistes d'ensemble. La quantification de l'incertitude a montré que les données de forçage sont celles qui contribuent le plus à la description de l'incertitude dans la détermination des niveaux d'eau. L'incertitude paramétrique, dans un contexte de prévision, est quant à elle négligeable. Le recours à des prévisions d'ensemble a permis de produire une prévision de niveau d'eau assez fiable et a montré que celle-ci est fortement liée à la qualité des données qui proviennent de la chaine de prévision hydrométéorologique à l'amont du système de prévision proposé.

Developing an ensemble machine learning framework for enhanced climate projections using CMIP6 data in the Middle East - Khosravi, Younes; Ouarda, Taha B.M.J.; Homayouni, Saeid (npj Climate and Atmospheric Science, 2025)
Abstract Climate change in the Middle East has intensified with rising temperatures, shifting rainfall patterns, and more frequent extreme events. This study introduces the Stacking-EML framework, which merges five machine learning models three meta-learners to predict maximum temperature, minimum temperature, and precipitation using CMIP6 data under SSP1-2.6, SSP2-4.5, and SSP5-8.5. The results indicate that Stacking-EML not only significantly improves prediction accuracy compared to individual models and traditional CMIP6 outputs but also enhances climate projections by integrating multiple ML models, offering more reliable, regionally refined forecasts. Findings show R² improvements to 0.99 for maximum temperature, 0.98 for minimum temperature, and 0.82 for precipitation. Under SSP5-8.5, summer temperatures in southern regions are expected to exceed 45 °C, exacerbating drought conditions due to reduced rainfall. Spatial analysis reveals that Saudi Arabia, Oman, Yemen, and Iran face the greatest heat and drought impacts, while Turkey and northern Iran may experience increased precipitation and flood risks.
Keywords: Infolettre; Infolettre_Mai_2025

Meteorologically Related Factors Leading to the 2008, 2018, and 2019 Major Spring Floods in the Transboundary Saint John River (Wolastoq) Basin - Rickard, Lisa J.; Déry, Stephen J.; Stewart, Ronald E.; Thériault, Julie M. (Journal of Hydrometeorology, 2025)
Abstract The flood-prone Saint John River (SJR, Wolastoq), which lies within a drainage basin of 55 110 km 2 , flows a length of 673 km from its source in northern Maine, United States, to its mouth in southern New Brunswick, Canada. Major industries in the basin include forestry, agriculture, and hydroelectric power. During the 1991–2020 reference period, the SJR basin (SJRB) experienced major spring flood events in 2008, 2018, and 2019. As part of the Saint John River Experiment on Cold Season Storms, the objective of this research is to characterize and contrast these three major spring flood events. Given that the floods all occurred during spring, the hypothesis being tested is that rapid snowmelt alone is the dominant driver of flooding in the SJRB. There were commonalities and differences regarding the contributing factors of the three flood years. When averaged across the upper basin, they showed consistency in terms of positive winter and spring total precipitation anomalies, positive snow water equivalent anomalies, and steep increases in April cumulative runoff. Rain-on-snow events were a prominent feature of all three flood years. However, differences between flood years were also evident, including inconsistencies with respect to ice jams and high tides. Certain factors were present in only one or two of the three flood years, including positive total precipitation anomalies in spring, positive heavy liquid precipitation anomalies in spring, positive heavy solid precipitation anomalies in winter, and positive temperature anomalies in spring. The dominant factor contributing to peak water levels was rapid snowmelt.
Keywords: Infolettre; Infolettre_Mars_2025

An overcooled coarse‐grained talus slope at low elevation: New insights on air circulation and environmental impacts, Cannon Cliff, New Hampshire, USA - Germain, Daniel; Milot, Jean‐François (Earth Surface Processes and Landforms, 2024)
Abstract Overcooled talus slopes are generally described as islands of sporadic permafrost below the lower alpine limit of permafrost. The negative thermal anomaly of the ground is mainly consecutive to the internal ventilation of the deposit, but it is also conditioned by multiple factors as topography, slope aspect and incline, openwork structure and coarseness of the deposit, air temperature, solar radiation and wind regime. Therefore, the study of the spatiotemporal dynamics of ventilation processes allows a better understanding of the phenomenon. At Cannon Cliff, New Hampshire (USA), several field visits and environmental monitoring allowed us to describe the varying nature and significance of the ventilation mechanisms that can be observed at the ground surface and associated with both the intensity and direction of the airflows in a talus debris accumulation/protalus rampart system. The thermal negative anomalies are strong enough to lower the ground temperature to the point of preserving ice during the late spring and summer seasons. The monitoring of the gradient between external (air) and internal (talus) temperatures coupled with several dendroecological and geomorphological analyses provided a complete environmental picture of the impacts, feedback and extent of the phenomenon.

Farmers Perceptions of Climate Change Issues in Tetritskaro Municipality, Georgia - Elizbarashvili, Mariam; Kvirkvelia, Bela; Chikhradze, Nino; Germaın, Daniel; Pal, Jeremy; Khuntselia, Tamar (Selcuk Journal of Agricultural and Food Sciences, 2024)
Agriculture is the traditional and leading field of economy of Tetritskaro Municipality, but faces the challenge of changing climate. The study investigates male and female farmers’ perception of climate change issues in Tetritskaro, their main source of information, adaptation measures choosen and their needs. Climate change data available in Tetritskaro focused on characteristic extreme weather events coupled with face-to-face interviews from 254 farmers (male - 53%, female - 47%) was analyzed. The study revealed that men and women have more or less similar perceptions of climate change issues. For male farmers, the main source of information on climate, seasonal prediction and weather forecast is conversations with fellow farmers, and for female farmers it is indigenous knowledge of the local environment. Male and female farmers, have adapted to the changes in climate similarly applying measures such as pesticides, fertilizer and irrigation, early sowing, and earlier harvest, while the exchange of information between fellow farmers, use of various hail protection products and crop diversification techniques is more frequent among male farmers. Farmers expressed the need for low interest loans to purchase agricultural products, equipment and restore/create windbreak zones. Most of the male farmers indicate the need for introduction new technologies, while female farmers are more in need of information and training in agricultural activities. The study shows the need for development of climate change adaptation policies and interventions in Tetritskaro. Obtained results can be used not only in other agricultural regions of Georgia, but in other countries with the same problems. , Agriculture is the traditional and leading field of economy of Tetritskaro Municipality, but faces the challenge of changing climate. The study investigates male and female farmers’ perception of climate change issues in Tetritskaro, their main source of information, adaptation measures choosen and their needs. Climate change data available in Tetritskaro focused on characteristic extreme weather events coupled with face-to-face interviews from 254 farmers (male - 53%, female - 47%) was analyzed. The study revealed that men and women have more or less similar perceptions of climate change issues. For male farmers, the main source of information on climate, seasonal prediction and weather forecast is conversations with fellow farmers, and for female farmers it is indigenous knowledge of the local environment. Male and female farmers, have adapted to the changes in climate similarly applying measures such as pesticides, fertilizer and irrigation, early sowing, and earlier harvest, while the exchange of information between fellow farmers, use of various hail protection products and crop diversification techniques is more frequent among male farmers. Farmers expressed the need for low interest loans to purchase agricultural products, equipment and restore/create windbreak zones. Most of the male farmers indicate the need for introduction new technologies, while female farmers are more in need of information and training in agricultural activities. The study shows the need for development of climate change adaptation policies and interventions in Tetritskaro. Obtained results can be used not only in other agricultural regions of Georgia, but in other countries with the same problems.

Design Optimization of Concrete Gravity Dam Subjected to Near-field Earthquake Based on Novel Lean-bubble Sort Approach - Faghfouri, Ali; Germain, Daniel; Fortin, Guillaume (KSCE Journal of Civil Engineering, 2024)
Due to limitations in traditional concrete gravity dam (CGD) design, a new approach is necessary. In this study, the lean analysis as a novel approach for CGD design, considering the interaction between dam and reservoir was considered. Maximum and minimum stresses at the heel and displacement of the crest were obtained as crucial input values of bubble sorting based on seismic analysis using Finite element analysis (FEA), and the Fuzzy Analytic Hierarchy Process (FAHP). The fuzzy bubble sorting analytic process, aimed at developing a novel method for selecting the best CGD configuration, was developed. Required Criteria, Sub-Criteria and developed models were applied to optimize the body of CGD. The weight of each sub-criterion and models were calculated based on pairwise comparison matrices. The novel approach was designed in MATLAB with the OPT-CGD code to select the best CGD model. The best weight of the Criteria, for selecting the best CGD model, based on the lean construction principles was selected from 60 developed models under implicit dynamic analysis. Statistical analysis reveals a 20% reduction in the concrete mass of the case study’s optimal body compared to the traditionally designed dam.

Quel regard porter sur le travail social à l’ère des changements climatiques? : le cas des inondations (2017-2019) au Québec - Hamelin, Marilou (2021)
Les changements climatiques anthropogéniques posent des défis énormes pour toutes les sociétés humaines. Ces défis majeurs mettront à l’épreuve les capacités d’adaptation des États et de ses institutions et des communautés partout dans le monde et devront se résoudre par un élan de solidarité humaine afin d’en atténuer les conséquences. Le Canada connaît déjà un réchauffement climatique important. Le pays a d’ailleurs récemment été touché par des événements climatiques extrêmes : des canicules, des feux de forêt, une sécheresse anormale et des inondations dont l’intensité est prévue d’augmenter avec les changements climatiques anthropogéniques. La province du Québec a quant à elle été touchée par de fortes inondations entre 2017 et 2019. L’objectif principal de la présente étude vise à discuter la manière dont le paradigme écosocial peut faire évoluer le travail social en tant que champ de savoir et d’intervention dans un contexte de changements climatiques. Cette étude s’est appuyée sur des données issues de groupes focus réalisés avec des intervenants suite aux inondations survenues au Québec (2017-2019). Notre analyse vise les interventions réalisées en contexte d’inondations, dans le sud de la province, mise en œuvre par le système de santé. Les données ont été collectées lors d’entrevues de groupe réalisées avec des intervenants psychosociaux et des gestionnaires de CI(U)SSS au courant des mois d’octobre et de novembre 2019. Les thèmes suivants ont émergé des analyses: les caractéristiques des inondations de 2019, les divergences d’opinions vis-à-vis des changements climatiques, l’aide et le soutien apportés durant les inondations et la participation citoyenne. J’insisterai également sur l’exacerbation possible des inégalités sociales dans ce contexte. D’autres thèmes se sont également révélés importants : l’engagement des intervenants psychosociaux, la participation et la décentralisation des décisions politiques. Enfin, mes réflexions porteront sur les conséquences sociales qu’entrainent les inondations et sur les types de pratiques sociales qui s’avèrent pertinentes à l’ère des changements climatiques et dans un contexte d’urgence.

L’évaluation du fonctionnement social aux temps des changements climatiques : l’importance des injustices environnementales - St-Amour, N; Hamel, A (L’intégration de l’évaluation du fonctionnement social à la pratique en travail social, 2024)

L’intervention individuelle et collective sous le prisme du travail écosocial - Larocque, E; Hamel, A; St-Amour, N (Mettre en œuvre le travail social de demain : renouvellement et défis de l’intervention sociale, 2024)

Processus de rétablissement et attachement au lieu dans un contexte de cumul d’inondations : perspective des résident.es d’un quartier socioéconomiquement défavorisé de Gatineau - Hamel, Ariane (Université du Québec en Outaouais, 2024)
Dans la dernière décennie, le Québec a été touché par plusieurs épisodes d’inondations majeures. C’est le cas des communautés riveraines de Pointe-Gatineau, frappées par des inondations historiques en 2017, 2019 et 2023. Depuis, le départ d’une grande partie des riverains de ce quartier socio-économiquement défavorisé et la destruction de plusieurs maisons laissent un grand vide. La présence de nombreux lots vacants amène de l’incertitude parmi les citoyen.nes qui sont resté.es, dans ce qui est considéré comme l’un des plus vieux quartiers de Gatineau (Conseil régional de l'environnement et du développement durable de l'Outaouais, 2021). Bien que ce domaine d’étude soit en émergence, on observe dans la littérature que l’attachement des individus à leur milieu suivant une ou des catastrophes exercerait une influence sur leur processus de rétablissement. Cette étude s’intéresse donc au processus de rétablissement d’individus provenant d’un quartier socioéconomiquement défavorisé qui ont vécu un cumul d’inondations, et au rôle de l’attachement au lieu dans ce processus. Cette recherche mobilise le cadre de désorientation et de réorientation proposé par Cox et Perry (2011) pour expliquer le processus de rétablissement d’individus dans un lieu modifié par un désastre. L’attachement au lieu est conceptualisé en fonction des dimensions recensées par Raymond et ses collègues (2010) et du sentiment d’être chez soi par Cox et Perry (2011). Quatorze personnes sinistrées qui ont vécu les inondations de 2017 et de 2019 dans le quartier de Pointe-Gatineau ont été rencontrées lors d’entrevues individuelles ou familiales en 2023. Parmi ce nombre, neuf demeurent encore dans les communautés riveraines de Pointe-Gatineau, alors que cinq ont quitté le quartier après les inondations de 2019. Les résultats révèlent que l’attachement au lieu joue un rôle prédominant dans le processus de rétablissement des sinistré.es. Selon les participant.es, l’attachement au lieu contribue à l’étape de désorientation ou favorise au contraire la réorientation. Les résultats soulignent en particulier que l’attachement que les participant.es ressentent envers leur domicile et leur environnement naturel et bâti constitue une motivation importante à vouloir demeurer dans le quartier inondable. Par contre, la recherche montre que des facteurs autres que la relation au lieu influencent également le processus de rétablissement, tels que la difficulté à naviguer dans les démarches administratives entourant les programmes d’indemnisation du gouvernement, le fait d’appartenir à un groupe vulnérable, le soutien social et certaines caractéristiques personnelles. De même, l’expérience de vivre plusieurs inondations amène des spécificités qui influencent elles aussi le processus de rétablissement. Les résultats dévoilent notamment des stratégies d’adaptation mises en place par les personnes participantes qui ont décidé de demeurer dans leur quartier. Les stratégies acquises avec l’expérience font en sorte qu’elles se sentent davantage préparées pour des éventuelles inondations. Cette recherche contribue à la littérature émergente qui s’intéresse au processus de rétablissement d’individus touchés par un cumul d’inondations et au rôle de l’attachement au lieu sur ce processus. Elle permet d’offrir des pistes de réflexion aux différents acteurs qui accompagnent les personnes sinistrées avant, pendant et après des inondations et propose des recommandations en ce sens.

Les bonnes pratiques d’interventions psychosociales à adopter lors d’inondation et les facteurs organisationnels favorisant leur bonne marche : point de vue d’intervenantes et d’intervenants de première et deuxième lignes - Maltais, Danielle; Hamel, Ariane; Lansard, Anne-Lise (Reflets, 2024)
En 2017 et en 2019, le Québec a vécu des inondations ayant provoqué d’importants dommages dans plus de 300 municipalités. Ces inondations ont mobilisé un grand nombre d’intervenantes et d’intervenants sociaux et municipaux afin d’assurer la sécurité et le bien-être des personnes sinistrées. Cet article présente le point de vue de ces personnes en lien avec les interventions psychosociales mises en place s’étant avérées efficaces pour atténuer ou prévenir l’apparition de problèmes de santé chez les individus sinistrés, ainsi que les facteurs organisationnels qui ont favorisé leur bon déroulement. Plusieurs types d’intervention psychosociale semblent avoir le potentiel de prévenir la détérioration de l’état de santé et le fonctionnement social des personnes sinistrées, dont l’adoption de l’approche « reaching out » et la mise en place d’équipes dédiées au rétablissement. , The floods that hit the province of Quebec in 2017 and 2019 resulted in significant damage to over 300 municipalities. Many social and municipal stakeholders were mobilized to ensure the safety and well-being of those affected by these floods. This article presents their point of view regarding the psychosocial interventions implemented. Interventions such as these have proven successful in mitigating or preventing health problems among disaster victims, as well as facilitating smooth operations. Psychosocial interventions, such as the “Reaching Out” approach and the creation of dedicated recovery teams, appear to be effective in preventing deterioration in the health status and social functioning of disaster victims.

Entre hydroélectricité, érosion et loisir: L’espace amphibien d’un réservoir navigable - Bouchard-Bastien, Emmanuelle (Anthropologie et Sociétés, 2023)

Espaces amphibiens, pouvoir et mémoire: les fluctuations de la rivière Sainte-Anne - Bouchard-Bastien, Emmanuelle (2023)
This thesis examines the main socio-environmental relationships related to recurrent floodings in the Sainte-Anne River watershed by mobilizing the history of land use, local knowledge and risk management policies. From a political ecology perspective, these relationships are part of both social representations of nature, power dynamics associated with the appropriation of ressources and multiple temporalities. By also mobilizing the theoreticals frameworks of the anthropology of disasters and amphibian anthropology, this study allow to retrace step by step what “flood zone” is as a socially constructed space by the authorities, and go back to the source of the advent of “flood” as a catastrophic event, where rising waters have been part of the characteristics of these territories since the beginning of the sedentarization of its inhabitants. Based on 93 semi-directed interviews (76 residents and 17 institutions stakeholders) realized between February to October 2019, non-participant observation and documentary research in municipal and regional archives, this ethnography of the Sainte-Anne River watershed allows a unique incursion with Quebec riverside residents who live with recurrent rising waters. Through four case studies (Saint-Raymond, Saint-Alban, Saint-Casimir and Sainte-Anne-de-la-Pérade), historical contexts of occupation of the territory were documented and significant events were described by focusing on local residents adaptation strategies and anticipated management by institutional stakeholders. The result is a portrait, in a temporal perspective, of the relationship of cohabitation between residents and the river and its overflows. This cohabitation is characterized by tensions and paradoxes associated with different social representations of water and temporality that coexist within the actors, as well as changes in power relations towards the environment. Cette thèse examine les principaux rapports socio-environnementaux liés aux inondations récurrentes dans le bassin versant de la rivière Sainte-Anne en mobilisant l’histoire de l’occupation du territoire, les savoirs locaux et les politiques de gestion des risques. Dans une perspective d’écologie politique, ces rapports s’inscrivent à la fois dans les représentations sociales de la nature, les dynamiques de pouvoir associées à l’appropriation des ressources et des temporalités multiples. En puisant également dans les cadres théoriques de l’anthropologie des catastrophes et de l’anthropologie amphibienne, cette étude permet notamment de retracer pas à pas ce qu’est la « zone inondable » en tant qu’espace construit socialement par les autorités, et de remonter à la source de l’avènement de « l’inondation » comme étant un événement catastrophique, alors que la montée des eaux fait partie des caractéristiques de ces territoires depuis le début de la sédentarisation des habitants. Basée sur 93 entrevues semi-dirigées (76 riverains et 17 acteurs institutionnels) menées de février à octobre 2019, de l’observation non participante et une recherche documentaire dans les archives municipales et régionales, cette ethnographie du bassin versant de la rivière Sainte-Anne permet une incursion unique auprès de citoyens québécois qui vivent avec la montée récurrente des eaux. Pour quatre municipalités riveraines (Saint-Raymond, Saint-Alban, Saint-Casimir et Sainte-Anne-de-la-Pérade), les contextes historiques de l’occupation du territoire ont été documentés et les événements significatifs ont été décrits en focalisant sur les stratégies d’adaptation des résidents et la gestion menée par des acteurs institutionnels. En résulte un portrait, dans une perspective temporelle, de la relation de cohabitation entre les riverains et la rivière et ses débordements. Cette cohabitation est caractérisée par des tensions et des paradoxes associés aux différentes représentations sociales de l’eau et de la temporalité qui coexistent au sein des acteurs, ainsi qu’aux changements dans les rapports de pouvoir envers l’environnement.
Keywords: Infolettre; Infolettre_Mars_2023

Impact of Hydrometeorological Events for the Selection of Parametric Models for Protozoan Pathogens in Drinking‐Water Sources - Sylvestre, Émile; Burnet, Jean‐Baptiste; Dorner, Sarah; Smeets, Patrick; Medema, Gertjan; Villion, Manuela; Hachad, Mounia; Prévost, Michèle (Risk Analysis, 2021)
Abstract Temporal variations in concentrations of pathogenic microorganisms in surface waters are well known to be influenced by hydrometeorological events. Reasonable methods for accounting for microbial peaks in the quantification of drinking water treatment requirements need to be addressed. Here, we applied a novel method for data collection and model validation to explicitly account for weather events (rainfall, snowmelt) when concentrations of pathogens are estimated in source water. Online in situ β ‐ d ‐glucuronidase activity measurements were used to trigger sequential grab sampling of source water to quantify Cryptosporidium and Giardia concentrations during rainfall and snowmelt events at an urban and an agricultural drinking water treatment plant in Quebec, Canada. We then evaluate if mixed Poisson distributions fitted to monthly sampling data ( = 30 samples) could accurately predict daily mean concentrations during these events. We found that using the gamma distribution underestimated high Cryptosporidium and Giardia concentrations measured with routine or event‐based monitoring. However, the log‐normal distribution accurately predicted these high concentrations. The selection of a log‐normal distribution in preference to a gamma distribution increased the annual mean concentration by less than 0.1‐log but increased the upper bound of the 95% credibility interval on the annual mean by about 0.5‐log. Therefore, considering parametric uncertainty in an exposure assessment is essential to account for microbial peaks in risk assessment.
Keywords: Dorner_Sarah

Using surrogate data to assess risks associated with microbial peak events in source water at drinking water treatment plants - Sylvestre, Émile; Prévost, Michèle; Burnet, Jean-Baptiste; Smeets, Patrick; Medema, Gertjan; Hachad, Mounia; Dorner, Sarah (Water Research, 2021)
Keywords: Dorner_Sarah

Comparative study of deterministic and probabilistic assessments of microbial risk associated with combined sewer overflows upstream of drinking water intakes - Kammoun, Raja; McQuaid, Natasha; Lessard, Vincent; Prévost, Michèle; Bichai, Françoise; Dorner, Sarah (Environmental Challenges, 2023)
Keywords: Dorner_Sarah

Evidence-Based Framework to Manage Cyanobacteria and Cyanotoxins in Water and Sludge from Drinking Water Treatment Plants - Jalili, Farhad; Moradinejad, Saber; Zamyadi, Arash; Dorner, Sarah; Sauvé, Sébastien; Prévost, Michèle (Toxins, 2022)
Freshwater bodies and, consequently, drinking water treatment plants (DWTPs) sources are increasingly facing toxic cyanobacterial blooms. Even though conventional treatment processes including coagulation, flocculation, sedimentation, and filtration can control cyanobacteria and cell-bound cyanotoxins, these processes may encounter challenges such as inefficient removal of dissolved metabolites and cyanobacterial cell breakthrough. Furthermore, conventional treatment processes may lead to the accumulation of cyanobacteria cells and cyanotoxins in sludge. Pre-oxidation can enhance coagulation efficiency as it provides the first barrier against cyanobacteria and cyanotoxins and it decreases cell accumulation in DWTP sludge. This critical review aims to: (i) evaluate the state of the science of cyanobacteria and cyanotoxin management throughout DWTPs, as well as their associated sludge, and (ii) develop a decision framework to manage cyanobacteria and cyanotoxins in DWTPs and sludge. The review identified that lab-cultured-based pre-oxidation studies may not represent the real bloom pre-oxidation efficacy. Moreover, the application of a common exposure unit CT (residual concentration × contact time) provides a proper understanding of cyanobacteria pre-oxidation efficiency. Recently, reported challenges on cyanobacterial survival and growth in sludge alongside the cell lysis and cyanotoxin release raised health and technical concerns with regards to sludge storage and sludge supernatant recycling to the head of DWTPs. According to the review, oxidation has not been identified as a feasible option to handle cyanobacterial-laden sludge due to low cell and cyanotoxin removal efficacy. Based on the reviewed literature, a decision framework is proposed to manage cyanobacteria and cyanotoxins and their associated sludge in DWTPs.
Keywords: Dorner_Sarah

Automated Targeted Sampling of Waterborne Pathogens and Microbial Source Tracking Markers Using Near-Real Time Monitoring of Microbiological Water Quality - Burnet, Jean-Baptiste; Habash, Marc; Hachad, Mounia; Khanafer, Zeinab; Prévost, Michèle; Servais, Pierre; Sylvestre, Emile; Dorner, Sarah (Water, 2021)
Waterborne pathogens are heterogeneously distributed across various spatiotemporal scales in water resources, and representative sampling is therefore crucial for accurate risk assessment. Since regulatory monitoring of microbiological water quality is usually conducted at fixed time intervals, it can miss short-term fecal contamination episodes and underestimate underlying microbial risks. In the present paper, we developed a new automated sampling methodology based on near real-time measurement of a biochemical indicator of fecal pollution. Online monitoring of β-D-glucuronidase (GLUC) activity was used to trigger an automated sampler during fecal contamination events in a drinking water supply and at an urban beach. Significant increases in protozoan parasites, microbial source tracking markers and E. coli were measured during short-term (<24 h) fecal pollution episodes, emphasizing the intermittent nature of their occurrence in water. Synchronous triggering of the automated sampler with online GLUC activity measurements further revealed a tight association between the biochemical indicator and culturable E. coli. The proposed event sampling methodology is versatile and in addition to the two triggering modes validated here, others can be designed based on specific needs and local settings. In support to regulatory monitoring schemes, it should ultimately help gathering crucial data on waterborne pathogens more efficiently during episodic fecal pollution events.
Keywords: Dorner_Sarah

Pour une défense collective face à la fatigue pandémique: L’urgence de renforcer les facteurs protecteurs - Généreux, Mélissa; Blouin-Genest, Gabriel; Landaverde, Elsa; Torres Orozco, Et Natalia (Global Health Promotion, 2024)
Résumé: De nombreux articles publiés récemment ont laissé apparaître l’émergence d’un nouveau phénomène dans notre rapport avec la pandémie de COVID-19 : la fatigue pandémique. Ce phénomène suggère l’apparition d’une tendance générale de lassitude face aux mesures sanitaires et à l’état d’urgence devenu permanent. L’objectif de cet article est de replacer cet enjeu dans le contexte de la réalisation d’un projet de recherche portant sur les impacts psychosociaux durant la pandémie. Si relativement peu de recherches se sont intéressées à la fatigue pandémique, la réalité de ce phénomène a été mise en évidence dans le cadre d’un projet de recherche multi-annuelle effectuée durant la pandémie. En termes de méthode, notre équipe multidisciplinaire à l’Université de Sherbrooke a développé un protocole d’enquête permettant d’évaluer les effets de la pandémie de COVID-19 sur la santé mentale à travers des études transversales répétées. La dernière phase de l’enquête inclut un volet additionnel qui cherche à comprendre de quelle manière les conséquences de la pandémie peuvent s’appliquer à d’autres crises systémiques, notamment aux changements climatiques. Différentes vagues d'enquêtes nationales et internationales ont ainsi été réalisées (8 pays, taille minimale de l’échantillon 1000–1500 et échantillonnage par quota mis en oeuvre adapté à chaque pays et basé sur les données démographiques disponibles), et suivant l’évolution de la pandémie, nous avons introduit la notion de fatigue pandémique, ainsi que de fatigue climatique, afin de pouvoir mesurer l’impact de l’exposition prolongée à ces crises mondiales. Ces nouvelles données confirment nos résultats originaux : l’impact psychosocial de la pandémie est immense, en particulier en termes de fatigue pandémique, phénomène qui se retrouve à la fois au niveau comportemental et informationnel. Cette fatigue est un indicateur important à considérer afin d’améliorer notre capacité de réaction et d’adaptation à cette crise, mais également à celles futures.
Keywords: Généreux_Mélissa

Quantifying the Probability of Decline in Quality: Implications for Selection Management in Northern Hardwood Forests - Moreau, Guillaume; Cecil-Cockwell, Malcolm J. L.; Achim, Alexis; Bédard, Steve; Guillemette, François; Caspersen, John (Forests, 2023)
Northern hardwoods are susceptible to a wide range of defects that can reduce the amount of sound wood with desirable qualities, such as the clear sapwood of sugar maple trees. Yet, the rate at which trees decline in quality due to the development of such defects has never been quantified in northern hardwood forests due to a dearth of repeat inventories that record the appearance of defects over time. As a result, it remains uncertain whether, and how, selection management reduces the probability of decline in quality. In this study, we quantify the rate at which trees decline in quality due to the development of defects, and we test several hypotheses regarding the influence of selection management on quality. Our results show that (1) the probability of decline in quality increases as trees grow larger; (2) crown dieback also increases the probability of decline in quality; (3) the probability of decline in quality is slightly lower in managed stands than in unmanaged stands, and (4) the probability of decline in quality increases with the mean annual temperature of the site. Finally, we combined our estimates of the probability of decline in quality with previous estimates of the probability of mortality to assess the overall risk associated with retaining trees of different species, sizes, and vigour profiles. The resulting metric can inform efforts to improve the management of northern hardwood forests by providing an integrated estimate of the risk that the value of a tree will be reduced, or eliminated, due to mortality or decline in quality.
Keywords: Guillemette_Francois

How many plots are needed to estimate sapling density and stocking in temperate forests? - Guillemette, François; Lambert, Marie-Claude; Power, Hugues; Raymond, Patricia (The Forestry Chronicle, 2023)
Performing a complete silvicultural diagnosis before a silvicultural treatment generally requires assessing the state of regeneration with the help of an inventory by sampling, particularly for stands dominated by sugar maple (Acer saccharum Marsh.) or yellow birch (Betula alleghaniensis Britt.), in which partial cuts are recommended. This inventory may then be compared to the standard or used in a growth model for saplings (trees for which the diameter measured at 1.3 m above the ground (DBH) varies from 1.1 cm to 9.0 cm). Some of these tools are based on sapling density, while others are based on the stocking of the saplings or on the stocking of total regeneration (combining saplings and seedlings with a DBH ≤ 1.0 cm). We assessed the number of plots required to estimate the density and the stocking of saplings with a given margin of error in 28 stands. The results show that more plots are required than usual in practice to inventory sapling density. The stocking is much easier to estimate precisely.
Keywords: Guillemette_Francois

Reviews and syntheses: Recent advances in microwave remote sensing in support of terrestrial carbon cycle science in Arctic–boreal regions - Mavrovic, Alex; Sonnentag, Oliver; Lemmetyinen, Juha; Baltzer, Jennifer L.; Kinnard, Christophe; Roy, Alexandre (Biogeosciences, 2023)
Abstract. Spaceborne microwave remote sensing (300 MHz–100 GHz) provides a valuable method for characterizing environmental changes, especially in Arctic–boreal regions (ABRs) where ground observations are generally spatially and temporally scarce. Although direct measurements of carbon fluxes are not feasible, spaceborne microwave radiometers and radar can monitor various important surface and near-surface variables that affect terrestrial carbon cycle processes such as respiratory carbon dioxide (CO2) fluxes; photosynthetic CO2 uptake; and processes related to net methane (CH4) exchange including CH4 production, transport and consumption. Examples of such controls include soil moisture and temperature, surface freeze–thaw cycles, vegetation water storage, snowpack properties and land cover. Microwave remote sensing also provides a means for independent aboveground biomass estimates that can be used to estimate aboveground carbon stocks. The microwave data record spans multiple decades going back to the 1970s with frequent (daily to weekly) global coverage independent of atmospheric conditions and solar illumination. Collectively, these advantages hold substantial untapped potential to monitor and better understand carbon cycle processes across ABRs. Given rapid climate warming across ABRs and the associated carbon cycle feedbacks to the global climate system, this review argues for the importance of rapid integration of microwave information into ABR terrestrial carbon cycle science.
Keywords: Kinnard_Christophe

Impacts of summer and winter conditions on summer river low flows in low elevation, snow-affected catchments - Kinnard, Christophe; Bzeouich, Ghada; Assani, Ali (Journal of Hydrology, 2022)
Reduced snow storage has been associated with lower river low flows in mountainous catchments, exacerbating summer hydrological droughts. However, the impacts of changing snow storage on summer low flows in low-elevation, snow-affected catchments has not yet been investigated. To address this knowledge gap, the dominant hydroclimate predictors of summer low flows were first identified through correlation analysis in 12 tributary catchments of the St. Lawrence River in the Canadian province of Quebec. The correlation results show that summer low flow is most sensitive to summer rainfall, while maximum snow water equivalent (SWE) is the dominant winter preconditioning factor of low flows, particularly at the end of summer. The multivariate sensitivity of summer low flow to hydroclimate predictors was then quantified by multilevel regression analysis, considering also the effect of catchment biophysical attributes. Accumulated rainfall since snow cover disappearance was found to be the prime control on summer low flow, as expected for the humid climate of Quebec. Maximum SWE had a secondary but significant positive influence on low flow, sometimes on the same order as the negative effect of evapotranspiration losses. As a whole, our results show that in these low elevation catchments, thicker winter snowpacks that last longer and melt slower in the spring are conducive to higher low flows in the following summer. More rugged and forested catchments with coarser soils were found to have higher summer low flows than flatter agricultural catchments with compacted clayed soils. This emphasizes the role of soils and geology on infiltration, aquifer recharge and related river baseflow in summer. Further climate warming and snowpack depletion could reduce future summer low flow, exacerbating hydrological droughts and impacting ecosystems integrity and ecological services.
Keywords: Infolettre; Infolettre_Juillet_2022; Kinnard_Christophe; Site_internet_RIISQ

Association between Beverage Consumption and Sleep Quality in Adolescents - Vézina-Im, Lydi-Anne; Beaulieu, Dominique; Turcotte, Stéphane; Turcotte, Anne-Frédérique; Delisle-Martel, Joannie; Labbé, Valérie; Lessard, Lily; Gingras, Mariane (Nutrients, 2024)
The objective of this study was to verify if the consumption of different beverages (such as water, 100% pure fruit juice, and sugar-sweetened beverages (SSBs)) is associated with adolescents’ sleep quality. French-speaking adolescents were recruited in person and online throughout the province of Québec (Canada) from the end of March to early July 2023. Beverage consumption and sleep quality were measured using French versions of validated questionnaires specifically designed for adolescents. A total of 218 adolescents (14–17 years; 55.5% female) completed the online survey. Among caffeinated SSBs, energy drink (rs = −0.16; p = 0.0197) and sugar-sweetened coffee (rs = −0.33; p < 0.0001) intake was correlated with adolescents’ sleep quality. Energy drink consumption (β = −0.0048; p = 0.0005) and being male (β = 0.6033; p < 0.0001) were associated with adolescents’ sleep quality. There was an interaction between sugar-sweetened coffee intake and biological sex that was associated with adolescents’ sleep quality (p = 0.0053). Sugar-sweetened coffee consumption was correlated with adolescent girls’ abilities to go to bed (rs = −0.21; p = 0.0203) and fall asleep (rs = −0.28; p = 0.0020), while in boys, it was only significantly correlated with their abilities to go to bed (rs = −0.27; p = 0.0069). Public health interventions aimed at adolescent boys should primarily target lowering energy drink consumption, while those aimed at girls should prioritize sugar-sweetened coffee intake to possibly improve their sleep quality.
Keywords: FRQ_S; Lessard_Lily

Invisible informal housing in the Global South - Lizarralde, Gonzalo; Fauveaud, Gabriel (Research Handbook on Housing, the Home and Society, 2024)
Keywords: Lizarralde_Gonzalo

Artefacts of disaster risk reduction: conceptualizing bottom-up initiatives of climate action in informal settlements - Lizarralde, Gonzalo; Herazo, Benjamín; Smith, David; Bornstein, Lisa; Gould, Kevin; Monsalve, Elsa; Ordoñez, Nicolás; López, Adriana; López, Oswaldo; Burdiles, Roberto; Araneda, Claudio; Olivera, Andrés (Disaster Prevention and Management: An International Journal, 2024)
Purpose Disaster risk reduction is of prime importance in informal settlements in the Global South, where several forms of vulnerability coexist. Policy and official programmes, however, rarely respond to the needs and expectations of citizens and local leaders living in these settlements. Even though these agents constantly attempt to reduce risks in their own way, we know very little about their activities, motivations and effective impact on risk reduction. Here we seek to conceptualize bottom-up initiatives to better grasp their origins, limitations and success. Design/methodology/approach Through a four-year action-research project in Colombia, Cuba and Chile, we theorize about the production of change by local agents. Through detailed case studies we explored the activism of 17 local leaders. Through narrative analysis we studied their motivations and explanations. Finally, by documenting 22 initiatives, we revealed effective changes in space. Findings In the face of risk and disasters, residents and leaders in informal settings engaged in symbolic, physical and social spaces of interaction. Their actions were guided by trust, emotions, time cycles and activism. Local agency was justified by narratives about risk and climate change that differ from those of authorities and scholars. Research limitations/implications There is still limited understanding of bottom-up initiatives in informal settings. It is crucial to conceptualize their origins, limitations and success. The focus on three specific countries necessitates further research for broader applicability and understanding. Practical implications A better comprehension of bottom-up actions is crucial for informing policies and programmes aimed at reducing risk in informal settings. Stakeholders must recognize the political, social and cultural roles of these actions for more impactful climate action. Originality/value We borrow Simon’s concept of “artefact” to introduce the notion of “Artefacts of Disaster Risk Reduction”, providing insights into the multifaceted nature of bottom-up initiatives. We also emphasize the simultaneous political and phenomenological character of these actions, contributing to a deeper understanding of their origins and impact.
Keywords: Infolettre; Infolettre_Ete_2024; Lizarralde_Gonzalo

The problem with net zero building policy: reflecting on the making, and future, of a global discourse - Hasan, L; Lizarralde, G; Lachapelle, E (IOP Conference Series: Earth and Environmental Science, 2023)
Abstract The Paris Agreement made net zero emissions a global target. In response, net zero carbon building standards have proliferated, making net zero a popular target for buildings. But to meaningfully contribute to global decarbonization efforts, net zero standards and the organizations who promote them, must be deemed legitimate. Given the building industry’s reputation for being highly fragmented and slow to change, how has this legitimacy been constructed? What are the implications of this legitimation process? This article seeks to answer these questions by exploring the narratives used by the World Green Building Council (WGBC) to legitimate Net Zero Carbon Buildings (NZCB) from 2015 to 2021. Our analysis is based on over 100 documents produced by the WGBC and 22 interviews with WGBC and Green Building Council representatives, policymakers, and industry actors. Results reveal six main storylines adopted by the WGBC to extend the legitimacy of sustainable green building movement actors to the new net zero governance space. This legitimation process allows the WGBC to develop and implement net zero standards quickly, but also creates tensions between efficiency and procedural integrity, potential and proven results, corporate and collective value. While NZCB are here to stay, these tensions highlight barriers to their wide-scale adoption and question their ability to deliver an economically viable, socially just, environmental, net zero transition.
Keywords: Lizarralde_Gonzalo

Numerical Study on Measures for Protecting the Go-Cong Coastlines (Vietnam) from Erosion - San, Dinh Cong; Duong, Nguyen Binh; Phong, Nguyen Cong; Tu, Le Xuan; Pham-Van-Bang, Damien; Guillou, Sylvain; Nguyen, Kim Dan (Water, 2022)
Every year, in the Vietnam Mekong Delta Coastal Zone (VMDCZ), erosions cause approximately 300 ha of agricultural land loss. Therefore, measures for shoreline protection are urgently needed. This paper discusses the impacts of protection measures in the Go-Cong Coastal Zone to prevent erosion/accretion processes, predicted by two numerical models, MIKE21-FM and TELEMAC-2D. Hard and soft measures have been proposed using breakwaters and sandbars, respectively. The simulations show that the erosion/accretion trends provided by both models are similar. For breakwaters, MIKE21-FM provides less accretion than TELEMAC-2D in areas extending over 300 m and 500 m from shorelines. However, for sandbars, MIKE21-FM shows higher accretion within areas extending over 500 m but less than 300 m. Sandbars cause higher accretion in a larger area, extending over 1000 m offshore. The simulation results allow us to propose two alternative measures: (1) a row of several breakwater units will be implanted at 300 m offshore. The length of each unit is 600 m, with a gap between two neighbouring units of 70 m and a crest elevation of 2.2 m above mean sea level (MSL). (2) A row of sandbar units will be posed at 500 m offshore, with a unit length of 1000 m and a gap between the two neighbouring units of 200 m. The crest elevation is fixed at MSL.
Keywords: PhamVanBang_Damien

Impacts of high precipitation on the energy and water budgets of a humid boreal forest - Isabelle, Pierre-Erik; Nadeau, Daniel F.; Anctil, François; Rousseau, Alain N.; Jutras, Sylvain; Music, Biljana (Agricultural and Forest Meteorology, 2020)
Keywords: Ouvrage_Collectif_Numéro1; Rousseau_Alain

Continuous streamflow prediction in ungauged basins: long short-term memory neural networks clearly outperform traditional hydrological models - Arsenault, Richard; Martel, Jean-Luc; Brunet, Frédéric; Brissette, François; Mai, Juliane (Hydrology and Earth System Sciences, 2023)
Abstract. This study investigates the ability of long short-term memory (LSTM) neural networks to perform streamflow prediction at ungauged basins. A set of state-of-the-art, hydrological model-dependent regionalization methods are applied to 148 catchments in northeast North America and compared to an LSTM model that uses the exact same available data as the hydrological models. While conceptual model-based methods attempt to derive parameterizations at ungauged sites from other similar or nearby catchments, the LSTM model uses all available data in the region to maximize the information content and increase its robustness. Furthermore, by design, the LSTM does not require explicit definition of hydrological processes and derives its own structure from the provided data. The LSTM networks were able to clearly outperform the hydrological models in a leave-one-out cross-validation regionalization setting on most catchments in the study area, with the LSTM model outperforming the hydrological models in 93 % to 97 % of catchments depending on the hydrological model. Furthermore, for up to 78 % of the catchments, the LSTM model was able to predict streamflow more accurately on pseudo-ungauged catchments than hydrological models calibrated on the target data, showing that the LSTM model's structure was better suited to convert the meteorological data and geophysical descriptors into streamflow than the hydrological models even calibrated to those sites in these cases. Furthermore, the LSTM model robustness was tested by varying its hyperparameters, and still outperformed hydrological models in regionalization in almost all cases. Overall, LSTM networks have the potential to change the regionalization research landscape by providing clear improvement pathways over traditional methods in the field of streamflow prediction in ungauged catchments.
Keywords: Brunet_Alain; Infolettre; Infolettre_Fevrier_2023

Développement du modèle d’incertitude associé à la mesure traditionnelle des lignes d’eau lors de crues pour les rivières du Québec méridional - Marquis, G.; Mineault; Paradis, A.; Roy, M.; Trudel, M.; Tremblay, V.; Desgens, C. (2022)
Keywords: Infolettre; Infolettre_Septembre_2022; Site_internet_RIISQ

Impact of Natural Disasters on Household Income and Expenditure Inequality in China - Wang, Weiwei; Zhao, Yifan (Sustainability, 2023)
Natural disasters have been demonstrated to cause devastating effects on economic and social development in China, but little is known about the relationship between natural disasters and income at the household level. This study explores the impact of natural disasters on household income, expenditure, and inequality in China as the first study of this nature for the country. The empirical analysis is conducted based on a unique panel dataset that contains six waves of the Chinese Household Income Project (CHIP) survey data over the 1988–2018 period, data on natural disasters, and other social and economic status of households. By employing the fixed effects models, we find that disasters increase contemporaneous levels of income inequality, and disasters that occurred in the previous year significantly increase expenditure inequality. Natural disasters increase operating income inequality but decrease transfer income inequality. Poor households are found to be more vulnerable to disasters and suffer significant income losses. However, there is no evidence to suggest that natural disasters significantly reduce the income of upper- and middle-income groups. These findings have important implications for policies aimed at poverty alleviation and revenue recycling, as they can help improve economic justice and enhance resilience to natural disasters.

Risk assessment of drinking water intake contamination from agricultural activities using a Bayesian network - Kammoun, Raja; McQuaid, Natasha; Lessard, Vincent; Goitom, Eyerusalem Adhanom; Prévost, Michèle; Bichai, Françoise; Dorner, Sarah (PLOS Water, 2023)
Agricultural activities can result in the contamination of surface runoff with pathogens, pesticides, and nutrients. These pollutants can enter surface water bodies in two ways: by direct discharge into surface waters or by infiltration and recharge into groundwater, followed by release to surface waters. Lack of financial resources makes risk assessment through analysis of drinking water pollutants challenging for drinking water suppliers. Inability to identify agricultural lands with a high-risk level and implement action measures might lead to public health issues. As a result, it is essential to identify hazards and conduct risk assessments even with limited data. This study proposes a risk assessment model for agricultural activities based on available data and integrating various types of knowledge, including expert and literature knowledge, to estimate the levels of hazard and risk that different agricultural activities could pose to the quality of withdrawal waters. To accomplish this, we built a Bayesian network with continuous and discrete inputs capturing raw water quality and land use upstream of drinking water intakes (DWIs). This probabilistic model integrates the DWI vulnerability, threat exposure, and threats from agricultural activities, including animal and crop production inventoried in drainage basins. The probabilistic dependencies between model nodes are established through a novel adaptation of a mixed aggregation method. The mixed aggregation method, a traditional approach used in ecological assessments following a deterministic framework, involves using fixed assumptions and parameters to estimate ecological outcomes in a specific case without considering inherent randomness and uncertainty within the system. After validation, this probabilistic model was used for four water intakes in a heavily urbanized watershed with agricultural activities in the south of Quebec, Canada. The findings imply that this methodology can assist stakeholders direct their efforts and investments on at-risk locations by identifying agricultural areas that can potentially pose a risk to DWIs.
Keywords: Dorner_Sarah

Ambidexterity capacities for a recovery culture: Combination of logics and emergence of new practices - Normandin, Julie-Maude; Therrien, Marie-Christine; Baril, Geneviève; Daoust Gauthier, Marie (International Journal of Disaster Risk Reduction, 2022)
Keywords: Infolettre; Infolettre_Septembre_2022; Site_internet_RIISQ

How African Nova Scotians envision culturally relevant and sustaining pedagogy as civic repair - Jean-Pierre, Johanne (British Journal of Sociology of Education, 2021)

Modelling nutrient dynamics in cold agricultural catchments: A review - Costa, Diogo; Baulch, Helen; Elliott, Jane; Pomeroy, John; Wheater, Howard (Environmental Modelling & Software, 2020)

Insights from socio-hydrological modeling to design sustainable wastewater reuse strategies for agriculture at the watershed scale - Jeong, Hanseok; Bhattarai, Rabin; Adamowski, Jan; Yu, David J. (Agricultural Water Management, 2020)

A dual isotopic framework for identifying nitrate sources in surface runoff in a small agricultural watershed, northeast China - Sui, Yuanyuan; Ou, Yang; Yan, Baixing; Rousseau, Alain N.; Fang, Yunting; Geng, Runzhe; Wang, Lixia; Ye, Nan (Journal of Cleaner Production, 2020)
Keywords: Rousseau_Alain

Spatial–temporal variability of seasonal daily minimum flows in southern Quebec: synthesis on the impacts of climate, agriculture and wetlands - Assani, Ali; Zeroual, Ayoub; Kinnard, Christophe; Roy, Alexandre (Hydrology Research, 2022)
Abstract This study compares the impacts of climate, agriculture and wetlands on the spatio-temporal variability of seasonal daily minimum flows during the period 1930–2019 in 17 watersheds of southern Quebec (Canada). In terms of spatial variability, correlation analysis revealed that seasonal daily minimum flows were mainly negatively correlated with the agricultural surface area in watersheds in spring, summer and fall. In winter, these flows were positively correlated with the wetland surface area and March temperatures but negatively correlated with snowfall. During all four seasons, spatial variability was characterized by higher daily minimum flow values on the north shore (smaller agricultural surface area and larger wetland surface area) than those on the south shore. As for temporal variability, the application of six tests of the long-term trend analysis showed that most agricultural watersheds are characterized by a significant increase in flows during the four seasons due to the reduction in agricultural area, thus favoring water infiltration, and increased rainfall in summer and fall. On the other hand, the reduction in the snowfall resulted in a reduction in summer daily minimum flows observed in several less agricultural watersheds.
Keywords: Kinnard_Christophe

Effects of plants and biochar on the performance of treatment wetlands for removal of the pesticide chlorantraniliprole from agricultural runoff - Abas, Khalil; Brisson, Jacques; Amyot, Marc; Brodeur, Jacques; Storck, Veronika; Montiel-León, Juan Manuel; Duy, Sung Vo; Sauvé, Sébastien; Kõiv-Vainik, Margit (Ecological Engineering, 2022)

Impacts of Agricultural Areas on Spatio-Temporal Variability of Daily Minimum Extreme Flows during the Transitional Seasons (Spring and Fall) in Southern Quebec - Assani, Ali Arkamose; Zeroual, Ayoub; Roy, Alexandre; Kinnard, Christophe (Water, 2021)
Several statistical methods were used to analyze the spatio-temporal variability of daily minimum extreme flows (DMEF) in 17 watersheds—divided into three homogenous hydroclimatic regions of southern Quebec—during the transitional seasons (spring and fall), during the 1930–2019 period. Regarding spatial variability, there was a clear difference between the south and north shores of the St. Lawrence River, south of 47° N. DMEF were lower in the more agricultural watersheds on the south shore during transitional seasons compared to those on the north shore. A correlation analysis showed that this difference in flows was mainly due to more agricultural areas ((larger area (>20%) on the south than on the north shore (<5%)). An analysis of the long-term trend of these flows showed that the DMEF of south-shore rivers have increased significantly since the 1960s, during the fall (October to December), due to an increase in rainfall and a reduction in cultivated land, which increased the infiltration in the region. Although there was little difference between the two shores in the spring (April to June), we observed a decrease in minimum extreme flows in half (50%) of the south-shore rivers located north of 47° N.
Keywords: Infolettre; Infolettre_Janvier_2022; Kinnard_Christophe; Site_internet_RIISQ

Responses of soil erosion to warming and wetting in a cold Canadian agricultural catchment - Aygün, Okan; Kinnard, Christophe; Campeau, Stéphane (Catena, 2021)
Abstract This study explores the potential impacts of climate change on soil erosion in an agricultural catchment in eastern Canada. The Modified Universal Soil Loss Equation (MUSLE) was used to calculate the sediment yields from the Acadie River Catchment for the historical 1996–2019 period. The runoff variables of the MUSLE were obtained from a physically based hydrological model previously built and validated for the catchment. Then, the hydrological model was perturbed using climate change projections and used to assess the climate sensitivity of the sediment yield. Two runoff types representing possible modes of soil erosion were considered. While type A represents a baseline case in which soil erosion occurs due to surface runoff only, type B is more realistic since it assumed that tile drains also contribute to sediment export, but with a varying efficiency throughout the year. The calibration and validation of the tile efficiency factors against measurements in 2009–2015 for type B suggest that tile drains export the sediments with an efficiency of 20% and 50% in freezing and non-freezing conditions, respectively. Results indicate that tile drains account for 39% of the total annual sediment yield in the present climate. The timing of highest soil erosion shifts from spring to winter in response to warming and wetting, which can be explained by increasing winter runoff caused by shifting snowmelt timing towards winter, a greater number of mid-winter melt events as well as increasing rainfall fractions. The large uncertainties in precipitation projections cascade down to the erosion uncertainties in the more realistic type B, with annual sediment yield increasing or decreasing according to the precipitation uncertainty in a given climate change scenario. This study demonstrates the benefit of conservation and no-till pratices, which could reduce the annual sediment yields by 20% and 60%, respectively, under any given climate change scenario.
Keywords: Kinnard_Christophe

Preconception and prenatal maternal stress are associated with broad autism phenotype in young adults: Project Ice Storm - Li, Xinyuan; Laplante, David P.; Elgbeili, Guillaume; King, Suzanne (Journal of Developmental Origins of Health and Disease, 2023)
Studies show associations between prenatal maternal stress (PNMS) and child autism, with little attention paid to PNMS and autism in young adulthood. The broad autism phenotype (BAP), encompassing sub-clinical levels of autism, includes aloof personality, pragmatic language impairment and rigid personality. It remains unclear whether different aspects of PNMS explain variance in different BAP domains in young adult offspring. We recruited women who were pregnant during, or within 3 months of, the 1998 Quebec ice storm crisis, and assessed three aspects of their stress (i.e., objective hardship, subjective distress and cognitive appraisal). At age 19, the young adult offspring (n = 33, 22F / 11M) completed a BAP self-report. Linear and logistic regressions were implemented to examine associations between PNMS and BAP traits. Up to 21.4% of the variance in BAP total score and in BAP three domains tended to be explained by at least one aspect of maternal stress, For example, 16.8% of the variance in aloof personality tended to be explained by maternal objective hardship; 15.1% of the variance in pragmatic language impairment tended to be explained by maternal subjective distress; 20.0% of the variance in rigid personality tended to be explained by maternal objective hardship and 14.3% by maternal cognitive appraisal. Given the small sample size, the results should be interpreted with caution. In conclusion, this small prospective study suggests that different aspects of maternal stress could have differential effects on different components of BAP traits in young adults.
Keywords: Infolettre; Infolettre_Ete_2023

Atypical brain structure and function in young adults exposed to disaster‐related prenatal maternal stress: Project Ice Storm - Li, Xinyuan; Qureshi, Muhammad Naveed Iqbal; Laplante, David P.; Elgbeili, Guillaume; Jones, Sherri Lee; Long, Xiangyu; Paquin, Vincent; Bezgin, Gleb; Lussier, Firoza; King, Suzanne; Rosa‐Neto, Pedro (Journal of Neuroscience Research, 2023)
Abstract Studies have shown that prenatal maternal stress (PNMS) affects brain structure and function in childhood. However, less research has examined whether PNMS effects on brain structure and function extend to young adulthood. We recruited women who were pregnant during or within 3 months following the 1998 Quebec ice storm, assessed their PNMS, and prospectively followed‐up their children. T1‐weighted magnetic resonance imaging (MRI) and resting‐state functional MRI were obtained from 19‐year‐old young adults with ( n = 39) and without ( n = 65) prenatal exposure to the ice storm. We examined between‐group differences in gray matter volume (GMV), surface area (SA), and cortical thickness (CT). We used the brain regions showing between‐group GMV differences as seeds to compare between‐group functional connectivity. Within the Ice Storm group, we examined (1) associations between PNMS and the atypical GMV, SA, CT, and functional connectivity, and (2) moderation by timing of exposure. Primarily, we found that, compared to Controls, the Ice Storm youth had larger GMV and higher functional connectivity of the anterior cingulate cortex, the precuneus, the left occipital pole, and the right hippocampus; they also had larger CT, but not SA, of the left occipital pole. Within the Ice Storm group, maternal subjective distress during preconception and mid‐to‐late pregnancy was associated with atypical left occipital pole CT. These results suggest the long‐lasting impact of disaster‐related PNMS on child brain structure and functional connectivity. Our study also indicates timing‐specific effects of the subjective aspect of PNMS on occipital thickness.
Keywords: Infolettre; Infolettre_Octobre_2023

A narrative review of the epigenetics of post-traumatic stress disorder and post-traumatic stress disorder treatment - Cao-Lei, Lei; Saumier, Daniel; Fortin, Justine; Brunet, Alain (Frontiers in Psychiatry, 2022)
Epigenetic research in post-traumatic stress disorder (PTSD) is essential, given that environmental stressors and fear play such a crucial role in its development. As such, it may provide a framework for understanding individual differences in the prevalence of the disorder and in treatment response. This paper reviews the epigenetic markers associated with PTSD and its treatment, including candidate genes and epigenome-wide studies. Because the etiopathogenesis of PTSD rests heavily on learning and memory, we also draw upon animal neuroepigenetic research on the acquisition, update and erasure of fear memory, focusing on the mechanisms associated with memory reconsolidation. Reconsolidation blockade (or impairment) treatment in PTSD has been studied in clinical trials and, from a neurological perspective, may hold promise for identifying epigenetic markers of successful therapy. We conclude this paper by discussing several key considerations and challenges in epigenetic research on PTSD in humans.
Keywords: Brunet_Alain

Personality beliefs, coping strategies and quality of life in a cognitive-behavioral therapy for posttraumatic stress disorder - Bourdon, Delphine-Émilie; El-Baalbaki, Ghassan; Beaulieu-Prévost, Dominic; Guay, Stéphane; Belleville, Geneviève; Marchand, André (European Journal of Trauma & Dissociation, 2021)
Introduction Studies have shown that, following psychotherapy for posttraumatic stress disorder (PTSD), symptoms and quality of life (QoL) may improve in many patients, but not always to the same extent. Dysfunctional core beliefs, such as personality beliefs (PB), are associated to psychopathology, including PTSD, and could be associated with the types of coping strategies deployed by an individual. Beliefs and coping strategies were also linked to psychotherapeutic outcomes. Objectives (1) To examine the associations between baseline PB as well as pre- and post-treatment coping strategies; (2) To investigate the mediation effects between PB and the changes in QoL, through changes in coping strategies in a cognitive-behavioral psychotherapy (CBT). Method Seventy-one adults with PTSD participating in a correlational/observational CBT study were assessed for PB before a CBT, as well as for coping strategies and QoL, before and after a CBT. Results PB were generally associated with post-treatment distancing coping. Moreover, changes in distancing coping mediated the relationships between avoidant or dependent PB and psychological QoL improvements. Conclusion This is the first study to show the relationships between PB and coping strategies in PTSD patients, and that higher avoidant or dependent PB predicts a lower reduction in the use of distancing coping through psychotherapy, which is associated with less improvement in psychological QoL. Future studies are needed to further define the role of these variables and target more precisely factors that may hamper the treatment effects of CBT for PTSD.
Keywords: Site_internet_RIISQ

Climate change and the nonlinear impact of precipitation anomalies on income inequality - Palagi, Elisa; Coronese, Matteo; Lamperti, Francesco; Roventini, Andrea (Proceedings of the National Academy of Sciences, 2022)
Climate anomalies, such as floods and droughts, as well as gradual temperature changes have been shown to adversely affect economies and societies. Although studies find that climate change might increase global inequality by widening disparities across countries, its effects on within-country income distribution have been little investigated, as has the role of rainfall anomalies. Here, we show that extreme levels of precipitation exacerbate within-country income inequality. The strength and direction of the effect depends on the agricultural intensity of an economy. In high-agricultural-intensity countries, climate anomalies that negatively impact the agricultural sector lower incomes at the bottom end of the distribution and generate greater income inequality. Our results indicate that a 1.5-SD increase in precipitation from average values has a 35-times-stronger impact on the bottom income shares for countries with high employment in agriculture compared to countries with low employment in the agricultural sector. Projections with modeled future precipitation and temperature reveal highly heterogeneous patterns on a global scale, with income inequality worsening in high-agricultural-intensity economies, particularly in Africa. Our findings suggest that rainfall anomalies and the degree of dependence on agriculture are crucial factors in assessing the negative impacts of climate change on the bottom of the income distribution.

The diffusion of climate change adaptation policy - Schoenefeld, Jonas J.; Schulze, Kai; Bruch, Nils (Wiley Interdisciplinary Reviews: Climate Change, 2022)
Adapting to some level of climate change has become unavoidable. However, there is surprisingly limited systematic knowledge about whether and how adaptation policies have diffused and could diffuse in the future. Most existing adaptation studies do not explicitly examine policy diffusion, which is a form of interdependent policy-making among jurisdictions at the same or across different levels of governance. To address this gap, we offer a new interpretation and assessment of the extensive adaptation policy literature through a policy diffusion perspective; we pay specific attention to diffusion drivers and barriers, motivations, mechanisms, outputs, and outcomes. We assess the extent to which four motivations and related mechanisms of policy diffusion—interests (linked with learning and competition), rights and duties (tied to coercion), ideology, and recognition (both connected with emulation)—are conceptually and empirically associated with adaptation. We also engage with adaptation policy characteristics, contextual conditions (e.g., problem severity) and different channels of adapation policy diffusion (e.g., transnational networks). We demonstrate that adaptation policy diffusion can be associated with different mechanisms, yet many of them remain remarkably understudied. So are the effects of adaptation policy diffusion in terms of changes in vulnerability and resilience. We thus identify manifold avenues for future research, and provide insights for practitioners who may hope to leverage diffusion mechanisms to enhance their adaptation efforts. This article is categorized under: Policy and Governance > Multilevel and Transnational Climate Change Governance Vulnerability and Adaptation to Climate Change > Institutions for Adaptation

Beyond fear: The role of emotions in disaster risk reduction in the face of climate change - Lizarralde, Gonzalo; Lajoie, Steffen; Gould, Kevin; Araneda, Claudio; Cruz-Panesso, Ilian; Diaz, Julia Helena; Monsalve, Elsa; Burdiles, Roberto; Herazo, Benjamin; Páez, Holmes; Valladares, Arturo; Bornstein, Lisa; et al. (Emotion, Space and Society, 2025)
Keywords: Infolettre; Infolettre_Decembre_2024

We said, they said: the politics of conceptual frameworks in disasters and climate change in Colombia and Latin America - Lizarralde, Gonzalo; Páez, Holmes; Lopez, Adriana; Lopez, Oswaldo; Bornstein, Lisa; Gould, Kevin; Herazo, Benjamin; Muñoz, Lissette (Disaster Prevention and Management: An International Journal, 2020)
Purpose Few people living in informal settlements in the Global South spontaneously claim that they are “resilient” or “adapting” to disaster risk or climate change. Surely, they often overcome multiple challenges, including natural hazards exacerbated by climate change. Yet their actions are increasingly examined through the framework of resilience, a notion developed in the North, and increasingly adopted in the South. To what extent eliminate’ do these initiatives correspond to the concepts that scholars and authorities place under the resilience framework? Design/methodology/approach Three longitudinal case studies in Yumbo, Salgar and San Andrés (Colombia) serve to investigate narratives of disaster risks and responses to them. Methods include narrative analysis from policy and project documents, presentations, five workshops, six focus groups and 24 interviews. Findings The discourse adopted by most international scholars and local authorities differs greatly from that used by citizens to explain risk and masks the politics involved in disaster reduction and the search for social justice. Besides, narratives of social change, aspirations and social status are increasingly masked in disaster risk explanations. Tensions are also concealed, including those regarding the winners and losers of interventions and the responsibilities for disaster risk reduction. Originality/value Our findings confirm previous results that have shown that the resilience framework contributes to “depoliticize” the analysis of risk and serves to mask and dilute the responsibility of political and economic elites in disaster risk creation. But they also show that resilience fails to explain the type of socioeconomic change that is required to reduce vulnerabilities in Latin America.
Keywords: Lizarralde_Gonzalo

Welfare in the 21st century: Increasing development, reducing inequality, the impact of climate change, and the cost of climate policies - Lomborg, Bjorn (Technological Forecasting and Social Change, 2020)

Local agency, adaptation, and planning betwixt and between urban risks and climate change in Panorama, Colombia - Lajoie, Steffen (2024)
Cette thèse explore l'adaptation urbaine au changement climatique dans les quartiers informels du Sud Global. Ce sont des lieux de grands défis et de réponses innovantes. Le contexte mondial d’exclusion postcoloniale et capitaliste entraîne la vulnérabilité et le risque supplémentaire du changement climatique augmente ces aléas contextuels. Des chercheurs ont critiqué les réponses traditionnelles en matière de planification de l’adaptation, les jugeant trop prescriptives, technologiquement dépendantes et manquant les besoins locaux. L’adaptation communautaire peut être trop isolée et axée sur les besoins des individus et des élites face à la diversité des défis locaux. Ni l’un ni l’autre ne prennent en compte les dimensions politiques de la planification de l’adaptation. En réponse, les spécialistes critiques de l’adaptation urbaine ont appelé à une meilleure compréhension des expériences locales afin de comprendre comment les gens priorisent, négocient et réagissent à une multiplicité de risques. En réponse à ces appels, ce projet cherche à mieux comprendre comment les gens perçoivent et répondent à ces défis à travers une étude de cas unique et exploratoire. Grâce à l’étude de cas qualitative dans le quartier de Panorama, situé dans la municipalité de Yumbo, en banlieue de Cali en Colombie, le projet cherche à comprendre comment l'identité et le pouvoir influencent l'accès aux ressources et aux institutions nécessaires pour s'adapter. Le projet se concentre sur deux sites de Panorama : un comité local d'aménagement soucieux de la sécurité foncière et une fondation écologique travaillant sur la conservation des espaces verts. Les résultats mettent en évidence des règles du jeu inégales où les habitants les plus vulnérables empruntent des voies parfois illégales pour accéder à la terre et au logement. Plus les résidents sont établis, plus ils bénéficient d'avantages et d'expérience pour jouer le système. Les dirigeants et les experts travaillent dur pour négocier entre les formalités. Cependant, l’absence d’un processus de planification transparent laisse divers intérêts se disputer les ressources, ce qui conduit parfois à des conflits et met fin à la créativité. Les résultats de la recherche suggèrent que la planification de l’adaptation urbaine dans les contextes informels des pays du Sud doit continuer à s’appuyer sur des recherches et des pratiques qui tiennent compte de la diversité et des conflits afin de mieux faciliter une réponse juste et équitable à la crise climatique.

Changes in extreme precipitation indices across Algeria climate zones - Hamitouche, Yasmine; Zeroual, Ayoub; Meddi, Mohamed; Assani, Ali Arkamose; Alkama, Ramdane (International Journal of Climatology, 2024)
Abstract Extreme precipitation events can have a significant impact on the environment, agriculture, economy and safety, making close monitoring of their short‐ and long‐term trends essential for the development of effective mitigation and adaptation strategies. In this study, we analysed 16 in situ observation datasets from four different climate zones in Algeria, spanning from 1969 to 2021. The trend analysis was conducted using the original Mann–Kendall test and seven modified tests to eliminate the effects of short‐term persistence. Our findings reveal a significant increasing trend of extreme precipitation variability for most stations in the Warm Mediterranean climate zone, except for the Consecutive dry days index, which showed a negative trend for the same zone, while stations in the Cold/Warm semi‐arid climate and Cold desert climate (Bwk) zones showed a decreasing trend. Additionally, all index series with significant long‐term trends were affected by a significant shift in their means, which was confirmed by both the Lombard and Pettitt tests. However, when we used the modified MPT and the test eliminating the effects of long‐term persistence, the significance of the shifts and the trend decreased. Our results suggest that while extreme precipitation events have been increasing in some parts of Algeria; the trend may not be statistically significant in the long‐run, indicating the necessity of revisiting and refreshing the findings of previous studies for a more current perspective.
Keywords: Infolettre; Infolettre_Ete_2024; Site_internet_RIISQ

The archaeology of climate change: The case for cultural diversity - Burke, Ariane; Peros, Matthew C.; Wren, Colin D.; Pausata, Francesco S. R.; Riel-Salvatore, Julien; Moine, Olivier; De Vernal, Anne; Kageyama, Masa; Boisard, Solène (Proceedings of the National Academy of Sciences, 2021)
Anthropogenic climate change is currently driving environmental transformation on a scale and at a pace that exceeds historical records. This represents an undeniably serious challenge to existing social, political, and economic systems. Humans have successfully faced similar challenges in the past, however. The archaeological record and Earth archives offer rare opportunities to observe the complex interaction between environmental and human systems under different climate regimes and at different spatial and temporal scales. The archaeology of climate change offers opportunities to identify the factors that promoted human resilience in the past and apply the knowledge gained to the present, contributing a much-needed, long-term perspective to climate research. One of the strengths of the archaeological record is the cultural diversity it encompasses, which offers alternatives to the solutions proposed from within the Western agro-industrial complex, which might not be viable cross-culturally. While contemporary climate discourse focuses on the importance of biodiversity, we highlight the importance of cultural diversity as a source of resilience.

Hydrological behaviour of an ice‐layered snowpack in a non‐mountainous environment - Paquotte, Andrea; Baraer, Michel (Hydrological Processes, 2022)
Abstract The increased frequency of mild rain‐on‐snow (R.O.S.) events in cold regions associated with climate change is projected to affect snowpack structure and hydrological behaviour. The ice layers that form in a cold snowpack when R.O.S. events occur have been shown to influence flowthrough processes and liquid water retention, with consequences for winter floods, groundwater recharge, and water resources management. This study explores interconnections between meteorological conditions, ice layer formation, and lateral flows during R.O.S. events throughout the 2018–2019 winter in meridional Quebec, Canada. Automated hydro‐meteorological measurements, such as water availability for runoff, snow water equivalent, and snowpit observations, are used to compute water and energy balances, making it possible to characterize a snowpack's internal conditions and flowthrough regimes. For compatibility assessment, water and energy balances‐based flowthrough scenarios are then compared to different hydro‐meteorological variables', such as water table or streamlet water levels. The results show an association between highly variable meteorological conditions, frequent R.O.S. events, and ice layer formation. Lateral flows were mainly observed during the early stage of the ablation period. The hydrologically significant lateral flows observed in the study are associated with winter conditions that are predicted to become more frequent in a changing climate, stressing the need for further evaluation of their potential impact at the watershed scale.
Keywords: Baraer_Michel; Infolettre; Infolettre_Ete_2023

Cumulative Effects of Watershed Disturbances and Run-of-river Dams on Mercury Cycling: Case Study and Recommendations for Environmental Managers - Amyot, M.; Bilodeau, F.; Tremblay, A.; Planas, D.; Walsh, D.; Ponton, D. E. (Environmental Management, 2024)
Abstract Run-of-river power plants (ROR) represent the majority of hydroelectric plants worldwide. Their environmental impacts are not well documented and are believed to be limited, particularly regarding the contamination of food webs by methylmercury (MeHg), a neurotoxin. RORs are typically installed in small rivers where combined effects of watershed disturbances with dam construction can complicate environmental management. We report a multi-year case study on the Saint-Maurice River (Canada) where an unpredicted temporary increase in MeHg accumulation in predator fish was observed after the construction of two ROR plants. The associated pondages acted as sedimentation basins for mercury (Hg) and organic matter from a watershed disturbed by a forest fire and by logging. This fresh organic carbon likely fueled microbial MeHg production. Hg methylation was more associated with environmental conditions than to the presence of Hg, and main methylating microbial groups were identified. A constructed wetland was a site of significant Hg methylation but was not the main source of the fish Hg increase. Organic carbon degradation was the main driver of MeHg accumulation at the base of the food chain whereas trophic levels explained the variations at the top of the food chain. Overall, carbon cycling was a key driver of Hg dynamics in this system, and ROR plants can cause temporary (ca. 12 years) Hg increase in food webs when developed in disturbed watersheds, although this increase is smaller than for large reservoirs. Recommendations for future ROR construction are to establish a good environmental monitoring plan with initial high temporal resolution and to consider recent and potential watershed disturbances in the plan.

Speculative Political Ecologies: (re)imagining urban futures of climate extremes - Rusca, Maria; Barcena, Alejandro; Savelli, Elisa; Messori, Gabriele (Journal of Political Ecology, 2023)
What role can a speculative political ecology play in (re)imaging urban futures of climate extremes? In recent years, narratives of dystopian futures of climate extremes have proliferated in geosciences, and across the media and creative arts. These anxiety-fueled narratives often generate a sense of resignation and unavoidability, which contributes to foreclosing the possibility of radically different political projects. In this article, we argue that these narratives conceal the coproduction of nature and society and treat nature as the problem, thereby locking futures into dystopic configurations. Political ecology scholarship can contribute to generate a politics of possibility by reconceptualizing the relations that constitute urban futures under climate extremes as socionatural. This, we argue, calls for a more experimental political ecology and new forms of theorizing. To this aim, we develop a speculative political ecological approach grounded on a numerical model that examines the potential of transformative change in the aftermath of extreme flood events in a capitalist city. Analytically, this opens a unique possibility of exploring urban futures beyond current trajectories, and how these alternative futures might transform vulnerability and inequality across urban spaces. From a policy perspective, we lay the foundations for a new generation of models that apprehend the role of power and agency in shaping uneven urban futures of climate extremes.

Seuils de précipitation, variabilité spatiotemporelle et tendances climatiques des pluies torrentielles en Haute-Gaspésie, Québec. Comptes rendus de la 8e conférence canadienne sur la géotechnique et les risques naturels (Géorisques 8), La Société canadienne de géotechnique, Québec. - Boulet, Y.; Gauthier, F.; Buffin-Bélanger, T.; Hétu, B. (2022)

Analyse des embâcles de glace sur le fleuve Saint-Laurent lors de l’hiver 2018-2019 et développement d’un outil d'évaluation des risques d’embâcles - Scalabrini, P. (2022)
Durant les mois de janvier et février 2019, trois embâcles ont forcé l’arrêt de la navigation commerciale vers le Port de Montréal. Ce mémoire présente les conditions météorologiques associées aux embâcles sur le fleuve Saint Laurent de l’hiver 2018-2019. Il explique que les embâcles se développent à la suite d’arrêts de glace dans le bief problématique du lac Saint-Pierre entre la courbe Louiseville et le bassin Yamachiche. Pour ce faire, l’étude considère la production de glace en amont jusqu’au lac Saint-Louis. Il explique pourquoi ce bief est si vulnérable à l’initiation d’embâcles en présentant les neuf concepts de vulnérabilité du lac Saint-Pierre. De plus, il propose quatorze recommandations concrètes pour améliorer la fiabilité de navigation hivernale en réduisant les risques d’embâcles. En considérant ces recommandations, différentes opportunités de télédétection et une interface utilisateur sont présentées. L’opportunité de télédétection introduit la possibilité d’usage d’images de RADARSAT Constellation Mission et de photographies par drone afin d’évaluer des éléments clés comme la progression du couvert de glace, la largeur effective du chenal, la concentration de glace en transit et la vitesse de la glace. L’interface est un prototype d’outil d’aide à la décision de source libre qui permet d’obtenir d’autres informations quantitatives sur les risques d’arrêts de glace et du même fait, d’embâcles de glace.

Floodplain Management for All: Addressing Inequities and Meeting Needs of Indigenous Communities - Zimmerman, Olivia Nicole; Eison, Tanya; Carey, Robert G.; Carey, Robert F.; Levin, Phillip S. (Social Science Research Network, 2022)

Understanding Uncertainty in Probabilistic Floodplain Mapping in the Time of Climate Change - Zahmatkesh, Zahra; Han, Shasha; Coulibaly, Paulin (Water, 2021)
An integrated framework was employed to develop probabilistic floodplain maps, taking into account hydrologic and hydraulic uncertainties under climate change impacts. To develop the maps, several scenarios representing the individual and compounding effects of the models’ input and parameters uncertainty were defined. Hydrologic model calibration and validation were performed using a Dynamically Dimensioned Search algorithm. A generalized likelihood uncertainty estimation method was used for quantifying uncertainty. To draw on the potential benefits of the proposed methodology, a flash-flood-prone urban watershed in the Greater Toronto Area, Canada, was selected. The developed floodplain maps were updated considering climate change impacts on the input uncertainty with rainfall Intensity–Duration–Frequency (IDF) projections of RCP8.5. The results indicated that the hydrologic model input poses the most uncertainty to floodplain delineation. Incorporating climate change impacts resulted in the expansion of the potential flood area and an increase in water depth. Comparison between stationary and non-stationary IDFs showed that the flood probability is higher when a non-stationary approach is used. The large inevitable uncertainty associated with floodplain mapping and increased future flood risk under climate change imply a great need for enhanced flood modeling techniques and tools. The probabilistic floodplain maps are beneficial for implementing risk management strategies and land-use planning.

Towards sustainable agricultural landscapes: Lessons from an interdisciplinary research-based framework applied to the Saint Lawrence floodplain - Watson, Christopher J; Mazzei, Renata; Bourgeois, Bérenger; Smedbol, Élise; Guiraud, Noé; Félix-Faure, Jim; Damar, Hada; Tremblay, Maxime; Bordeleau, Pierre-Andé; Vaillancourt, Mathieu; Bertolo, Andrea; Cabana, Gilbert; et al. (Basic and Applied Ecology, 2024)
Keywords: Infolettre; Infolettre_Octobre_2024

Establishment of reed canarygrass ( Phalaris arundinacea ) in the context of floodplain restoration: impact of companion plant and sowing rate - Vaillancourt, Mathieu; Čapkun-Huot, Catherine; Jean Jacques, Samuel; Bourgeois, Bérenger; Poulin, Monique (Botany, 2024)
Habitat loss and degradation is a leading cause of the current biodiversity crisis. In the lake Saint-Pierre floodplain, agricultural intensification has led to the loss of substantial spawning and rearing areas for the yellow perch ( Perca flavescens Mitchill). Restoring perennial vegetation cover is key to ensure the persistence of the population, but the floodplain conditions limit our ability to do so. In this study, we tested the impact of companion plants ( Avena sativa L., Lolium multiflorum L.) and sowing rate on the establishment success of reed canarygrass ( Phalaris arundinacea L.; RCG) in year 2. RCG tolerates a wide range of environmental conditions and can provide the plant cover essential to the reproduction of yellow perch. We hypothesized that companion plants would reduce weed pressure and in turn improve RCG establishment, and that increasing the sowing rate would improve the establishment success. Contrary to our expectations, using companion plants generally reduced the cover and biomass of RCG. It also led to increased weed prevalence in most treatments. In addition, sowing at high rates did not impact RCG cover and biomass. Sowing RCG alone appears to be the most effective option to establish perennial vegetation supporting the recovery of the yellow perch population.
Keywords: Infolettre; Infolettre_Mai_2024

Associations between Historical Redlining and Current and Future Exposure to Stormwater Flooding in New York City - Steinberg-McElroy, Ivy; Tangtrakul, Korin; Alizadehtazi, Bita; Rosenzweig, B.; Gurian, Patrick L.; Montalto, Franco (2023)

Earlywood Vessels in Black Ash (Fraxinus nigra Marsh.) Trees Show Contrasting Sensitivity to Hydroclimate Variables According to Flood Exposure - Tardif, Jacques Clément; Kames, Susanne; Nolin, Alexandre Florent; Bergeron, Yves (Frontiers in Plant Science, 2021)
In recent years, the utility of earlywood vessels anatomical characteristics in identifying and reconstructing hydrological conditions has been fully recognized. In riparian ring-porous species, flood rings have been used to identify discrete flood events, and chronologies developed from cross-sectional lumen areas of earlywood vessels have been used to successfully reconstruct seasonal discharge. In contrast, the utility of the earlywood vessel chronologies in non-riparian habitats has been less compelling. No studies have contrasted within species their earlywood vessel anatomical characteristics, specifically from trees that are inversely exposed to flooding. In this study, earlywood vessel and ring-width chronologies were compared between flooded and non-flooded control Fraxinus nigra trees. The association between chronologies and hydroclimate variables was also assessed. Fraxinus nigra trees from both settings shared similar mean tree-ring width but floodplain trees did produce, on average, thicker earlywood. Vessel chronologies from the floodplain trees generally recorded higher mean sensitivity (standard deviation) and lower autocorrelation than corresponding control chronologies indicating higher year-to-year variations. Principal components analysis (PCA) revealed that control and floodplain chronologies shared little variance indicating habitat-specific signals. At the habitat level, the PCA indicated that vessel characteristics were strongly associated with tree-ring width descriptors in control trees whereas, in floodplain trees, they were decoupled from the width. The most striking difference found between flood exposures related to the chronologies' associations with hydroclimatic variables. Floodplain vessel chronologies were strongly associated with climate variables modulating spring-flood conditions as well as with spring discharge whereas control ones showed weaker and few consistent correlations. Our results illustrated how spring flood conditions modulate earlywood vessel plasticity. In floodplain F. nigra trees, the use of earlywood vessel characteristics could potentially be extended to assess and/or mitigate anthropogenic modifications of hydrological regimes. In absence of major recurring environmental stressors like spring flooding, our results support the idea that the production of continuous earlywood vessel chronologies may be of limited utility in dendroclimatology.
Keywords: Site_internet_RIISQ

Dynamics of household welfare change and analysis of coping strategies during floods: an empirical investigation - Senapati, Sibananda (International Journal of Social Economics, 2024)
Purpose This study aims to understand the socioeconomic impact of flood events on households, especially household welfare in terms of changes in consumption and coping strategies to deal with flood risk. This study is based on Bihar, one of the most frequently flood-affected, most populous and economically backward states in India. Design/methodology/approach Primary data were collected from 700 households in the seven most frequently flood-affected districts in Bihar. A total of 100 individuals from each district were randomly selected from flood-affected villages. Based on a detailed literature review, an econometric (probit) model was developed to test the null hypothesis of the availability of consumption insurance, and the multivariate probability approach was used to analyze the various coping strategies of these households. Findings The results of this study suggest that flood-affected households maintain their consumption by overcoming various losses, including income, house damage and livestock loss. Households depend on financial transfers, borrowings and relief, and migrate to overcome losses. Borrowing could be an extra burden as the government compensates for house damage and crop loss late to the affected households. Again, there is no compensation to overcome livelihood loss and deal with occurrences of post-flood diseases, which further emphasizes the policy implications of strengthening the health infrastructure in the state and generating alternative livelihood opportunities. Originality/value This study discusses flood risk in terms of changes in household welfare, identifies the most effective risk-coping capabilities of rural communities and contributes to the shortcomings of the government insurance and relief model. Peer review The peer review history for this article is available at: https://publons.com/publon/10.1108/IJSE-07-2023-0569

Integrating climate change induced flood risk into future population projections - Shu, Evelyn G.; Porter, Jeremy R.; Hauer, Mathew E.; Sandoval Olascoaga, Sebastian; Gourevitch, Jesse; Wilson, Bradley; Pope, Mariah; Melecio-Vazquez, David; Kearns, Edward (Nature Communications, 2023)
Abstract Flood exposure has been linked to shifts in population sizes and composition. Traditionally, these changes have been observed at a local level providing insight to local dynamics but not general trends, or at a coarse resolution that does not capture localized shifts. Using historic flood data between 2000-2023 across the Contiguous United States (CONUS), we identify the relationships between flood exposure and population change. We demonstrate that observed declines in population are statistically associated with higher levels of historic flood exposure, which may be subsequently coupled with future population projections. Several locations have already begun to see population responses to observed flood exposure and are forecasted to have decreased future growth rates as a result. Finally, we find that exposure to high frequency flooding (5 and 20-year return periods) results in 2-7% lower growth rates than baseline projections. This is exacerbated in areas with relatively high exposure to frequent flooding where growth is expected to decline over the next 30 years.

Flood impact on income inequality in the Itapocu River basin, Brazil - Silva Araújo, Rafael; Ohara, Miho; Miyamoto, Mamoru; Takeuchi, Kuniyoshi (Journal of Flood Risk Management, 2022)
Abstract Disasters worldwide tend to affect the poorest more severely and increase inequality. Brazil is one of the countries with high income‐inequality rates and has unplanned urbanization issues and an extensive disaster risk profile with little knowledge on how those disasters affect people's welfare. Thus, disasters often hit the poorest hardest, increasing the country's income inequality and poverty rates. This study proposes a method to assess the impact of floods on households spatially based on their income levels by conducting flood analysis and income analysis. The method is applied to the Itapocu River basin (IRB) located in Santa Catarina State, Brazil. The flood is assessed by conducting rainfall analysis and hydrological simulation and generating flood inundation maps. The income is evaluated using downloaded 2010 census data and a dasymetric approach. Flood and income information is combined to analyze flood‐impacted households by income level and flood return period. The results confirm the initial assumption that flood events in the IRB are more likely to affect the lowest‐income households rather than the highest‐income levels, thus, increasing the income inequality.

A network-based analysis of critical resource accessibility during floods - Preisser, Matthew; Passalacqua, Paola; Bixler, R. Patrick; Boyles, Stephen D. (2023)
Numerous government and non-governmental agencies are increasing their efforts to better quantify the disproportionate effects of climate risk on vulnerable populations with the goal of creating more resilient communities. Sociodemographic based indices have been the primary source of vulnerability information the past few decades. However, using these indices fails to capture other facets of vulnerability, such as the ability to access critical resources (e.g., grocery stores, hospitals, pharmacies, etc.). Furthermore, methods to estimate resource accessibility as storms occur (i.e., in near-real time) are not readily available to local stakeholders. We address this gap by creating a model built on strictly open-source data to solve the user equilibrium traffic assignment problem to calculate how an individual's access to critical resources changes during and immediately after a flood event. Redundancy, reliability, and recoverability metrics at the household and network scales reveal the inequitable distribution of the flood's impact. In our case-study for Austin, Texas we found that the most vulnerable households are the least resilient to the impacts of floods and experience the most volatile shifts in metric values. Concurrently, the least vulnerable quarter of the population often carries the smallest burdens. We show that small and moderate inequalities become large inequities when accounting for more vulnerable communities' lower ability to cope with the loss of accessibility, with the most vulnerable quarter of the population carrying four times as much of the burden as the least vulnerable quarter. The near-real time and open-source model we developed can benefit emergency planning stakeholders by helping identify households that require specific resources during and immediately after hazard events.

Peaks-over-threshold model in flood frequency analysis: a scoping review - Pan, Xiao; Rahman, Ataur; Haddad, Khaled; Ouarda, Taha B. M. J. (Stochastic Environmental Research and Risk Assessment, 2022)
Abstract In flood frequency analysis (FFA), annual maximum (AM) model is widely adopted in practice due to its straightforward sampling process. However, AM model has been criticized for its limited flexibility. FFA using peaks-over-threshold (POT) model is an alternative to AM model, which offers several theoretical advantages; however, this model is currently underemployed internationally. This study aims to bridge the current knowledge gap by conducting a scoping review covering several aspects of the POT approach including model assumptions, independence criteria, threshold selection, parameter estimation, probability distribution, regionalization and stationarity. We have reviewed the previously published articles on POT model to investigate: (a) possible reasons for underemployment of the POT model in FFA; and (b) challenges in applying the POT model. It is highlighted that the POT model offers a greater flexibility compared to the AM model due to the nature of sampling process associated with the POT model. The POT is more capable of providing less biased flood estimates for frequent floods. The underemployment of POT model in FFA is mainly due to the complexity in selecting a threshold (e.g., physical threshold to satisfy independence criteria and statistical threshold for Generalized Pareto distribution – the most commonly applied distribution in POT modelling). It is also found that the uncertainty due to individual variable and combined effects of the variables are not well assessed in previous research, and there is a lack of established guideline to apply POT model in FFA.
Keywords: Infolettre; Infolettre_Avril_2022; Site_internet_RIISQ

Distributive Justice and Urban Form Adaptation to Flooding Risks: Spatial Analysis to Identify Toronto's Priority Neighborhoods - Mohtat, Niloofar; Khirfan, Luna (Frontiers in Sustainable Cities, 2022)
Empirical evidence points out that urban form adaptation to climate-induced flooding events—through interventions in land uses and town plans (i. e., street networks, building footprints, and urban blocks)—might exacerbate vulnerabilities and exposures, engendering risk inequalities and climate injustice. We develop a multicriteria model that draws on distributive justice's interconnections with the risk drivers of social vulnerabilities, flood hazard exposures, and the adaptive capacity of urban form (through land uses and town plans). The model assesses “who” is unequally at-risk to flooding events, hence, should be prioritized in adaptation responses; “where” are the high-risk priority areas located; and “how” can urban form adaptive interventions advance climate justice in the priority areas. We test the model in Toronto, Ontario, Canada, where there are indications of increased rainfall events and disparities in social vulnerabilities. Our methodology started with surveying Toronto-based flooding experts who assigned weights to the risk drivers based on their importance. Using ArcGIS, we then mapped and overlayed the risk drivers' values in all the neighborhoods across the city based on the experts' assigned weights. Accordingly, we identified four high-risk tower communities with old infrastructure and vulnerable populations as the priority neighborhoods for adaptation interventions within the urban form. These four neighborhoods are typical of inner-city tower blocks built in the 20 th century across North America, Europe, and Asia based on modern architectural ideas. Considering the lifespan of these blocks, this study calls for future studies to investigate how these types of neighborhoods can be adapted to climate change to advance climate justice.

Causes, impacts and patterns of disastrous river floods - Merz, Bruno; Blöschl, Günter; Vorogushyn, Sergiy; Dottori, Francesco; Aerts, Jeroen C. J. H.; Bates, Paul D.; Bertola, Miriam; Kemter, Matthias; Kreibich, Heidi; Lall, Upmanu; Macdonald, Elena (2021)
Disastrous floods have caused millions of fatalities in the twentieth century, tens of billions of dollars of direct economic loss each year and serious disruption to global trade. In this Review, we provide a synthesis of the atmospheric, land surface and socio-economic processes that produce river floods with disastrous consequences. Disastrous floods have often been caused by processes fundamentally different from those of non-disastrous floods, such as unusual but recurring atmospheric circulation patterns or failures of flood defences, which lead to high levels of damage because they are unexpected both by citizens and by flood managers. Past trends in economic flood impacts show widespread increases, mostly driven by economic and population growth. However, the number of fatalities and people affected has decreased since the mid-1990s because of risk reduction measures, such as improved risk awareness and structural flood defences. Disastrous flooding is projected to increase in many regions, particularly in Asia and Africa, owing to climate and socio-economic changes, although substantial uncertainties remain. Assessing the risk of disastrous river floods requires a deeper understanding of their distinct causes. Transdisciplinary research is needed to understand the potential for surprise in flood risk systems better and to operationalize risk management concepts that account for limited knowledge and unexpected developments. River floods have direct and indirect consequences for society, and can cause fatalities, displacement and economic loss. This Review examines the physical and socioeconomic causes and impacts of disastrous river flooding, and past and projected trends in their occurrence.

Coastal Flooding Associated with Hurricane Irma in Central Cuba (Ciego de Ávila Province) - Matos-Pupo, Felipe; Peros, Matthew C.; González-De Zayas, Roberto; Valero-Jorge, Alexey; Pérez-López, Osvaldo E.; Álvarez-Taboada, Flor; Sorí, Rogert (Atmosphere, 2023)
Irma was a major hurricane that developed during the 2017 season. It was a category 5 on the Saffir–Simpson Hurricane wind scale. This hurricane caused severe damage in the Caribbean area and the Florida Keys. The social, economic, and environmental impacts, mainly related to coastal flooding, were also significant in Cuba. The maximum limits of coastal flooding caused by this hurricane were determined in this research. Field trips and the use of the GPS supported our work, which focused on both the northern and southern coasts of the Ciego de Ávila province. This work has been critical for improving coastal flooding scenarios related to a strong hurricane, as it has been the first experience according to hurricane data since 1851. Results showed that the Punta Alegre and Júcaro towns were the most affected coastal towns. The locals had never seen similar flooding in these places before. The differences between flood areas associated with Hurricane Irma and previous modeled hazard scenarios were evident (the flooded areas associated with Hurricane Irma were smaller than those modeled for categories 1, 3, and 5 hurricanes). The effects of this hurricane on the most vulnerable coastal settlements, including the impacts on the archeological site “Los Buchillones”, were also assessed.
Keywords: Infolettre; Infolettre_Octobre_2023

Urban form and structure explain variability in spatial inequality of property flood risk among US counties - Ma, Junwei; Mostafavi, Ali (Communications Earth & Environment, 2024)
Abstract Understanding the relationship between urban form and structure and spatial inequality of property flood risk has been a longstanding challenge in urban planning and emergency management. Here we explore eight urban form and structure features to explain variability in spatial inequality of property flood risk among 2567 US counties. Using datasets related to human mobility and facility distribution, we identify notable variation in spatial inequality of property flood risk, particularly in coastline and metropolitan counties. The results reveal variations in spatial inequality of property flood risk can be explained based on principal components of development density, economic activity, and centrality and segregation. The classification and regression tree model further demonstrates how these principal components interact and form pathways that explain spatial inequality of property flood risk. The findings underscore the critical role of urban planning in mitigating flood risk inequality, offering valuable insights for crafting integrated strategies as urbanization progresses.

Prenatal maternal subjective distress predicts higher autistic-like traits in offspring: The Iowa Flood Study - Lapierre, Mylène; Elgbeili, Guillaume; Laplante, David P.; O’Hara, Michael W.; D’Antono, Bianca; King, Suzanne (Development and Psychopathology, 2024)
Abstract Autism spectrum disorder prevalence more than quadrupled in the United States between 2000 and 2020. Ice storm-related prenatal maternal stress (PNMS) predicts autistic-like trait severity in children exposed early in gestation. The objective was to determine the extent to which PNMS influences the severity and trajectory of autistic-like traits in prenatally flood-exposed children at ages 4–7 years and to test moderation by sex and gestational timing. Soon after the June 2008 floods in Iowa, USA, 268 women pregnant during the disaster were assessed for objective hardship, subjective distress, and cognitive appraisal of the experience. When their children were 4, 5½, and 7 years old, mothers completed the Social Communication Questionnaire (SCQ) to assess their children’s autistic-like traits; 137 mothers completed the SCQ for at least one age. The final longitudinal multilevel model showed that the greater the maternal subjective distress, the more severe the child’s autistic-like traits, controlling for objective hardship. The effect of PNMS on rate of change was not significant, and there were no significant main effects or interactions involving sex or timing. Prenatal maternal subjective distress, but not objective hardship or cognitive appraisal, predicted more severe autistic-like traits at age 4, and this effect remained stable through age 7.
Keywords: Infolettre; Infolettre_Novembre_2024

The wider the gap between rich and poor the higher the flood mortality - Lindersson, Sara; Raffetti, Elena; Rusca, Maria; Brandimarte, Luigia; Mård, Johanna; Di Baldassarre, Giuliano (Nature Sustainability, 2023)
Economic inequality is rising within many countries globally, and this can significantly influence the social vulnerability to natural hazards. We analysed income inequality and flood disasters in 67 middle- and high-income countries between 1990 and 2018 and found that unequal countries tend to suffer more flood fatalities. This study integrates geocoded mortality records from 573 major flood disasters with population and economic data to perform generalized linear mixed regression modelling. Our results show that the significant association between income inequality and flood mortality persists after accounting for the per-capita real gross domestic product, population size in flood-affected regions and other potentially confounding variables. The protective effect of increasing gross domestic product disappeared when accounting for income inequality and population size in flood-affected regions. On the basis of our results, we argue that the increasingly uneven distribution of wealth deserves more attention within international disaster-risk research and policy arenas.

Multi-Scale Flood Mapping under Climate Change Scenarios in Hexagonal Discrete Global Grids - Li, Mingke; McGrath, Heather; Stefanakis, Emmanuel (ISPRS International Journal of Geo-Information, 2022)
Among the most prevalent natural hazards, flooding has been threatening human lives and properties. Robust flood simulation is required for effective response and prevention. Machine learning is widely used in flood modeling due to its high performance and scalability. Nonetheless, data pre-processing of heterogeneous sources can be cumbersome, and traditional data processing and modeling have been limited to a single resolution. This study employed an Icosahedral Snyder Equal Area Aperture 3 Hexagonal Discrete Global Grid System (ISEA3H DGGS) as a scalable, standard spatial framework for computation, integration, and analysis of multi-source geospatial data. We managed to incorporate external machine learning algorithms with a DGGS-based data framework, and project future flood risks under multiple climate change scenarios for southern New Brunswick, Canada. A total of 32 explanatory factors including topographical, hydrological, geomorphic, meteorological, and anthropogenic were investigated. Results showed that low elevation and proximity to permanent waterbodies were primary factors of flooding events, and rising spring temperatures can increase flood risk. Flooding extent was predicted to occupy 135–203% of the 2019 flood area, one of the most recent major flooding events, by the year 2100. Our results assisted in understanding the potential impact of climate change on flood risk, and indicated the feasibility of DGGS as the standard data fabric for heterogeneous data integration and incorporated in multi-scale data mining.

The behavioral turn in flood risk management, its assumptions and potential implications - Kuhlicke, Christian; Seebauer, Sebastian; Hudson, Paul; Begg, Chloe; Bubeck, Philip; Dittmer, Cordula; Grothmann, Torsten; Heidenreich, Anna; Kreibich, Heidi; Lorenz, Daniel F.; Masson, Torsten; Reiter, Jessica; et al. (WIREs Water, 2020)
Abstract Recent policy changes highlight the need for citizens to take adaptive actions to reduce flood‐related impacts. Here, we argue that these changes represent a wider behavioral turn in flood risk management (FRM). The behavioral turn is based on three fundamental assumptions: first, that the motivations of citizens to take adaptive actions can be well understood so that these motivations can be targeted in the practice of FRM; second, that private adaptive measures and actions are effective in reducing flood risk; and third, that individuals have the capacities to implement such measures. We assess the extent to which the assumptions can be supported by empirical evidence. We do this by engaging with three intellectual catchments. We turn to research by psychologists and other behavioral scientists which focus on the sociopsychological factors which influence individual motivations (Assumption 1). We engage with economists, engineers, and quantitative risk analysts who explore the extent to which individuals can reduce flood related impacts by quantifying the effectiveness and efficiency of household‐level adaptive measures (Assumption 2). We converse with human geographers and sociologists who explore the types of capacities households require to adapt to and cope with threatening events (Assumption 3). We believe that an investigation of the behavioral turn is important because if the outlined assumptions do not hold, there is a risk of creating and strengthening inequalities in FRM. Therefore, we outline the current intellectual and empirical knowledge as well as future research needs. Generally, we argue that more collaboration across intellectual catchments is needed, that future research should be more theoretically grounded and become methodologically more rigorous and at the same time focus more explicitly on the normative underpinnings of the behavioral turn. This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance Science of Water > Water Extremes

Turkmen women’s traditional craft skills in post-disaster recovery: the case of the 2019 Northeast floods in Iran - Hassani, Atoosa; Fayazi, Mahmood; Mottaki, Zoheir; Adib, Morteza; Dehbandi, Ramin; Khalili Gheidari, Yasamam; Seraji, Fatemeh (Disaster Prevention and Management: An International Journal, 2025)
Purpose This study investigates why Turkmen women’s traditional handicraft skills have declined and explains how the local, traditional craft skills accelerated the post-flood recovery of Turkmen women in the aftermath of the 2019 Northeast floods in Iran. Design/methodology/approach The research adopts a case study approach, employing reflective thematic analysis. Findings Post-disaster recovery spurred a shift from traditional to modern lifestyles through new housing designs, enhanced female literacy and greater economic participation. However, this transition devalued traditional crafts due to heightened household chores, material scarcity and reduced market demand. Nonetheless, women with craft skills played a pivotal role in household recovery by repairing damaged items and crafting dowries for their daughters, illustrating their contribution to social and economic resilience. Social implications These research findings shed light on the importance of traditional craft skills in enabling the female household member, in particular, to recover from disasters and contribute to the recovery of their households and communities. Originality/value The originality of this study lies in its focus on the specific context of Turkmen women’s traditional craft skills and their role in post-disaster recovery, particularly after the 2019 Northeast floods in Iran. While there is existing research on post-disaster recovery mechanisms, this study uniquely examines the under-researched impact of traditional craft skills on the recovery process, specifically for female household members.
Keywords: Infolettre; Infolettre_Fevrier_2025

Spatiotemporal variations of riverine flood fatalities: 70 years global to regional perspective - Hamidifar, Hossein; Nones, Michael (2023)
Abstract Floods are among the most devastating natural hazards worldwide. While rainfall is the primary trigger of floods, human activities and climate change can exacerbate the impacts of floods and lead to more significant economic and social consequences. In this research, fluvial flood fatalities in the 1951–2020 period have been studied, analyzing the information reported in the Emergency Database (EM‐DAT). The EM‐DAT data were classified into five categories in terms of the number of events and fatalities connected with riverine floods, considering only events that caused more than 10 fatalities. The results show that the severity of flood‐related fatalities is not equally distributed worldwide, but presents specific geographical patterns. The flood fatality coefficient, which represents the ratio between the total number of fatalities and the number of flood events, calculated for different countries, identified that the Southern, Eastern, and South‐Eastern regions of Asia have the deadliest floods in the world. The number of flood events has been increasing since 1951 and peaked in 2007, following a relative decline since then. Though, the resulting fatalities do not follow a statistically significant trend. An analysis of the number of flood events in different decades shows that the 2001–2010 decade saw the highest number of events, which corresponds to the largest precipitation anomaly in the world. The lethality of riverine floods decreased over time, from 412 per flood in 1951–1960 to 67 in the 2011–2020 decade. This declining trend is probably a consequence of a more resilient environment and better risk reduction strategies. Based on the presented data and using regression analysis, relationships between flood fatalities and the number of flood events with population density and gross domestic product are developed and discussed.

Urinary 1H NMR Metabolomic Analysis of Prenatal Maternal Stress Due to a Natural Disaster Reveals Metabolic Risk Factors for Non-Communicable Diseases: The QF2011 Queensland Flood Study - Heynen, Joshua P.; McHugh, Rebecca R.; Boora, Naveenjyote S.; Simcock, Gabrielle; Kildea, Sue; Austin, Marie-Paule; Laplante, David P.; King, Suzanne; Montina, Tony; Metz, Gerlinde A. S. (Metabolites, 2023)
Prenatal stress alters fetal programming, potentially predisposing the ensuing offspring to long-term adverse health outcomes. To gain insight into environmental influences on fetal development, this QF2011 study evaluated the urinary metabolomes of 4-year-old children (n = 89) who were exposed to the 2011 Queensland flood in utero. Proton nuclear magnetic resonance spectroscopy was used to analyze urinary metabolic fingerprints based on maternal levels of objective hardship and subjective distress resulting from the natural disaster. In both males and females, differences were observed between high and low levels of maternal objective hardship and maternal subjective distress groups. Greater prenatal stress exposure was associated with alterations in metabolites associated with protein synthesis, energy metabolism, and carbohydrate metabolism. These alterations suggest profound changes in oxidative and antioxidative pathways that may indicate a higher risk for chronic non-communicable diseases such obesity, insulin resistance, and diabetes, as well as mental illnesses, including depression and schizophrenia. Thus, prenatal stress-associated metabolic biomarkers may provide early predictors of lifetime health trajectories, and potentially serve as prognostic markers for therapeutic strategies in mitigating adverse health outcomes.
Keywords: Infolettre; Infolettre_Mai_2023

Fair strategies to tackle unfair risks? Justice considerations within flood risk management - Herve, Mathilde de Goër de (International journal of disaster risk reduction, 2021)
Risk management, justice (i.e. equity, fairness), and sustainability are tightly interconnected. This literature review investigates how and why justice is considered in flood risk management. 20 scientific documents published between 2015 and 2020 are analyzed in depth. The results show a distinction between distributive and procedural justice and a complicated judgment of fairness based on different philosophies that vary depending on the country, the type of flood, and the type of strategy studied. Equity is found to be an under-discussed topic compared to its importance. Justice in flood risk management matters because (i) the impacts of floods affect different people unevenly, (ii) the interest in equity evinced by public authorities influences societal transformation, and (iii) the perception of fairness matters at both individual and collective levels. This paper analyzes the link between justice considerations and sustainability in relation to four dimensions: social, ecological, spatial, and temporal. Social and spatial issues are the most commonly studied in the literature, while ecological and temporal ones have generally been overlooked, creating a research gap. The results are discussed in terms of their diversities of justice concepts, places of investigation, and types of strategies. Various justice frameworks are used, but since none of them focus specifically on the contribution of flood risk management to sustainability through justice considerations, a flood risk justice framework is developed, which translates into theoretical and practical tools. It is based on the considerations of both humans and non-humans into different spatio-temporal scales. • Justice issues are under-discussed while they matter for flood risk management. • Diverse case studies in various places show procedural and distributive (in)justice. • There is no agreement in the literature on how to judge the fairness of a strategy. • The literature is mostly limited to social and spatial justice aspects. • Flood risk justice includes social, ecological, spatial, and temporal issues.

Temporal and Spatial Amplification of Extreme Rainfall and Extreme Floods in a Warmer Climate - Faghih, Mina; Brissette, François (Journal of Hydrometeorology, 2023)
Abstract This work explores the relationship between catchment size, rainfall duration, and future streamflow increases on 133 North American catchments with sizes ranging from 66.5 to 9886 km2. It uses the outputs from a high spatial (0.11°) and temporal (1-h) resolution single model initial-condition large ensemble (SMILE) and a hydrological model to compute extreme rainfall and streamflow for durations ranging from 1 to 72 h and for return periods of between 2 and 300 years. Increases in extreme precipitation are observed across all durations and return periods. The projected increases are strongly related to duration, frequency, and catchment size, with the shortest durations, longest return periods, and smaller catchments witnessing the largest relative rainfall increases. These increases can be quite significant, with the 100-yr rainfall becoming up to 20 times more frequent over the smaller catchments. A similar duration–frequency–size pattern of increases is also observed for future extreme streamflow, but with even larger relative increases. These results imply that future increases in extreme rainfall will disproportionately impact smaller catchments, and particularly so for impervious urban catchments which are typically small, and whose stormwater drainage infrastructures are designed for long-return-period flows, both being conditions for which the amplification of future flow will be maximized.
Keywords: Infolettre; Infolettre_Septembre_2023

Establishing perennial strips in a cultivated floodplain for habitat restoration: monitoring over 4 years and success drivers - Damar, Hada; Vaillancourt, Mathieu; Bourgeois, Bérenger; Poulin, Monique (Restoration Ecology, 2024)
Floodplains, one of the most biologically diverse and productive ecosystems, are under threat from intensive crop production. Implementing perennial strips alongside agricultural ditches and streams could reduce negative impacts of intensive agriculture and restore wildlife habitats in cultivated floodplains. To successfully set up perennial strips, it is important to understand the parameters that drive their establishment. Here we assessed the establishment success of reed canarygrass (RCG; Phalaris arundinacea ) strips in the lake Saint Pierre (LSP) floodplain, Québec, Canada by monitoring RCG biomass and vegetation height over 4 years and identify the factors driving its establishment. A total of 26 RCG strips across six municipalities of LSP were monitored. Biomass and vegetation height of RCG increased over time to reach an average of 5048 kg/ha in year 4 and 104 cm in year 3 in established strips. The RCG established successfully in 62% of surveyed plots and three environmental parameters explained 61% of this success. Establishment of RCG was most successful when a first rain came right after seeding (<3 days). High clay content and low elevation were associated with establishment failures. Overall, our results highlight the ability of RCG strips to restore dense perennial vegetation cover in cultivated floodplain, thereby providing suitable habitat for fish spawning during spring floods. This study provides significant insight into the drivers of establishment of perennial grass strips in highly constrained cultivated areas such as floodplains.
Keywords: Infolettre; Infolettre_Novembre_2024

Using remote sensing to assess how intensive agriculture impacts the turbidity of a fluvial lake floodplain - Clermont, Maxime; Kinnard, Christophe; Dubé-Richard, Daphney; Campeau, Stéphane; Bordeleau, Pierre-André; de Grandpré, Arthur; Ziyad, Jawad; Roy, Alexandre (Journal of Great Lakes Research, 2023)
Keywords: Infolettre; Infolettre_Fevrier_2024; Kinnard_Christophe

Efficient or Fair? Operationalizing Ethical Principles in Flood Risk Management: A Case Study on the Dutch‐German Rhine - Ciullo, Alessio; Kwakkel, Jan H.; De Bruijn, Karin M.; Doorn, Neelke; Klijn, Frans (Risk Analysis, 2020)
Abstract Flood risk management decisions in many countries are based on decision‐support frameworks which rely on cost‐benefit analyses. Such frameworks are seldom informative about the geographical distribution of risk, raising questions on the fairness of the proposed policies. In the present work, we propose a new decision criterion that accounts for the distribution of risk reduction and apply it to support flood risk management decisions on a transboundary stretch of the Rhine River. Three types of interventions are considered: embankment heightening, making Room for the River, and changing the discharge distribution of the river branches. The analysis involves solving a flood risk management problem according to four alternative formulations, based on different ethical principles. Formulations based on cost optimization lead to very poor performances in some areas for the sake of reducing the overall aggregated costs. Formulations that also include equity criteria have different results depending on how these are defined. When risk reduction is distributed equally, very poor economic performance is achieved. When risk is distributed equally, results are in line with formulations based on cost optimization, while a fairer risk distribution is achieved. Risk reduction measures also differ, with the cost optimization approach strongly favoring the leverage of changing the discharge distribution and the alternative formulations spending more on embankment heightening and Room for the River, to rebalance inequalities in risk levels. The proposed method advances risk‐based decision‐making by allowing to consider risk distribution aspects and their impacts on the choice of risk reduction measures.

Comparative analysis of local and large-scale approaches to floodplain mapping: a case study of the Chaudière River - Bessar, M. A.; Choné, G.; Lavoie, A.; Buffin-Bélanger, T.; Biron, P. M.; Matte, P.; Anctil, F. (Canadian Water Resources Journal / Revue canadienne des ressources hydriques, 2021)
Floods are among natural disasters that increasingly threaten society, especially with current and future climate change trends. Several tools have been developed to help planners manage the risks associated to flooding, including the mapping of flood-prone areas, but one of the major challenges is still the availability of detailed data, particularly bathymetry. This manuscript compares two modeling approaches to produce flood maps. An innovative large-scale approach that, without bathymetric data, estimates by inverse modeling the bed section for a given flow and a given roughness coefficient through 1 D/2D hydraulic modeling (LISFLOOD-FP). And a local approach, with a detailed coupled 1 D/2D hydraulic model (HEC-RAS) that uses all available information at the bed and floodplain (LiDAR and bathymetry). Both implementations revealed good performance values for flood peak levels as well as excellent fit indices in describing the areal extent of flooding. As expected, the local approach is more accurate, but the results of the large-scale approach are very promising especially for areas lacking bathymetric data and for large-scale governmental programs.

Elemental analysis of hair provides biomarkers of maternal hardship linked to adverse behavioural outcomes in 4-year-old children: The QF2011 Queensland Flood Study - Ambeskovic, Mirela; Laplante, David P.; Kenney, Thomas; Elgbeili, Guillaume; Beaumier, Pierre; Azat, Nagy; Simcock, Gabrielle; Kildea, Sue; King, Suzanne; Metz, Gerlinde A. S. (Journal of Trace Elements in Medicine and Biology, 2022)
Background Exposure to adverse experiences during pregnancy, such as a natural disaster, can modify development of the child with potential long-term consequences. Elemental hair analysis may provide useful indicators of cellular homeostasis and child health. The present study investigated (1) if flood-induced prenatal maternal stress is associated with altered hair elemental profiles in 4-year-old children, and (2) if hair elemental profiles are associated with behavioural outcomes in children. Methods Participants were 75 children (39 boys; 36 girls) whose mothers were exposed to varying levels of stress due to a natural disaster (2011 Queensland Flood, Australia) during pregnancy. At 4 years of age, language development, attention and internalizing and externalizing problems were assessed and scalp hair was collected. Hair was analyzed by inductively coupled plasma mass spectrometry (ICP-MS) for 28 chemical elements. Results A significant curvilinear association was found between maternal objective hardship and copper levels in boys, as low and high maternal objective hardship levels were associated with the highest hair copper levels. Mediation analysis revealed that low levels of maternal objective hardship and high levels of copper were associated with lower vocabulary scores. Higher levels of maternal objective hardship were associated with higher magnesium levels, which in turn were associated with attention problems and aggression in boys. In girls, high and low maternal objective hardship levels were associated with high calcium/potassium ratios. Conclusion Elemental hair analysis may provide a sensitive biomonitoring tool for early identification of health risks in vulnerable children.
Keywords: Infolettre; Infolettre_Octobre_2022

Change point detection of flood events using a functional data framework - Alaya, Mohamed Ben; Ternynck, Camille; Dabo-Niang, Sophie; Chebana, Fateh; Ouarda, Taha B. M. J. (Advances in Water Resources, 2020)
Abstract Change point detection methods have an important role in many hydrological and hydraulic studies of river basins. These methods are very useful to characterize changes in hydrological regimes and can, therefore, lead to better understanding changes in extreme flows behavior. Flood events are generally characterized by a finite number of characteristics that may not include the entire information available in a discharge time series. The aim of the current work is to present a new approach to detect changes in flood events based on a functional data analysis framework. The use of the functional approach allows taking into account the whole information contained in the discharge time series of flood events. The presented methodology is illustrated on a flood analysis case study, from the province of Quebec, Canada. Obtained results using the proposed approach are consistent with those obtained using a traditional change point method, and demonstrate the capability of the functional framework to simultaneously consider several flood features and, therefore, presenting a comprehensive way for a better exploitation of the information contained in a discharge time series.

Sensibilisation au risque d’inondation par une séquence d’enseignement en probabilités - Thibault, Mathieu (2024)
Je fais partie d’une équipe interdisciplinaire d’un projet de recherche subventionné qui vise à sensibiliser les élèves du premier cycle du secondaire (12-14 ans) au risque d’inondation. Avec une didacticienne de la géographie, deux personnes didacticiennes des sciences et technologie et deux spécialistes de l’hydrologie et de l’hydraulique, nous avons fait ressortir des points d’ancrage à prendre en compte pour concevoir une séquence didactique interdisciplinaire (en mathématiques, sciences et technologie, univers social) sur ce sujet. Ce projet s’inscrit dans une approche de recherche- développement (Bergeron et Rousseau, 2021), ayant une double finalité de développement (concevoir un produit en réponse aux besoins du milieu de pratique) et de recherche (contribuer à l’avancement des connaissances scientifiques). Cet article présente : 1. Des informations sur les inondations ainsi que les concepts associés (aléa, exposition, vulnérabilité et risque) ; 2. Une analyse des programmes de formation de l’école québécoise (PFEQ) en mathématiques au secondaire (Gouvernement du Québec, 2006, 2016a) et de la progression des apprentissages (PDA) au primaire (Gouvernement du Québec, 2009) et au secondaire (Gouvernement du Québec, 2016b) au sujet du risque d’inondation ; 3. Les grandes lignes d’une séquence d’enseignement en probabilités visant à sensibiliser les élèves du premier cycle du secondaire au risque d’inondation.
Keywords: Infolettre; Infolettre_Mai_2024; Site_internet_RIISQ

Conséquences des inondations de 2019 chez les intervenants de première et de deuxième lignes : le point de vue des principaux intéressés - Maltais, Danielle; Hamel, Ariane; Lansard, Anne-Lise (Canadian Social Work Review, 2024)
Keywords: Infolettre; Infolettre_Octobre_2024

Impact of the Carbon Cycle on Mercury Dynamics in a River Impacted by Run-Of-The-River Power Plants, Logging and Forest Fire - Amyot, Marc; Ponton, Dominic; Bilodeau, François; Harrisson, Makaila; Leclerc, Maxime; Millera Ferriz, Lise; Lavoie, Raphaël; Storck, Veronika; Planas, Dolors; Poulain, Alexandre; Walsh, David (Goldschmidt2020, 2020)

Défis de l’action intersectorielle et pistes de réflexion pour renforcer la concertation dans les milieux ruraux du Québec en contexte de pandémie - Richard, Julie; Bergeron, Dave A.; Lessard, Lily; Toupin, Isabelle; Ouellet, Nicole; Bédard, Emmanuelle (Global Health Promotion, 2021)
La présente pandémie nécessite le recours aux mécanismes qui favorisent l’action intersectorielle entre les autorités et les partenaires de différents secteurs de la santé et de la société civile pour coordonner et adapter la réponse socio-sanitaire en fonction des particularités des milieux et de l’évolution de la pandémie. Ce commentaire propose de mettre en lumière quelques défis qui se posent actuellement dans la mise en œuvre d’actions intersectorielles dans les milieux ruraux du Québec. Des pistes de réflexion en faveur du renforcement des mécanismes de concertation nécessaires à la gestion de la pandémie sont proposées.
Keywords: Lessard_Lily

Mémoire du risque et autonomisation comme facteurs d’adaptation dans un contexte d’inondations récurrentes - Bouchard-Bastien, Emmanuelle; Doyon, Sabrina (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Regards sur les mécanismes et les facteurs contrôlant les inondations des bassins versants du Québec méridional - Bourgault, Marc-André; Boivin, Maxime; Roy, René; Desrochers, Georges; Anctil, François (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Boivin_Maxime; Chapitre_Ouvrage_Collectif_Numero1

Prise en compte des risques d’inondation par les autorités locales : le cas des territoires concernés par les crues du lac des Deux-Montagnes (région de Montréal, Québec) - Fournier, Caroline; L. Van Neste, Sophie (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Conséquences sociosanitaires des inondations printanières de 2019 : comprendre afin de mieux agir - Généreux, Mélissa; Landaverde, Elsa; Maltais, Danielle (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Généreux_Mélissa

Intervenir auprès des jeunes après une catastrophe : les rôles et les responsabilités du personnel scolaire - Lansard, Anne-Lise; Maltais, Danielle (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)

Exposition aux inondations : stress, difficultés vécues et conséquences sur différentes sphères de vie des sinistrés - Maltais, Danielle; Gilbert, Simon (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Interventions déployées lors des inondations de 2019 par les intervenants de première et de deuxième lignes - Maltais, Danielle; Lansard, Anne-Lise; Généreux, Mélissa; Martel, Jimmy (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Généreux_Mélissa

Les stratégies d’intervention déployées lors des inondations de 2019 : le point de vue d’intervenants de première et de deuxième lignes sur les avenues prometteuses - Maltais, Danielle; Lansard, Anne-Lise; Généreux, Mélissa (2021)
Au printemps 2017 et 2019, plus 300 municipalités du Québec ont été confrontées à de graves inondations qui ont provoqué d’importants dommages aux propriétés, aux biens personnels de milliers de citoyens et à plusieurs infrastructures municipales. Dans le contexte des inondations de 2019, il faut toutefois souligner l’importante différence entre celles vécues par la municipalité de Sainte-Marthe-sur-le-Lac et celles survenues dans les autres municipalités du Québec. À Sainte-Marthe-sur-le-Lac, les inondations ont été soudaines, et rapides, car elles ont été provoquées par la rupture d’une digue. Ce sinistre, de nature anthropique, a occasionné la relocalisation d’urgence de plusieurs centaines de familles. Quant aux autres municipalités, c’est la crue printanière qui a généré des inondations fluviales, un sinistre de cause naturelle, dont l’ampleur et la durée ont dépassé les précédents évènements historiques, y compris ceux de 2017. Lors de ces inondations, les municipalités et divers partenaires gouvernementaux (CIUSSS/CISSS, MSP, SQ…) et certains organismes bénévoles en sécurité civile (Croix-Rouge Canadienne, Armée du Salut, Ambulance St-Jean, etc.), ont déployé leurs intervenants afin d’apporter leur aide et leur soutien aux municipalités et aux personnes sinistrées. Des centaines de policiers, pompiers, employés municipaux, gestionnaires, chefs d’équipe, militaires, intervenants psychosociaux, bénévoles spécialisés en recherche et sauvetage ou en soutien émotionnel ont alors travaillé sans relâche pour assurer la sécurité des personnes et des biens, mais pour aussi amortir, autant que possible, les impacts psychosociaux inévitablement causés par ce type de sinistre. Ce rapport synthèse présente le point de vue d’une centaine d’intervenants, provenant de différentes régions du Québec qui ont contribué à la gestion et la coordination des efforts pour orchestrer la réponse nécessaire lors des inondations de 2019. Ils ont été invités à documenter les stratégies mises en place à court et à moyen terme qui, selon leurs observations, ont contribué à : •Augmenter le sentiment de sécurité des sinistrés ; •Diminuer leur niveau d’anxiété et d’isolement ; et •Prévenir la détérioration de leur état de santé physique et psychologique.
Keywords: Généreux_Mélissa

Adolescents Exposed to Cumulative Natural Disasters: A Comparison Between their Realities in Rural and Urban Areas - Pouliot, Eve; Maltais, Danielle; Gervais, Christine; Tardif-Grenier, Kristel; Simard, Ann-Sophie; Gauthier, Pascal; Maltais-Dufour, Olivia; Hamel, Ariane (Prehospital and Disaster Medicine, 2023)
Introduction: Over the past years, the Outaouais region (Quebec, Canada) and their residents have had to endure no less than five natural disasters (floods, tornadoes). These disasters are likely to have a variety of consequences on the physical and mental health of adolescents, as well as on their personal, family, school and social lives. The experiences of teenagers are also likely to vary depending on whether they live in rural or urban areas. Method: Data were collected via a self-administered questionnaire in February 2022. A total of 1307 teenagers from two high schools participated in the study by completing an online survey. The questionnaire measured various aspects of the youth's mental health using validated tests, such as manifestations of post-traumatic stress, anxiety and depression, as well as the presence of suicidal thoughts and self-harm. Other aspects of the youth's experience were measured, including their level of social support, school engagement, alcohol and drug use, and coping strategies. Results: One third of young students (n=1307) were experiencing depressive symptoms and suicidal thoughts, as well as significant daily stress. More than 25% of the students had moderate or severe anxiety and thoughts of self-harm. These problems were significantly more prevalent among youths with prior exposure to a natural disaster. The study data also revealed that youths living in rural areas had a more worrying profile than those living in urban areas. Conclusion: Similar to other studies (Ran et al., 2015; Stratta et al., 2014), our research data revealed that youths living in rural areas presented a more concerning profile than those residing in urban areas. It therefore seems important, in future studies and services, to focus more specifically on these teenagers to better understand their needs and to develop adapted services more likely to meet them.

Les facteurs associés à la présence de pensées suicidaires chez les jeunes en contexte de catastrophe : quelles leçons tirer des études existantes en contexte de pandémie ? - Pouliot, Eve; Dubois, Pascale; Maltais, Danielle; Lansard, Anne-Lise; Simard, Ann-Sophie (Enfance en difficulté, 2022)
Il est largement reconnu que les catastrophes naturelles engendrent des conséquences importantes pour les populations exposées. Les jeunes sont particulièrement vulnérables à développer des problèmes de santé mentale après un désastre, notamment des pensées suicidaires. Or, dans le contexte de la pandémie de la COVID-19, il s’avère important de documenter ce phénomène afin d’intervenir efficacement, d’autant plus que les catastrophes et les risques de pandémie tendent à augmenter. Cette revue systématique des écrits vise à identifier les facteurs associés positivement ou négativement à la présence de pensées suicidaires chez les jeunes à la suite d’une catastrophe. Au total, 24 articles scientifiques ont été retenus pour l’analyse et ont permis de dégager plusieurs facteurs associés aux pensées suicidaires, tels que la dépression, le stress post-traumatique, l’âge, l’exposition au désastre, ainsi que les traumatismes antérieurs. Des pistes concrètes découlent de la présente analyse afin d’orienter l’intervention auprès des jeunes dans ce contexte. , It is widely recognized that natural disasters have significant consequences for exposed populations. Teenagers are particularly vulnerable to develop mental health problems after a disaster, including suicidal thoughts. However, in the context of the COVID-19 pandemic, it is important to document this reality in order to prevent suicidal thoughts, especially as disasters and pandemic risks tend to increase. This systematic review of the literature aims to identify factors associated positively or negatively with the presence of suicidal thoughts in teenagers following a disaster. 24 scientific articles were selected for analysis and have allowed to identify several associated factors, such as depression, post-traumatic stress, age, exposure to disaster, and previous trauma. Concrete avenues emerge from this analysis to guide intervention with teenagers in this context.

Applicabilité du concept d’espace de liberté dans les pratiques de gestion des cours d’eau et des plaines inondables au Québec - Massé, Simon; Buffin-Belanger, Thomas; Biron, Pascale; Ruiz, Julie (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Réaménagement résilient et innovant face aux inondations : qu’apprendre des stratégies coconstruites à Saint-André d’Argenteuil ? - Thomas, Isabelle; Gagnon, Alexandre; Biron, Pascale; Gauthier, Myriam; Bonneville, Marie-Claude; Morin, Stéphanie (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Thomas_Isabelle

Atmospheric blocking events in the North Atlantic: trends and links to climate anomalies and teleconnections - Wazneh, Hussein; Gachon, Philippe; Laprise, René; de Vernal, Anne; Tremblay, Bruno (Climate Dynamics, 2021)
Atmospheric blockings are generally associated with large-scale high-pressure systems that interrupt west-to-east atmospheric flow in mid and high latitudes. Blockings cause several days of quasi-stationary weather conditions, and therefore can result in monthly or seasonal climate anomalies and extreme weather events on the affected regions. In this paper, the long-term coupled CERA-20C reanalysis data from 1901 to 2010 are used to evaluate the links between blocking events over the North Atlantic north of 35° N, and atmospheric and oceanic modes of climate variability on decadal time scales. This study indicates more frequent and longer lasting blocking events than previous studies using other reanalyses products. A strong relationship was found between North Atlantic blocking events and North Atlantic Oscillation (NAO), Atlantic Multidecadal Oscillation (AMO) and Baffin Island–West Atlantic (BWA) indices, in fall, winter and spring. More blocking events occur during the negative phases of the NAO index and positive phases of the BWA mode. In some situations, the BWA patterns provide clearer links with the North Atlantic blocking occurrence than with the NAO alone. The correlation between the synchronous occurrences of AMO and blocking is generally weak, although it does increase for a lag of about 6–10 years. Convergent cross mapping (CCM) furthermore demonstrates a significant two-way causal effect between blocking occurrences and the NAO and BWA indices. Finally, while we find no significant trends in blocking frequencies over the last 110 years in the Northern Hemisphere, these events become longer lasting in summer and fall, and more intense in spring in the North Atlantic.
Keywords: Gachon_Philippe

Predicting malaria risk considering vector control interventions under climate change scenarios - Sadoine, Margaux L.; Zinszer, Kate; Liu, Ying; Gachon, Philippe; Fournier, Michel; Dueymes, Guillaume; Dorsey, Grant; Llerena, Ana; Namuganga, Jane Frances; Nasri, Bouchra; Smargiassi, Audrey (Scientific Reports, 2024)
Many studies have projected malaria risks with climate change scenarios by modelling one or two environmental variables and without the consideration of malaria control interventions. We aimed to predict the risk of malaria with climate change considering the influence of rainfall, humidity, temperatures, vegetation, and vector control interventions (indoor residual spraying (IRS) and long-lasting insecticidal nets (LLIN)). We used negative binomial models based on weekly malaria data from six facility-based surveillance sites in Uganda from 2010–2018, to estimate associations between malaria, environmental variables and interventions, accounting for the non-linearity of environmental variables. Associations were applied to future climate scenarios to predict malaria distribution using an ensemble of Regional Climate Models under two Representative Concentration Pathways (RCP4.5 and RCP8.5). Predictions including interaction effects between environmental variables and interventions were also explored. The results showed upward trends in the annual malaria cases by 25% to 30% by 2050s in the absence of intervention but there was great variability in the predictions (historical vs RCP 4.5 medians [Min–Max]: 16,785 [9,902–74,382] vs 21,289 [11,796–70,606]). The combination of IRS and LLIN, IRS alone, and LLIN alone would contribute to reducing the malaria burden by 76%, 63% and 35% respectively. Similar conclusions were drawn from the predictions of the models with and without interactions between environmental factors and interventions, suggesting that the interactions have no added value for the predictions. The results highlight the need for maintaining vector control interventions for malaria prevention and control in the context of climate change given the potential public health and economic implications of increasing malaria in Uganda.
Keywords: Gachon_Philippe

Differential Influence of Environmental Factors on Malaria Due to Vector Control Interventions in Uganda - Sadoine, Margaux L.; Smargiassi, Audrey; Liu, Ying; Gachon, Philippe; Fournier, Michel; Dueymes, Guillaume; Namuganga, Jane Frances; Dorsey, Grant; Nasri, Bouchra; Zinszer, Kate (International Journal of Environmental Research and Public Health, 2023)
Background: Few studies have explored how vector control interventions may modify associations between environmental factors and malaria. Methods: We used weekly malaria cases reported from six public health facilities in Uganda. Environmental variables (temperature, rainfall, humidity, and vegetation) were extracted from remote sensing sources. The non-linearity of environmental variables was investigated, and negative binomial regression models were used to explore the influence of indoor residual spraying (IRS) and long-lasting insecticidal nets (LLINs) on associations between environmental factors and malaria incident cases for each site as well as pooled across the facilities, with or without considering the interaction between environmental variables and vector control interventions. Results: An average of 73.3 weekly malaria cases per site (range: 0–597) occurred between 2010 and 2018. From the pooled model, malaria risk related to environmental variables was reduced by about 35% with LLINs and 63% with IRS. Significant interactions were observed between some environmental variables and vector control interventions. There was site-specific variability in the shape of the environment–malaria risk relationship and in the influence of interventions (6 to 72% reduction in cases with LLINs and 43 to 74% with IRS). Conclusion: The influence of vector control interventions on the malaria–environment relationship need to be considered at a local scale in order to efficiently guide control programs.
Keywords: Gachon_Philippe

The influence of the environment and indoor residual spraying on malaria risk in a cohort of children in Uganda - Sadoine, Margaux L.; Smargiassi, Audrey; Liu, Ying; Gachon, Philippe; Dueymes, Guillaume; Dorsey, Grant; Fournier, Michel; Nankabirwa, Joaniter I.; Rek, John; Zinszer, Kate (Scientific Reports, 2022)
Studies have estimated the impact of the environment on malaria incidence although few have explored the differential impact due to malaria control interventions. Therefore, the objective of the study was to evaluate the effect of indoor residual spraying (IRS) on the relationship between malaria and environment (i.e. rainfall, temperatures, humidity, and vegetation) using data from a dynamic cohort of children from three sub-counties in Uganda. Environmental variables were extracted from remote sensing sources and averaged over different time periods. General linear mixed models were constructed for each sub-counties based on a log-binomial distribution. The influence of IRS was analysed by comparing marginal effects of environment in models adjusted and unadjusted for IRS. Great regional variability in the shape (linear and non-linear), direction, and magnitude of environmental associations with malaria risk were observed between sub-counties. IRS was significantly associated with malaria risk reduction (risk ratios vary from RR = 0.03, CI 95% [0.03–0.08] to RR = 0.35, CI95% [0.28–0.42]). Model adjustment for this intervention changed the magnitude and/or direction of environment-malaria associations, suggesting an interaction effect. This study evaluated the potential influence of IRS in the malaria-environment association and highlighted the necessity to control for interventions when they are performed to properly estimate the environmental influence on malaria. Local models are more informative to guide intervention program compared to national models.
Keywords: Gachon_Philippe

Assessment of simulations of a polar low with the Canadian Regional Climate Model - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (PLOS ONE, 2023)
Polar lows (PLs), which are intense maritime polar mesoscale cyclones, are associated with severe weather conditions. Due to their small size and rapid development, PL forecasting remains a challenge. Convection-permitting models are adequate to forecast PLs since, compared to coarser models, they provide a better representation of convection as well as surface and near-surface processes. A PL that formed over the Norwegian Sea on 25 March 2019 was simulated using the convection-permitting Canadian Regional Climate Model version 6 (CRCM6/GEM4, using a grid mesh of 2.5 km) driven by the reanalysis ERA5. The objectives of this study were to quantify the impact of the initial conditions on the simulation of the PL, and to assess the skill of the CRCM6/GEM4 at reproducing the PL. The results show that the skill of the CRCM6/GEM4 at reproducing the PL strongly depends on the initial conditions. Although in all simulations the synoptic environment is favourable for PL development, with a strong low-level temperature gradient and an upper-level through, only the low-level atmospheric fields of three of the simulations lead to PL development through baroclinic instability. The two simulations that best captured the PL represent a PL deeper than the observed one, and they show higher temperature mean bias compared to the other simulations, indicating that the ocean surface fluxes may be too strong. In general, ERA5 has more skill than the simulations at reproducing the observed PL, but the CRCM6/GEM4 simulation with initialisation time closer to the genesis time of the PL reproduces quite well small scale features as low-level baroclinic instability during the PL development phase.
Keywords: Gachon_Philippe

Analysis of the Development Mechanisms of a Polar Low over the Norwegian Sea Simulated with the Canadian Regional Climate Model - Moreno-Ibáñez, Marta; Laprise, René; Gachon, Philippe (Atmosphere, 2023)
Polar lows (PLs) are maritime mesoscale cyclones associated with severe weather. They develop during marine cold air outbreaks near coastlines and the sea ice edge. Unfortunately, our knowledge about the mechanisms leading to PL development is still incomplete. This study aims to provide a detailed analysis of the development mechanisms of a PL that formed over the Norwegian Sea on 25 March 2019 using the output of a simulation with the sixth version of the Canadian Regional Climate Model (CRCM6/GEM4), a convection-permitting model. First, the life cycle of the PL is described and the vertical wind shear environment is analysed. Then, the horizontal wind divergence and the baroclinic conversion term are computed, and a surface pressure tendency equation is developed. In addition, the roles of atmospheric static stability, latent heat release, and surface heat and moisture fluxes are explored. The results show that the PL developed in a forward-shear environment and that moist baroclinic instability played a major role in its genesis and intensification. Baroclinic instability was initially only present at low levels of the atmosphere, but later extended upward until it reached the mid-troposphere. Whereas the latent heat of condensation and the surface heat fluxes also contributed to the development of the PL, convective available potential energy and barotropic conversion do not seem to have played a major role in its intensification. In conclusion, this study shows that a convection-permitting model simulation is a powerful tool to study the details of the structure of PLs, as well as their development mechanisms.
Keywords: Gachon_Philippe

Climate change alone cannot explain boreal caribou range recession in Quebec since 1850 - Morineau, Chloé; Boulanger, Yan; Gachon, Philippe; Plante, Sabrina; St‐Laurent, Martin‐Hugues (Global Change Biology, 2023)
Abstract The contraction of species range is one of the most significant symptoms of biodiversity loss worldwide. While anthropogenic activities and habitat alteration are major threats for several species, climate change should also be considered. For species at risk, differentiating the effects of human disturbances and climate change on past and current range transformations is an important step towards improved conservation strategies. We paired historical range maps with global atmospheric reanalyses from different sources to assess the potential effects of recent climate change on the observed northward contraction of the range of boreal populations of woodland caribou ( Rangifer tarandus caribou ) in Quebec (Canada) since 1850. We quantified these effects by highlighting the discrepancies between different southern limits of the caribou's range (used as references) observed in the past and reconstitutions obtained through the hindcasting of the climate conditions within which caribou are currently found. Hindcasted southern limits moved ~105 km north over time under all reanalysis datasets, a trend drastically different from the ~620 km reported for observed southern limits since 1850. The differences in latitudinal shift through time between the observed and hindcasted southern limits of distribution suggest that caribou range recession should have been only 17% of what has been observed since 1850 if recent climate change had been the only disturbance driver. This relatively limited impact of climate reinforces the scientific consensus stating that caribou range recession in Quebec is mainly caused by anthropogenic drivers (i.e. logging, development of the road network, agriculture, urbanization) that have modified the structure and composition of the forest over the past 160 years, paving the way for habitat‐mediated apparent competition and overharvesting. Our results also call for a reconsideration of past ranges in models aiming at projecting future distributions, especially for endangered species.
Keywords: Gachon_Philippe

Corridors fluviaux résilients : qu’est-ce que le Québec peut apprendre de l’international ? - Mayer-Jouanjean, Isabelle; Boucher, Étienne; Lavoie, Roxane; Gachon, Philippe (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Gachon_Philippe

Respiratory and Otolaryngology Symptoms Following the 2019 Spring Floods in Quebec - Landaverde, Elsa; Généreux, Mélissa; Maltais, Danielle; Gachon, Philippe (International Journal of Environmental Research and Public Health, 2022)
Background: Although floods may have important respiratory health impacts, few studies have examined this issue. This study aims to document the long-term impacts of the spring floods of 2019 in Quebec by (1) describing the population affected by the floods; (2) assessing the impacts on the respiratory system according to levels of exposure; and (3) determining the association between stressors and respiratory health. Methods: A population health survey was carried out across the six most affected regions 8–10 months post-floods. Data were collected on self-reported otolaryngology (ENT) and respiratory symptoms, along with primary and secondary stressors. Three levels of exposure were examined: flooded, disrupted and unaffected. Results: One in ten respondents declared being flooded and 31.4% being disrupted by the floods. Flooded and disrupted participants reported significantly more ENT symptoms (adjusted odds ratio (aOR): 3.18; 95% CI: 2.45–4.14; aOR: 1.76; 95% CI: 1.45–2.14) and respiratory symptoms (aOR: 3.41; 95% CI: 2.45–4.75; aOR: 1.45; 95% CI: 1.10–1.91) than the unaffected participants. All primary stressors and certain secondary stressors assessed were significantly associated with both ENT and respiratory symptoms, but no “dose–response” gradient could be observed. Conclusion: This study highlights the long-term adverse effects of flood exposure on respiratory health.
Keywords: Gachon_Philippe; Généreux_Mélissa; Infolettre; Infolettre_Octobre_2022; Site_internet_RIISQ

Analyse des liens entre la précipitation extrême et la température : étude de cas dans le bassin versant de la rivière des Outaouais (BVRO) à partir des simulations du modèle climatique régional développé au centre ESCER - Llerena, Ana (2021)
Dans le contexte du réchauffement planétaire, la relation de Clausius Clapeyron (CC) est utilisée comme un indicateur de l’évolution des précipitations extrêmes. Parmi les théories proposées, nous utilisons dans notre recherche une relation exponentielle qui fait le lien entre l’évolution des centiles les plus extrêmes des précipitations et le changement de la température ΔT dans le climat actuel. Selon cette théorie, les précipitations augmentent au même rythme que la capacité de rétention d'humidité dans l’atmosphère, expliquée par la relation de CC, avec un taux de changement d'environ 7 % par degré Celsius pour des valeurs de température et de pression près de la surface. Ainsi, le présent travail vise à vérifier l’existence de liens physiquement plausibles dans la relation entre les précipitations extrêmes et la température de l’air pour la région du Bassin Versant de la Rivière des Outaouais (BVRO) sur la période 1981-2010, à l’aide des simulations du Modèle Régional Canadien du Climat (MRCC) (versions 5 et 6), développé au centre ESCER, et de deux produits de réanalyses du Centre Européen pour les prévisions météorologiques à moyen terme (CEPMMT) à différentes résolutions spatiales. En général, les précipitations quotidiennes suivent un taux de changement inférieur à celui de CC ; tandis que les précipitations horaires augmentent plus rapidement avec la température. Dans ce dernier cas, pour la simulation du MRCC5 à plus haute résolution spatiale, des taux de changement supérieurs à CC ont même été produits, jusqu’à 10,2 %/°C. Ce travail a également mis en évidence qu’au-delà du seuil de 20°C, la capacité de rétention d'humidité de l’atmosphère n’est pas le seul facteur déterminant pour générer des précipitations extrêmes, et que d’autres facteurs sont à considérer, comme la disponibilité de l'humidité au moment de l'événement de précipitation et la présence de mécanismes dynamiques qui favorisent les mouvements verticaux ascendants. Un comportement sous forme de crochet, qui décrit une augmentation des précipitations jusqu'à un seuil de température, est observé dans la saison estivale avec le MRCC5, mais il a disparu avec les simulations du MRCC6, ce qui pourrait être une conséquence d’avoir seulement une année de simulation disponible ou bien d’une conséquence de la très haute résolution du modèle sur les intervalles de température et sur les effets locaux. En conclusion, l'applicabilité de la relation de CC ne doit pas être généralisée quant à l’étude des précipitations extrêmes, il est également important de considérer l'échelle temporelle, la résolution du modèle utilisé et la saison de l'année. L’évolution de cette relation de CC devrait être évaluée avec des simulations à très haute résolution spatiale (version en développement au centre ESCER), et pour d’autres zones climatiques, sachant que les intervalles de températures et les effets locaux exercent un rôle majeur sur les occurrences et les intensités des fortes précipitations. Ces éléments sont essentiels à intégrer dans le contexte des changements climatiques, en raison des conséquences associées aux fortes précipitations, notamment sur l’occurrence des inondations. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : Clausius-Clapeyron, évènements extrêmes, aléas météorologiques, risques d’inondation, changements climatiques
Keywords: Gachon_Philippe

The 2023 wildfire season in Québec: an overview of extreme conditions, impacts, lessons learned and considerations for the future - Boulanger, Yan; Arseneault, Dominique; Bélisle, Annie Claude; Bergeron, Yves; Boucher, Jonathan; Boucher, Yan; Danneyrolles, Victor; Erni, Sandy; Gachon, Philippe; Girardin, Martin P.; Grant, Eliane; Grondin, Pierre; et al. (Canadian Journal of Forest Research, 2024)
The 2023 wildfire season in Québec set records due to extreme warm and dry conditions, burning 4.5 million hectares and indicating persistent and escalating impacts associated with climate change. This study reviews the unusual weather conditions that led to the fires, discussing their extensive impacts on the forest sector, fire management, boreal caribou habitats, and particularly the profound effects on First Nation communities. The wildfires led to significant declines in forest productivity and timber supply, overwhelming fire management resources, and necessitating widespread evacuations. First Nation territories were dramatically altered, facing severe air quality issues and disruptions. While caribou impacts were modest across the province, the broader ecological, economical, and social repercussions were considerable. To mitigate future extreme wildfire seasons, the study suggests changes in forest management practices to increase forest resilience and resistance, adapting industrial structures to changes in wood type harvested, and enhancing fire suppression and risk management strategies. It calls for a comprehensive, unified approach to risk management that incorporates the lessons learned from the 2023 fire season and accounts for ongoing climate change. The studyunderscores the urgent need for detailed planning and proactive measures to reduce the growing risks and impacts of wildfires in a changing climate.
Keywords: Gachon_Philippe; Guillemette_Francois

Overview of Retrogressive Landslide Risk Analysis in Sensitive Clay Slope - Richer, Blanche; Saeidi, Ali; Boivin, Maxime; Rouleau, Alain (Geosciences, 2020)
Sensitive clays are known for producing retrogressive landslides, also called spread or flowslides. The key characteristics associated with the occurrence of these landslides on a sensitive clay slope must be assessed, and the potential retrogressive distance must be evaluated. Common risk analysis methods include empirical methods for estimating the distance of potential retrogression, analytical limit equilibrium methods, numerical modelling methods using the strength reduction technique, and the integration of a progressive failure mechanism into numerical methods. Methods developed for zoning purposes in Norway and Quebec provide conservative results in most cases, even if they don’t cover the worst cases scenario. A flowslide can be partially analysed using analytical limit equilibrium methods and numerical methods having strength reduction factor tools. Numerical modelling of progressive failure mechanisms using numerical methods can define the critical parameters of spread-type landslides, such as critical unloading and the retrogression distance of the failure. Continuous improvements to the large-deformation numerical modeling approach allow its application to all types of sensitive clay landslides.
Keywords: Boivin_Maxime

Use of digital elevation models for flood susceptibility assessment via a hydrogeomorphic approach: A case study of the Basento River in Italy - Albano, Raffaele; Adamowski, Jan (Natural Hazards, 2025)
Abstract Floods are the most common and threatening natural risk for many countries in the world. Flood risk mapping is therefore of great importance for managing socio-economic and environmental impacts. Several researchers have proposed low-complexity and cost-effective flood mapping solutions that are useful for data scarce environments or at large-scale. Among these approaches, a line of recent research focuses on hydrogeomorphic methods that, due to digital elevation models (DEMs), exploit the causality between past flood events and the hydraulic geometry of floodplains. This study aims to compare the use of freely-available DEMs to support an advanced hydrogeomorphic method, Geomorphic Flood Index (GFI), to map flood-prone areas of the Basento River basin (Italy). The five selected DEMs are obtained from different sources, are characterized by different resolutions, spatial coverage, acquisition process, processing and validation, etc., and include: (i) HydroSHEDS v.1.1 (resolution 3 arc-seconds), hydrologically conditioned, derived primarily from STRM (NASA) and characterized by global coverage; (ii) ASTER GDEM v.3 with a res. of around 30 m (source: METI and NASA) and global coverage; (iii) EU-DEM v. 1.1 (res. 1 arc-second), Pan-European and combining SRTM and ASTER GDEM, customized to obtain a consistency with the EU-Hydro and screened to remove artefacts (source: Copernicus Land Monitoring Service); (iv) TinItaly DEM v. 1.1, (res. 10 m-cell size grid) and produced and distributed by INGV with coverage of the entire Italian territory; (v) Laser Scanner DEM with high resolution (5 m cell size grid) produced on the basis of Ground e Model Keypoint and available as part of the RSDI geoportal of the Basilicata Region with coverage at the regional administrative level. The effects of DEMs on the performance of the GFI calibration on the main reach of the Basento River, and its validation on one of its mountain tributaries (Gallitello Creek), were evaluated with widely accepted statistical metrics, i.e., the Area Under the Receiver Operating Characteristics (ROC) curve (AUC), Accuracy, Sensitivity and Specificity. Results confirmed the merits of the GFI in flood mapping using simple watershed characteristics and showed high Accuracy (AUC reached a value over 0.9 in all simulations) and low dependency on changes in the adopted DEMs and standard flood maps (1D and 2D hydraulic models or three return periods). The EU-DEM was identified as the most suitable data source for supporting GFI mapping with an AUC > 0.97 in the calibration phase for the main river reach. This may be due in part to its appropriate resolution for hydrological application but was also due to its customized pre-processing that supported an optimal description of the river network morphology. Indeed, EU-DEM obtained the highest performances (e.g., Accuracy around 98%) even in the validation phase where better results were expected from the high-resolution DEM (due to the very small size of Gallitello Creek cross-sections). For other DEMs, GFI generally showed an increase in metrics performance when, in the calibration phase, it neglected the floodplains of the river delta, where the standard flood map is produced using a 2D hydraulic model. However, if the DEMs were hydrologically conditioned with a relatively simple algorithm that forced the stream flow in the main river network, the GFI could be applied to the whole Basento watershed, including the delta, with a similar performance.
Keywords: Infolettre; Infolettre_Fevrier_2025

County-scale flood risk assessment of properties and associated population in the United States - Srivastava, Shivendra; Gerdes, Tyler; Roy, Tirthankar (Natural Hazards, 2024)

Soil Erosion in the United States. Present and Future (2020-2050) - Shojaeezadeh, Shahab Aldin; Al-Wardy, Malik; Nikoo, Mohammad Reza; Mooselu, Mehrdad Ghorbani; Alizadeh, Mohammad Reza; Adamowski, Jan Franklin; Moradkhani, Hamid; Alamdari, Nasrin; Gandomi, Amir H. (2022)
Soil erosion is a significant threat to the environment and long-term land management around the world. Accelerated soil erosion by human activities inflicts extreme changes in terrestrial and aquatic ecosystems, which is not fully surveyed/predicted for the present and probable future at field-scales (30-m). Here, we estimate/predict soil erosion rates by water erosion, (sheet and rill erosion), using three alternative (2.6, 4.5, and 8.5) Shared Socioeconomic Pathway and Representative Concentration Pathway (SSP-RCP) scenarios across the contiguous United States. Field Scale Soil Erosion Model (FSSLM) estimations rely on a high resolution (30-m) G2 erosion model integrated by satellite- and imagery-based estimations of land use and land cover (LULC), gauge observations of long-term precipitation, and scenarios of the Coupled Model Intercomparison Project Phase 6 (CMIP6). The baseline model (2020) estimates soil erosion rates of 2.32 Mg ha 1 yr 1 with current agricultural conservation practices (CPs). Future scenarios with current CPs indicate an increase between 8% to 21% under different combinations of SSP-RCP scenarios of climate and LULC changes. The soil erosion forecast for 2050 suggests that all the climate and LULC scenarios indicate either an increase in extreme events or a change in the spatial location of extremes largely from the southern to the eastern and northeastern regions of the United States.
Keywords: Infolettre; Infolettre_Ete_2024

A 600‐year marine record associated with the dynamics of the eastern Penny Ice Cap (Baffin Island, Nunavut, Canada) - Rodríguez‐Cuicas, María‐Emilia; Montero‐Serrano, Jean‐Carlos; St‐Onge, Guillaume; Normandeau, Alexandre (Journal of Quaternary Science, 2023)
ABSTRACT Two composite sedimentary sequences sampled in the ice‐proximal (12CS) and ice‐distal (02CS) areas of Coronation Fjord (Baffin Island, Nunavut, Canada) were investigated in order to reconstruct the effect of climate variability on 600 years of changes in sediment transfer from the eastern Penny Ice Cap (PIC). Detrital proxies, and physical and sedimentological analyses revealed that glacial meltwater discharges led to frequent rapidly deposited layers (RDLs) in ice‐proximal settings. RDLs in ice‐distal settings involved the sudden release of a large quantity of sediment‐laden water during floods probably originating from adjacent fjords with large sandur deltas. Laminated sediments with ice‐rafted debris throughout the Little Ice Age interval in the ice‐proximal environment suggest that colder conditions promoted glacier growth, leading to successive episodes of turbid hyperpycnal meltwater plumes and iceberg calving in Coronation Fjord. Since 1850 ce , the accelerated Coronation retreat in response to modern warming has led to increased sedimentation rates, abrupt mineralogical and grain size proxy variations and more frequent RDLs. Similar trends between the detrital proxies of the ice‐proximal core and Atlantic Multidecadal Oscillation record and Arctic surface air temperature suggest high connectivity between atmospheric and sea surface temperature variations and PIC dynamics over the last 600 years.
Keywords: Infolettre; Infolettre_Juin_2023

Short-duration precipitation extremes over Canada in a warmer climate - Oh, Seok-Geun; Sushama, Laxmi (Climate Dynamics, 2020)
Short-duration precipitation extremes are widely used in the design of engineering infrastructure systems and they also lead to high impact flash flood events and landslides. Better understanding of these events in a changing climate is therefore critical. This study assesses characteristics of short-duration precipitation extremes of 1-, 3-, 6- and 12-h durations in terms of the precipitation-temperature (P–T) relationship in current and future climates for ten Canadian climatic regions using the limited area version of the global environment multiscale (GEM) model. The GEM simulations, driven by ERA-Interim reanalysis and two coupled global climate models (CanESM2 and MPI-ESM), reproduce the general observed regional P–T relationship characteristics in current climate (1981–2010), such as sub-CC (Clausius–Clapeyron) and CC scalings for the coastal and northern, and inland regions, respectively, albeit with some underestimation. Analysis of the transient climate change simulations suggests important shifts and/or extensions of the P–T curve to higher temperature bins in future climate (2071–2100) for RCP4.5 and 8.5 scenarios, particularly for 1-h duration. Analysis of the spatial patterns of dew point depression (temperature minus dew point temperature) and convective available potential energy (CAPE) corresponding to short-duration precipitation extremes for different temperature bins show their changing relative importance from low to high temperature bins. For the low-temperature bins, short-duration precipitation extremes are largely due to high relative humidity, while for high-temperature bins, strong convection due to atmospheric instability brought by surface warming is largely responsible. The analysis thus addresses some of the key knowledge gaps related to the behavior of P–T relationship and associated mechanisms for the Canadian regions.

A 247‐year tree‐ring reconstruction of spring temperature and relation to spring flooding in eastern boreal Canada - Nolin, Alexandre Florent; Girardin, Martin Philippe; Tardif, Jacques Clément; Guo, Xiao Jing; Conciatori, France; Bergeron, Yves (International Journal of Climatology, 2022)
Abstract Few records of spring paleoclimate are available for boreal Canada, as biological proxies recording the beginning of the warm season are uncommon. Given the spring warming observed during the last decades, and its impact on snowmelt and hydrological processes, searching for spring climate proxies is receiving increasing attention. Tree‐ring anatomical features and intra‐annual widths were used to reconstruct the regional March to May mean air temperature from 1770 to 2016 in eastern boreal Canada. Nested principal component regressions calibrated on 116 years of gridded temperature data were developed from one Fraxinus nigra and 10 Pinus banksiana sites. The reconstruction indicated three distinct phases in spring temperature variability since 1770. Ample phases of multi‐decadal warm and cold springs persisted until the end of the Little Ice Age (1850–1870 CE) and were gradually replaced since the 1940s by decadal to interannual variability associated with an increase in the frequency and magnitude of warm springs. Significant correlations with other paleotemperature records, gridded snow cover extent and runoff support that historical high flooding were associated with late, cold springs with heavy snow cover. Most of the high magnitude spring floods reconstructed for the nearby Harricana River also coincided with the lowest reconstructed spring temperature per decade. However, the last 40 years of observed and reconstructed mean spring temperature showed a reduction in the number of extreme cold springs contrasting with the last few decades of extreme flooding in the eastern Canadian boreal region. This result indicates that warmer late spring mean temperatures on average may contribute, among other factors, to advance the spring break‐up and to likely shift the contribution of snow to rain in spring flooding processes.
Keywords: Infolettre; Infolettre_Avril_2022

Changes in floodplain regimes over Canada due to climate change impacts: Observations from CMIP6 models - Mohanty, Mohit Prakash; Simonovic, Slobodan P. (Science of The Total Environment, 2021)
Abstract With the recent Coupled Model Intercomparison Project Phase 6 (CMIP6), water experts and flood modellers are curious to explore the efficacy of the new and upgraded climate models in representing flood inundation dynamics and how they will be impacted in the future by climate change. In this study, for the first time, we consider the latest group of General Circulation Models (GCMs) from CMIP6 to examine the probable changes in floodplain regimes over Canada. A set of 17 GCMs from Shared Socioeconomic Pathways (SSPs) 4.5 (medium forcing) and 8.5 (high end forcing) common to historical (1980 to 2019), near-future (2021 to 2060), and far-future (2061 to 2100) time-periods are selected. A comprehensive framework consisting of hydrodynamic flood modelling, and statistical experiments are put forward to derive high-resolution Canada-wide floodplain maps for 100 and 200-yr return periods. The changes in floodplain regimes for the future periods are analyzed over drainage basin scale in terms of (i) changes in flood inundation extents, (ii) changes in flood hazards (high and very-high classes), and (iii) changes in flood frequency. Our results show a significant rise (>30%) in flood inundation extents in the future periods; particularly intense over western and eastern regions. The flood hazards are expected to cover ~16% more geographical area of Canada. We also find that large areas in northern and western Canada and a few spots in the eastern parts of Canada will be getting flooded more frequently compared to the historical period. The observations derived from this study are vital for enhancing flood preparedness, optimal land-use planning, and refurbishing both structural and non-structural flood control options for improved resilience. The study instills new knowledge on revamping the existing flood management approaches and adaptation strategies for future protection.

A Comprehensive Approach for Floodplain Mapping Through Identification of Hazard Using Publicly Available Data Sets Over Canada - Mohanty, M.P.P; Simonovic, Slobodan P. (2022)
Flood events and their associated damages have escalated significantly in the last few decades. To add to the gruesome situation, many reports and studies warn that flood risk would aggravate significantly in future periods due to significant alterations in the climate patterns and socio-economic dynamics. Floodplain mapping is looked upon as a viable option to tackle this global issue as it provides both quantitative and qualitative information on flood dynamics. Moreover, with the increasing availability of global data and enhancement in computational simulations, it has become easier to simlate flooding patterns at large scales. This study deter-mines the usability of publicly available datasets in capturing flood hazards over Canada. Run-off data set from the North American Regional Reanalysis (NARR), along with a few other rele-vant inputs are fed to CaMa-Flood, a robust global hydrodynamic model to generate flooding patterns for 1 in 100 and 1 in 200-yr return period events over Canada . The simulated maps are compared and validated with the existing maps of a few flood-prone regions in Canada, thereby establishing their performance over both regional and country-scale. Later, the simulated flood-plain maps are used in conjunction with property related information at 34 cities (within the top 100 populous cities in Canada) to determine the degree of exposure due to flooding in 1991, 2001, and 2011. The results indicate that around 80 percent of inundated spots belong to high and very-high hazard classes in a 200-yr event, which is roughly 4 percent more than simulated for 100-yr event. NARR derived floodplain maps perform very well while compared over the six flood-prone regions. While analyzing the exposure of properties to flooding, we notice an in-crease in the number during the last three decades, with the maximum rise observed in Toronto, followed by Montreal, and Edmonton. To disseminate the extensive flood-related information, a web-based public tool, Flood Map Viewer (http://www.floodmapviewer.com/) is developed. The development of the tool was motivated by the commitment of the Canadian government to provide $63 M over the next three years for the completion of flood maps for higher-risk areas. The study reaches out to demonstrate how publicly available datasets can be utilized with a lesser degree of uncertainty in representing flooding patterns over large regions. The flood re-lated information derived from the study can be used along with vulnerability for quantifying flood risk, which will help in developing appropriate pathways for resilience building for long-term sustainable benefits.

Will Evolving Climate Conditions Increase the Risk of Floods of the Large U.S.‐Canada Transboundary Richelieu River Basin? - Lucas‐Picher, Philippe; Lachance‐Cloutier, Simon; Arsenault, Richard; Poulin, Annie; Ricard, Simon; Turcotte, Richard; Brissette, François (JAWRA Journal of the American Water Resources Association, 2021)
Abstract In spring 2011, an unprecedented flood hit the complex eastern United States (U.S.)–Canada transboundary Lake Champlain–Richelieu River (LCRR) Basin, destructing properties and inducing negative impacts on agriculture and fish habitats. The damages, covered by the Governments of Canada and the U.S., were estimated to C$90M. This natural disaster motivated the study of mitigation measures to prevent such disasters from reoccurring. When evaluating flood risks, long‐term evolving climate change should be taken into account to adopt mitigation measures that will remain relevant in the future. To assess the impacts of climate change on flood risks of the LCRR basin, three bias‐corrected multi‐resolution ensembles of climate projections for two greenhouse gas concentration scenarios were used to force a state‐of‐the‐art, high‐resolution, distributed hydrological model. The analysis of the hydrological simulations indicates that the 20‐year return period flood (corresponding to a medium flood) should decrease between 8% and 35% for the end of the 21st Century (2070–2099) time horizon and for the high‐emission scenario representative concentration pathway (RCP) 8.5. The reduction in flood risks is explained by a decrease in snow accumulation and an increase in evapotranspiration expected with the future warming of the region. Nevertheless, due to the large climate inter‐annual variability, short‐term flood probabilities should remain similar to those experienced in the recent past.

Mechanisms of spring freshet generation in southern Quebec, Canada - Kinnard, Christophe; Nemri, Saida; Assani, Ali (2023)
Seasonal forecasting of spring floods in snow-covered basins is challenging due to the ambiguity in the driving processes, uncertain estimations of antecedent catchment conditions and the choice of predictor variables. In this study we attempt to improve the prediction of spring flow peaks in southern Quebec, Canada, by studying the preconditioning mechanisms of runoff generation and their impact on inter-annual variations in the timing and magnitude of spring peak flow. Historical observations and simulated data from a hydrological and snowmelt model were used to study the antecedent conditions that control flood characteristics in twelve snow-dominated catchments. Maximum snow accumulation (peak SWE), snowmelt and rainfall volume, snowmelt and rainfall intensity, and soil moisture were estimated during the pre-flood period. Stepwise multivariate linear regression analysis was used to identify the most relevant predictors and assess their relative contribution to the interannual variability of flood characteristics. Results show that interannual variations in spring peak flow are controlled differently between basins. Overall, interannual variations in peak flow were mainly governed, in order of importance, by snowmelt intensity, rainfall intensity, snowmelt volume, rainfall volume, peak SWE, and soil moisture. Variations in the timing of peak flow were controlled in most basins by rainfall volume and rainfall and snowmelt intensity. In the northernmost, snow-dominated basins, pre-flood rainfall amount and intensity mostly controlled peak flow variability, whereas in the southern, rainier basins snowpack conditions and melt dynamics controlled this variability. Snowpack interannual variations were found to be less important than variations in rainfall in forested basins, where snowmelt is more gradual. Conversely, peak flow was more sensitive to snowpack conditions in agricultural basins where snowmelt occurs faster. These results highlight the impact of land cover and use on spring flood generation mechanism, and the limited predictability potential of spring floods using simple methods and antecedent hydrological factors.
Keywords: Infolettre; Infolettre_Fevrier_2025; Kinnard_Christophe

Using the theory of planned behavior to identify key beliefs underlying flood-related adaptive behaviors in the province of Québec, Canada - Jacob, Johann; Valois, Pierre; Tessier, Maxime; Talbot, Denis; Anctil, François; Cloutier, Geneviève; Renaud, Jean-Sébastien (Journal of Flood Risk Management, 2023)
Given that flooding episodes are occurring at a greater rate due to climate change, individuals must adopt certain adaptation behaviors to prevent or mitigate the anticipated or negative impact of such events. However, few studies have assessed if and how households and individuals have actually taken action in this regard. Because some individual beliefs can be linked to facilitating factors and barriers to action, a better understanding of the adoption of adaptive behaviors requires a combined analysis of individual psychosocial factors. The purpose of this study was to develop a better understanding of the reasons underlying the adoption of behaviors related to structural adaptation to flooding by people living in or near flood-prone areas in the Province of Québec (Canada). Results of a series of structural equation modeling showed that behavioral, normative and control beliefs were all significant predictors of the respondents' intention to adopt structural flood protective behaviors, with normative beliefs being the strongest. By identifying the best psychosocial predictors of the adoption of such behaviors, the results of this study provide valuable insights regarding the most effective factors to be used in public health messages to promote the adoption of behaviors related to structural adaptation to flooding.
Keywords: Infolettre; Infolettre_Mai_2023

Meteorological control on snow depth evolution and snowpack energy exchanges in an agro-forested environment by a measurement-based approach: A case study in Sainte-Marthe, Eastern Canada - Dharmadasa, Vasana; Kinnard, Christophe; Baraër, Michel (Agricultural and Forest Meteorology, 2024)
Keywords: Baraer_Michel; Kinnard_Christophe

Inondations des printemps 2017 et 2019 dans le bassin versant de la rivière des Outaouais (Québec, Canada) : analyse des facteurs physiographiques et météorologiques en cause - Benoit, Clémence; Demers, Isabelle; Roberge, François; Gachon, Philippe; Laprise, René (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Gachon_Philippe

Évaluation du risque d'inondation à Rigaud (Québec, Canada) : le cas de l'inondation printanière de 2017 - Benoit, Clémence (Département de géographie, Université du Québec à Montréal, 2021)
Ce travail de recherche a pour objectif d’évaluer le risque d’inondation printanier à Rigaud (Québec, Canada), en faisant une analyse de cas de l’inondation historique du printemps 2017. Dans la première partie de ce mémoire, une analyse des conditions météorologiques printanières dans le bassin versant de la rivière des Outaouais (BVRO) est d’abord réalisée à partir des données météorologiques sous forme de grille (DAYMET) à 1 km de résolution (1980 à 2017), mais également à partir des données météorologiques de stations d’Environnement et Changement climatique Canada (1963 à 2017). La sévérité des aléas d’inondation à Rigaud (1963 à 2019) est ensuite évaluée en termes d’ampleur de l’aléa hydrologique et des dommages potentiels associés. Dans la seconde partie de ce mémoire,l’exposition au risque d’inondation à Rigaud ainsi que les conditions socio-environnementales contribuant à exacerber le risque d’inondation à l’exutoire du bassin sont caractérisées. Une analyse multicritère qui tient compte de la pente, de la capacité de drainage des sols et de l’utilisation du sol en plus des caractéristiques de l’aléa météorologique dans le BVRO permet d’estimer la contribution des sous-bassins versants (SBV) à l’inondation printanière de 2017 à Rigaud. Au printemps 2017, le dégel brusque du début avril ainsi que le caractère exceptionnellement intense et régulier des événements de précipitation liquide aux mois d’avril et mai, généralisés sur l’ensemble du BVRO, ont contribué en partie à la sévérité de l’inondation. Ces facteurs météorologiques ont eu des conséquences importantes sur l’occurrence et l’intensité de l’inondation durant ces mois, d’autant plus que les conditions les plus extrêmes se sont produites dans les SBV les plus près de l’exutoire et les plus vulnérables, compte tenu de leurs fortes pentes et des modifications importantes au territoire engendrées par les activités humaines entre 1990 et 2010. L’indice de sévérité révèle que les inondations de 2017 et de 2019 se distinguent des autres inondations majeures en raison de l’intensité des débits journaliers enregistrés à l’exutoire du BVRO sur une durée de plus de 40 jours, alors que les dernières inondations historiques de 1974 et 1976 ont plutôt enregistré des niveaux d’eau records à l’exutoire du bassin. À Rigaud, l’exposition au risque d’inondation s’est également accrue entre 1970 et 2017, en raison du développement de l’aménagement périurbain (infrastructure et construction résidentielle) au cours de ces années, résultant en un potentiel de dommages beaucoup plus important lors des événements récents de 2017 et 2019. _____________________________________________________________________________ MOTS-CLÉS DE L’AUTEUR : inondation, risque d’inondation, aléa, facteurs de risque, conditions socioenvironnementales, conditions hydrométéorologiques, exposition, bassin versant de la rivière des Outaouais, Rigaud
Keywords: Gachon_Philippe; Ouvrage_Collectif_Numéro1; Site_internet_RIISQ

Spatiotemporal variability of fall daily maximum flows in southern Quebec (Canada) from 1930 to 2018 - Assani, Ali A. (Journal of Flood Risk Management, 2024)
Abstract Quebec is experiencing a significant increase in summer and fall temperatures and rainfall. This study compares the spatiotemporal variability of maximum daily flows generated by rainfall during the fall season (September–December) in relation to this climatic change and physiographic and land use factors. Analysis of the spatial variability of these maximum flows measured from 1930 to 2018 in 17 watersheds revealed that the magnitude of flows is approximately twice as low on the north shore as it is on the south shore south of 47° N. This difference is explained by three main factors: wetlands (negative correlation) and agricultural (positive correlation) surface area, and summer–fall total precipitation (positive correlation). As for the temporal variability of flows, the different Mann–Kendall statistical tests showed a significant increase in flows due to increased rainfall. The increase of flows was more widespread on the north shore than on the south because the storage capacity of wetlands and other water bodies does not change over time to store excess rainfall. On the south shore, the increase in flows over time is limited due to the significant reduction in agricultural areas since the modernization of agriculture. This reduction favored infiltration to the detriment of runoff.
Keywords: Infolettre; Infolettre_Septembre_2024; Site_internet_RIISQ

Comparison of Spatio-Temporal Variability of Daily Maximum Flows in Cold-Season (Winter and Spring) in Southern Quebec (Canada) - Assani, Ali Arkamose (Hydrology, 2023)
Quebec has experienced a significant decrease in the amount of snow and an increase in temperature during the cold season. The objective of this study is to analyze the impacts of these climate changes on the spatio-temporal variability of the daily maximum flows generated by snowmelt in winter and spring using several statistical tests of correlation (spatial variability) and long-term trend (temporal variability). The study is based on the analysis of flows measured in 17 watersheds (1930–2019) grouped into three hydroclimatic regions. Regarding the spatial variability, the correlation analysis revealed that in winter, the flows are positively correlated with the agricultural area and the daily maximum winter temperature. In the spring, the flows are positively correlated with the drainage density and the snowfall but negatively correlated with the area of wetlands and the daily maximum spring temperature. As for temporal variability (long-term trend), the application of eight statistical tests revealed a generalized increase in flows in winter due to early snowmelt. In the spring, despite the decreased snow cover, no negative trend was observed due to the increase in the spring rainfall, which compensates for the decrease in the snowfall. This temporal evolution of flows in the spring does not correspond to the predictions of climate models. These predict a decrease in the magnitude of spring floods due to the decrease in the snowfall in southern Quebec.
Keywords: Infolettre; Infolettre_Avril_2023; Site_internet_RIISQ

Variability of Mean Annual Flows in Southern Quebec (Canada) - Assani, Ali A. (Water, 2022)
Snow is the main source of streamflow in temperate regions characterized by very cold and snowy winters. Due to global warming, these regions are experiencing a significant decrease in snowfall. The main objective of this study is to analyze the impacts of snowfall on the spatio-temporal variability of mean annual flows (MAFs) of 17 rivers, grouped into three hydroclimatic regions, from 1930 to 2019 in southern Quebec. In terms of spatial variability, snowfall is the variable most correlated with MAFs (positive correlation), followed by drainage density (positive correlation) and wetland surface areas (negative correlation). Due to the influence of these three factors, MAF values are generally higher in the most agricultural watersheds of the southeastern hydroclimatic region on the south shore than in the less agricultural watersheds of the southwestern hydroclimatic region on the north shore of the St. Lawrence River. As for temporal variability, the four statistical tests applied to the hydrological series detect no significant downward trend in MAFs, despite having reduced snowfall. Instead, they suggest an evolution toward an increase in mean annual flows, as a result of increased rainfall due to the increase in temperature. This evolution is more pronounced on the north shore than on the south shore, likely due to the presence of wetlands and others water bodies, whose runoff water storage capacity does not change over time to be able to store the surplus of the quantity of water brought by the increase in rain.

The disaster trap: Cyclones, tourism, colonial legacies, and the systemic feedbacks exacerbating disaster risk - Lazarus, Eli D. (Transactions of the Institute of British Geographers, 2021)
The long, open-ended period of recovery from a disaster event is the phase of a disaster that the interdisciplinary field of disaster studies struggles to understand. In the process of rebuilding, places do not simply reset – they transform, often in ways that confound any reduction of disaster risk, instead making people and settings more vulnerable to future hazard events. Reducing disaster risk is regarded as a global priority, but policies intended to reduce disaster risk have been largely ineffective. This obduracy represents a grand challenge in disaster studies. Here, I propose that the correlated trends of runaway economic costs of disaster events, growing social inequity, environmental degradation, and resistance to policy intervention in disaster settings are hallmark indicators of a system trap – a dynamic in which self-reinforcing feedbacks drive a system toward an undesirable and seemingly inescapable state, with negative consequences that tend to amplify each other over time. I offer that these trends in disaster settings are the collective expression of an especially powerful and distinct kind of system trap, which here I term the “disaster trap” – a new theoretical concept to help explain and address runaway disaster risk. I suggest that disaster traps are likely strongest in tourism-dominated coastal settings with high exposure to tropical cyclones and colonial histories of racial capitalism, which I explore with an empirical illustration from Antigua & Barbuda. Formalising a linkage between gilded and safe-development traps matters because their effects likely compound each other nonlinearly, such that disaster risk only increases and disaster risk reduction becomes increasingly difficult to achieve. Addressing traps requires understanding them as dynamic systems, described as fundamentally and completely as possible – their components, mechanisms, drivers, and structure – in order to reveal when and where interventions might be most effective at reducing disaster risk.

Evaluating the Dependence between Temperature and Precipitation to Better Estimate the Risks of Concurrent Extreme Weather Events - Wazneh, Hussein; Arain, M. Altaf; Coulibaly, Paulin; Gachon, Philippe (Advances in Meteorology, 2020)
Precipitation and temperature are among major climatic variables that are used to characterize extreme weather events, which can have profound impacts on ecosystems and society. Accurate simulation of these variables at the local scale is essential to adapt urban systems and policies to future climatic changes. However, accurate simulation of these climatic variables is difficult due to possible interdependence and feedbacks among them. In this paper, the concept of copulas was used to model seasonal interdependence between precipitation and temperature. Five copula functions were fitted to grid (approximately 10 km × 10 km) climate data from 1960 to 2013 in southern Ontario, Canada. Theoretical and empirical copulas were then compared with each other to select the most appropriate copula family for this region. Results showed that, of the tested copulas, none of them consistently performed the best over the entire region during all seasons. However, Gumbel copula was the best performer during the winter season, and Clayton performed best in the summer. More variability in terms of best copula was found in spring and fall seasons. By examining the likelihoods of concurrent extreme temperature and precipitation periods including wet/cool in the winter and dry/hot in the summer, we found that ignoring the joint distribution and confounding impacts of precipitation and temperature lead to the underestimation of occurrence of probabilities for these two concurrent extreme modes. This underestimation can also lead to incorrect conclusions and flawed decisions in terms of the severity of these extreme events.
Keywords: Gachon_Philippe

Winter hydrometeorological extreme events modulated by large-scale atmospheric circulation in southern Ontario - Champagne, Olivier; Leduc, Martin; Coulibaly, Paulin; Arain, M. Altaf (Earth System Dynamics, 2020)
Extreme events are widely studied across the world because of their major implications for many aspects of society and especially floods. These events are generally studied in terms of precipitation or temperature extreme indices that are often not adapted for regions affected by floods caused by snowmelt. The rain on snow index has been widely used, but it neglects rain-only events which are expected to be more frequent in the future. In this study, we identified a new winter compound index and assessed how large-scale atmospheric circulation controls the past and future evolution of these events in the Great Lakes region. The future evolution of this index was projected using temperature and precipitation from the Canadian Regional Climate Model large ensemble (CRCM5-LE). These climate data were used as input in Precipitation Runoff Modelling System (PRMS) hydrological model to simulate the future evolution of high flows in three watersheds in southern Ontario. We also used five recurrent large-scale atmospheric circulation patterns in north-eastern North America and identified how they control the past and future variability of the newly created index and high flows. The results show that daily precipitation higher than 10 mm and temperature higher than 5 ∘C were necessary historical conditions to produce high flows in these three watersheds. In the historical period, the occurrences of these heavy rain and warm events as well as high flows were associated with two main patterns characterized by high Z500 anomalies centred on eastern Great Lakes (HP regime) and the Atlantic Ocean (South regime). These hydrometeorological extreme events will still be associated with the same atmospheric patterns in the near future. The future evolution of the index will be modulated by the internal variability of the climate system, as higher Z500 on the east coast will amplify the increase in the number of events, especially the warm events. The relationship between the extreme weather index and high flows will be modified in the future as the snowpack reduces and rain becomes the main component of high-flow generation. This study shows the value of the CRCM5-LE dataset in simulating hydrometeorological extreme events in eastern Canada and better understanding the uncertainties associated with internal variability of climate.

Spatially Disaggregated Assessment of Environmental Inequalities Among Vulnerable Groups due to Urban Rainstorm Flooding - Bosisio, Andrea Cecilia; Jiménez, Antonio Moreno (Applied Spatial Analysis and Policy, 2022)

High-resolution synthetic population mapping for quantifying disparities in disaster impacts: An application in the Bangladesh Coastal Zone - Rubinyi, Steven; Verschuur, Jasper; Goldblatt, Ran; Gussenbauer, Johannes; Kowarik, Alexander; Mannix, Jenny; Bottoms, Brad; Hall, Jim W. (Frontiers in Environmental Science, 2022)
The impacts of natural disasters are often disproportionally borne by poor or otherwise marginalized groups. However, while disaster risk modelling studies have made progress in quantifying the exposure of populations, limited advances have been made in determining the socioeconomic characteristics of these exposed populations. Here, we generate synthetic structural and socioeconomic microdata for around 9.5 million persons for six districts in Bangladesh as vector points using a combination of spatial microsimulation techniques and dasymetric modelling. We overlay the dataset with satellite-derived flood extents of Cyclone Fani, affecting the region in 2019, quantifying the number of exposed households, their socioeconomic characteristics, and the exposure bias of certain household variables. We demonstrate how combining various modelling techniques could provide novel insights into the exposure of poor and vulnerable groups, which could help inform the emergency response after extreme events as well targeting adaptation options to those most in need of them.

High-resolution spatiotemporal analysis of hydrologic connectivity in the historical floodplain of straightened lowland agricultural streams - Marchand, Jean-Philippe; Biron, Pascale; Buffin-Bélanger, Thomas; Larocque, Marie (River Research and Applications, 2022)
In agricultural watersheds, human interventions such as channel straightening have disrupted the hydrologic connectivity between headwater streams and their riparian environment and have thus undermined the ecological services provided by these small streams. Knowledge of the hydrologic connectivity between these streams and their immediate environment (shallow riparian groundwater in the historical floodplain and on adjacent hillslopes) in human-impacted settings is critical for understanding and restoring these hydrological systems but remains largely incomplete. The objective of this research is to investigate the hydrogeomorphological conditions controlling hydrologic connectivity in the historical floodplain of straightened lowland streams. Detailed measurements on the spatiotemporal variability of groundwater-surface water interactions between straightened reaches, historical floodplain including abandoned meanders, and the adjacent hillslopes were obtained using a dense network of piezometers at two sites in the St. Lawrence Lowlands (Quebec, Canada). Results show that the complex mechanisms controlling hydrologic connectivity in naturally meandering lowland rivers also operate in highly disturbed straightened reaches, despite backfilling and agricultural practices. The pre-straightening hydrogeomorphological configuration of the floodplain partly explains the complex patterns of piezometric fluctuations observed at the sites. The apex of the abandoned meanders stands out as a focal area of hydrologic connectivity as water levels indicate pressure transfer that may reflect flows from the stream, the hillslopes, and the surrounding historical floodplain. These unique field observations suggest that abandoned meanders should be promoted as key elements of restoration strategies in lowland agricultural straightened headwater streams.
Keywords: Infolettre; Infolettre_Juillet_2022; Site_internet_RIISQ

Outils de gestion intégrée des risques pour les municipalités basés sur l’approche par conséquences - Robert, Benoît; Hémond, Yannick (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Hémond_Yannick

Analyse des variables associées aux comportements préventifs à l'inondation - Hountondji, Lionel (Université Laval, 2023)
Analyse des variables associées aux comportements préventifs à l'inondation, Hountondji, Lionel, 2023, Université Laval. Copyright by the author unless stated otherwise.

Standardised indicators for “resilient cities”: the folly of devising a technical solution to a political problem - Chmutina, Ksenia; Lizarralde, Gonzalo; Von Meding, Jason; Bosher, Lee (International Journal of Disaster Resilience in the Built Environment, 2023)
Purpose Driven by the New Urban Agenda and the Sustainable Development Goals, decision makers have been striving to reorientate policy debates towards the aspiration of achieving urban resilience and monitoring the effectiveness of adaptive measures through the implementation of standardised indicators. Consequently, there has been a rise of indicator systems measuring resilience. This paper aims to argue that the ambition of making cities resilient does not always make them less vulnerable, more habitable, equitable and just. Design/methodology/approach Using an inductive policy analysis of ISO standard 37123:2019 “Sustainable cities and communities — Indicators for resilient cities”, the authors examine the extent to which the root causes of risks are being addressed by the urban resilience agenda. Findings The authors show that the current standardisation of resilience fails to adequately address the political dimension of disaster risk reduction, reducing resilience to a management tool and missing the opportunity to address the socio-political sources of risks. Originality/value Such critical analysis of the Standard is important as it moves away from a hazard-centric approach and, instead, permits to shed light on the socio-political processes of risk creation and to adopt a more nuanced and sensitive understanding of urban characteristics and governance mechanisms.
Keywords: Infolettre; Infolettre_Juin_2023; Lizarralde_Gonzalo

Communication des risques en lien avec les inondations : vers une communication inclusive et participative - Bourgeois, Ève; Therrien, Marie-Christine (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Pratiques et approches déployées pour la prévention des risques liés aux inondations au Québec : Le cas des territoires concernés par les inondations du lac des Deux Montagnes - Fournier, Catherine (Université du Québec, Institut national de la recherche scientifique, 2022)
Les politiques québécoises de prévention des risques liés aux inondations ont été sujettes à débat ces dernières années, avec une remise en cause du modèle centralisé et uniforme à travers le Québec, pour une approche plus intégrée. Celle-ci fait notamment la promotion de mesures axées sur la vulnérabilité et d’une participation plus active des acteurs territoriaux. On en sait toutefois très peu sur les déclinaisons locales de l’approche intégrée dans le contexte québécois. Ce mémoire propose d’interroger les différentes approches locales de la prévention et de soulever les enjeux qu’elles posent du point de vue des autorités qui y participent. L’étude se penche sur le cas des territoires concernés par les inondations du lac des Deux Montagnes (Région hydrographique de l'Outaouais et de Montréal). Le cadre d’analyse met de l’avant l’approche des instruments d’action publique pour comprendre leur appropriation par les acteurs locaux et une approche pragmatique qui consiste à centrer notre regard sur les pratiques et les stratégies de réduction des risques d’inondation. La recherche s’appuie sur trois sources de données : une analyse documentaire des régimes provinciaux de régulation des risques d’inondation, un recensement des pratiques de prévention déployées par les autorités locales concernées par les inondations du lac des Deux Montagnes et une série de 15 entretiens réalisés avec les personnes travaillant au sein de ces différentes autorités. Le cas illustre la difficulté et le faible engagement de prévenir les risques autrement que par l’approche de réduction de l’exposition aux risques imposée par la Politique de protection des rives, du littoral et des plaines inondables (PPRLPI). Toutefois, après les inondations de 2017 et de 2019, des approches alternatives propres aux contextes territoriaux ont été envisagées par différentes organisations. Celles-ci devraient davantage être documentées et mises en débat afin d’envisager un régime provincial de la gestion des risques plus flexible et ouvert à leur coexistence. Uniformed and centralized model of Quebec's flood prevention policies have been recently debated. Integrated approach to flood risk prevention is now put forward, which focus more on vulnerability and foster an active participation of local authorities. Local declinations of the approach are relatively unknown in Quebec. This study presents different local approaches to flood risk prevention and raise issues they pose from the perspective of local authorities involved. It is based on the authority’s concerns by Lac des Deux Montagnes flooding (Outaouais and Montreal hydrographic region). Combining a political sociology approach to policy instruments and a pragmatic approach, we focus on risk regulation regimes, practices and risk reduction strategies. Three sources of data were used: an analysis of flood risk regulation regimes, an inventory of prevention practices deployed by local authorities and 15 interviews conducted with professionals among these authorities. Results show the difficulty and low commitment to implement local distinct approaches apart from prohibiting and discouraging exposure to flood risk enforced by the Protection Policy for Lakeshores, Riverbanks, Littoral Zones and Floodplains. However, after the floods of 2017 and 2019, alternative strategies specific to different territorial contexts were considered. These should be better documented and debated in order to consider a more flexible and coexistence provincial policy.
Keywords: Site_internet_RIISQ

Disrupting the riskscapes of inequities: a case study of planning for resilience in Canada’s Metro Vancouver region - Yumagulova, Lilia (Cambridge Journal of Regions, Economy and Society, 2020)
Abstract The analysis across spatial, temporal and governance scales shows an inequitable distribution of risk across Canada’s Metro Vancouver region. For First Nation communities in this region, this risk is rooted in the colonial history of land dispossession. This article makes a contribution by expanding our understanding of historic creation of riskscapes and a discussion of its implications as a multiscale governance issue that persists across space and time. This article also situates the impacts of projected sea level rise on Indigenous communities in the context of regional, provincial and federal settler-colonial flood risk management regime.

Resilience patterns of human mobility in response to extreme urban floods - Tang, Junqing; Zhao, Pengjun; Gong, Zhaoya; Zhao, Hongbo; Huang, Fengjue; Li, Jiaying; Chen, Zhihe; Yu, Ling; Chen, Jun (National Science Review, 2023)
ABSTRACT Large-scale disasters can disproportionately impact different population groups, causing prominent disparity and inequality, especially for the vulnerable and marginalized. Here, we investigate the resilience of human mobility under the disturbance of the unprecedented ‘720’ Zhengzhou flood in China in 2021 using records of 1.32 billion mobile phone signaling generated by 4.35 million people. We find that although pluvial floods can trigger mobility reductions, the overall structural dynamics of mobility networks remain relatively stable. We also find that the low levels of mobility resilience in female, adolescent and older adult groups are mainly due to their insufficient capabilities to maintain business-as-usual travel frequency during the flood. Most importantly, we reveal three types of counter-intuitive, yet widely existing, resilience patterns of human mobility (namely, ‘reverse bathtub’, ‘ever-increasing’ and ‘ever-decreasing’ patterns), and demonstrate a universal mechanism of disaster-avoidance response by further corroborating that those abnormal resilience patterns are not associated with people’s gender or age. In view of the common association between travel behaviors and travelers’ socio-demographic characteristics, our findings provide a caveat for scholars when disclosing disparities in human travel behaviors during flood-induced emergencies.

Justice and Resilience in Flood Risk Management: What Are the Socio-Political Implications? - Thaler, Thomas (2021)
Flood risk management requires to comprehensively assess how policy strategies may affect individuals and communities. However, policy development and implementation often downplay or even increase social inequality. Analysis of the social and societal implications of strategies and implementation projects to manage flood hazards is still in its infancy. To close this gap, this chapter critically questions the roles of social justice and their political implications for flood risk management with regard to resilience. The chapter discusses and argues how different theoretical concepts as well as different perspectives on justice (e.g. social, environmental and climate justice) and resilience in flood risk management are related. There is a strong need to have a broader and more in-depth discussion about the role of justice in the current resilience debate. Finally, the chapter presents the outline of a future research agenda.

Dependence of tropical cyclone damage on maximum wind speed and socioeconomic factors - Ye, Mengqi; Wu, Jidong; Liu, Wenhui; He, Xin; Wang, Cailin (Environmental Research Letters, 2020)
© 2020 The Author(s). Published by IOP Publishing Ltd.Tropical cyclones (TCs) have devastating impacts and are responsible for significant damage. Consequently, for TC-induced direct economic loss (DEL) attribution all factors associated with risk (i.e. hazard, exposure and vulnerability) must be examined. This research quantifies the relationship between TC-induced DELs and maximum wind speed, asset value and Gross Domestic Product (GDP) per capita using a regression model with TC records from 2000 to 2015 for China's mainland area. The coefficient of the maximum wind speed term indicates that a doubling of the maximum wind speed increases DELs by 225% [97%, 435%] when the other two variables are held constant. The coefficient of the asset value term indicates that a doubling of asset value exposed to TCs increases DELs by 79% [58%, 103%]; thus, if hazard and vulnerability are assumed to be constant in the future, then a dramatic escalation in TC-induced DELs will occur given the increase in asset value, suggesting that TC-prone areas with rapid urbanization and wealth accumulation will inevitably be subject to higher risk. Reducing the asset value exposure via land-use planning, for example, is important for decreasing TC risk. The coefficient of GDP per capita term indicates that a doubling in GDP per capita could decrease DELs by 54% [39%, 66%]. Because accumulated assets constantly increase people's demand for improved security, stakeholders must invest in risk identification, early warning systems, emergency management and other effective prevention measures with increasing income to reduce vulnerability. This research aims to quantitatively connect TC risk (expected DELs, specifically) to physical and socioeconomic drivers and emphasizes how human dimensions could contribute to TC risk. Moreover, the model can be used to estimate TC risk under climate change and future socioeconomic development in the context of China.

Four core principles to reconcile sociocultural conditions and disaster risk reduction in pursuit of community resilience - Graveline, Marie-Hélène; Germain, Daniel; Boyer-Villemaire, Ursule; Guimond, Laurie (Environmental Hazards, 2025)
Keywords: Infolettre; Infolettre_Fevrier_2025

How Plans Prepare for Future Uncertainty: Integrating Land Change Modeling and the Plan Integration for Resilience Scorecard™ - Kim, Youjung; Newman, Galen; Berke, Philip; Lee, Jaekyung; Malecha, Matthew; Yu, Siyu (Journal of Planning Education and Research, 2024)
This study integrates Land Change Modeling with the Plan Integration for Resilience Scorecard™ methodology to assess coastal communities’ preparedness for uncertain future urban growth and flood hazards. Findings indicate that, under static climate conditions, the network of plans in Tampa is well prepared across all urban growth scenarios, but less so in the face of a changing climate. Specifically, scenario outputs that consider climate change suggest the need for more resilient growth to reduce flood vulnerability compared with the current land use plan. Notably, some existing policies are likely to lead to counterproductive outcomes in a future with more extensive flooding.
Keywords: Infolettre; Infolettre_Septembre_2024

Operating urban resilience strategies to face climate change and associated risks: some advances from theory to application in Canada and France - Heinzlef, Charlotte; Robert, Benoît; Hémond, Yannick; Serre, Damien (Cities, 2020)
Keywords: Hémond_Yannick; Ouvrage_Collectif_Numéro1

Influence of cross-scale measures on neighborhood resilience - Buck, Kyle D.; Dunn, Rebecca J.; Bennett, Mary K.; Bousquin, Justin (Natural Hazards, 2022)
The increasing severity and frequency of disasters across the USA is revealing a landscape that is not entirely prepared to cope with these exposures. Resilience as a socio-ecological concept has become progressively more important as a means of assessing and mitigating these losses. Technological advances and planning have improved many outcomes, but all populations have not experienced the benefits. In this paper, we focus on the shortcomings of current resilience measures in capturing neighborhood disparities. Much like vulnerability and sustainability, local disparities will have a deleterious impact on the community as a whole. We use the Baseline Resilience Indicators for Communities (BRIC) framework and downscale the index using neighborhood-level Census data (tracts) and variations in household access to community resources. These added variables represent the variation of resilience indicators across a community and capture cross-scale relationships that exist between county and Census tract characteristics. We apply scaled variables in the Pensacola Bay Watershed to demonstrate cross-scaled interactions in the Florida panhandle. Potential modifications and applications of the concepts are also discussed.

Risk and Resilience: A Case of Perception versus Reality in Flood Management - Agrawal, Nirupama; Elliott, Mark; Simonovic, Slobodan P. (Water, 2020)
Canada’s vast regions are reacting to climate change in uncertain ways. Understanding of local disaster risks and knowledge of underlying causes for negative impacts of disasters are critical factors to working toward a resilient environment across the social, economic, and the built sectors. Historically, floods have caused more economical and social damage around the world than other types of natural hazards. Since the 1900s, the most frequent hazards in Canada have been floods, wildfire, drought, and extreme cold, in terms of economic damage. The recent flood events in the Canadian provinces of Ontario, New Brunswick, Quebec, Alberta, and Manitoba have raised compelling concerns. These include should communities be educated with useful knowledge on hazard risk and resilience so they would be interested in the discussion on the vital role they can play in building resilience in their communities. Increasing awareness that perceived risk can be very different from the real threat is the motivation behind this study. The main objectives of this study include identifying and quantifying the gap between people’s perception of exposure and susceptibility to the risk and a lack of coping capacity and objective assessment of risk and resilience, as well as estimating an integrated measure of disaster resilience in a community. The proposed method has been applied to floods as an example, using actual data on the geomorphology of the study area, including terrain and low lying regions. It is hoped that the study will encourage a broader debate if a unified strategy for disaster resilience would be feasible and beneficial in Canada.

Social inequalities in climate change-attributed impacts of Hurricane Harvey. - Smiley, Kevin T.; Noy, Ilan; Wehner, Michael F.; Frame, Dave; Sampson, Christopher C.; Wing, Oliver E J (Nature Communications, 2022)
Climate change is already increasing the severity of extreme weather events such as with rainfall during hurricanes. But little research to date investigates if, and to what extent, there are social inequalities in climate change-attributed extreme weather event impacts. Here, we use climate change attribution science paired with hydrological flood models to estimate climate change-attributed flood depths and damages during Hurricane Harvey in Harris County, Texas. Using detailed land-parcel and census tract socio-economic data, we then describe the socio-spatial characteristics associated with these climate change-induced impacts. We show that 30 to 50% of the flooded properties would not have flooded without climate change. Climate change-attributed impacts were particularly felt in Latina/x/o neighborhoods, and especially so in Latina/x/o neighborhoods that were low-income and among those located outside of FEMA's 100-year floodplain. Our focus is thus on climate justice challenges that not only concern future climate change-induced risks, but are already affecting vulnerable populations disproportionately now.

Social justice in socio-hydrology—how we can integrate the two different perspectives - Thaler, Thomas (Hydrological Sciences Journal-journal Des Sciences Hydrologiques, 2021)
Socio-hydrology has become an important platform for discussion and exchange in current water research. A key challenge is the integration of the social into socio-hydrological logic. To date, most...

Energy poverty: an overlooked determinant of health and climate resilience in Canada - Riva, Mylène; Kingunza Makasi, Sophie; O’Sullivan, Kimberley C.; Das, Runa R.; Dufresne, Philippe; Kaiser, David; Breau, Sébastien (Canadian Journal of Public Health, 2023)
Abstract Objective Despite Canada being an important energy producer, not all Canadians can access or afford adequate levels of energy services at home to meet their needs, maintain healthy indoor temperatures, and live a decent life—a situation known as energy poverty. Depending on the measure, 6–19% of Canadian households face energy poverty. Health risks associated with energy poverty are documented in countries with milder climates. This study explores, for the first time in the Canadian context, the association between energy poverty and health. Methods Cross-sectional data are from the 2018 Canadian Housing Survey. Analyses are conducted on a sample weighted to represent 14 million Canadian households. The associations between expenditure-based and self-reported measures of energy poverty and self-rated general and mental health were assessed using logistic regression models, adjusted for potential confounding variables. Results The odds of rating one’s general (OR: 1.48; 95%CI: 1.29, 1.70) and mental (OR: 1.21; 1.04, 1.41) health as poor are significantly higher for Canadian adults in households with a high share of energy expenditure to income. The likelihood of poor general and mental health was significantly higher for those dissatisfied with the energy efficiency of their dwelling, and with their ability to maintain a comfortable temperature both in the winter and in the summer. Conclusion Exposure to energy poverty is associated with significantly increased likelihood of poor general and mental health. Given the high proportion of Canadian households facing energy poverty, with demonstrated implications for population health, tackling energy poverty is essential for an equitable energy transition and for climate resilience. , Résumé Objectif Bien que le Canada soit un important producteur d’énergie, entre 6 % et 19 % des ménages canadiens, selon la mesure retenue, sont en précarité énergétique, une situation qui survient lorsqu’un ménage n’a pas les moyens ou l’accès à des services énergétiques résidentiels adéquats pour maintenir une température ambiante confortable, répondre à ses besoins et vivre dans la dignité. Les risques socio-sanitaires associés à la précarité énergétique sont documentés dans des pays au climat tempéré. Cette étude explore, pour la première fois dans le contexte canadien, l’association entre la précarité énergétique et la santé. Méthodes Les données transversales proviennent de l’Enquête canadienne sur le logement de 2018. Les associations entre différentes mesures de précarité énergétique (mesures basées sur les dépenses des ménages et auto-rapportées) et la santé générale et mentale perçue sont estimées à l’aide de modèles de régression logistique ajustés pour des variables de confusion potentielles. Les analyses sont réalisées sur un échantillon pondéré pour représenter 14 millions de ménages. Résultats Les probabilités de déclarer une mauvaise santé générale (OR : 1,48; IC95% : 1,29-1,70) et mentale (OR : 1,21; 1,04-1,41) sont significativement plus élevées pour les adultes canadiens dont le ménage consacre une part importante de son revenu aux coûts énergétiques. Elles sont aussi significativement plus élevées pour ceux qui déclarent être insatisfaits avec l’efficacité énergétique de leur logement et de leur capacité à maintenir une température confortable en hiver et en été. Conclusion Vivre en situation de précarité énergétique est associée à des probabilités accrues de déclarer une mauvaise santé générale et mentale chez les adultes canadiens. En raison de la proportion élevée de ménages canadiens confrontés à la précarité énergétique et des effets socio-sanitaires que cette situation engendre, lutter contre la précarité énergétique est essentiel pour une transition énergétique équitable et pour la résilience climatique.

L’acceptabilité sociale : trajectoire d’une nouvelle norme d’action publique - Simard, Louis (Politique et Sociétés, 2021)
La notion d’acceptabilité sociale est devenue incontournable dans plusieurs secteurs de l’action publique. Au coeur des grands projets d’aménagement et d’urbanisme, énergétiques, d’extraction des ressources, ou qui concernent l’environnement en général, cette nouvelle norme publique apparaît comme un traceur de changements importants en matière de décision tant sur le plan substantif que processuel. Comment comprendre cette notion ? Comment l’étudier et quelle trajectoire a-t-elle connu au Québec ? Dans cet article nous proposons dans un premier temps un cadre théorique pour étudier cet objet : l’approche par les instruments d’action publique, en la considérant comme un instrument de type normatif visant à favoriser la coordination, la coopération et la prévisibilité dans un environnement complexe, par la recherche d’un ajustement négocié sur des bases scientifiques et politiques. Nous présentons ensuite les principales composantes pour bien définir l’acceptabilité sociale. Enfin nous proposons d’étudier la trajectoire de cette norme sur plus de 40 ans au Québec à travers l’étude des rapports du Bureau d’audiences publiques sur l’environnement, le Chantier sur l’acceptabilité sociale (2014-2015) et deux jugements des tribunaux (Cour supérieure du Québec en 2017 et Cour d’appel du Québec en 2020). Nous constatons une montée en importance de l’acceptabilité sociale au cours des décennies, pour devenir le critère ultime de décision en plus de s’institutionnaliser jusqu’à être confirmée dans sa portée juridique et pouvant apparaître comme le chaînon manquant entre démocratie participative et démocratie représentative. , The notion of social acceptability has become unavoidable in many areas of public policy. At the heart of major planning and urban planning projects, energy, resource extraction, or the environment in general, this new public standard appears to be a tracer of significant decision-making changes, both substantive and procedural. How is this notion understood? How can it be studied and what was its trajectory in Quebec? We first propose a theoretical framework for studying this object, that is, the approach by public policy instruments as a normative instrument aimed at promoting coordination, cooperation, and predictability in a complex environment, through the search for a negotiated adjustment based on scientific and political grounds. We then present the main components for a definition of social acceptability. Finally, we propose to study the trajectory of this standard over more than forty years in Quebec through the study of the reports of the Office of Public Hearings on the Environment, the governmental workshop on social acceptability (2014-2015), and two court judgments (2017 and 2020). We found an increase in importance of social acceptability over the decades, to the point of becoming the ultimate criterion of decision and institutionalizing, and being confirmed in its legal scope; it may appear to be the missing link between participatory democracy and representative democracy.
Keywords: Ouvrage_Collectif_Numéro1

Social housing construction and improvements in housing outcomes for Inuit in Northern Canada - Riva, Mylene; Perreault, Karine; Dufresne, Philippe; Fletcher, Christopher; Muckle, Gina; Potvin, Louise; Bailie, Ross; Baron, Marie (Housing Studies, 2021)

Scenarios of Human Responses to Unprecedented Social‐Environmental Extreme Events - Rusca, Maria; Messori, Gabriele; Di Baldassarre, Giuliano (Earth's Future, 2021)
Abstract In a rapidly changing world, what is today an unprecedented extreme may soon become the norm. As a result, extreme‐related disasters are expected to become more frequent and intense. This will have widespread socio‐economic consequences and affect the ability of different societal groups to recover from and adapt to rapidly changing environmental conditions. Therefore, there is the need to decipher the relation between genesis of unprecedented events, accumulation and distribution of risk, and recovery trajectories across different societal groups. Here, we develop an analytical approach to unravel the complexity of future extremes and multiscalar societal responses—from households to national governments and from immediate impacts to longer term recovery. This requires creating new forms of knowledge that integrate analyses of the past—that is, structural causes and political processes of risk accumulation and differentiated recovery trajectories—with plausible scenarios of future environmental extremes grounded in the event‐specific literature. We specifically seek to combine the physical characteristics of the extremes with examinations of how culture, politics, power, and policy visions shape societal responses to unprecedented events, and interpret the events as social‐environmental extremes. This new approach, at the nexus between social and natural sciences, has the concrete advantage of providing an impact‐focused vision of future social‐environmental risks, beyond what is achievable within conventional disciplinary boundaries. In this paper, we focus on extreme flooding events and the societal responses they elicit. However, our approach is flexible and applicable to a wide range of extreme events. We see it as the first building block of a new field of research, allowing for novel and integrated theoretical explanations and forecasting of social‐environmental extremes. , Key Points We conceptualize unprecedented extremes as social‐environmental processes shaped by institutional, political, and economic change As social‐environmental extremes become more frequent, there is an urgency to unravel their genesis and the possible societal responses This approach is the first building block of a new field of research in social‐environmental extreme event forecasts , Plain Language Summary The world is seeing increases in a range of extreme events, and this increase may continue or even accelerate in the future, due to anthropogenic climate change. Furthermore, it is often those who are already vulnerable that experience the biggest impacts from these extremes. Yet, there is little understanding of the possible societal responses to unprecedented events. This underscores the urgency of creating innovative approaches to develop plausible scenarios of societal responses and, in turn, mitigate hazards and reduce vulnerability and exposure to extreme events. In this commentary, we develop a truly interdisciplinary conceptual approach to better understand how different societal groups might interact with and respond to future unprecedented extreme events. We combine social science theories describing how different societal groups are affected by, and recover from, extreme events with projections from the literature identifying plausible areas at risk of unprecedented occurrences and local analyses of past extreme events. We see this as the first building block of a new field of research in forecasting social‐environmental extremes that could support governments, civil protection agencies, and civil society organizations to ensure a fairer, improved response to future events.

Indice du potentiel de participation sociale des Québécois âgés : cartographie des inégalités des zones métropolitaines, urbaines et rurales: IPPS : cartographie des inégalités - Naud, Daniel; Généreux, Mélissa; Bruneau, Jean-François; Levasseur, Mélanie (Canadian Journal on Aging / La Revue canadienne du vieillissement, 2024)
Afin de mieux comprendre la distribution géographique des facilitateurs et des obstacles à la participation sociale des Québécois âgés, cette étude visait à documenter l’Indice du potentiel de participation sociale (IPPS) selon les zones métropolitaines, urbaines et rurales. Des analyses de données secondaires, dont l’Enquête transversale sur la santé des collectivités canadiennes, ont permis de développer et de cartographier un indice composé de facteurs environnementaux associés à la participation sociale, pondérés par une analyse factorielle. En zones métropolitaines, l’IPPS était supérieur au centre qu’en périphérie, compte tenu d’une concentration accrue d’aînés et des transports. Bien qu’atténuée, la configuration était similaire en zones urbaines. En zone rurale, un IPPS élevé était associé à une concentration d’aînés et un accès aux ressources accru, sans configuration spatiale. Pour favoriser la participation sociale, l’IPPS soutient que les transports et l’accès aux ressources doivent respectivement être améliorés en périphérie des métropoles et en zone rurale., AbstractTo better understand the geographic distribution of facilitators of, and barriers to, social participation among older Quebecers, this study aimed to document the Social Participation Potential Index (SPPI; Indice du potentiel de participation sociale) in metropolitan, urban and rural areas. Secondary data analyses, including the Canadian Community Health Survey, were used to develop and map a composite index of environmental factors associated with social participation, weighted by factor analysis. In metropolitan areas, the SPPI was higher in the center than in the periphery, due to an increased concentration of seniors and transportation. Although reduced, the pattern was similar in urban areas. In rural areas, a higher SPPI was associated with an increased concentration of older adults and access to resources, showing no spatial pattern. To promote social participation, the SPPI suggests that transportation and access to resources must be improved in the periphery of metropolitan areas and in rural areas, respectively.
Keywords: Généreux_Mélissa

Modeling the Impacts of Urban Flood Risk Management on Social Inequality - Moulds, Simon; Buytaert, Wouter; Templeton, Michael R.; Kanu, Ishmael (Water Resources Research, 2021)
Abstract The exposure of urban populations to flooding is highly heterogeneous, with the negative impacts of flooding experienced disproportionately by the poor. In developing countries experiencing rapid urbanization and population growth a key distinction in the urban landscape is between planned development and unplanned, informal development, which often occurs on marginal, flood‐prone land. Flood risk management in the context of informality is challenging, and may exacerbate existing social inequalities and entrench poverty. Here, we adapt an existing socio‐hydrological model of human‐flood interactions to account for a stratified urban society consisting of planned and informal settlements. In the first instance, we use the model to construct four system archetypes based on idealized scenarios of risk reduction and disaster recovery. We then perform a sensitivity analysis to examine the relative importance of the differential values of vulnerability, risk‐aversion, and flood awareness in determining the relationship between flood risk management and social inequality. The model results suggest that reducing the vulnerability of informal communities to flooding plays an important role in reducing social inequality and enabling sustainable economic growth, even when the exposure to the flood hazard remains high. Conversely, our model shows that increasing risk aversion may accelerate the decline of informal communities by suppressing economic growth. On this basis, we argue for urban flood risk management which is rooted in pro‐poor urban governance and planning agendas which recognize the legitimacy and permanence of informal communities in cities. , Key Points The distribution of flood risk in urban areas is uneven, with the negative impacts experienced disproportionately by the urban poor Our model shows that reducing the vulnerability of informal residents to flooding can reduce inequality, even when their exposure is high Based on the model results, we argue that urban flood risk management should be rooted in pro‐poor urban governance and planning agendas

Flooded Social Connections - Ratnadiwakara, Dimuthu (The Quarterly Journal of Finance, 2021)
Does salient information on social media influence individuals’ economic decisions and beliefs? Using aggregated data from Facebook and a difference-in-differences strategy, I show that individuals who are socially connected to someone affected by Hurricane Harvey are more likely to purchase flood insurance policies after the event. This effect is stronger in areas at higher risk of flooding. Being socially connected to someone affected by Hurricane Harvey also influences individuals’ perceptions of global warming.

Energy poverty in Canada: Prevalence, social and spatial distribution, and implications for research and policy - Riva, Mylene; Kingunza Makasi, Sophie; Dufresne, Philippe; O'Sullivan, Kimberley; Toth, Megan (Energy Research & Social Science, 2021)

Les facteurs ayant facilité l’intervention sociale auprès de sinistrés lors des inondations de 2019 : point de vue de gestionnaires et d’intervenants sociaux - Maltais, Danielle; Hamel, Ariane; Lansard, Anne-Lise (INTERVENTION 2024, 2024)

Human displacements, fatalities, and economic damages linked to remotely observed floods - Mester, Benedikt; Frieler, Katja; Schewe, Jacob (Scientific Data, 2023)
Abstract We present a new open source dataset FLODIS that links estimates of flood-induced human displacements, fatalities, and economic damages to flooded areas observed through remote sensing. The dataset connects displacement data from the Internal Displacement Monitoring Centre (IDMC), as well as data on fatalities and damages from the Emergency Events Database (EM-DAT), with the Global Flood Database (GFD), a satellite-based inventory of historic flood footprints. It thereby provides a spatially explicit estimate of the flood hazard underlying each individual disaster event. FLODIS contains two datasets with event-specific information for 335 human displacement events and 695 mortality/damage events that occurred around the world between 2000 and 2018. Additionally, we provide estimates of affected population, GDP, and critical infrastructure, as well as socio-economic indicators; and we provide geocoding for displacement events ascribed to other types of disasters, such as tropical cyclones, so that they may be linked to corresponding hazard estimates in future work. FLODIS facilitates integrated flood risk analysis, allowing, for example, for detailed assessments of local flood-damage and displacement vulnerability.

Conséquences des inondations sur la santé physique et mentale des adultes : résultats d’une recension des écrits - Maltais, Danielle; Gilbert, Simon; Généreux, Mélissa (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1; Généreux_Mélissa

Intervention de crise en contexte d’inondations : les conséquences sur la santé et la performance au travail des intervenants psychosociaux - Maltais, Danielle; Lansard, Anne-Lise (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Eco-anxiety in children: A scoping review of the mental health impacts of the awareness of climate change - Léger-Goodes, Terra; Malboeuf-Hurtubise, Catherine; Mastine, Trinity; Généreux, Mélissa; Paradis, Pier-Olivier; Camden, Chantal (Frontiers in Psychology, 2022)
Background Youth are increasingly aware of the negative effects of climate change on the planet and human health, but this knowledge can often come with significant affective responses, such as psychological distress, anger, or despair. Experiencing major “negative” emotions, like worry, guilt, and hopelessness in anticipation of climate change has been identified with the term eco-anxiety. Emerging literature focuses on adults' experience; however, little is known about the ways in which children and youth experience eco-anxiety. Objectives The aim of this review was to: (1) identify the available evidence on the topic of eco-anxiety in children, (2) clarify the mental health consequences brought by the awareness of climate change in this population, and (3) identify knowledge gaps in the literature and considerations for future research. Methods Given that the research on the topic of eco-anxiety in children is limited, that there are very few randomized controlled trials, and that the goal is not to analyze individual studies in-depth, a scoping review was used. Keywords pertaining to the themes of eco-anxiety, climate change and children (aged < 18 years) were used as search terms in five databases. Journal articles using qualitative and quantitative methods, as well as gray literature were examined by two independent reviewers. A descriptive-analytical method was used to chart the data that emerged from the literature. Eighteen articles were considered in the final analysis. Results Evidence confirms that children experience affective responses and eco-anxiety in reaction to then awareness of climate change. Mental health outcomes include depression, anxiety, and extreme emotions like sadness, anger, and fear. Youth from vulnerable communities, like indigenous communities, or those who have strong ties to the land are often identified as being emotionally impacted by climate change. The literature analyzed also describes how children and youth are coping with eco-anxiety, including maladaptive (e.g., denial) and adaptive responses (such as constructive hope, used as a positive coping mechanism). Preliminary considerations for parents, teachers and educators, mental health care providers, school systems, adults and people of power include adding age-appropriate climate education to the school curriculum, considering youth's emotions, and promoting healthy coping through empowerment. Important gaps exist in the definition of eco-anxiety in youth, as various characterizations of this emerging concept are found across articles.
Keywords: Généreux_Mélissa

Flood occurrence and impact models for socioeconomic applications over Canada and the United States - Grenier, Manuel; Boudreault, Mathieu; Carozza, David A.; Boudreault, Jérémie; Raymond, Sébastien (Natural Hazards and Earth System Sciences, 2024)
Abstract. Large-scale socioeconomic studies of the impacts of floods are difficult and costly for countries such as Canada and the United States due to the large number of rivers and size of watersheds. Such studies are however very important for analyzing spatial patterns and temporal trends to inform large-scale flood risk management decisions and policies. In this paper, we present different flood occurrence and impact models based upon statistical and machine learning methods of over 31 000 watersheds spread across Canada and the US. The models can be quickly calibrated and thereby easily run predictions over thousands of scenarios in a matter of minutes. As applications of the models, we present the geographical distribution of the modelled average annual number of people displaced due to flooding in Canada and the US, as well as various scenario analyses. We find for example that an increase of 10 % in average precipitation yields an increase in the displaced population of 18 % in Canada and 14 % in the US. The model can therefore be used by a broad range of end users ranging from climate scientists to economists who seek to translate climate and socioeconomic scenarios into flood probabilities and impacts measured in terms of the displaced population.
Keywords: Infolettre; Infolettre_Decembre_2024

L’intervention sociale auprès des groupes en région ressource : regard sur les expériences d’intervention vécues par les intervenantes issues du travail social - Labra, Oscar; Castro, Carol; Grenier, Stéphane (Canadian Social Work Review, 2024)
Nous en connaissons peu sur la pratique d’intervention de groupe en région, ce qui ouvre un champ de questions qui dépassent de loin la simple description des conditions de travail en intervention. Ce travail souhaite valoriser et rendre « visible » la pratique d’intervention de groupe des professionnelles issues du travail social, dans un contexte québécois, et plus spécifiquement dans un environnement de région ressource, environnement qui pose des défis et des enjeux importants reliés à ce mode d’intervention. À travers une recherche qualitative et un processus de théorisation ancrée, ce mode d’intervention a été exploré auprès de 10 intervenantes. Les principaux résultats nous permettent d’identifier les spécificités régionales de l’intervention de groupe, telles qu’une pratique destinée fondamentalement aux femmes avec des approches choisies pour l’intervention, la confidentialité et la protection de la vie privée des participantes du groupe, le manque de transport en commun, et une pratique de groupe plus présente dans le milieu communautaire. , We know little about the practice of group intervention in remote areas, which leads to an array of questions that go far beyond the mere description of working conditions in this context of practice. This article aims to acknowledge and increase visibility of social work with groups in Quebec, most specifically in remote regions where mostly female social work professionals practice this type of intervention, an environment that poses important challenges related to this type of practice. Through qualitative research and a process of grounded theorizing, this type of intervention was explored using feedback from 10 female participants (social workers). The main results highlight regional specificities, such as a practice fundamentally aimed at women, confidentiality and privacy of group participants, the lack of public transportation, and a group practice more present in the community setting

Interregional imbalance in the Yellow River Basin: Insights from flood-sediment transport, socioeconomic, and environmental subsystems - Hu, Hao; Tian, Guiliang; Adamowski, Jan F.; Albano, Raffaele; Liu, Yixue; Jing, Xiaodong; Zhao, Qiuya (Journal of Environmental Management, 2024)
Keywords: Infolettre; Infolettre_Decembre_2024

Climate change, poverty and child health inequality: evidence from Vietnam’s provincial analysis - Huynh, Cong Minh; Tran, Bao Khuyen (Economic Change and Restructuring, 2024)

I think they should give primary health care a little more priority. The Primary Health Care in Caribbean SIDS: What can be said about adaptation to the changing climate? The case of Dominica. A qualitative study - Harris-Glenville, Fiona; Cloos, Patrick (2023)
Abstract Background Climate change (CC) adaptation is considered a priority for Caribbean Small Islands Developing States (SIDS), as these territories and communities are considered particularly vulnerable to climate-related events. The primary health care (PHC) system is an important actor in contributing to climate change adaptation. However, knowledge on how PHC is prepared for CC in Caribbean SIDS is very limited. The objective of this paper is to discuss health adaptation to climate change focusing on the PHC system. Methods We explored the perspectives of PHC professionals in Dominica on climate change. Focus group discussions (FGDs) were conducted in each of the seven health districts in Dominica, a Caribbean SIDS, between November 2021 and January 2022. The semi-structured interview guide was based on the Essential Public Health Functions: assessment, access to health care services, policy development and resource allocation. Data coding was organized accordingly. Results Findings suggest that health care providers perceive climate change as contributing to an increase in NCDs and mental health problems. Climate-related events create barriers to care and exacerbate the chronic deficiencies within the health system, especially in the absence of high-level policy support. Healthcare providers need to take a holistic view of health and act accordingly in terms of disease prevention and health promotion, epidemiological surveillance, and ensuring the widest possible access to health care, with a particular focus on the ecological and social determinants of vulnerability. Conclusion The Primary Health Care system should be a key actor in designing and operationalizing adaptation and transformative resilience. The Essential Public Health Functions should integrate social and climate and ecological determinants of health to guide primary care activities to protect the health of communities. This indicates a need for improved research on the linkages between climate events and health outcomes, surveillance, and development of plans that are guided by contextual knowledge in the SIDS.
Keywords: Cloos_Patrick

Conséquences des désastres sur les enfants et les adolescent·e·s et implications pour le travail social : recension des écrits et pistes d’intervention - Hamel, Ariane; St-Amour, Nathalie (Service social, 2023)
Plusieurs chercheur.euse.s s’intéressent à la question des conséquences des désastres sur les enfants et les adolescent.e.s. La majorité des études effectuées sont quantitatives et se concentrent sur les symptômes anxieux, dépressifs et post-traumatiques que développent ces jeunes. Peu d’études qualitatives se préoccupent des effets plus systémiques que provoquent ces catastrophes, tels que les conséquences d’une relocalisation dans un nouveau quartier ou les difficultés familiales et la violence envers les enfants qui peuvent s’ensuivre. De plus, peu d’études proposent des pistes d’intervention en travail social. L’objectif principal de cet article vise donc à fournir une recension des écrits récente, francophone et systémique au sujet des conséquences vécues par les jeunes d’âge mineur à la suite d’un désastre. Cela afin de soutenir les intervenant.e.s en travail social en regroupant dans un même article quelques pistes d’intervention individuelle, familiale, de groupe et collective. , Many researchers have focused on the influence of disasters exposure on children and teenagers. Most of the research performed are quantitative studies that center predominantly on posttraumatic stress, depression, and anxiety symptoms developed by youth. Few qualitative research take an interest in a more holistic picture of the impacts of disasters, such as the relocation in new communities or challenged interpersonal family dynamics, which can lead to violence against children. Moreover, few articles discuss implications for social work. The main objective of this article is to offer a recent and francophone literature review with an ecological approach about the impacts of disasters exposure on children and teenagers. Furthermore, to better equip social workers, promising avenues of individual, family focused, group and community-based interventions are discussed.
Keywords: StAmour_Nathalie

HIV/AIDS knowledge and attitudes among social work students: A comparative study - Labra, Oscar; Ependa, Augustin; Chamblas, Isis; Gingras-Lacroix, Gabriel; Antoniadis, André; Biston, Cristine; Mukeshimana, Marthe; Giroux, Marie-Ève (International Social Work, 2023)
The article describes a quantitative cross-sectional study of a sample of 674 university students enrolled in social work programmes in four countries: Belgium, Canada, Chile and Switzerland. The study aimed to assess HIV/AIDS knowledge and attitudes among participants. The median HIV-KQ-18 score for the sample was 14.0, which Carey and Schroder classify as indicating borderline low levels of knowledge. Based on the results, the authors argue that social work education and training programmes should more comprehensively address HIV/AIDS within their curricula to better equip future social workers to challenge stigmatising and exclusionary practices rooted in long-standing lack of knowledge and erroneous beliefs about the disease.

Mesurer et prédire l'adaptation aux changements climatiques dans les municipalités québécoises : Développement et validation d'indices et mesure des déterminants psychosociaux de l'action - Jacob, Johann (2022)

Impacts psychosociaux et leurs stresseurs suite aux inondations de 2019 au Québec : analyse qualitative de groupes Facebook - Landaverde, E. (Département de santé environnementale et santé au travail, Université de Sherbrooke, 2021)
Keywords: Ouvrage_Collectif_Numéro1

Caregiver Support in Mental Health Recovery: A Critical Realist Qualitative Research - Lauzier-Jobin, François; Houle, Janie (Qualitative Health Research, 2021)
Support from caregivers is an important element of mental health recovery. However, the mechanisms by which social support influences the recovery of persons with depressive, anxiety, or bipolar disorders are less understood. In this study, we describe the social support mechanisms that influence mental health recovery. A cross-sectional qualitative study was undertaken in Québec (Canada) with 15 persons in recovery and 15 caregivers—those having played the most significant role in their recovery. A deductive thematic analysis allowed for the identification and description of different mechanisms through a triangulation of perspectives from different actors. Regarding classic social support functions, several of the support mechanisms for mental health recovery were identified (emotional support, companionship, instrumental support, and validation). However, informational support was not mentioned. New mechanisms were also identified: presence, communication, and influence. Social support mechanisms evoke a model containing a hierarchy as well as links among them.

Pistes d'interventions psychosociales pour préserver les jeunes des impacts des catastrophes naturelles ou technologiques - Lansard, Anne-Lise; Maltais, Danielle; Généreux, Mélissa (2020)
Cette recension a pour objectifs de documenter les approches et les principes d'intervention recommandés dans les écrits pour intervenir auprès des jeunes en contexte de catastrophe, de décrire des techniques, des stratégies, des programmes et des types d'intervention ayant déjà été mis en place auprès d'enfants et d'adolescents en contexte de catastrophe et d'identifier les facteurs ayant contribué à l'efficacité des interventions.
Keywords: Généreux_Mélissa; Ouvrage_Collectif_Numéro1; Site_internet_RIISQ

Assessment of socio-economic strategies for managing regional flood risk in an urban coastal catchment - Ghosh, Mousumi; Ghosh, Subimal; Karmakar, Subhankar (Urban Climate, 2024)

Intersectoral approaches: the key to mitigating psychosocial and health consequences of disasters and systemic risks - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Disaster Prevention and Management: An International Journal, 2023)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Infolettre; Infolettre_Fevrier_2023; Lessard_Lily; Site_internet_RIISQ

Regards croisés sur le phénomène « d’écoanxiété » : perspectives psychologique, sociale et éducationnelle - Gousse-Lessard, Anne-Sophie; Lebrun-Paré, Félix (Éducation relative à l'environnement, 2022)
Keywords: Gousse-Lessard_Anne-Sophie

Intersectoral research and multi-risk approaches in Québec: systemic risk management and its psychosocial consequences - Gousse-Lessard, Anne-Sophie; Gachon, Philippe; Lessard, Lily; Vermeulen, Valérie; Boivin, Maxime; Maltais, Danielle; Landaverde, Elsa; Généreux, Mélissa; Motulsky, Bernard; Le Beller, Julien (Contribution paper to the Global Assessment Report on Disaster Risk Reduction, 2022)
Purpose The current pandemic and ongoing climate risks highlight the limited capacity of various systems, including health and social ones, to respond to population-scale and long-term threats. Practices to reduce the impacts on the health and well-being of populations must evolve from a reactive mode to preventive, proactive and concerted actions beginning at individual and community levels. Experiences and lessons learned from the pandemic will help to better prevent and reduce the psychosocial impacts of floods, or other hydroclimatic risks, in a climate change context. Design/methodology/approach The present paper first describes the complexity and the challenges associated with climate change and systemic risks. It also presents some systemic frameworks of mental health determinants, and provides an overview of the different types of psychosocial impacts of disasters. Through various Quebec case studies and using lessons learned from past and recent flood-related events, recommendations are made on how to better integrate individual and community factors in disaster response. Findings Results highlight the fact that people who have been affected by the events are significantly more likely to have mental health problems than those not exposed to flooding. They further demonstrate the adverse and long-term effects of floods on psychological health, notably stemming from indirect stressors at the community and institutional levels. Different strategies are proposed from individual-centered to systemic approaches, in putting forward the advantages from intersectoral and multirisk researches and interventions. Originality/value The establishment of an intersectoral flood network, namely the InterSectoral Flood Network of Québec (RIISQ), is presented as an interesting avenue to foster interdisciplinary collaboration and a systemic view of flood risks. Intersectoral work is proving to be a major issue in the management of systemic risks, and should concern communities, health and mental health professionals, and the various levels of governance. As climate change is called upon to lead to more and more systemic risks, close collaboration between all the areas concerned with the management of the factors of vulnerability and exposure of populations will be necessary to respond effectively to damages and impacts (direct and indirect) linked to new meteorological and compound hazards. This means as well to better integrate the communication managers into the risk management team.
Keywords: Boivin_Maxime; Gachon_Philippe; Gousse-Lessard_Anne-Sophie; Généreux_Mélissa; Lessard_Lily; Site_internet_RIISQ

Health impacts of climate change in the UK: A qualitative synthesis detailing the conjuncture of social structure, extreme weather, and mental health - Dodd, Steven; Kragh-Furbo, Mette; Davies, Jessica; Butterfield, Scott; Morris, Abigail; Brown, Heather (SSM - Qualitative Research in Health, 2024)

The effect of an Internet‐based cognitive behavioral therapy intervention on social support in disaster evacuees - Frenette, Émilie; Ouellet, Marie‐Christine; Guay, Stéphane; Lebel, Jessica; Békés, Vera; Belleville, Geneviève (Journal of Clinical Psychology, 2023)
Abstract Introduction Both exposure to a natural disaster and psychological symptoms may lead to decreases in social support. Few studies have examined ways to improve social support among victims of natural disasters. Aims The objective of the study was to assess emotional and tangible support following a 12‐session Internet‐based cognitive behavioral therapy (ICBT) targeting posttraumatic stress (PTS), insomnia, and depression symptoms and to examine the association between posttreatment symptoms and emotional and tangible support. Materials and Methods One hundred and seventy‐eight wildfire evacuees with significant PTS, depression and/or insomnia symptoms were given access to the ICBT. They completed questionnaires at pre‐ and posttreatment to measure social support and symptom severity. Results Results show that completion of the treatment led to an improvement in emotional support. Lower posttreatment PTS and insomnia symptoms were associated with higher posttreatment emotional support. Conclusion ICBT may contribute to enhance emotional support through symptom improvement and probably more so when social support is address directly in treatment.
Keywords: Infolettre; Infolettre_Mars_2023

Portrait des risques liés aux inondations dans les bassins versants des rivières Mitis et Coaticook à partir des données d’aide financière versée à la suite d’inondations depuis 1990 - Dumont, Frédérique; Buffin-Belanger, Thomas (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Article introductif – L’acceptabilité sociale, une question de démocratie participative ? - Friser, Alice; Yates, Stéphanie (Revue internationale de psychosociologie et de gestion des comportements organisationnels, 2021)
La construction de l’acceptabilité sociale, conçue comme le jugement collectif des populations à l’endroit d’une politique ou d’un projet donné, s’appuie parfois sur la participation des acteurs sociaux concernés aux discussions éclairant la prise de décision publique. Les instances de démocratie intermédiaires où sont déployés divers dispositifs participatifs jouent ainsi un rôle de premier plan quant à l’émergence de l’acceptabilité. Or, la question des effets des processus participatifs sur les dynamiques d’acceptabilité sociale demeure aujourd’hui peu étudiée, que ce soit par les travaux sur l’acceptabilité sociale ou ceux portant sur la participation publique. À partir de projets soulevant des préoccupations de nature environnementale, ce numéro spécial puise à l’intersection de ces deux champs théoriques en vue d’analyser l’impact des dispositifs de démocratie participative sur la prise de décision et la construction de l’accessibilité sociale. Les contributions permettent ainsi de réfléchir à la façon dont les instances de démocratie intermédiaires contribuent ou non à l’acceptabilité sociale. De manière plus spécifique, elles explorent l’institutionnalisation du concept comme nouvelle norme de gestion publique, les effets des processus participatifs déployés dans ces instances sur l’acceptabilité d’un projet donné, de même que les effets sur les décisions finales. En somme, la réflexion proposée dans ce numéro permet de voir dans quelle mesure les dispositifs participatifs offrent les conditions d’un débat constructif permettant de mieux canaliser les conflits sociétaux que suscitent certains projets industriels ou politiques publiques, en vue de construire des compromis qui se projettent dans une vision d’avenir du développement.
Keywords: Ouvrage_Collectif_Numéro1

Measuring social equity in flood recovery funding - Emrich, Christopher T.; Tate, Eric; Larson, Sarah E.; Zhou, Yao (Environmental Hazards, 2020)

Socioeconomic implications of national flood insurance policy reform and flood insurance rate map revisions - Frazier, Tim; Boyden, Elizabeth E.; Wood, Erik (Natural Hazards, 2020)

Social Justice in Urban–Rural Flood Exposure: A Case Study of Nanjing, China - Chen, Yi; Liu, Hui; Ye, Zhicong; Zhang, Hao; Jiang, Bifeng; Zhang, Yang (Land, 2022)
The environmental justice research on urban–rural exposure to flooding is underdeveloped and few empirical studies have been conducted in China. This study addresses this gap by exploring the probabilities of exposure to floods (10-, 20-, and 50-year) and examining the relationship between vulnerable groups and flooding in Nanjing, an important central city on the Yangtze River. Statistical analysis is based on multivariable generalised estimating equation (GEE) models that describe sociodemographic disparities at the census-tract level. The results revealed that (1) highly educated people in the urban centre are more likely to live in areas with high flood risk because of the abundance of education resources, and employment opportunities are concentrated in the urban centre. (2) Natives in suburban areas are more likely to live in flood-prone areas due to their favourable ecological environments near rivers and lakes. (3) Women in rural areas are more likely to live in high-flood-risk zones because most of the men are migrant workers. These findings highlight the urgent need to develop mitigation strategies to reduce flood exposure, especially in districts with high proportions of socially disadvantaged people. The linkages between rural and urban areas need to be strengthened in order to reduce flood exposure.

Assessing social vulnerability and identifying spatial hotspots of flood risk to inform socially just flood management policy. - Chakraborty, Liton; Thistlethwaite, Jason; Scott, Daniel; Henstra, Daniel; Minano, Andrea; Rus, Horatiu A. (Risk Analysis, 2022)
This study presents the first nationwide spatial assessment of flood risk to identify social vulnerability and flood exposure hotspots that support policies aimed at protecting high-risk populations and geographical regions of Canada. The study used a national-scale flood hazard dataset (pluvial, fluvial, and coastal) to estimate a 1-in-100-year flood exposure of all residential properties across 5721 census tracts. Residential flood exposure data were spatially integrated with a census-based multidimensional social vulnerability index (SoVI) that included demographic, racial/ethnic, and socioeconomic indicators influencing vulnerability. Using Bivariate Local Indicators of Spatial Association (BiLISA) cluster maps, the study identified geographic concentration of flood risk hotspots where high vulnerability coincided with high flood exposure. The results revealed considerable spatial variations in tract-level social vulnerability and flood exposure. Flood risk hotspots belonged to 410 census tracts, 21 census metropolitan areas, and eight provinces comprising about 1.7 million of the total population and 51% of half-a-million residential properties in Canada. Results identify populations and the geographic regions near the core and dense urban areas predominantly occupying those hotspots. Recognizing priority locations is critically important for government interventions and risk mitigation initiatives considering socio-physical aspects of vulnerability to flooding. Findings reinforce a better understanding of geographic flood-disadvantaged neighborhoods across Canada, where interventions are required to target preparedness, response, and recovery resources that foster socially just flood management strategies.

Avoiding the vicious cycle, engendering the virtuous circle: Understanding the interaction of human, social and organizational capitals in non-profit and voluntary organizations - Currie, Denise; McCracken, Martin; Venter, Katharine (Journal of Business Research, 2022)

La réforme Barrette et sa mise en oeuvre dans les services sociaux : perceptions des travailleuses sociales - Bourque, Mélanie; Barbe, Mylène; Leroux, Maxime; Grenier, Josée; St-Amour, Nathalie (Intervention, 2024)
Cet article vise à partager les résultats préliminaires du projet de recherche « Les travailleuses sociales cinq ans après l’implantation de la réforme Barrette : standardisation de la pratique ou nouvelles normes locales des établissements? ». Ce projet de recherche a pour but de mieux comprendre la mise en oeuvre de la réforme du système de santé et des services sociaux de 2015 au Québec. De juin à décembre 2022, près de 60 personnes participantes ont accepté de répondre à un entretien semi-dirigé. La très grande majorité d’entre elles détiennent plus de dix ans d’expérience, ce qui permet de comprendre l’avant et l’après réforme Barrette et de saisir les effets de cette réforme sur les équipes de travail, mais aussi sur la prestation des services fournis à la population. L’analyse initiale des données met en lumière la poursuite, voire l’accentuation, de la perspective descendante (top down) du processus décisionnel, de la reddition de comptes par le biais de mesures quantitatives et de l’harmonisation des services s’illustrant en standardisation des pratiques, en dépit des particularités territoriales inhérentes aux différentes régions du Québec. Par rapport à notre recherche précédente, force est de constater que les méthodes de la nouvelle gestion publique se sont accentuées au sein du réseau de la santé et des services sociaux, qualifié de « maison des fous » par plusieurs personnes participantes.
Keywords: StAmour_Nathalie

Conséquences des inondations sur les finances des ménages - Bourdeau-Brien, Michael; Boudreault, Mathieu; Villeneuve, Thierry (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Bourdeau-Brien_Michael; Chapitre_Ouvrage_Collectif_Numero1

L’épreuve d’acceptabilité sociale, ou la composition disputée du collectif - Barbier, Rémi (Revue internationale de psychosociologie et de gestion des comportements organisationnels, 2021)
Parfois contestée, faiblement théorisée, la notion d’acceptabilité sociale tend néanmoins à s’imposer dans divers secteurs d’activité. Face à ce constat, cet article fait le pari qu’il peut être pertinent de la conserver et de l’utiliser comme « locution frontière » permettant de communiquer avec de nombreux acteurs. Mais cette concession est redoublée par une ambition de consolidation théorique de la notion, et par un souci de symétrisation de la charge d’acceptabilité d’un projet : celle-ci ne peut reposer uniquement sur un social récalcitrant à éduquer et à convaincre, elle doit également remettre en jeu le design du projet. L’article prend appui pour ce faire sur l’analyse des conflits spatialisés autour des équipements d’environnement. Il s’inscrit au croisement des approches STS et pragmatistes : ce cadre conceptuel est retenu car il permet d’étudier la composition d’un collectif (le monde social étendu à sa matérialité constitutive) sans présupposer d’asymétrie entre négociations sociales et techniques. L’épreuve d’acceptabilité porte plus précisément sur la compatibilité problématique entre deux ensembles rendus provisoirement indéterminés par le conflit : un dispositif sociotechnique d’un côté, un ou plusieurs milieux concernés de l’autre. L’article interprète cette épreuve d’acceptabilité en tant que régulation civique d’un projet technique, complétant la régulation de base dont il est normalement l’objet. Il prolonge enfin l’usage de cette notion avec une perspective opérationnelle, en proposant des pistes permettant à un éventuel tiers arbitre de piloter cette épreuve et d’en tirer démocratiquement les leçons.
Keywords: Ouvrage_Collectif_Numéro1

Limite à vie sur les inondations successives : vers un nouveau pacte social ? - Boudreault, Mathieu; Bourdeau-Brien, Michaël (Assurances et gestion des risques / Insurance and Risk Management, 2020)
Après les nombreuses crues printanières qui ont affecté le sud du Québec depuis 2011, le gouvernement du Québec a annoncé en avril 2019 une refonte importante de son programme d’aide financière aux sinistrés. Le programme introduit désormais une couverture limitée à vie de 100 000 $ pour les inondations successives, une mesure unique au Canada. L’objectif de cet article est d’analyser le coût des inondations successives et les impacts financiers de cette limite de couverture pour les ménages.
Keywords: Bourdeau-Brien_Michael; Ouvrage_Collectif_Numéro1; Site_internet_RIISQ

Déterminants sociaux et iniquités en santé des Canadiens Noirs : un aperçu. - Abdillahi, Ifrah; Shaw, Ashley (2020)

Un cadre de gouvernance collaboratif dédié à l’appréciation des risques des systèmes essentiels dans un contexte de changements climatiques - Robert, Benoît; Hémond, Yannick; Baril, Geneviève; Therrien, Marie-Christine (Canadian Journal of Emergency Management, 2022)
The fall 2021 climate events in British Columbia raise questions about the resiliency of communities, but also of critical systems, with respect to the allocation of roads, telecommunications, drinking water, electricity, etc. The interdependence of these systems can quickly generate serious consequences for populations and socio-economic activities that local and regional authorities must manage. The diversity and number of stakeholders require these authorities to coordinate well. How then can the risks to which they are exposed be better assessed? How can we ensure coherence in the measures put in place in terms of planning, preparation and response? The concepts and results presented in this article are the result of an action-research project carried out with the participation of numerous partners, particularly, but not exclusively, from municipal milieus in two regions of Quebec (Argenteuil and Brome-Missisquoi MRCs). This active collaboration with these regional partners has made it possible to propose an approach for implementing a collaborative governance framework combined with a risk assessment process. The tools and mechanisms associated with this approach will allow regional authorities to better understand the impact of climate change on the territory and to ensure consistency in the risk management actions of the various stakeholders. , Les événements climatiques de l’automne 2021 en Colombie-Britannique soulèvent des questions sur la résilience des communautés, mais aussi des systèmes essentiels, en regard de l’affectation des réseaux routiers, de télécommunication, d’eau potable, d’électricité, etc. L’interdépendance de ces systèmes génère rapidement des conséquences graves pour la population et les activités socioéconomiques que les autorités locales et régionales doivent gérer. La diversité des intervenants ainsi que leur nombre exigent de ces autorités de bien se coordonner. Comment alors peut-on mieux apprécier les risques auxquels ils sont exposés ? Comment s’assurer d’une cohérence dans les mesures mises en place autant dans la planification, la préparation que l’intervention ? Les concepts et résultats présentés dans cet article sont issus d’un projet de recherche-action réalisé avec la participation de nombreux partenaires, particulièrement, mais non exclusivement du milieu municipal dans deux régions du Québec (MRC d’Argenteuil et de Brome-Missisquoi). Cette collaboration active avec ces partenaires régionaux permet de proposer une démarche pour mettre en place un cadre de gouvernance collaboratif combiné à un processus d’appréciation des risques. Les outils et mécanismes associés à cette démarche permettront, alors, aux autorités régionales de mieux comprendre l’impact des changements climatiques sur le territoire et d’assurer une cohérence dans les actions de gestion des risques des différentes parties prenantes.
Keywords: Hémond_Yannick

Multicriteria Decision Analysis to Assist in the Selection of Coastal Defence Measures: Involving Coastal Managers and Professionals in the Identification and Weighting of Criteria - Sauvé, Philippe; Bernatchez, Pascal; Glaus, Mathias (Frontiers in Marine Science, 2022)
Coastal socio-ecological systems are complex adaptive systems with nonlinear changing properties and multi-scale dynamics. They are influenced by unpredictable coastal hazards accentuated by the effects of climate change, and they can quickly be altered if critical thresholds are crossed. Additional pressures come from coastal activities and development, both of which attracting stakeholders with different perspectives and interests. While coastal defence measures (CDMs) have been implemented to mitigate coastal hazards for centuries, a lack of knowledge and tools available to make informed decision has led to coastal managers favouring the choice of seawalls or rock armours with little consideration for socio-ecological systems features, and stakeholders’ priorities. Though it is not currently widely applied in coastal zone management, multicriteria decision analysis (MCDA) is a tool that can be useful to facilitate decision making. PROMETHEE, an outranking method, was chosen to support the multicriteria decision analysis for the evaluation of CDMs in the context of four study sites characterized by distinct environmental features. The aim was to determine the relevance and benefits of a MCDA by integrating coastal zone stakeholders in a participatory decision-making process in order to select CDMs that are better adapted to the whole socio-ecological system. First, in a series of five workshops, stakeholders were asked to identify and weigh criteria that were relevant to their local conditions. Second and third, CDMs were evaluated in relation to each criterion within the local context, then, hierarchized. Initial results show that vegetation came first in three of the four sites, while rock armour ranked first in the fourth site. A post-evaluation of the participatory process indicated that the weighting phase is an effective way to integrate local knowledge into the decision-making process, but the identification of criteria could be streamlined by the presentation of a predefined list from which participants could make a selection. This would ensure criteria that are standardized, and in a format that is compatible with the MCDA. Coupled with a participatory process MCDA proved to be a flexible methodology that can synthetize multiple aspects of the problem, and contribute in a meaningful way to the coastal engineering and management decision-making process.
Keywords: Infolettre; Infolettre_Juillet_2022; Site_internet_RIISQ

Gouvernance régionale et stratégies d’adaptation aux inondations en contexte de changements climatiques : une étude de cas, la MRC de Vaudreuil-Soulanges - Thivierge, Caroline (2021)
L’objectif de cette recherche est d’identifier les stratégies d’adaptation qui sont requises et du ressort d’une municipalité régionale de comté face aux inondations. Le réchauffement global des températures soulève plusieurs inquiétudes quant à la modification du cycle hydrologique. Les inondations figurent en tête de liste des enjeux de sécurité civile des municipalités riveraines. Au Québec, on prévoit une augmentation des précipitations printanières, automnales et hivernales, ainsi que des débits hivernaux plus élevés et un devancement des crues printanières. Des projections qui peuvent influencer l’approche de gestion des barrages, bien que le contrôle des niveaux d’eau ne soit pas une panacée vis-à-vis des inondations. Il suppose une gestion intégrée de l’eau parfois complexe. Aussi, les administrations locales ne siègent pas toujours aux comités responsables de la régularisation des cours d’eau. Celles-ci se retrouvent sur la ligne de front sans pour autant avoir le pouvoir et les ressources financières pour y faire face. Les crues exceptionnelles de 2017 et 2019 ont conduit la Municipalité régionale de comté de Vaudreuil-Soulanges à mettre à jour ses plans d’urgence et à mettre en place une cellule de crise. Elle applique une stratégie d’adaptation correspondant aux 4 axes du Plan de protection du territoire face aux inondations du ministère des Affaires municipales et de l’Habitation. Ces outils enrichissent leur capacité d’adaptation par l’acquisition de nouvelles connaissances et d’une nouvelle cartographie des zones inondables. Les vulnérabilités qui résultent de contraintes liées à l’aménagement du territoire, ainsi que d’enjeux réglementaires posent un défi pour le développement du territoire et la relocalisation de résidences inondées. Il convient de sonder la population sur sa vision de la résilience afin d’assurer une meilleure acceptabilité sociale des décisions à venir. Une vulnérabilité importante réside dans les écarts de perception du risque entre les municipalités et entre les individus ; ce qui engendre des enjeux de sécurité, de communication et de gouvernance. Les instances locales peuvent miser sur leurs habiletés de mobilisation pour réunir la communauté autour du développement d’un plan d’adaptation aux changements climatiques et ainsi harmoniser les perceptions. Finalement, l’épuisement des ressources humaines des municipalités inondées à répétition est à considérer. Il appert qu’il est essentiel d’identifier et de mettre en place les outils et ressources pour les soutenir.
Keywords: Ouvrage_Collectif_Numéro1

Aménagement du territoire et gestion des zones inondables : enjeux de gouvernance et d’encadrement réglementaire - Gauthier, Mario; Biron, Pascale; Buffin-Belanger, Thomas (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Gouvernance régionale et leviers mobilisables d’une gestion intégrée de l’eau : le cas de Vaudreuil-Soulanges - Létourneau, Alain; Thivierge, Caroline (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Improving flood resilience through governance strategies: Gauging the state of the art - Matczak, Piotr; Hegger, Dries (WIREs Water, 2021)
Abstract There has been an upsurge in studies of flood risk governance (FRG): steering and decision‐making by public and private actors as a complement to risk assessments and technical management options. The scholarly debate is, however, highly fragmented, complicating the production of cumulative insights. To address this knowledge gap, we used six governance strategies for achieving flood resilience that previously have been put forward as a conceptual framework to review 121 articles published between 2016 and 2019, complemented with insights contained in recent overview articles, to gauge the state‐of‐the‐art in FRG literature: to (a) diversify flood risk management strategies; (b) align the strategies; (c) adequately involve private actors, including citizens; (d) put an adequate rule system in place; (e) cater for sufficient monetary and non‐monetary resources; (f) inspire an open and inclusive normative debate. We found, first, that literature is producing insights on increasingly technically advanced risk assessments and agent‐based models but societal debate on justice in flood risk governance is getting attention. A clearly emerging topic is that of citizen engagement in flood risk governance. Second, the geographical focus of the studies is still skewed toward the Global North. To make progress in understanding flood risk governance for better resilience more systematic and comparative empirical assessments of flood risk governance in order to derive generalizable lessons while better taking into account the context‐specificity of FRG. Testing flood risk governance solutions against comparative cases, by balancing the geographical scope of research efforts, and enhancing interdisciplinary and transdisciplinary working is a way to deliver knowledge for more resilience. This article is categorized under: Human Water > Water Governance Engineering Water > Planning Water
Keywords: Ouvrage_Collectif_Numéro1

Resilience in the Anthropocene: governance and politics at the end of the world - Chandler, David; Grove, Kevin; Wakefield, Stephanie (Routledge research in the Anthropocene, 2020)
"This book offers the first critical, multi-disciplinary study of how the concepts of resilience and the Anthropocene have combined to shape contemporary thought and governmental practice. Faced with the climate catastrophe of the Anthropocene, theorists and policymakers are increasingly turning to 'sustainable', 'creative' and 'bottom-up' imaginaries of governance. The book brings together cutting-edge insights from leading geographers, international relations scholars and philosophers to explore how the concepts of resilience and the Anthropocene challenge and transform prevailing understandings of Earth, space, time and knowledge, and how these transformations reshape governance, ethics and critique today. This book examines how the Anthropocene calls into question established categories through which modern societies have tended to make sense of the world and engage in critical reflection and analysis. It also considers how resilience approaches attempt to re-stabilize these categories - and the ethical and political effects that result from these resilience-based efforts. Offering innovative insights into the problem of how environmental change is known and governed in the Anthropocene, this book will be of interest to students in fields such as geography, international relations, anthropology, science and technology studies, sociology, and the environmental humanities"--
Keywords: Nobert_Sebastien

Limited progress in global reduction of vulnerability to flood impacts over the past two decades - Sauer, Inga J.; Mester, Benedikt; Frieler, Katja; Zimmermann, Sandra; Schewe, Jacob; Otto, Christian (Communications Earth & Environment, 2024)
Abstract Global flood impacts have risen in recent decades. While increasing exposure was the dominant driver of surging impacts, counteracting vulnerability reductions have been detected, but were too weak to reverse this trend. To assess the ongoing progress on vulnerability reduction, we combine a recently available dataset of flooded areas derived from satellite imagery for 913 events with four global disaster databases and socio-economic data. Event-specific flood vulnerabilities for assets, fatalities and displacements reveal a lack of progress in reducing global flood vulnerability from 2000—2018. We examine the relationship between vulnerabilities and human development, inequality, flood exposure and local structural characteristics. We find that vulnerability levels are significantly lower in areas with good structural characteristics and significantly higher in low developed areas. However, socio-economic development was insufficient to reduce vulnerabilities over the study period. Nevertheless, the strong correlation between vulnerability and structural characteristics suggests further potential for adaptation through vulnerability reduction.

Methodological approach for mapping the flood physical vulnerability index with geographical open-source data: an example in a small-middle city (Ponferrada, Spain) - Tascón-González, Laura; Ferrer-Julià, Montserrat; García-Meléndez, Eduardo (Natural Hazards, 2024)
Abstract To increase the resilience of communities against floods, it is necessary to develop methodologies to estimate the vulnerability. The concept of vulnerability is multidimensional, but most flood vulnerability studies have focused only on the social approach. Nevertheless, in recent years, following seismic analysis, the physical point of view has increased its relevance. Therefore, the present study proposes a methodology to map the flood physical vulnerability and applies it using an index at urban parcel scale for a medium-sized town (Ponferrada, Spain). This index is based on multiple indicators fed by geographical open-source data, once they have been normalized and combined with different weights extracted from an Analytic Hierarchic Process. The results show a raster map of the physical vulnerability index that facilitates future emergency and flood risk management to diminish potential damages. A total of 22.7% of the urban parcels in the studied town present an index value higher than 0.4, which is considered highly vulnerable. The location of these urban parcels would have passed unnoticed without the use of open governmental datasets, when an average value would have been calculated for the overall municipality. Moreover, the building percentage covered by water was the most influential indicator in the study area, where the simulated flood was generated by an alleged dam break. The study exceeds the spatial constraints of collecting this type of data by direct interviews with inhabitants and allows for working with larger areas, identifying the physical buildings and infrastructure differences among the urban parcels.

Trajectoires de la vulnérabilité aux inondations dans les bassins versants des rivières Cascapédia et Petite Cascapédia à l'est du Québec - Tomety, Yaovi Djivenou (Université du Québec à Rimouski, 2022)
RÉSUMÉ : Les inondations dans la MRC de Bonaventure, à l'instar des inondations de 2017 et de 2019 aux Québec, amènent à repenser les politiques de gestion préventive des inondations dans les municipalités mais il est nécessaire de revisiter le passé pour mieux anticiper le futur. A l'heure actuelle, aucune étude dans la MRC de Bonaventure n'a abordé la trajectoire de la vulnérabilité aux inondations. Le projet de recherche avait pour objectif d'évaluer l'évolution spatio-temporelle de la vulnérabilité aux inondations dans la MRC de Bonaventure plus précisément dans les bassins versants des rivières Cascapédia et petite Cascapédia. Cette recherche s'est particulièrement intéressée à : - 1) - identifier les indicateurs de vulnérabilité aux inondations les plus pertinents et leurs interactions et - 2) - comprendre la trajectoire de la vulnérabilité aux inondations dans le temps. La méthode indicielle a permis de calculer les indices de vulnérabilité par addition d'indicateurs pondérés dans l'analyse de la trajectoire de la vulnérabilité pour les années 1986, 1996, 2006 et de 2016 à partir de 43 indicateurs sélectionnés, adaptés au contexte de la zone d'étude et validés par la MRC de Bonaventure. L'évaluation de la trajectoire de la vulnérabilité aux inondations révèle que les variables socio-économiques sont les plus importantes contribuant à faire varier la vulnérabilité dans le temps dans les corridors fluviaux des rivières Cascapédia et petite Cascapédia. Cette étude expose le caractère dynamique, temporel et transformationnel de la vulnérabilité. Les cartographies de vulnérabilité générées en maillages de 200 m x 200 m et les enquêtes sur le terrain ont permis de mieux appréhender les changements globaux qui ont contribué à l'évolution de la vulnérabilité aux inondations et de comprendre la nature de la vulnérabilité aux inondations. Cette analyse permettra aux décideurs d'anticiper le futur pour une planification concrète de l'adaptation et des mesures de prévention. La trajectoire de la vulnérabilité se présente alors comme un outil de prévention et de prospection pour les décideurs. Elle permet d'appréhender la vulnérabilité du passé, comprendre la vulnérabilité du présent et anticiper sur la vulnérabilité du futur. -- Mot(s) clé(s) en français : Trajectoire, vulnérabilité, inondation, indice de vulnérabilité, gestion préventive. -- ABSTRACT : The floods in the MRC of Bonaventure, like the floods of 2017 and 2019 in Quebec, lead to a rethink of the preventive flood management policies in the municipalities, but it is necessary to revisit the past to better anticipate the future. At present, no study in the MRC of Bonaventure has addressed the trajectory of vulnerability to flooding. The objective of the research project was to assess the spatio-temporal evolution of vulnerability to flooding in the MRC of Bonaventure, more specifically in the watersheds of the Cascapedia and Petite Cascapedia rivers. This research was particularly interested in: - 1) - identifying the most relevant flood vulnerability indicators and their interactions and - 2) - understanding the trajectory of flood vulnerability over time. The index method made it possible to calculate the vulnerability indices by adding weighted indicators in the analysis of the trajectory of vulnerability for the years 1986, 1996, 2006 and 2016 from 43 selected indicators, adapted to the context of the study area and validated by the MRC of Bonaventure. The evaluation of the trajectory of vulnerability to flooding reveals that socio-economic variables are the most important contributing to varying vulnerability over time in the fluvial corridors of the Cascapedia and Petite Cascapedia rivers. This study exposes the dynamic, temporal and transformational character of vulnerability. The vulnerability maps generated in 200 m x 200 m grids and the field surveys have made it possible to better understand the global changes that have contributed to the evolution of vulnerability to floods and to understand the nature of vulnerability to floods. This analysis will allow decision-makers to anticipate the future for concrete planning of adaptation and prevention measures. The trajectory of vulnerability is then presented as a prevention and prospecting tool for decision-makers. It makes it possible to apprehend the vulnerability of the past, to understand the vulnerability of the present and to anticipate the vulnerability of the future. -- Mot(s) clé(s) en anglais : Trajectory, vulnerability, flooding, vulnerability index, preventive management.

The challenges of dynamic vulnerability and how to assess it - Ruiter, Marleen C. de; Loon, Anne F. Van (iScience, 2022)
Recent disasters have demonstrated the challenges faced by society as a result of the increasing complexity of disaster risk. In this perspective article, we discuss the complex interactions between hazards and vulnerability and suggest methodological approaches to assess and include dynamics of vulnerability in our risk assessments, learning from the compound and multi-hazard, socio-hydrology, and socio-ecological research communities. We argue for a changed perspective, starting with the circumstances that determine dynamic vulnerability. We identify three types of dynamics of vulnerability: (1) the underlying dynamics of vulnerability, (2) changes in vulnerability during long-lasting disasters, and (3) changes in vulnerability during compounding disasters and societal shocks. We conclude that there is great potential to capture the dynamics of vulnerability using qualitative and model-based methods, both for reproducing historic and projecting future dynamics of vulnerability. We provide examples using narratives, agent-based models, and system dynamics.

Méthode d’évaluation et de cartographie de la vulnérabilité et du risque humain liés à une inondation en cours au Québec - Tanguy, Marion; Chokmani, Karem; Bernier, Monique; Poulin, Jimmy; Gauthier, Yves; Oubennaceur, Khalid (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Inondations de 2017 à 2019 à Pierrefonds-Roxboro : quand un diagnostic collectif et des interventions publiques ciblées limitent les vulnérabilités et les conséquences - Tchuitchou Dueyou, Clémentine Rose; Vandelac, Louise (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Consultations sur les vulnérabilités psychosociales des inondations en contexte de changements climatiques - Annexe 1 - Projet CASSSIOPÉE - Turmel, J.; Lessard, L.; Lafond, A.; Robitaille, M-A (2022)

Flood exposure and social vulnerability in the United States - Tate, Eric; Rahman, Asif; Emrich, Christopher T.; Sampson, Christopher C. (Natural Hazards, 2021)
Human exposure to floods continues to increase, driven by changes in hydrology and land use. Adverse impacts amplify for socially vulnerable populations, who disproportionately inhabit flood-prone areas. This study explores the geography of flood exposure and social vulnerability in the conterminous United States based on spatial analysis of fluvial and pluvial flood extent, land cover, and social vulnerability. Using bivariate Local Indicators of Spatial Association, we map hotspots where high flood exposure and high social vulnerability converge and identify dominant indicators of social vulnerability within these places. The hotspots, home to approximately 19 million people, occur predominantly in rural areas and across the US South. Mobile homes and racial minorities are most overrepresented in hotspots compared to elsewhere. The results identify priority locations where interventions can mitigate both physical and social aspects of flood vulnerability. The variables that most distinguish the clusters are used to develop an indicator set of social vulnerability to flood exposure. Understanding who is most exposed to floods and where, can be used to tailor mitigation strategies to target those most in need.

An Empirical Social Vulnerability Map for Flood Risk Assessment at Global Scale (“GlobE‐SoVI”) - Reimann, Lena; Koks, Elco; De Moel, Hans; Ton, Marijn J.; Aerts, Jeroen C. J. H. (Earth's Future, 2024)
Abstract Fatalities caused by natural hazards are driven not only by population exposure, but also by their vulnerability to these events, determined by intersecting characteristics such as education, age and income. Empirical evidence of the drivers of social vulnerability, however, is limited due to a lack of relevant data, in particular on a global scale. Consequently, existing global‐scale risk assessments rarely account for social vulnerability. To address this gap, we estimate regression models that predict fatalities caused by past flooding events ( n = 913) based on potential social vulnerability drivers. Analyzing 47 variables calculated from publicly available spatial data sets, we establish five statistically significant vulnerability variables: mean years of schooling; share of elderly; gender income gap; rural settlements; and walking time to nearest healthcare facility. We use the regression coefficients as weights to calculate the “ Glob al‐ E mpirical So cial V ulnerability I ndex (GlobE‐SoVI)” at a spatial resolution of ∼1 km. We find distinct spatial patterns of vulnerability within and across countries, with low GlobE‐SoVI scores (i.e., 1–2) in for example, Northern America, northern Europe, and Australia; and high scores (i.e., 9–10) in for example, northern Africa, the Middle East, and southern Asia. Globally, education has the highest relative contribution to vulnerability (roughly 58%), acting as a driver that reduces vulnerability; all other drivers increase vulnerability, with the gender income gap contributing ∼24% and the elderly another 11%. Due to its empirical foundation, the GlobE‐SoVI advances our understanding of social vulnerability drivers at global scale and can be used for global (flood) risk assessments. , Plain Language Summary Social vulnerability is rarely accounted for in global‐scale risk assessments. We develop an empirical social vulnerability map (“GlobE‐SoVI”) based on five key drivers of social vulnerability to flooding, that is, education, elderly, income inequality, rural settlements and travel time to healthcare, which we establish based on flood fatalities caused by past flooding events. Globally, we find education to have a high and reducing effect on social vulnerability, while all other drivers increase vulnerability. Integrating social vulnerability in global‐scale (flood) risk assessments can help inform global policy frameworks that aim to reduce risks posed by natural hazards and climate change as well as to foster more equitable development globally. , Key Points We develop a global map of social vulnerability at ∼1 km spatial resolution based on five key vulnerability drivers (“GlobE‐SoVI”) We establish vulnerability drivers empirically based on their contribution to predicting fatalities caused by past flooding events Accounting for social vulnerability in global‐scale (flood) risk assessments can inform global policy frameworks that aim to reduce risk

Spatial distribution of socio-demographic and housing-based factors in relation to flash and slow-rise flooding hazards in the U.S - Oke, Oluwatobi; Dougherty, Erin; Rasmussen, Kristen L.; Morrison, Ryan R.; Ellison Carter (2023)
Abstract Previous studies have drawn attention to racial and socioeconomic disparities in exposures associated with flood events at varying spatial scales, but most of these studies have not differentiated flood risk. Assessing flood risk without differentiating floods by their characteristics (e.g. duration and intensity of precipitation leading to flooding) may lead to less accurate estimates of the most vulnerable locations and populations. In this study, we compare the spatial patterning of social vulnerability, types of housing, and housing tenure (i.e. rented vs. owned) between two specific flood types used operationally by the National Weather Service—flash floods and slow-rise floods—in the floodplains across the Contiguous United States (CONUS). We synthesized several datasets, including established distributions of flood hazards and flooding characteristics, indicators of socioeconomic status, social vulnerability, and housing characteristics, and used generalized estimating equations to examine the proportion of socially vulnerable populations and housing types and tenure residing in the flash and slow-rise flood extents. Our statistical findings show that the proportion of the slow-rise flooded area in the floodplains is significantly greater in tracts characterized by higher percentages of socially vulnerable. However, the results could not confirm the hypothesis that they are exposed considerably more than less vulnerable in the flash flooded floodplains. Considering housing-occupancy vulnerability, the percentage of renter-occupancies are greater in the flash flood floodplains compared to slow-rise, especially in areas with high rainfall accumulation producing storms (e.g. in the Southeast). This assessment contributes insights into how specific flood types could impact different populations and housing tenure across the CONUS and informs strategies to support urban and rural community resilience and planning at local and state levels.

Comparing spatially explicit approaches to assess social vulnerability dynamics to flooding - Meijer, L.G.; Reimann, L.; Aerts, J.C.J.H. (International Journal of Disaster Risk Reduction, 2023)

Aléas fluviaux des cours d’eau mobiles dans l’est du Québec - Maltais, Maxime; Buffin-Belanger, Thomas; Boivin, Maxime (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Boivin_Maxime; Chapitre_Ouvrage_Collectif_Numero1

Spatiotemporal Variations in Meteorological Disasters and Vulnerability in China During 2001–2020 - Li, Ying; Zhao, Shanshan; Zhao, Shiqiang; Wang, Guojie (Frontiers in Earth Science, 2021)
Based on the Yearbook of Meteorological Disasters in China, we analyzed the spatiotemporal variations in major meteorological disaster (MD) losses at the provincial scale during 2001–2020 to determine the spatiotemporal variations in MDs and vulnerability in China. Our results suggest that the impacts of MDs, including floods, droughts, hail and strong winds (HSs), low temperature and frosts (LTFs), and typhoons, have been substantial in China. MDs in China affect an average of 316.3 million people and 34.3 million hectares of crops each year, causing 1,739 deaths and costing 372.3 billion yuan in direct economic losses (DELs). Floods and droughts affected more of the population in China than the other MDs. Fatalities and DELs were mainly caused by floods, and the affected crop area was mainly impacted by drought. The national average MD losses decreased significantly, except for DELs. The trends in the affected population and crop area were mainly caused by droughts, and the trends in fatalities and DELs were dominated by floods. Floods and typhoons showed increasing influence in the last two decades relative to other disasters. The annual mean and long-term trends in MD losses exhibited regional heterogeneity and were subject to different dominant hazards in different regions. The disaster losses and their trends in southeastern China were mainly attributed to typhoons. The affected population, crop area, and DELs were all significantly and positively correlated with exposure. The vulnerability of the population, crops, and economy tended to decrease. Economic development reduced the vulnerability of the population and economy but showed no significant influence on the vulnerability of crops. Our findings suggest that more focus should be placed on the impacts of floods and typhoons and that socioeconomic development has an important influence on the vulnerability of the population and economy. These results provide a foundation for designing effective disaster prevention and mitigation measures.

Vulnérabilités psychosociales des populations rurales du Québec en temps de pandémie - Lessard, Lily; Simard, Dominic; Morin, Marie-Hélène (Santé Publique, 2021)
Keywords: Lessard_Lily

Impact of climate change on the vulnerability of drinking water intakes in a northern region - Leveque, B.; Burnet, J.-B.; Dorner, S.; Bichai, F. (Sustainable Cities and Society, 2021)
Keywords: Dorner_Sarah

Flood hazards, environmental rewards, and the social reproduction of risk - Oulahen, Greg (Geoforum, 2021)

Integrating social vulnerability into high-resolution global flood risk mapping - Fox, Sean; Agyemang, Felix; Hawker, Laurence; Neal, Jeffrey (Nature Communications, 2024)
Abstract High-resolution global flood risk maps are increasingly used to inform disaster risk planning and response, particularly in lower income countries with limited data or capacity. However, current approaches do not adequately account for spatial variation in social vulnerability, which is a key determinant of variation in outcomes for exposed populations. Here we integrate annual average exceedance probability estimates from a high-resolution fluvial flood model with gridded population and poverty data to create a global vulnerability-adjusted risk index for flooding (VARI Flood) at 90-meter resolution. The index provides estimates of relative risk within or between countries and changes how we understand the geography of risk by identifying ‘hotspots’ characterised by high population density and high levels of social vulnerability. This approach, which emphasises risks to human well-being, could be used as a complement to traditional population or asset-centred approaches.

What can be said about risks, vulnerabilities, and adaptation to climate change in Caribbean small island developing states (SIDS)? The case of Dominica. A qualitative study - Cooper, Sarah; Abraham, Christiana; Ravaliere, Terrilia; Harris-Glenville, Fiona; McPherson, Nickez; Cloos, Patrick (2023)
IntroductionCaribbean Small island developing states (SIDS) are generally qualified as disproportionately vulnerable to climate change, including extreme weather events like hurricanes. While many studies already documented the impacts of climate change on health in the wealthiest countries, there is little knowledge in this field in Caribbean SIDS. Our study aims to discuss health risks and vulnerabilities in a Caribbean context to inform future adaptation measures to climate change.MethodsOur paper is based on a qualitative study that was conducted in Dominica, a Caribbean SIDS. The data come from semi-structured interviews organized between March 2020 and January 2021 with people internally displaced following an extreme climate event, either tropical storm Erika (2015) or Hurricane Maria (2017), and with some people who migrated to Guadeloupe after Hurricane Maria. Interview guides were based on conceptual frameworks on climate change, migration and health, and vulnerability to climate change. Data were analyzed deductively based on frameworks and inductively to allow new codes to emerge.ResultsOur findings suggest that current knowledge of climate change by those who have been displaced by an extreme climate event varied greatly depending on the education level, class, and socioeconomic condition of the participant. Participants experienced various negative consequences from a storm or hurricane such as increased risk of relocation, lack of access to healthcare, and food, job, and water insecurities – all circumstances know to correlate with mental health issues. Participants suggested stronger dwellings, community preparedness committees to act sooner, and climate change sensitization and awareness campaigns to foster community unity and solidarity.ConclusionThese findings contribute to the perspectives and knowledge of climate change, highlighting that existing extreme climate event committees and government officials need to address structural and social barriers that can potentially increase social inequalities and lead to maladaptation to climate change with potential consequences on public health.
Keywords: Cloos_Patrick

Flood risk quantification and mapping: An integrated vulnerability-based approach at the local scale in New Brunswick, Canada - Duhamel, Francis; Germain, Daniel; Fortin, Guillaume (International Journal of Disaster Risk Reduction, 2022)
This paper explores the risk approach, considering both the physical and human dimensions of the phenomenon in order to produce a more realistic and spatial analysis of risk. Exposure and vulnerability were combined and evaluated multidimensionally, considering individual, socio-economic, and structural (building-related) aspects. These risk factors were then integrated in a multi-criteria analysis in order to produce a comprehensive risk index that could be visualized at the building scale. The relative importance of the indicators was determined through a participatory process involving local and national experts on civil security and flooding. Particular attention was paid to individual vulnerability, including perception and preparedness for flood risk, which were explored directly with local people using a questionnaire. Qualitative and quantitative analyses of the responses allowed for a better understanding of the perception and preparedness of populations exposed to flooding. These data should help to improve risk communication between the authorities concerned and the populations at risk, as well as encouraging implementation of appropriate measures and a bottom-up participatory management approach. The integration of data in a geographic information system enables the visualization and spatialization of risk, but also each of its components.
Keywords: Infolettre; Infolettre_Fevrier_2023

Declining vulnerability but rising impacts: the trends of climatic disasters in Nepal - Chapagain, Dipesh; Bharati, Luna; Borgemeister, Christian (Regional Environmental Change, 2022)
Abstract The impacts of climatic disasters have been rising globally. Several studies argue that this upward trend is due to rapid growth in the population and wealth exposed to disasters. Others argue that rising extreme weather events due to anthropogenic climate change are responsible for the increase. Hence, the causes of the increase in disaster impacts remain elusive. Disaster impacts relative to income are higher in low-income countries, but existing studies are mostly from developed countries or at the cross-country level. Here we assess the spatiotemporal trends of climatic disaster impacts and vulnerability and their attribution to climatic and socioeconomic factors at the subnational scale in a low-income country, using Nepal as a case study. Loss of life is the most extreme consequence of disasters. Therefore, we employed human mortality as a measure of disaster impacts, and mortality normalized by exposed population as a measure of human vulnerability. We found that climatic disaster frequency and mortality increased in Nepal from 1992 to 2021. However, vulnerability decreased, most likely due to economic growth and progress in disaster risk reduction and climate change adaptation. Disaster mortality is positively correlated with disaster frequency and negatively correlated with per capita income but is not correlated with the exposed population. Hence, population growth may not have caused the rise in disaster mortality in Nepal. The strong rise in disaster incidence, potentially due to climate change, has overcome the effect of decreasing vulnerability and caused the rise in disaster mortality.

Mesures concrètes pour réduire les vulnérabilités face aux inondations et leur mise en œuvre au Québec - Eyquem, Joanna (Les inondations au Québec : risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités, 2022)
Keywords: Chapitre_Ouvrage_Collectif_Numero1

Leveraging Hazard, Exposure, and Social Vulnerability Data to Assess Flood Risk to Indigenous Communities in Canada - Chakraborty, Liton; Thistlethwaite, Jason; Minano, Andrea; Henstra, Daniel; Scott, Daniel (International Journal of Disaster Risk Science, 2021)
Abstract This study integrates novel data on 100-year flood hazard extents, exposure of residential properties, and place-based social vulnerability to comprehensively assess and compare flood risk between Indigenous communities living on 985 reserve lands and other Canadian communities across 3701 census subdivisions. National-scale exposure of residential properties to fluvial, pluvial, and coastal flooding was estimated at the 100-year return period. A social vulnerability index (SVI) was developed and included 49 variables from the national census that represent demographic, social, economic, cultural, and infrastructure/community indicators of vulnerability. Geographic information system-based bivariate choropleth mapping of the composite SVI scores and of flood exposure of residential properties and population was completed to assess the spatial variation of flood risk. We found that about 81% of the 985 Indigenous land reserves had some flood exposure that impacted either population or residential properties. Our analysis indicates that residential property-level flood exposure is similar between non-Indigenous and Indigenous communities, but socioeconomic vulnerability is higher on reserve lands, which confirms that the overall risk of Indigenous communities is higher. Findings suggest the need for more local verification of flood risk in Indigenous communities to address uncertainty in national scale analysis.

Environmental vulnerability and resilience: Social differentiation in short‐ and long‐term flood impacts - Houston, Donald; Werritty, Alan; Ball, Tom; Black, Andrew (Transactions of the Institute of British Geographers, 2021)
This paper finds that social differentiation in flood impacts is relatively small soon after a flood, with some surprising results such as professionals and homeowners badly affected in the short‐term – but widens over time, with socially disadvantaged groups displaying less recovery. The paper concludes that vulnerability and resilience to flooding are sensitive to financial resources, institutional support (chiefly from a landlord), and capacity to deal with disruption (chiefly time availability, which is low among professionals and high among retired people). An implication of these findings is that existing indices of flood vulnerability that use multiple measures of social deprivation should be used with caution, as not all conventional aspects of social deprivation are necessarily associated with greater vulnerability to flood impacts. , This paper reports household questionnaire survey results on vulnerability and resilience to flooding from one of the largest and most representative samples ( n = 593) of households up to 12 years after they were flooded, and is one of the first to provide detailed analysis of social differentiation in long‐term flood impacts. A novel finding is that social differentiation in flood impacts is relatively small soon after a flood, but widens over time, with socially disadvantaged groups displaying less recovery. The patterns of social differentiation in vulnerability and resilience to flooding differ markedly according to the type and timescale of the impact, with some normally socially advantaged groups (e.g., professionals and homeowners) being most vulnerable to short‐term impacts. Consistent with some existing studies, we found that older residents (age 70+) have greater resilience to flood impacts, although our sample may not capture the frailest individuals. As in previous research, low income is linked to lower resilience, particularly in the long term. We find that prior experience of flooding, despite enhancing preparedness, overall erodes rather than enhances resilience to flooding. Flood warnings are effective at reducing vulnerability to short‐term impacts. Underlying influences on resilience to natural disasters are complex and may only be revealed by multivariate analysis and not always be evident in simple observed patterns. The paper concludes that vulnerability and resilience to flooding are sensitive to financial resources, institutional support (chiefly from a landlord), and capacity to deal with disruption (chiefly time availability, which is low among professionals and high among retired people). An implication of these findings is that existing indices of flood vulnerability that use multiple measures of social deprivation should be used with caution, as not all conventional aspects of social deprivation are necessarily associated with greater vulnerability to flood impacts.

Physical Vulnerability and Local Responses to Flood Damage in Peri-Urban Areas of Dhaka, Bangladesh - Fatemi, Nawrose; Okyere, Seth Asare; Diko, Stephen Kofi; Kita, Michihiro; Shimoda, Motoki; Matsubara, Shigeki (Sustainability, 2020)
In Eastern Dhaka, perennial flood remains a constant threat to people and livelihoods. Learning from the micro-level experiences of the poor in the peri-urban areas of Dhaka provides insights on the intersections between physical vulnerability, flood response strategies, and adaptive capacity. Through a convergent mixed method, this study examines the physical vulnerability of residential buildings, flood damages, and local physical responses in three neighborhoods of Eastern Dhaka. Results show that the level of damage to buildings is the most important predictor of physical vulnerability to floods. Buildings that are older than 20 years old and built with natural materials are likely to experience high flood damages compared to buildings that are less than 10 years and constructed with durable materials. The study concludes that in addition to socio-economic interventions, a targeted and people-centered flood management regime that pays attention to age, material composition, and structural quality of houses is necessary to build residents’ adaptive capacities and long-term resilience to flooding. This study contributes to the emerging work on grassroots responses to flood vulnerabilities with practical insights for urban planners and disaster management professionals on particular interventions needed to improve the performance of local responses to flood risks and vulnerabilities.

Les inondations au Québec: Risques, aménagement du territoire, impacts socioéconomiques et transformation des vulnérabilités - Buffin-Bélanger, Thomas; Maltais, Danielle; Gauthier, Mario (Presses de l'Université du Québec, 2022)
Keywords: Ouvrage_Collectif_Numéro1

Modification of the DRASTIC Framework for Mapping Groundwater Vulnerability Zones - Barzegar, Rahim; Asghari Moghaddam, Asghar; Norallahi, Shahrokh; Inam, Azhar; Adamowski, Jan; Alizadeh, Mohammad Reza; Bou Nassar, Jessica (Groundwater, 2020)
Abstract The DRASTIC technique is commonly used to assess groundwater vulnerability. The main disadvantage of the DRASTIC method is the difficulty associated with identifying appropriate ratings and weight assignments for each parameter. To mitigate this issue, ratings and weights can be approximated using different methods appropriate to the conditions of the study area. In this study, different linear (i.e., Wilcoxon test and statistical approaches) and nonlinear (Genetic algorithm [GA]) modifications for calibration of the DRASTIC framework using nitrate (NO 3 ) concentrations were compared through the preparation of groundwater vulnerability maps of the Meshqin‐Shahr plain, Iran. Twenty‐two groundwater samples were collected from wells in the study area, and their respective NO 3 concentrations were used to modify the ratings and weights of the DRASTIC parameters. The areas found to have the highest vulnerability were in the eastern, central, and western regions of the plain. Results showed that the modified DRASTIC frameworks performed well, compared to the unmodified DRASTIC. When measured NO 3 concentrations were correlated with the vulnerability indices produced by each method, the unmodified DRASTIC method performed most poorly, and the Wilcoxon–GA–DRASTIC method proved optimal. Compared to the unmodified DRASTIC method with an R 2 of 0.22, the Wilcoxon–GA–DRASTIC obtained a maximum R 2 value of 0.78. Modification of DRASTIC parameter ratings was found to be more efficient than the modification of the weights in establishing an accurately calibrated DRASTIC framework. However, modification of parameter ratings and weights together increased the R 2 value to the highest degree. , Article impact statement : The results showed that both linear and nonlinear methods are useful in modifying the ratings and weights of the DRASTIC method for assessing the groundwater vulnerability.

A place-based socioeconomic status index: Measuring social vulnerability to flood hazards in the context of environmental justice - Chakraborty, Liton; Rus, Horatiu; Henstra, Daniel; Thistlethwaite, Jason; Scott, Daniel (International Journal of Disaster Risk Reduction, 2020)
Keywords: Ouvrage_Collectif_Numéro1